La formation du contrat électronique : dispositif légal (répressif) de protection du cyberconsommateur et modes alternatifs de règlement des conflits (M.A.R.C.) - Diallo, Boubacary (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
L’objectif principal de cette étude est de révéler le dispositif légal répressif de protection du cyberconsommateur. Les résultats de cette étude montrent que le législateur malien, communautaire, sous régional et régional y compris, ont misé beaucoup sur la protection des cyberconsommateurs, en adoptant une politique qui s’articule principalement sur la confidentialité, la protection de la vie privée, la protection de la propriété intellectuelle, et le règlement des conflits par les modes alternatifs de règlement des conflits (M.A.R.C.) déclenchés entre les différentes parties de la transaction en ligne.
Keywords: Contrat électronique; Cyberconsommation; E-commerce; MARC; Règlement des conflits

Approche critique du mécanisme de règlement des différends commerciaux devant la CCI - Kesse, Julia Sainte-Colombe (Université de Montréal, 2026)
Cette étude analyse de manière critique le mécanisme de résolution des litiges commerciaux de la Chambre de commerce internationale (CCI) en trois étapes : précontentieux, contentieux et post contentieux. Il examine d’abord l’évolution des méthodes amiables telles que la médiation, la conciliation ou les commissions de règlement des différends mises en œuvre par la CPI pour la prévention des conflits. Ensuite, la validité, les conditions de validité et les conditions applicables de la procédure d'arbitrage sont analysées. Enfin, elle se penche sur la question de la contestation de l'exécution du jugement, notamment par le biais de la Convention de New York. Cet ouvrage met en lumière les apports et les lacunes du système, en insistant sur les différences sectorielles, les résistances culturelles (en Afrique) et les défis de légitimation. L’on a conclu qu’il était nécessaire de renforcer la complémentarité entre le règlement amiable et l’arbitrage afin d’établir une justice commerciale plus efficace, universelle et durable. This thesis critically analyses the International Chamber of Commerce (ICC) mechanism for resolving commercial disputes at three stages: pre-dispute, dispute and post-dispute. First, it examines the development of amicable procedures such as mediation, arbitration or dispute settlement bodies adopted by the ICC to prevent conflicts. It then analyses the effectiveness of arbitration proceedings, the conditions for their entry into force and the elements for their applicability. Finally, it questions the enforcement of arbitration awards, especially under the New York Convention. The study highlights the strengths and weaknesses of the system, underlining sectoral differences, cultural resistance (in Africa and Asia) and legitimacy challenges. It concludes that in order to build a more effective, universal and sustainable commercial justice system, it is necessary to strengthen the complementarity between amicable settlement and arbitration.
Keywords: Alternative; Arbitrage commercial international; Chambre de commerce internationale; Commercial litigation; Contentieux commercial; Convention de New York (1958); Enforcement of arbitral awards; Exécution des sentences arbitrales; International Chamber of Commerce (ICC); International commercial arbitration; International commercial mediation; Médiation commerciale internationale; New York Convention

Arbitration and state sovereignty in commercial disputes resolution within ohada laws - Buma, Roland Sigala; Biya, Fabilou (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Long ago before the creation of the state courts, men had resorted to arbitration for the resolution of diputes. Today, based on the principle of monopoly of the state to render justice, the power to judge is given only to the state. Rendering of justice is one of the areas where the state exeercises its sovereign powers. This has made us to ask the question : is arbitration a violation of the sovereignty of the state in the domain of dispute resolution ? Arbitration is not a violation of the sovereign powers of the state because, it is not all disputes that are resolved via arbitration (for example, crimnal, tax disputes etc can not be settled via arbitration) and the state courts intervene in arbitratin when ever it is necessary. The sate courts intervene in arbitration to grant exequatur, order interim mesaures etc. Nonetheless, since OHADA legislator has not given a complete list of all disputes that can not be resolve via arbitration, we recomend that OHADA should provide a list of all disputes whcih can be settle via arbitration as it is the case with the Arbitration Act of Zimbabw. This article aims at identifying those cases that can not be settled by way of arbitration and those instances in which the state courts intervene in arbitration. Avant la création des tribunaux étatiques, les hommes ont eu recours à l'arbitrage pour la résolution des litiges. Aujourd'hui, sur la base du principe du monopole de l'État à rendre la justice, le pouvoir de juger n'est conféré qu'à l'État. Le fait de rendre la justice est l'un des domaines dans lesquels l'État exerce ses pouvoirs souverains. Cela nous a amenés à poser la question : l'arbitrage constitue-t-il une violation de la souveraineté de l'État dans le domaine du règlement des différends ? L'arbitrage n'est pas une violation des pouvoirs souverains de l'État car, d'une part, tous les litiges ne sont pas résolus par voie d'arbitrage (par exemple, les litiges pénaux, fiscaux, etc. ne peuvent pas être réglés par arbitrage) et, d'autre part, les tribunaux étatiques interviennent dans l'arbitrage chaque fois que cela est nécessaire. Les tribunaux étatiques interviennent dans l'arbitrage pour accorder l'exequatur, ordonner des mesures provisoires, etc. Néanmoins, étant donné que le législateur de l'OHADA n'a pas établi une liste exhaustive de tous les litiges qui ne peuvent pas être résolus par arbitrage, nous recommandons que l'OHADA fournisse une liste de tous les litiges qui peuvent être réglés par voie d'arbitrage, comme c'est le cas dans la loi sur l'arbitrage du Zimbabwe. Cet article vise à identifier les litiges qui ne peuvent pas être réglés par voie d'arbitrage ainsi que les situations dans lesquelles les tribunaux étatiques interviennent dans l'arbitrage.
Keywords: Arbitrage; Arbitrage commerciale; Arbitragem; Arbitraje; Arbitration; Commercial disputes; Droit OHADA; Litiges commerciaux; OHADA law; Souveraineté; Sovereignty

L’impact des clauses d’arbitrage entre investisseurs étrangers et Etats sur la souveraineté : une analyse de l'équilibre entre protection des investisseurs étrangers et la souveraineté - Ahouyanganga Matondo, Dan Salomon (Université de Montréal, 2026)
Ce mémoire analyse l’impact des clauses d’arbitrage entre investisseurs étrangers et États sur la souveraineté étatique, en s’intéressant à l’équilibre entre protection des investisseurs et capacité réglementaire des États. Dans un contexte de mondialisation marqué par les crises sanitaires et les tensions géopolitiques, les États cherchent à attirer les investissements étrangers tout en préservant leur souveraineté économique. Le travail met en lumière le rôle du mécanisme RDIE, permettant aux investisseurs étrangers de contester les mesures étatiques devant des tribunaux arbitraux internationaux, contournant ainsi les juridictions nationales. Bien qu’il sécurise les flux d’investissements et renforce la confiance des investisseurs, le RDIE peut créer des déséquilibres, limitant la marge de manœuvre des États dans des domaines sensibles tels que la santé publique, l’environnement ou les droits sociaux. À travers l’analyse de cas emblématiques et des traités internationaux d’investissement, le mémoire propose des pistes pour concilier la protection juridique des investisseurs et le respect de la souveraineté étatique. Il conclut que le RDIE, tout en étant un outil essentiel de sécurisation des investissements, nécessite des réformes pour garantir un équilibre durable entre intérêts privés et intérêt général. This research study will analyze the impact of arbitration clauses between foreign investors and states on state sovereignty, focusing on the balance between investor protection and the regulatory capacity of states. In a globalized context marked by health crises and geopolitical tensions, states seek to attract foreign investment while preserving their economic sovereignty. The study highlights the role of the ISDS mechanism, which allows foreign investors to challenge state measures before international arbitration tribunals, thus bypassing national courts. Although it ensures investment flows and strengthens investor confidence, the ISDS system can create imbalances, limiting states' room for maneuver in sensitive areas such as public health, the environment, and social rights. Through analysis of historical cases and international investment treaties, the thesis proposes ways to reconcile legal protection for investors with respect for state sovereignty. It concludes that while ISDS remains an essential tool for securing investments, it requires reform to ensure a sustainable balance between private interests and the public good.
Keywords: Arbitration clauses; Clauses d’arbitrage; Foreign investors; ISDS; Investisseurs étrangers; Investment treaties; RDIE; Souveraineté; Sovereignty; States; Traités d’investissement; États

Artifical intelligence and international arbitration law: revolution or evolution - Łągiewska, Magdalena (Routledge research in international commercial law, 2026)
The book asks whether the use of Artificial Intelligence (AI) and Generative AI (GenAI) in international arbitration represents a revolution or an evolution of the international dispute resolution landscape. Critically engaging with the transformative impact of the Fourth Industrial Revolution (4IR), this book focuses on the integration of AI and GenAI into international commercial arbitration. Set against the backdrop of rapid technological advancement, it explores how arbitral tribunals and stakeholders are cautiously yet progressively adopting these innovations in a manner that respects and preserves the foundational principles of arbitration. Through an interdisciplinary and practice-oriented approach, the book examines the evolving role of AI in arbitration. It analyzes how AI is perceived and applied by parties, arbitral institutions, and arbitrators, as well as assesses the legal frameworks in place to govern it. Offering a balanced analysis of both the opportunities and legal and ethical dilemmas posed by emerging technologies, the book asks if a duty of disclosure is relevant in relation to AI use, and what challenges this might entail. It also covers the status of AI-generated arbitral awards under international law, as well as copyright law. This book will be of interest to researchers in the field of international arbitration and commercial law
Keywords: Arbitrage; Artificial Intelligence; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Intelligence artificielle; International commercial arbitration; UNCITRAL Model Law on International Commercial Arbitration (1985)

Réflexion sur la procédure de médiation de l’acte uniforme de l’OHADA relatif à la Médiation (AUM) - Adjita, Shamsidine Akrawati (Revue Internationale de Droit et Science Politique, 2025)
La médiation n’est pas une invention du législateur de l’OHADA. Elle est aussi vieille que le monde. Sa consécration légale à travers l’Acte uniforme relatif à la médiation met en évidence son importance dans la résolution des litiges à l’amiable dans l’ordonnancement juridique de l’OHADA. Cela s’explique car la médiation renvoie à l’idée de justice. Le sentiment de justice n’est pas lié à une époque, il est plutôt inhérent à l’existence humaine et porte en lui-même une exigence, une valeur fondamentale universellement reconnue. Il s’agit du droit à la justice dont le respect permet d’apprécier de façon efficiente les valeurs auxquelles une société est attachée. Toute société a besoin de justice, mais elle ne peut la rendre de façon satisfaisante avec le procédé traditionnel qu’est le jugement. Le juge ne peut pas tout. Le bon sens dicte de l’éviter. Selon un adage populaire, « un mauvais accord vaut mieux qu’un bon procès ». Là où il y a une société, il y a des différends. Là où il y a des différends, il y a des modes de règlement des différends parmi lesquels la médiation occupe une place de choix. Avatar médiatisé de la justice consensuelle, panacée de la déjudiciarisation et de la déjuridicisation, la médiation est parée de toutes les vertus pour éviter le procès. Elle apparaît donc comme une alternative à laquelle peuvent recourir les parties en conflit pour régler leur malentendu à l’amiable tout en préservant leurs relations d’affaires. Elle n’est pas une procédure laissée à l’appréciation du juge, mais plutôt à celle des parties en conflit qui en sont les principales actrices. Cependant elles ne peuvent parvenir à la résolution de leur litige que par l’intermédiaire d’un tiers appelée médiateur et sans lequel la procédure serait incomplète. On a donc, d’un côté, les parties à la médiation qui la considèrent comme étant leur affaire et, de l’autre, le médiateur qui est considéré comme le chef d’orchestre de la procédure. Mediation is not an invention of the OHADA legislator. It is as old as the world itself. Its legal recognition through the Uniform Act on Mediation highlights its importance in the amicable resolution of disputes within the OHADA legal system. This is because mediation refers to the idea of justice. The sense of justice is not tied to a particular era; rather, it is inherent to human existence and carries with it a requirement, a universally recognized fundamental value. It is the right to justice, respect for which allows for the efficient appreciation of the values to which a society is attached. Every society needs justice, but it cannot deliver it satisfactorily through the traditional process of judgment. Judges cannot do everything. Common sense dictates that it should be avoided. According to a popular saying, “a bad agreement is better than a good trial.” Where there is society, there are disputes. Where there are disputes, there are ways of resolving them, among which mediation occupies a prominent place. As the media-friendly face of consensual justice and the panacea for reducing court cases and legal proceedings, mediation is seen as the ideal way to avoid litigation. It therefore appears to be an alternative that parties in conflict can use to settle their differences amicably while preserving their business relationships. It is not a procedure left to the discretion of the judge, but rather to that of the parties in conflict, who are the main actors. However, they can only resolve their dispute through a third party called a mediator, without whom the procedure would be incomplete. On the one hand, therefore, we have the parties to the mediation, who consider it to be their business, and on the other, the mediator, who is considered to be the conductor of the procedure.
Keywords: Acte uniforme; Judge; Juge; Mediation; Mediator; Médiateur; Médiation; Parties en conflit; Parties to the dispute; Uniform Act

La contribution de la technologie vers une modernisation efficace des modes alternatifs de règlement de conflits - Sangare, Abou Bakary (Université de Montréal, 2025)
Les modes alternatifs de règlement de conflits ont révolutionné le monde du règlement de litiges grâce à leurs nombreux avantages. Les coûts moins onéreux en dehors de l’arbitrage, la célérité des procédures, la confidentialité, le dialogue ouvert, l’émergence de solutions créatives profitant plus ou moins à chacune des parties, constituent entre autres les nombreux éléments qui les rendent plus efficaces par rapport à une procédure contentieuse devant une instance judiciaire ordinaire. Cependant, ces modes alternatifs de règlement de conflits font quand même face à bien d’écueils qui les rendent au fil du temps moins efficaces. L’imprévisibilité des situations conflictuelles apportées à la table des instances de résolution, entraîne une inadéquation des solutions envisagées. De plus, le capital humain fait aussi défaut quand on sait que le nombre de ces règlements amiables de litiges de ces dernières années accroît considérablement, acculant ainsi le personnel de gestion de ces conflits qui se retrouve à faire face aux mêmes défis que le personnel des instances judiciaires contentieuses. De plus, l’humain ne pouvant se détacher indéfiniment de ses émotions peut très rapidement tomber dans la partialité quand il s’agit de prendre des décisions. Il est dès lors capital de penser à une modernisation de ces modes alternatifs de règlement de conflits afin de les rendre plus efficaces par le biais de nouveaux moyens technologiques. Certes, la Résolution de litiges en ligne existe depuis quelques années maintenant. Cependant, il est temps d’y apporter de nouveaux ingrédients afin de rendre meilleure la recette. Alternative dispute resolution has revolutionized the world of dispute resolution thanks to its many advantages. Lower costs, faster procedures, confidentiality, open dialogue and the emergence of creative solutions that benefit both parties to a greater or lesser extent - these are just some of the factors that make alternative dispute resolution more effective than litigation in the ordinary courts. However, these alternative dispute resolution methods do face a number of pitfalls that make them less effective over time. The unpredictability of conflict situations brought to the resolution table leads to inadequate solutions. What's more, human capital is also in short supply, as the number of out-of-court settlements in recent years has risen sharply, leaving conflict management staff facing the same challenges as staff in contentious legal proceedings. What's more, since human beings are unable to detach themselves from their emotions indefinitely, they can quickly fall into the trap of bias when it comes to making decisions. It is therefore vital to consider modernizing these alternative dispute resolution methods, in order to make them more effective through new technological means. Online dispute resolution has been around for some years now. However, it's time to add new ingredients to make the recipe even better.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitration; Blockchain; Chatbots; Conciliation; ICT; Internet; Justice; Justice prédictive; MARD; Mediation; Modes alternatifs de règlement de conflits; Médiation; Négociation; ODR; Online dispute resolution; Predictive justice; Règlement de litiges en ligne; TIC; Technologie; Technology; Transaction

L'équilibre de la relation entre investisseur étranger et État hôte dans la jurisprudence arbitrale - Jorland, Maxime (Université Paris-Saclay, 2025)
Le droit des investissements internationaux s'est construit sous l'impulsion des tribunaux arbitraux qui, dans leur rôle d'interprétation du droit international coutumier et des traités d'investissement, ont contribué à enrichir le droit matériel des investissements. La multiplication des sentences rendues a constitué progressivement une véritable jurisprudence, visant à équilibrer la relation entre l'investisseur étranger et l'État hôte. Cependant, l'interprétation des traités par les tribunaux arbitraux s'est souvent faite dans un objectif de protection de l'investisseur face à la puissance publique de l'État, jusqu'à inverser parfois le rapport de force entre les deux opérateurs. De plus, l'absence de principe de précédent en arbitrage d'investissement a contribué à créer un flou notionnel, du fait des interprétations changeantes des dispositions des traités protégeant l'investisseur étranger. 2Cette étude vise donc à faire état du droit positif des investissements internationaux en déterminant un courant doctrinal commun aux sentences arbitrales. Une fois ce travail de compilation réalisé, l'objectif sera alors de déterminer l'état de l'équilibre des forces entre les deux opérateurs et proposer un rééquilibrage du droit des investissements. Ce rééquilibrage passe notamment par une redéfinition des critères jurisprudentiels imprécis ou changeants et une adaptation de la protection de l'investisseur étranger aux enjeux modernes du commerce international, tout en veillant à permettre à l'Etat hôte de conserver ses prérogatives de puissance publique. International investment law has largely been shaped by arbitral tribunals, whose interpretative function with regard to customary international law and investment treaties has contributed significantly to the development of substantive investment law. The proliferation of arbitral awards has progressively given rise to a de facto jurisprudence, aimed at striking a balance between the interests of foreign investors and the sovereign rights of host States. However, treaty interpretation by arbitral tribunals has often been guided by a protective logic in favour of the investor, at times to the extent of inverting the power dynamic between the two actors. Furthermore, the absence of a binding precedent doctrine in investment arbitration has fostered conceptual uncertainty, resulting from fluctuating interpretations of the treaty provisions safeguarding foreign investors.This study seeks to provide an overview of the current state of positive international investment law by identifying a coherent doctrinal trend emerging from arbitral case law. Based on this synthesis, the aim is to evaluate the prevailing balance of power between the investor and the host State, and to propose avenues for rebalancing investment law. Such rebalancing entails, in particular, a clarification of vague or inconsistent jurisprudential standards and an adaptation of investor protection to contemporary challenges of international trade, while ensuring that host States retain their sovereign regulatory authority.
Keywords: Arbitrage; Arbitrage commercial international; Arbitration; CIRDI; Etat hôte; FDI; Host state; ICSID; International; Investissements; Investissements étrangers; Investisseur; Investments; Investor

La revalorisation des mécanismes locaux de prévention et de gestion des conflits au Mali : une valeur ajoutée inestimable pour le système judiciaire moderne - Yalcouyé, Seydou; Dolo, Anidjou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La cohabitation entre les mécanismes modernes et traditionnels de prévention et de gestion des conflits au Mali (notamment dans en milieu rural) est une réalité. Entre les mécanismes modernes et les mécanismes traditionnels, le choix des communautés porte essentiellement sur les seconds ; quoique les premiers ne sont pas non plus en abandon. Comme raisons avancées pour justifier leur choix, elles considèrent de façon générale que le recours aux mécanismes modernes ne permet pas de vider totalement leur contentieux. Les communautés trouvent que ces mécanismes modernes rendent leurs conflits plus complexes et plus difficiles à gérer. D’où la méfiance du règlement administratif ou judiciaire des conflits car trop couteux et aux procédures trop complexes. Sur la base de ces constats, il reste permis de constater la nécessité de réaliser des compromis entre mécanismes modernes et mécanismes traditionnels de gestion des conflits en revalorisant davantage les seconds. Seul à ce prix que les défis de la décentralisation (gouvernance locale) et ceux de la démocratie seront relevés. The coexistence of modern and traditional conflict prevention and management mechanisms in Mali (particularly in rural areas) is a reality. Compared to modern and traditional mechanisms, communities primarily choose the latter; although they have not abandoned the former either. As reasons given to justify their choice, they generally consider that resorting to modern mechanisms does not completely resolve their disputes. Communities find that these modern mechanisms make their conflicts more complex and more difficult to manage. Hence their distrust of administrative or judicial conflict resolution, as they are too costly and require overly complex procedures. Based on these observations, it remains clear that compromises must be made between modern and traditional conflict management mechanisms by further revaluing the latter. Only in this way will the challenges of decentralization (local governance) and democracy be met.
Keywords: Autorité traditionnelle; Conflict management; Conflict prevention; Gestion des conflits; Gouvernance locale; Local governance; Légitimité traditionnelle; Prévention des conflits; Traditional authorities; Traditional legitimacy

The Interpretation of UNCITRAL Law in Australian Courts: A Roadmap for Elevating the UN Sales Convention’s Status to That of Arbitration Law - Hayward, Benjamin (Sydney Law Review, 2025)
Despite being part of Australian law for more than 30 years, the United Nations Convention on Contracts for the International Sale of Goods (‘CISG’) has not secured the internationally minded interpretation that CISG art 7(1) requires. Australia’s international commercial arbitration (‘ICA’) laws, however, are routinely approached by Australian courts with an internationalist perspective, as their own interpretative rules require. It is tempting to conclude that Australia’s approach to interpreting its ICA laws is transferable to the CISG context. In this article I address a previously unexplored nuance affecting that conclusion. Australian courts routinely accept Singaporean, Hong Kong and New Zealand interpretative influence concerning ICA laws. In the CISG context, however, significantly less influence from those jurisdictions exists. That being so, I explore how Australia’s courts might better apply the CISG in an internationalist manner. First, I recommend that Australia’s courts emphasise to practitioners the need to consider the CISG’s application and its internationalist interpretation requirements. Second, I recommend that Australian courts use the amicus curiae procedure to solicit third party submissions addressing the CISG’s interpretation. Both techniques are applied by foreign courts in the ICA context and would assist Australian courts in discharging their CISG art 7(1) obligations.
Keywords: Asia-Pacific; Australia; CISG; Harmonisation; International commercial arbitration; Model Law; New York Convention; Sales law; Statutory interpretation

The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

Analyse critique du développement de la médiation en France : les résistances à l'essor de la médiation en droit privé - Prêté, Safya Bayoub (Université Bourgogne Franche-Comté, 2025)
La médiation est une technique de communication faisant intervenir un tiers impartial, neutre et indépendant, pour aider des individus à trouver une issue à leur crise conflictuelle. Par essence, la médiation est un outil de résolution des conflits pacifiant, fondé sur la responsabilisation des parties. Attrayante par sa souplesse, louée pour son coût présenté comme modéré, le législateur en a encouragé l’expansion. Alors que l’article 21 du code de procédure civile confie au juge la mission de concilier les parties, la médiation devient l’un des outils privilégiés par les pouvoirs publics pour permettre la réalisation de cette mission. Ainsi, la loi n°95-125 du 8 février 1995, relative à l’organisation des juridictions et à la procédure civile, pénale et administrative, institue la médiation judiciaire. Elle marque le début d’un ancrage législatif en faveur de ce processus. Ce premier mouvement en faveur de la médiation s’est accéléré en France, à l’initiative de l’Union européenne qui a fait adopter le 21 mai 2008 la Directive 2008/52/CE portant sur la médiation en matière civile et commerciale. Le postulat de départ de ce texte est qu’un « cadre juridique prévisible peut permettre aux citoyens de l’Union européenne (UE) de bénéficier pleinement des avantages de la médiation en tant que mécanisme de résolution des conflits, notamment sur le plan de la rentabilité et de la rapidité ». Puis, la médiation conventionnelle a été encadrée au sein du code de procédure civile. L’intégration de la Directive 2008/52/CE au sein du corpus de normes du droit interne positif a permis de créer une définition légale de la médiation en ces termes : « La médiation régie par le présent chapitre s'entend de tout processus structuré, quelle qu'en soit la dénomination, par lequel deux ou plusieurs parties tentent de parvenir à un accord en vue de la résolution amiable de leurs différends, avec l'aide d'un tiers, le médiateur, choisi par elles ou désigné, avec leur accord, par le juge saisi du litige ».Or, le mouvement d’expansion de la médiation semble freiné par un jeu de résistances. Certaines de ces résistances concernent le processus et sont prévisibles. D’autres tiennent à des variables exogènes, résultats de questionnements sur la médiation, le médiateur, l’office du juge, la déjudiciarisation, la déjuridictionnalisation, et l’ordre public. L’étude pose que l’essor de la médiation est contrarié par une méconnaissance de la médiation, ainsi qu’en raison d’une méconnaissance des acteurs de la médiation.Le mouvement d’encouragement des pouvoirs publics à la tentative de médiation, pour prévenir ou traiter des contentieux du droit privé, semble se muer en une politique globale de l’amiable, recentrée sur la mission du juge de concilier les parties. Cette politique de l’amiable persiste à produire des normes tendant, notamment, à encadrer la médiation, à créer un statut pour le médiateur, dans l’optique d’acculturer les justiciables à ce mode amiable.L’objet de la présente thèse est d’analyser les résistances à l’essor de la médiation en droit privé et leurs conséquences sur son développement en France. Il s’agit de saisir ces résistances et leurs enjeux ; et de redonner force au processus de médiation, en offrant à ses prescripteurs un faisceau d’arguments intelligibles. Mediation is a communication technique involving an impartial, neutral and independent third party to help individuals find a way out of their conflict crisis. By nature, mediation is a pacifying conflict resolution tool, based on the accountability of the parties. Attractive for its flexibility, praised for its moderate cost, the legislator encouraged its expansion. While Article 21 of the Code of Civil Procedure entrusts the judge with the task of reconciling the parties, mediation is becoming one of the tools favoured by the public authorities to enable this mission to be carried out. Thus, Law No. 95-125 of February 8, 1995, relating to the organization of the courts and civil, criminal and administrative procedure, establishes judicial mediation. It marks the beginning of a legislative anchoring in favour of this process. This initial movement in favour of mediation has accelerated in France, at the initiative of the European Union, which adopted Directive 2008/52/EC on mediation in civil and commercial matters on May 21, 2008. The premise of this text is that "a predictable legal framework can allow citizens of the European Union (EU) to fully benefit from the advantages of mediation as a dispute resolution mechanism, particularly in terms of cost-effectiveness and speed". Then, conventional mediation was framed in the Code of Civil Procedure. The incorporation of Directive 2008/52/EC into the body of norms of positive domestic law has made it possible to create a legal definition of mediation in the following terms: "Mediation governed by this chapter means any structured process, whatever its name, by which two or more parties attempt to reach an agreement with a view to the amicable resolution of their disputes, with the help of a third party, the mediator, chosen by them or appointed, with their agreement, by the judge hearing the dispute". However, the movement towards the expansion of mediation seems to be slowed down by a game of resistance. Some of these resistances are process-related and predictable. Others relate to exogenous variables, the result of questions about mediation, the mediator, the judge's office, diversion, dejurisdictionalization, and public order. The study posits that the development of mediation is thwarted by a lack of knowledge of mediation, as well as because of a lack of knowledge of the actors involved in mediation. The movement to encourage the public authorities to attempt mediation, to prevent or deal with private law disputes, seems to be turning into a global policy of amicable litigation, refocused on the judge's mission to reconcile the parties. This amicable policy persists in producing standards tending, in particular, to regulate mediation, to create a status for the mediator, with a view to acculturating litigants to this amicable method. The purpose of this thesis is to analyze the resistance to the rise of mediation in private law and their consequences on its development in France. It is a question of grasping these resistances and their stakes; and to give strength to the mediation process, by offering its prescribers a bundle of intelligible arguments.
Keywords: Amiable; Arbitrage (droit); Arbitration; Civil Law; Contract Law; Contrats; Droit civil; Droit des contrats; Droit privé; France; Mediation; Médiation; Private Law; Procedure Law; Procédure civile; Settlment

El arbitraje como justicia alternativa y eficaz - Nieto, Gastón Fabricio Correa (Polo del Conocimiento, 2025)
El presente ensayo surge de la experiencia del ejercicio profesional de la abogacía en la que en el ámbito judicial, extrajudicial, donde se ha observado diferentes vicisitudes en el desarrollo y ejecución de procesos judiciales, generando de esta forma ineficiencia en la administración de justicia; para lo cual como alternativa viable surgen los métodos alternativos de solución de conflictos con la promulgación de la Ley de Arbitraje y Mediación surgen en septiembre de 1997 como una opción ante la deficiente administración de Justicia.Sin embargo, esta ineficiencia procesal representa a su vez un obstáculo real para su ejercicio efectivo de derechos, especialmente obtener “justicia” para los ciudadanos que enfrentan demoras prolongadas y procedimientos burocráticos que terminan por vulnerar sus derechos. Uno de los objetivos del artículo es la de establecer las medidas efectivas que se pueden adoptar en instancia extrajudicial y elementos necesarios alcanzar la tan preciada “Justicia” siendo esta “la constante y perpetua voluntad de dar a cada quien lo que le corresponde” (Ulpiano, 2015).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Deficiencia judicial; Justicia; Negligencia; Retardo

Comercio sostenible y arbitraje internacional: un enlace estratégico para la resolución de conflictos - León, Jorge Guillermo Cedeño; Erazo, Angie Gabriela Sánchez (Polo del Conocimiento, 2025)
El arbitraje internacional ha emergido como una herramienta clave para la resolución de controversias en el comercio sostenible, ofreciendo un marco eficiente y flexible. Este estudio analiza el uso del arbitraje en casos relacionados con comercio y sostenibilidad, evaluando su efectividad en la promoción de prácticas comerciales responsables.
Keywords: Arbitrage international; Arbitraje internacional; Comercio sostenible; Commerce durable; International commercial arbitration; Prácticas responsables; Resolución de controversias; Sostenibilidad

Impacto de las tecnologías emergentes en la confidencialidad y transparencia del arbitraje internacional - Pérez-Pacheco, Yaritza; Lee, Díckar Bonyuet (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
El arbitraje comercial internacional enfrenta el desafío de integrar tecnologías emergentes como la inteligencia artificial, el Big Data y el blockchain, sin comprometer sus principios fundamentales de confidencialidad y transparencia. Este artículo analiza, a partir de una revisión documental y comparativa, cómo el uso de estas tecnologías im-pacta la gestión de casos, el análisis predictivo y la ejecución de laudos, al tiempo que mejora la eficiencia y accesibilidad del arbitraje, pero también genera riesgos en materia de privacidad, ciberseguridad y protección de datos sensibles. Asimismo, se analizan los enfoques regulatorios adoptados en distintas jurisdicciones, incluyendo el Reglamento de la Unión Europea, el modelo flexible de Estados Unidos y las iniciativas tecnológi-cas de países asiáticos como China y Hong Kong. La investigación concluye que, para equilibrar la innovación y la protección de la información, es indispensable implementar protocolos globales y estándares éticos que garanticen un arbitraje confiable y seguro en entornos digitales. International commercial arbitration faces the challenge of integrating technologies such as artificial intelligence, Big Data, and blockchain, without undermining confidentiality and transparency. This article examines how these tools impact case management, predictive analysis, and the enforcement of awards, improving efficiency while also raising concerns about privacy and cybersecurity. Regulatory approaches are explored, from the European Union’s framework to the more flexible model of the United States and technological initiatives in Asia. The research concludes that it is essential to establish global and ethical standards to ensure a secure and reliable arbitration process in the digital era.
Keywords: Arbitrage; Arbitragem; Arbitraje internacional; Arbitral award enforcement; Arbitration; Confidentiality; Confidentialité; Ejecución de laudos arbitrales; Emerging technologies; International arbitration; International dispute resolution; Resolución internacional de disputas; Tecnologías emergentes; Transparence; Transparency

Transparency in Investor-State Arbitration Under USMCA - Petrova Georgieva, Virdzhiniya (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
The provisions of USMCA and their interpretation and application in the developing case law of international arbitral tribunals constituted under its investment chapter show a progressive move towards a higher transparency standard in the resolution of inves-tor-State disputes. The incorporation of most of the UNCITRAL Rules on Transparen-cy in USMCA Annex 14-D expanded the scope of NAFTA’s transparency rules. The entry into force of USMCA and the recent end of NAFTA’s “legacy claims” is to bring normative uniformity across the case law of arbitral tribunals on issues of procedural transparency. In addition, better access to arbitral orders and awards under USMCA will promote the quality of the decisions, as tribunals and parties will be able to lean on the experience of their predecessors. Las disposiciones del T-MEC y su aplicación en la jurisprudencia arbitral internacional muestran un avance hacia mayores estándares de transparencia en disputas inversionista-Estado. Al incorporar la mayoría de las Reglas de Transparencia de la CNUDMI en su Anexo 14-D, el T-MEC amplió el marco del TLCAN. La entrada en vigor del T-MEC y el fin de las “reclamaciones heredadas” del TLCAN promueven una mayor uniformidad normativa en torno a la transparencia procesal. Esta coherencia fortalecerá la aceptación del capítulo de inversión del T-MEC y aumentará la legitimidad del arbitraje de inversiones a nivel global.
Keywords: Arbitraje internacional de inversiones; Arbitrajes entre Inversionistas y Estados; CNUDMI; International Investment Arbitration; NAFTA; Procedural transparency; T-MEC; TLCAN; Transparencia procedimental; UNCITRAL Rules on Transparency; USMCA

La transparencia en el arbitraje internacional: avances y nuevos retos - Pollero, Marianela Bruno (Jurídica Ibero: Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
Este artículo responde a la propuesta académica del Departamento de Derecho de la Uni-versidad Iberoamericana en conmemoración del 10.° aniversario de las normas de trans-parencia de la Comisión de las Naciones Unidas para el Derecho Mercantil (CNUDMI) y complementa la actividad académica realizada por la Universidad Iberoamericana, la Secretaría de Relaciones Exteriores de México y el Centro de Mediación y Arbitraje de la Cámara de Comercio de la Ciudad de México (CANACO), con el apoyo de la Secre-taría de la CNUDMI, en el marco del UNCITRAL LAC DAYS- México 2024. Durante esta actividad se organizaron tres mesas de debate integradas por desta-cados miembros de la comunidad arbitral, de la sociedad civil y del sector privado. La temática de estudio brindó desde México una visión sobre la confidencialidad vs. la transparencia, así como los avances y los retos de la transparencia en el arbitraje inter-nacional.
Keywords: Arbitrage international; Arbitragem Internacional; Arbitraje internacional; Arbitration; Transparence (droit); Transparencia

Reflexiones sobre el régimen de transparencia en el arbitraje comercial internacional - Rendón, Martha Angélica Alvarez (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
From an approach to the concepts of transparency, confidentiality, and privacy, this article examines the tension that may arise between these principles in international commercial arbitration. It also analyzes how arbitration rules address confidentiality and transparency, questioning whether a balance between the two has been achieved. Additionally, it reflects on the impact of public interest in promoting transparency in arbitral proceedings, considering whether the measures adopted are compatible with this type of arbitration. Desde un acercamiento a las nociones de transparencia, confidencialidad y privacidad, en este artículo se valora la tensión que puede existir entre dichos conceptos en el arbi-traje comercial internacional. Asimismo, se alude a algunos reglamentos de arbitraje que abordan la confidencialidad y la transparencia, parar mostrar si se alcanza un equilibrio entre los principios analizados. Además, se llama a reflexionar sobre el impacto del inte-rés público en la búsqueda de la transparencia en los procesos arbitrales, con la finalidad de abrir el debate sobre la compatibilidad de las medidas que se han adoptado en este rubro en el arbitraje comercial.
Keywords: Arbitrage; Arbitragem; Arbitraje comercial internacional; Arbitraje de inversión; Arbitration; Confidencialidad; Confidentiality; International commercial arbitration; Interés público; Investment arbitration; Privacidad; Privacy; Public interest; Transparence; Transparencia; Transparency

Les ADR comme mécanismes de gestion des différends sociaux et environnementaux dans les grands projets miniers au Cameroun - Abane Engolo, Patrick Edgard; Abomo Efoua, Christiane (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Les grands projets miniers sont porteurs d’enjeux économiques, sociaux, et environnementaux au Cameroun. L’exploitation minière est dans ce sens juridiquement encadrée par le Code minier. Elle implique autant d’opportunités que de risques susceptibles d’engendrer des différends sociaux et environnementaux. La gestion de ces différends implique la convocation des Alternative Dispute Resolution (ADR), qui constituent une voie d’accès à la résolution des litiges aussi importante que la saisine du juge. Cependant, l’apparente libéralité de ces ADR suscite des inquiétudes quant à l’efficacité de leur mise en œuvre et leur force juridique. Il en ressort que, bien que ces mécanismes soient consacrés, leur encadrement juridique nécessite d’être renforcé. Major mining projects pose economic, social and environmental challenges in Cameroon. Mining operations are therefore legally regulated by the Mining Code. They present both opportunities and risks that can lead to social and environmental disputes. Managing these disputes therefore requires the convening of Alternative Dispute Resolution (ADR) mechanisms, which constitute a means of accessing justice as important as going to court. However, the apparent liberality of these ADR mechanisms raises concerns about the effectiveness of their implementation and their legal force. It appears that although these mechanisms are established, their legal framework needs to be strengthened.
Keywords: Arbitrage; Arbitration; Conciliation; Mediation; Médiation; Parties prenantes; Stakeholders

L’apport du juge à l’autorité de la chose jugée de la sentence arbitrale en contentieux du sport au Cameroun - Mandeng, Naomie Audrey (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Par le truchement de la résolution des litiges nés du mouvement et des acteurs sportifs, le juge statuant dans le contentieux sportif se préoccupe également de l’applicabilité de ses décisions juridictionnelles. Sauf que l’on ne devrait pas généraliser le poids de celle-ci sur tous les cas rendus par le juge sportif. Se voulant intelligible ce dernier l’acuité de l’autorité de chose jugée face à certains incidents de procédure. Cette négation est davantage entretenue par des modalités spécifiques. Par ailleurs, dans son énoncé, le juge sportif prescrit de se référer au dispositif pour dériver prosaïquement les termes de l’autorité de chose jugée et la force exécutoire de la sentence arbitrale.
Keywords: Autorité de la chose jugée; Cameroun; Juge; Sentence arbitrale; Sport

Libres propos sur la volonté des parties dans l’arbitrage OHADA - Waham Mayegle, Joseph Laurent (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
L’arbitrage est une réalité en Afrique depuis longtemps déjà. C’est avec l’avènement de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires que ce domaine a pu avoir un dispositif bien structuré. Etant un mode alternatif de règlement des différends, l’arbitrage a pour fondement prépondérant la volonté des parties qui y font recours. Il s’est donc posé en filigrane la question de la portée de la volonté des parties à l’arbitrage OHADA. Le constat est que tout comme en matière contractuelle, elle est un élément indispensable à l’efficacité de ce mode de résolution des litiges. C’est la raison pour laquelle sa portée est traduite par une prégnance avérée, et un recul tout de même constaté.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Volonté des parties

La seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario - Muñoz, Nohely Alejandra Zambrano; Pacheco, Marco Antonio Acosta; Reyes, Eloísa Carolina Solís; Parra, José Antonio Velez (Polo del Conocimiento, 2025)
El estudio de la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario tuvo como objetivo analizar la incidencia de la seguridad jurídica en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario como garantía de los procesos judiciales. Para lo cual, se utilizó una investigación de tipo desriptiva y de campo, con un enfoque mixto y el método hermenéutico; para la recopilación de información primaria se aplicó una encuesta y entrevista a los juristas en libre ejercicio de su profesión. Se obtuvo que que todas las personas tienen derecho al debido proceso, el cual está ligado estrechamente al derecho a la seguridad jurídica ya que, este segundo implica el conocimiento y certeza del derecho positivo, la confianza de la sociedad en las instituciones del Estado y en el orden jurídico y la existencia de mecanismos jurídicos frente a las afectaciones que pudieren existir. Se concluyó que la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales es esencial para mantener la confianza en el sistema legal y para proteger los derechos fundamentales de las personas involucradas en cualquier procedimiento legal, ya sea voluntario, sumario u ordinario.
Keywords: Debido proceso; Due process; Judicial decisions; Legal certainty; Ordinary procedure; Procedimiento ordinario; Procedimiento sumario; Procedimiento voluntario; Resoluciones judiciales; Seguridad jurídica; Summary procedure; Voluntary procedure

Promoting Treaties in Nigeria and Operationalising the Singapore Convention on Mediation - Okoli, Pontian (African Journal of Legal Studies, 2025)
In Nigeria, the United Nations Convention on International Settlement Agreements Resulting from Mediation (2018) has entered into force. This Convention was incorporated or domesticated by referring to it in the Arbitration and Mediation Act (2023), but statutes are often dedicated to the domestication of treaties. There is no consensus on the most pragmatic way(s) to facilitate Nigerian treaty engagement. This article examines the Nigerian legal regime on treaties and explores the extent to which the regime can be maximised considering the Vienna Convention on the Law of Treaties (1969). A case is made for a principled basis to underpin the domestication of treaties that facilitate international business, including dispute resolution treaties. This analytical basis should enable legislative flexibility already woven into the overarching legal regime. The article articulates how such flexibility can be used to promote the operationalisation of relevant treaties using the Arbitration and Mediation Act as a paradigm.
Keywords: Good faith; International commercial mediation; Legislative flexibility; Singapore Convention; Treaties; Vienna Convention

International Arbitration: Impact on Global Economy - Jahan, Bushrat (International Journal of Innovation and Applied Studies, 2025)
The significant increase in the development of world economy over the last few decades have been experienced a considerable increase in the number of commercial disputes. When there is any business and dealings with contracts the question of dispute must be happened. But all of the parties actually want to run their business well and smoothly. In recent world a massive part of global economy depends on the trans-border business. But disputes in such business dealings sometimes can be the reasons to become risk the inter-relation of those parties. Which can affect the global economy as a whole. Comparing to the disputes inside domestic entities the trans-border or international business disputes can arise as bigger problem because of different jurisdictions, diverse legal systems and tradition. International Court of Justice (ICJ) already has the jurisdiction to try all the international civil suits but Alternative Dispute Resolution (ADR) mechanism also considered as a viable alternative to resolve the dispute over the court. The international arbitration arises as a way of alternative dispute resolution mechanism which upraise benefits both of the parties and maintain the confidentiality. In this paper details of international arbitration and the broader impact of this mechanism in the global business economy will be focused. The legal status and the implementation process of international arbitration also be the discussing point of this paper.
Keywords: Business economy; Enforcement of awards; Globalization; International Arbitration

L'amélioration de l'accès à la justice au Bénin dans le domaine commercial et foncier : comment les modes alternatifs de règlement des conflits et la technologie peuvent être mis à contribution ? - Agoïnon, Fifamè Danielle Esperancia (Université de Montréal, 2025)
En dépit de l'importance cruciale de la justice au sein de notre société, il est manifeste que le système judiciaire béninois présente d'importants défis en matière d'accessibilité, d'efficacité et de confiance publique. Les coûts de la justice, la perte de contrôle des problèmes, les délais d’attente avant procès, la structure labyrinthique des tribunaux, l'impossibilité de se représenter seul, ainsi que le caractère inhospitalier des tribunaux constituent des indicateurs d'un système judiciaire défaillant. En effet, des limitations dans l'accès à la justice alimentent la méfiance des citoyens à l'égard du système judiciaire étatique. Dans un souci de célérité et d'efficacité de la justice, un vent de généralisation des modes alternatifs de règlement des conflits et de recours des technologies souffle sur les procédures judiciaires en général et sur les procédures civiles et commerciales en particulier. S’inscrivant dans cette logique, la loi n° 2020-08 du 23 Avril 2020 portant modernisation de la justice en République du Bénin n’a pas manqué de faire faire une place aux modes alternatifs de règlement des conflits. Elle met également un accent sur la dématérialisation progressive des procédures judiciaires concernant la saisine des juridictions, le suivi des procédures et le paiement électronique des frais afférents. Cependant, malgré ces mesures à encourager, les juridictions, au risque de rompre, ploient toujours devant les litiges fonciers et commerciaux. La présente étude a pour objet d'analyser les forces et les faiblesses du système judicaire béninois et vérifier si la modernisation des modes alternatifs de règlement des différends et l’intégration de la technologie dans les processus de résolution des différends peuvent être un vecteur de l’accès à la justice au Bénin. Despite the crucial importance of justice in our society, it is clear that the Beninese justice system presents significant challenges in terms of accessibility, efficiency and public trust. The costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent the costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent oneself, as well as the inhospitable nature of the courts are indicators of a broken justice system. Indeed, limitations in access to justice fuel citizens' mistrust of the state justice system. In the interests of speed and efficiency of justice, a wind of generalization of alternative methods of dispute resolution and recourse of technologies is blowing through judicial procedures in general and civil and commercial procedures in particular. In line with this logic, Law No. 2020-08 of 23 April 2020 on the modernization of justice in the Republic of Benin did not fail to make room for alternative methods of conflict resolution. It also emphasizes the gradual dematerialization of judicial procedures concerning the referral of cases to the courts, the monitoring of procedures and the electronic payment of related costs. However, despite these measures to be encouraged, the courts, at the risk of breaking down, are still bending before land and commercial disputes. The purpose of this study is to analyze the strengths and weaknesses of the Beninese judicial system and to verify whether the modernization of alternative dispute resolution methods and the integration of technology into dispute resolution processes can be a vector of access to justice in Benin.
Keywords: ACCESS TO JUSTICE; ADR; Accès à la justice; Business; Bénin; Commercial; Différend; Dispute; Foncier; Information; Land; MARD; Technologie; Technology

The UNCITRAL Model Law: "Follow you follow me" or "I do it my way" - Wilske, Stephan (Contemporary Asia arbitration Journal, 2025)
Keywords: Arbitral Awards; Arbitral procedure; Arbitration agreements; Arbitration friendliness; Domestic arbitration law; Germany; Harmonization; Harmonization of law; International Commercial Arbitration; International standards; Modernization; Recognition and enforcement; Statutory frameworks; Taiwan; UNCITRAL Model Law

The Middle Eastern and African Arbitration Review 2025 : Telecoms disputes in the Middle East and Africa - Mouzoula, Natalia; Kamau, Alice (Global Arbitration Review, 2025)

Arbitration Fees, Expenses and Determination Controls - Al-Taani, Muhanned; Al-Majali, Tawfiq; Mosabeh, Rageh; Mayah, Yousef (Jordan Journal of Applied Science-Humanities Series, 2025)

Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation, Mediation, and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation, Industrial; Officials and employees; Social justice

La mise en œuvre de la médiation institutionnelle en droit OHADA - Oueina, Florent; Oussale, Aladji Aberridjoua Aubin Hugues (Revue africaine de droit des affaires, 2025)
Il ne suffit pas d’adopter un nouvel Acte uniforme pour satisfaire à la demande ou garantir une sécurité juridique apparente du droit africain des affaires ou encore enrichir le régime uniforme du règlement des différends dans l’espace OHADA ; ou même pallier le vide législatif qui existait encore au sein de l’OHADA sur la médiation. Il ne s’agit pas d’un Acte uniforme de plus, mais d’un réel instrument juridique qui pourrait favoriser le retour des investisseurs et améliorer les conditions des affaires dans l’espace OHADA. Il faut chercher à savoir si cette nouvelle approche de la justice sera une réussite dans ledit espace.

Mediación y Arbitraje en Línea: Ventajas y Desafíos - Salguero, Katherine Coraima Guano; López, Vilma Patricia Salguero; Cáceres, Alez Remigio Escobar; Chávez, Luis Alberto Morales (Polo del Conocimiento, 2025)
La mediación y el arbitraje en línea han surgido como soluciones eficaces para la resolución de conflictos en un mundo digitalizado, ofreciendo ventajas como reducción de costos, accesibilidad y flexibilidad horaria. Sin embargo, enfrentan desafíos como la brecha digital y la seguridad de la información. Un estudio basado en encuestas a profesionales y usuarios confirma la utilidad de estas herramientas, pero subraya la necesidad de mejorar la infraestructura tecnológica y establecer marcos regulatorios claros. A pesar de los obstáculos, estos métodos representan una evolución significativa en la gestión de disputas legales.
Keywords: Arbitrage; Arbitragem; Arbitraje en línea; Arbitration; Brecha digital; Mediación; Mediation; ODR; Online dispute resolution

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy

L'équité dans l'arbitrage - Djeudjo Tankeu, Ghislain (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Le tribunal arbitral tranche le litige conformément aux règles de droit, mais cette garantie est fragile car le législateur OHADA ajoute à moins que les parties lui aient conféré mission de statuer en amiable composition. Ces amiables compositeurs sont donc des arbitres qui peuvent ne pas appliquer la loi, qui peuvent statuer en équité, ce qui implique la reconnaissance, aux arbitres, d’un pouvoir modérateur sur les obligations contractuelles litigieuses. Mais cette autorisation de statuer en amiable composition ne leur interdit pas de statuer en droit, simplement, le tribunal arbitral amiable compositeur qui appliquerait exclusivement les règles de droit, doit s’expliquer sur la conformité de celles-ci à l’équité. L’arbitrage tend aussi à la satisfaction de l’idéal du procès équitable. C’est ainsi que l’équité est une exigence dans la constitution et lors des suites du tribunal arbitral. The arbitral tribunal shall decide the dispute in accordance with the rules of law; but this guarantee is fragile because the OHADA legislator adds unless the parties have given him the mission to rule in amicable composition. These amicable composers are therefore arbiters who may not apply the law, who can rule in equity; which implies the recognition, to the arbitrators, of a moderating power over the disputed contractual obligations. But this authorization to rule in amicable composition does not prevent them from ruling in law. Clearly, the amicable arbitral tribunal which would exclusively apply the rules of law, must explain their compliance with fairness. Arbitration also tends to satisfy the ideal of a fair trial. This is how fairness becomes a requirement in the constitution and during the proceedings of the arbitral tribunal.

Le règlement des différends en matière d’environnement au Cameroun - Gueukam Tchako, Yannick (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
La présente contribution intitulée « Le règlement des différends en matière d’environnement au Cameroun » ; vise la mise en œuvre des règles de protection de l’environnement de par l’impact des actes mis en cause ou du préjudice causé, selon l’origine des acteurs ou selon les règles invocables. Ce faisant, elle s’intéresse aux solutions qu’apportent certaines dispositions relatives à la matière environnementale au cameroun. A l’analyse, on observe dans la première hypothèse, que les modes alternatifs de règlement non contentieux des différends se veulent plus rapide et accessibles tout en favorisant le respect des lois environnementales. Dans la seconde hypothèse, il s’agit de faire appel au juge judiciaire pour trancher les différends. De par son impact, la position du juge apparaît comme l’outil essentiel d’identification des dommages susceptibles d’être causés à l’environnement et constituant le socle sur lequel est construit le plan de gestion de l’environnement. The present contribution entiled « The settlement of environmental disputes in Cameroon » ; aims at the implementation of environmental protection rules according to the impact of the acts in question or of the damage caused, depending on the origin of the impact or according to the invocable rules. In doing so, it looks at the solutions provited by certain provisions relating to environmental matters in Cameroun. On analysis, it can be observed in the first hypothesis, the alternative methods of non-contentious settlement of disputes that are intented to be faster and more accessible while promoting compliance with environmental laws. In the second hyperthesis, it is a question of appealing to the judicial judge to settle disputes. Because of its impact, the position of the judge appears to be the essentiel tool for identifying the damage likely to be caused to the environment and constituting the basis on which the environmental management plan is built.
Keywords: Différends; Disputes; Environment; Environnement; Jurisdictional settlement; MARD; Non-jurisdictional settlement; Règlement juridctionnel; Règlement non juridictionnel

Transforming arbitration: exploring the impact of AI, blockchain, metaverse and Web3 - Piers, Maud; McCarthy, Sean (Radboud University Press, 2025)
In an era where technology is rapidly transforming the legal landscape, Transforming Arbitration explores how innovations like AI, blockchain, the Metaverse, and Web3 are reshaping arbitration as a key form of dispute resolution. The book features insights from leading academics, practitioners, and policymakers, offering a comprehensive look at how these advancements are influencing our conceptual, substantive and procedural understandings of many parts of this field. Each chapter examines the challenges and opportunities presented by these technologies, raising important questions about the compatibility of traditional arbitration processes with digital innovations. As the legal field adapts to developments like cryptocurrencies, NFTs, and 'virtual' disputes, this book provides valuable guidance on the future implications for arbitration. By questioning established norms and advocating for fresh approaches, Transforming Arbitration is a vital resource for legal professionals and scholars committed to evolving with the times. Combining theoretical exploration with practical recommendations, this collaborative volume equips the legal community with the tools to navigate the complexities of our digital age with confidence and foresight.
Keywords: AI; Arbitrage; Arbitragem; Arbitration; Artificial Intelligence; Blockchain; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Electronic Commerce; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Du dessaisissement du juge étatique face à la convention d'arbitrage en droit de l'OHADA - Anciza Migani, Ryan; Mbazi, Grâce Beda; Murhula Bahati, Pacifique; Iragi Ntwali, Valéry (Studia Universitatis Babeș-Bolyai Studia Europaea, 2024)
The State Judge's Relinquishment of Jurisdiction over Arbitration Agreements under Ohada Law. The use of arbitration instead of state judges is increasingly popular in the business world. The parties to contracts thus prefer to choose a judge more quickly and less cumbersomely, with more confidentiality and less publicity. If the advantages of resorting to arbitration are undoubted, its effects leading to the total withdrawal of state jurisdictions attract the attention of many. The incompetence of the judge due to arbitration then tends to completely rule out the latter, which merits a better understanding of the powers and competence of the arbitrator and a good understanding of the place of the state judge in the arbitration procedure.
Keywords: Arbitration agreement; Convention d’arbitrage; Divestiture; Droit OHADA; Juge étatique; OHADA law; State judge

From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

Confidentialité, secret, protection des données et intelligence artificielle dans la procédure arbitrale - Zengue, Laurent-Fabrice (Modes Alternatifs de Règlement des Différends (MARD), Justice amiable, 2024)
L’arbitrage étant l’un des modes alternatifs de règlement des différends, sa particularité est qu’il est confidentiel, secret, rapide, conventionnel et juridictionnel. En ce qui concerne spécifiquement l’obligation de confidentialité et de secret, son étendue est double. D’abord, il y a l’étendue matérielle, qui porte sur la procédure arbitrale, la composition du tribunal arbitral, la nature du litige, les ordonnances du tribunal arbitral, les documents soumis par les parties litigantes, les délibérations et la sentence. En second lieu, il y a l’étendue personnelle, qui concerne les témoins, les parties, les arbitres, le comité d’arbitrage, l’institution ou le centre d’arbitrage, le secrétaire du tribunal arbitral, les experts et tous les autres intervenants de la procédure arbitrale. La problématique centrale est d’analyser comment la confidentialité, le secret, la protection des données personnelles, y compris dans l’hypothèse du recours à l’intelligence artificielle peut être adressée et solutionnée dans le cadre d’une procédure arbitrale.
Keywords: Arbitrage; Arbitration; Confidentialité des données; Intelligence artificielle; Protection des données

Essai sur les critères d'arbitrabilité des litiges en Droit OHADA et en Droit Français - Dizo, Kevin (Nantes Université, 2024)
Le sujet de thèse explore comment définir les critères d’arbitrabilité des litiges acceptés par la justice arbitrale et étatique en France et dans l’espace OHADA. Les recherches ont montré que chaque système juridique a déjà des critères établis par les législateurs et la doctrine. L’arbitrage, étant à la fois juridictionnel et conventionnel, implique une interaction entre les justices arbitrales et étatiques, nécessitant des critères d’arbitrabilité efficaces. Ces critères doivent distinguer clairement les litiges arbitrables des inarbitrables et repartir soigneusement les compétences entre les juridictions. Alors, notre thèse questionne l’efficacité de ces critères et propose des améliorations pour remédier à leurs limites. The thesis topic explores how to define the arbitrability criteria of disputes accepted by arbitration and state justice in France and in the OHADA space. Research has shown that every legal system already has criteria set by legislators and doctrine. Arbitration, being both jurisdictional and conventional, involves an interaction between the arbitral and state courts, requiring effective arbitrability criteria. These criteria must clearly distinguish between arbitrable and non-arbitrable disputes and carefully allocate jurisdiction between the courts. So, our thesis questions the effectiveness of these criteria and proposes improvements to remedy their limitations.
Keywords: Arbitrability; Arbitrabilité; Arbitrage (droit); Arbitration; Criteria; Critères; Droit prospectif; Effectiveness; Efficacité; Pays de l'OHADA; Prospective law

L'autonomie de la clause compromissoire en droit de l'arbitrage Marocain et Québécois: entre consécration et limites - Rafai, Khawla (Université de Montréal, 2024)
Le principe de l’autonomie de la clause compromissoire est au cœur du mécanisme de l’arbitrage, tout en demeurant complexe et polyvalent. Cette étude met en lumière les différentes dimensions de ce principe, tout en identifiant ses limites face aux exigences fondamentales de justice et d’ordre public. L’autonomie de la clause compromissoire signifie d’abord que cette clause, bien qu’intégrée dans un contrat principal, existe et survit de manière indépendante. Concrètement, cela veut dire qu’une contestation ou une invalidité du contrat principal n’affecte pas automatiquement la clause compromissoire. Cette indépendance permet aux parties de préserver leur engagement à soumettre les litiges à un tribunal arbitral, offrant ainsi une sécurité juridique et une continuité au processus de résolution des conflits. L’arbitrage repose ici sur un engagement volontaire et anticipé, qui ne saurait être remis en cause par des circonstances affectant le contrat lui-même. Au-delà de cette indépendance, l’évolution du principe d’autonomie a permis d’introduire une autre dimension : la liberté de choix dans les règles qui régissent la clause compromissoire. Cela signifie que les parties ne sont pas nécessairement liées aux règles du contrat principal. Cette forme d’autonomie favorise la flexibilité, permettant aux parties de concevoir une procédure arbitrale adaptée à leurs besoins spécifiques. Cependant, cette liberté rencontre certaines limites, notamment en matière d’ordre public, qui agit comme un rempart pour protéger les valeurs fondamentales de justice et d’équité. Un autre aspect fondamental de ce principe est son interaction avec le concept de compétence-compétence, selon lequel le tribunal arbitral est habilité à statuer sur sa propre compétence. Cette relation étroite entre les deux principes peut créer une certaine confusion, car si l’autonomie de la clause concerne sa validité et son indépendance, la compétence-compétence relève plutôt du pouvoir décisionnel des arbitres. Toutefois, ces deux notions, bien que distinctes, contribuent ensemble à garantir l’efficacité de l’arbitrage en permettant de résoudre rapidement les questions liées à la compétence et à la validité de la clause. L’étude aborde également la transmissibilité de la clause compromissoire, qui pose un défi théorique à l’idée d’autonomie. En cas de cession ou de transfert du contrat principal, la clause compromissoire accompagne généralement le contrat, ce qui semble paradoxal par rapport à son indépendance. Cette apparente contradiction s’explique toutefois par la nécessité pratique d’assurer la continuité des mécanismes d’arbitrage, en particulier dans des situations complexes comme les contrats multipartites ou les groupes d’entreprises. Enfin, le principe d’autonomie, malgré sa robustesse et son importance dans l’arbitrage, demeure encadré. La protection des intérêts fondamentaux des parties les plus vulnérables et des principes essentiels de justice impose des limites nécessaires. L’ordre public joue ici un rôle clé en veillant à ce que la liberté contractuelle ne se traduise pas par une atteinte aux droits fondamentaux ou aux valeurs essentielles de la société. En conclusion, l’autonomie de la clause compromissoire est un instrument essentiel qui garantit la stabilité et l’efficacité de l’arbitrage. Elle repose sur une double dynamique : une indépendance par rapport au contrat principal et une flexibilité permettant aux parties d’organiser librement la procédure arbitrale. Toutefois, cette autonomie doit coexister avec des limites claires pour concilier la liberté contractuelle avec les exigences de justice, assurant ainsi un équilibre nécessaire entre efficacité et protection des principes fondamentaux. The principle of the autonomy of the arbitration clause is central to the arbitration mechanism, while remaining both complex and multifaceted. This study sheds light on the various dimensions of this principle and identifies its limits in the face of fundamental justice and public policy requirements. The autonomy of the arbitration clause primarily signifies that the clause, although incorporated into a principal contract, exists and survives independently. In practical terms, this means that a dispute regarding or the invalidity of the principal contract does not automatically affect the arbitration clause. This independence enables the parties to uphold their agreement to submit disputes to arbitration, thereby ensuring legal certainty and continuity in conflict resolution processes. Arbitration thus rests on a voluntary and preemptive commitment that cannot be undermined by circumstances affecting the main contract. In addition to this independence, the development of the principle of autonomy has introduced another significant aspect: the freedom of the parties to determine the rules governing the arbitration clause. This autonomy allows the parties to deviate from the rules of the principal contract, fostering flexibility and enabling the design of arbitration procedures that meet their specific needs. However, this freedom is not without limits, particularly where public policy intervenes as a safeguard to preserve fundamental principles of justice and fairness. A crucial component of this principle is its interaction with the kompetenz-kompetenz doctrine, which empowers the arbitral tribunal to rule on its own jurisdiction. This close relationship between the two concepts may cause confusion: the autonomy of the arbitration clause concerns its validity and independence, whereas kompetenz-kompetenz pertains to the decision-making authority of arbitrators. Despite their distinctions, both principles collectively enhance the effectiveness of arbitration by facilitating the prompt resolution of jurisdictional and validity-related challenges. This study also explores the issue of the arbitration clause’s transmissibility, which presents a theoretical challenge to the notion of autonomy. In cases where the principal contract is assigned or transferred, the arbitration clause typically follows the contract, creating a seemingly paradoxical situation regarding its independence. This apparent contradiction can, however, be justified by the practical need to maintain the continuity of arbitration mechanisms, particularly in complex contexts such as multiparty contracts or corporate groups. Ultimately, despite its essential role and resilience, the autonomy of the arbitration clause is subject to necessary constraints. The protection of vulnerable parties and the preservation of fundamental principles of justice impose clear limitations. Public policy serves as a crucial safeguard to ensure that contractual freedom does not infringe upon fundamental rights or societal values. In conclusion, the autonomy of the arbitration clause is a cornerstone of arbitration’s stability and effectiveness. It is characterized by independence from the principal contract and the flexibility afforded to the parties in shaping their arbitration proceedings. However, this autonomy must be balanced against clear limits to harmonize contractual freedom with justice requirements, ensuring an essential equilibrium between efficiency and the protection of core principles.
Keywords: Arbitrability; Arbitrabilité; Arbitration; Arbitration clause; Autonomie; Autonomy; Clause compromissoire; Extension; Ordre public; Public policy; Transmissibility; Transmission

The role and mandate of the motor industry ombudsman of South Africa : addressing prospects and challenges to enhance consumer protection - Tshabalala, Thapelo; Magau, Phemelo (PER / PELJ, 2024)
The Motor Industry Ombudsman of South Africa (MIOSA) is an industry ombud recognised under the Consumer Protection Act 68 of 2008 (CPA). The MIOSA regulates the interaction and provides for alternative dispute resolution in the automotive and related industries in South Africa. Moreover, the MIOSA is an impartial organisation that focusses on the resolution of disputes where a deadlock has been reached between the automotive and related industries and their customers, as well as relationships among participants in the automotive and related industries to the benefit of the parties. The role of the MIOSA is to make recommendations in cases referred to it where parties cannot reach common ground and are unable to arrive at mutually acceptable agreements following a dispute. This analysis explores and proffers possible solutions to address the challenges that impede the MIOSA from discharging its role and mandate under the CPA effectively in resolving consumer disputes in the South African automotive industry.
Keywords: Automotive industry; Consumer protection; Dispute resolution; MIOSA; Ombuds

Legal Certainty in the Resolution Process of Business Disputes due to Default on Payment with Bank Guarantee through Arbitration - Wijaya, Didit Wijayanto (International Journal of Science and Research, 2024)
Corporations have been established and recognized in Indonesia as entities engaged in business activities since 1602. In these business activities, disputes can occur regarding the non-disbursement of Bank Guarantees through the Indonesian National Arbitration Board (BANI). Therefore, this research uses the Normative Juridical method through a literature review. The research questions considered are (1) What is the guarantee of legal certainty in the process of resolving business disputes regarding Bank Guarantee payments through the Arbitration Board? (20) What can the Supreme Court Decision provide legal certainty for resolving business disputes through arbitration in Indonesia? The process of resolving business disputes in default on Bank Guarantee payments through the Arbitration Court has fulfilled the legal certainty principle. The results showed that the rules were available through different Arbitration and Alternative Dispute Resolution Laws, as well as other laws applied consistently in the BANI Surabaya Decision Number 59/ARB/BANI-SBY/XI/2021. The Supreme Court Decision Number 918 B/Pdt.Sus-Arbt/2023 tried the appeal case and rejected the application for annulment of the arbitration decision from the Applicant. In addition, legal certainty is created for corporate legal efforts to take the arbitration route.
Keywords: Arbitrage; Arbitragem; Arbitration; Business Disputes; Default; Legal Certainty

The Middle Eastern and African Arbitration Review 2024 : CRCICA and new CRCICA Arbitration Rules - Selim, Ismail; Hafez, Mohamed (Global Arbitration Review, 2024)

Lawyers and Non-Lawyers in International Arbitration: Discovering Diminishing Diversity - Nottage, Luke; Teramura, Nobumichi; Tanna, James (Loyola of Los Angeles International and Comparative Law Review, 2024)

A Proposal for Reforming the Calculation of Damages in Investment Treaty Arbitration = Proposition pour le calcul des dommages-intérêts dans l’arbitrage au titre des traités d’investissement = Propuesta para Reformar el Cálculo de Daños en el Arbitraje de Los Tratados de Inversión - Jarrett, Martin (Investment Treaty News, 2024)

Characterization (and Registration) of a “BRI Dispute” - Kirkwood, Jamieson (Asian Journal of International Law, 2024)
This article explores the terms “BRI dispute” and “BRI jurisprudence”. It undertakes a practical and theoretical analysis that considers whether “BRI disputes” have distinct and visible characteristics and are capable of being identified in a legal sense. This is important since practitioners – arbitration centres and law firms – use the term broadly and without specific criteria. By exploring the customary usage and the approach of legal scholars to the term, presenting examples of “BRI disputes” and examining their unique features, and constructing a theoretical approach (utilizing the concepts of ratione materiae, ratione loci, ratione temporis, and ratione personae; and considering the jurisprudence of the ICSID), this article moves from a broad to a narrow analysis to develop both a definition and a system of registration of “BRI disputes” for use by academics, practitioners, and policymakers.
Keywords: BRI; Belt and Road; China; Dispute Settlement; ICSID

Favoriser la culture du règlement amiable des différends : étude du droit béninois à la lumière du droit français - Ligan, Cyrille Sèmako (Université de Limoges, 2024)
Cette réflexion se propose de contribuer au développement des modes amiables de règlement des différends dans la culture juridique béninoise afin de permettre aux justiciables, majoritairement analphabètes, d'avoir des alternatives opportunes aux voies judiciaires classiques. Tandis que la justice fait face à de nombreux défis, aussi bien en France qu'au Bénin, le développement et la promotion remarqués des modes amiables de règlement des différends connaissent un certain succès en la matière en France. Au Bénin, le législateur encourage, incite mais ne propose aucun régime particulier pour le recours effectif au règlement amiable des différends. Cette recherche tente ainsi d'examiner de façon approfondie et d'interroger les différends mécanismes législatifs existants, tant les enjeux en termes d'accès à la justice sont considérables. Les principaux enjeux de cette thèse sont donc liées aux perspectives du développement des mode amiables et à leur encadrement pour remédier aux insuffisances et contre-performances de la justice étatique béninoise.
Keywords: Amicable settlement; Bénin / OHADA; Civil Procedure; Culture; France; Justice; MARD; Mediación; Mediation; Mediação; Médiation; Procédure civile; Règlement amiable

The impact of ISDS arbitration claims and adjudication on cross-border direct investment - Du, Julan; Zhang, Yifei (Transnational Corporations Review, 2024)
This study investigates the impact of the arbitration cases under the Investor-State Dispute Settlement (ISDS) scheme on cross-border direct investment in the form of merger and acquisition deals. The initiation of ISDS claims has significant and negative effects on direct investment from the claimant home country to the developing or weak-institution responding country. Indirect expropriation claims often have stronger effects than direct expropriation claims. The investor-win arbitration cases produce a significant substantiation effect by reducing merger flows, while the state-win cases produce an acquittal effect that encourages the subsequent capital inflow to the respondent state. Both effects are more striking in weak-institution or less developed target countries. We also detect some spillover effects of ISDS arbitration.
Keywords: Arbitration decisions; Cross-border merger deals; Direct and indirect expropriations; ISDS claims

Les qualités essentielles de l'arbitre en droit OHADA - Agbénoto, Koffi Mawunyo (Revue africaine de droit des affaires, 2024)

Les actualités de l'arbitrage maritime - Delebecque, Philippe (Revue africaine de droit des affaires, 2024)

Panorama critique de l’arbitrage OHADA - Ngono, Véronique Carole (Revue africaine de droit des affaires, 2024)

The Enforcement of Settlement Agreements Under the Ohada Uniform Act on Mediation - Nshom, Kelese George (IUS LAW Journal, 2024)
On 23 November 2017, OHADA member states adopted the Uniform Act on Mediation. The Act lays down rules relating to mediation of disputes which, if successful, ends in a settlement agreement. Settlement agreements that are not freely respected by the parties will have no effect unless they are forcefully executed. Forceful execution is made with the help of a court or notably public who are empowered to insert an executory formula on the agreement after verification of its regularity. These local authorities involved in the enforcement process rely on domestic laws of member states which vary from state to state. This has the effect of tainting the harmonization process intended by the OHADA lawmaker and may be inimical to investors. This raises the problem of the suitability of the Act to dispute settlement as regards enforcement of settlement agreements. With the help of qualitative and comparative analysis, this article brings to limelight the intricacies of the enforcement of settlement agreements underOHADA. It concludes that enforcement of settlement agreements is rendered simple and rapid but faces serious drawbacks which could be alleviated by setting up OHADA mediation institution to oversee the entire mediation process, besides other recommendations.
Keywords: Agreement; Enforcement; Exequatur; MARD; Mediación; Mediation; Mediação; Médiation

A renúncia a direitos fundamentais processuais na arbitragem: o caso particular do direito a requerer a anulação da sentença arbitral na arbitragem internacional - Teles, Joana Ataíde Cordeiro Galvão (Universidade Nova de Lisboa, 2024)
A arbitragem é um meio de resolução de litígios, que se alicerça na autonomia privada e é reconhecida, quer internacionalmente, quer nas constituições estaduais analisadas, como um modo de exercício, alternativo aos tribunais estaduais, do direito fundamental constitucional à tutela jurisdicional efetiva. A questão que se coloca é a de saber se, em primeiro lugar, as partes podem acordar renunciar, validamente, a direitos fundamentais processuais na arbitragem e, podendo, com que requisitos e dentro de que limites, para, em segundo lugar e em particular, aplicar os requisitos e limites referidos à (in)admissibilidade da renúncia ao direito a requerer a anulação da sentença arbitral na arbitragem internacional. Partindo da ponderação do âmbito, conteúdo e regime dos direitos fundamentais em confronto, de um lado, à tutela jurisdicional efetiva, incluindo o direito à arbitragem e outros direitos fundamentais processuais, como o de impugnar a sentença arbitral em determinados casos e, do outro lado, à autonomia privada, que fundamenta a renúncia, e sem prejuízo de a ponderação dever ser feita em cada caso concreto, concluo que a renúncia àqueles direitos é válida, se cumprir determinados requisitos subjetivos e objetivos, que identifico, incluindo os limites e os respetivos critérios para aferir da referida (in)validade. Quanto ao direito a requerer a anulação da sentença arbitral na arbitragem internacional, concluo que, sem prejuízo e com base nas soluções consagradas de jure constituto, a renúncia por acordo das partes é, do ponto de vista constitucional normativo e, de jure constituendo no direito português, válida, desde que se respeitem aqueles requisitos. Em particular, tem de existir um meio de impugnar a sentença arbitral, quando esta viole, de forma grave, direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, que não estão na disponibilidade das partes, nos casos e termos necessários a garantir o conteúdo essencial do direito fundamental à tutela jurisdicional efetiva. No entanto, há margem do legislador para adotar o regime mais adequado ao propósito referido. Na arbitragem internacional, do ponto de vista normativo-constitucional, podem as partes renunciar, total e/ou parcialmente, à anulação na sede, quando há a possibilidade de controlo último, pelo menos de violações graves de direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, aquando do reconhecimento e execução da sentença arbitral, sendo esta a solução legal que, na minha opinião, melhor se coaduna com a arbitragem internacional no seu todo. Arbitration is a dispute resolution mechanism rooted in private autonomy and internationally recognised, as well as in the national constitutions analysed, as an alternative means to state courts for exercising the constitutional fundamental right to effective judicial protection. The primary question of this dissertation is whether the parties can validly agree to waive fundamental procedural rights in arbitration, and if so, under what conditions and within what limits. Secondly, I specifically apply these conditions and limits to the (in)admissibility of waiving the right to seek annulment of the arbitral award in international arbitration. By weighing the scope, content and framework of conflicting fundamental rights – the right to effective judicial protection (encompassing the right to arbitration and other fundamental procedural rights, such as the right to challenge the arbitral award in certain cases), against private autonomy (which justifies the waiver) – and, without prejudice to the necessary case-by-case balancing, I conclude that the waiver of these rights is valid, provided that subjective and objective requirements, including the limits and criteria for assessing the (in)validity of the waiver, are met. Regarding the right to request annulment of the arbitral award in international arbitration, I conclude that, without prejudice to and relying on legal solutions established de jure constituto, the waiver by agreement of the parties is valid from a normative constitutional perspective and de jure constituendo under Portuguese Law, provided such subjective and objective requirements are respected. Specifically, there must be a means to challenge the arbitral award when it seriously violates fundamental procedural rights and/or public order interests of each State, which are beyond the parties’ disposal, in certain cases and under certain terms as necessary to protect the core essence of the fundamental right to effective judicial protection. However, the legislator retains discretion to adopt the most appropriate legal framework for this purpose. In the context of international arbitration, from a normative-constitutional perspective, the parties may waive annulment at the seat, in whole and/or in part, provided there is the possibility of ultimate oversight, particularly in cases involving serious violations of fundamental procedural rights and/or public order interests of each State at the stage of recognition and enforcement of the arbitral award. In my opinion, this legal solution is the one that best aligns with the global system of international arbitration.
Keywords: Annulment; Anulação; Arbitragem; Arbitragem Internacional; Arbitration; Autonomia Privada; Direitos Fundamentais Processuais; Fundamental Procedural Rights; International Arbitration; Private Autonomy; Renúncia; Waiver

L'amiable au service du sauvetage de l'entreprise en difficulté en droit OHADA : la médiation et la conciliation - Toe Adouabou, Laure (Revue africaine de droit des affaires, 2024)
L’acte uniforme originel sur les procédures collectives avait prévu une procédure préventive, le règlement préventif, au bénéfice des débiteurs qui traversent des difficultés sérieuses. La nécessité de la consécration d’une procédure à la fois amiable et préventive s’est imposée. C’est désormais chose faite depuis la révision de 2015. Le législateur a ainsi consacré les procédures de conciliation et de médiation à l’article 2-1 de l’Acte uniforme sur les procédures collectives d’apurement du passif (AUPC). Si pour la mise en œuvre de la première, il faut se référer à l’AUPC, la deuxième est règlementée dans l’Acte uniforme sur la médiation (AUM). Nous proposons donc dans cette étude, à la suite de la présentation de ces procédures amiables comme modes anticipatifs et efficaces de sauvetage d’entreprises, des pistes de réflexion afin de rendre effectif le recours à cet arsenal juridique.

L’autorité de la chose jugée dans l’arbitrage OHADA - Toe, Souleymane (Revue africaine de droit des affaires, 2024)

Transformative impact of blockchain technology and smart contracts on dispute resolution: legal challenges and other implications. - Christie, David; Mante, Joseph; Mak, Charles Ho Wang (10th Kuwait International Law School annual international academic conference (KILAW 2024), 2024)
This paper comprehensively analyses the potential of blockchain technology and smart contracts to revolutionise dispute resolution. As dispute resolution methods evolve, blockchain and smart contracts, which offer efficiency, transparency, and fairness, are becoming more critical. That is especially the case in mediation and construction adjudication, which are less traditionally formal and tend to be carried through much more quickly than other forms of dispute resolution. The opportunity of blockchain comes from its ability to demonstrate a tamper-proof, clear record, reducing risks of misunderstanding and bias. This facilitates the transfer and verification of evidence both in the carrying out of projects and during dispute resolution processes. Smart–digital contracts with terms coded indirectly- allow for automated contract enforcement. They execute automatically upon meeting specific conditions. This automation brings a new efficiency level, cutting the time and costs of conventional dispute resolution. Nonetheless, integrating blockchain and smart contracts in dispute resolution faces several challenges. The current limited understanding and acceptance of these technologies in the legal sector is an imminent issue. Legislative changes are necessary to provide a solid legal framework for these technologies in legal processes and to address potential inconsistencies of approach. Such reform requires strong cooperation among lawmakers, technologists, and legal experts to ensure implementation that adheres to legal and ethical norms and ensures that the technologies can be applied with confidence by the stakeholders within the process. This collective effort is crucial for seamlessly integrating blockchain and smart contracts into legal frameworks.
Keywords: Blockchain technology; Dispute resolution methods; English law; Smart contracts

Current Issues of the Utilization of Online Dispute Resolution as a Method for International Trade Dispute Settlement - Rohmah, Nuzul Quraniati (Ipso Jure, 2024)
The transformation of international trade from conventional to digital impacts several things, including resolving international trade disputes. In order to realize an efficient and effective dispute resolution process, many countries have implemented ODR to settle international trade disputes. This study aims to analyze the implementation of ODR in various countries and examine issues with unclear guidelines based on international law. This research observes the development of ODR in Indonesia and the urgency for its implementation in Indonesia. The research is normative juridical, with a statutory and comparative approach. The results obtained in this study are model law arrangements relating to the standardization of ODR Providers aimed to protect the personal data of the parties, unification of ODR dispute resolution clauses, and formulation of national legal instruments to create legal certainty regarding ODR, including ODR proceedings, permits, and monitoring,  as well as recognition and execution process of electronic ODR decisions.
Keywords: International Trade; ODR; Online Dispute Resolution; Regulation

L'agence de régulation des télécommunications au Cameroun : un centre d'arbitrage d'une nature particulière - Silabing Ouethy, Jasmine Diane (Revue africaine de droit des affaires, 2024)
La Procédure de règlement des différends opposant les opérateurs de communications électroniques au Cameroun prévoit, en premier, la saisine de l’Agence de Régulation des Télécommunications (ART). Cette dernière devra tenter de concilier les parties. Si cette tentative de conciliation échoue, alors le dossier sera transmis au Comité de Règlement des Différends (CRD) qui devra trancher le litige. Au cas où la décision intervenue est contestée par une des parties, elle pourra saisir soit les juridictions de droit commun, soit l’arbitre. Cependant, le législateur de 2010 n’a pas résolu toutes les questions relatives à l’intervention de cet arbitre. Par exemple, qui le constitue ? Quelles règles gouvernent la procédure et sur la base de quelles normes doit-il trancher ? Où aura lieu l’arbitrage ? L’examen de la loi de 1998 qui a été abrogée par celle de 2010, plus explicite sur la question, nous livre un régime qui tantôt rapproche le régulateur d’un centre d’arbitrage sur certains aspects, tantôt l’éloigne sur d’autres.

L'adaptabilité de l'arbitrage OHADA au contexte africain - Zakari, Amadou Hamani (Revue africaine de droit des affaires, 2024)
Le règlement des différends par les parties à une relation d’affaires, à travers l’arbitrage, n’est pas un fait nouveau dans les pays africains. Seulement, la nécessité était posée d’adapter ce mode alternatif aux réalités économiques africaines. Pendant longtemps, la majeure partie des contentieux dans lesquels les parties africaines sont impliquées, était réglée en dehors de ses frontières. Ce qui ne favorisait pas leur participation active. Mais la mise en place de l’OHADA et surtout, la création de la CCJA et plus tard son Centre d’arbitrage, suivis par les différents Centres d’arbitrage des Etats ont permis de faire de l’effectivité de l’arbitrage, une réalité. De l’arbitrage traditionnel, l’OHADA, a élargi le champ d’application de ce droit, en y incluant l’arbitrage des investissements, à l’occasion de la réforme du 23 et 24 novembre 2017. Actuellement, cette réforme fait l’objet de nombreuses critiques, notamment, sur le fait que pour certains, ce mécanisme favorise plus l’investisseur étranger que l’Etat partenaire, et que la notion même de l’investissement, n’a jusque-là pas fait l’objet d’une définition claire, tant en droit, en jurisprudence encore moins en doctrine. Pour mettre en œuvre l’arbitrage, les parties font recours à des arbitres, auxquels elles confient leurs différends suivant une convention d’arbitrage ou un instrument d’investissement qui détermine leur mission. Cette dernière peut être accomplie selon les cas, sous la forme d’un arbitrage institutionnel ou ad hoc, et finira par une sentence arbitrale, qui tranchera ce conflit. Comme dans la justice étatique, cette sentence est susceptible des voies de recours. L’arbitrage ne va pas sans écueils : de la constitution du tribunal arbitral à la sentence finale, plusieurs difficultés peuvent surgir.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Part XV Chapter 2, Conciliation beyond the courts: aspirations and limits of mandated and voluntary court mediation programmes from a multi-jurisdictional perspective - Ali, Shahla (Comparative Procedural Law and Justice, 2024)
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

Evaluating the International Arbitration of Oil and Gas Investment Dispute Settlement in Nigeria - Bisina, Lucky N. (African Journal of International Energy & Environmental Law, 2024)
This paper examined international arbitration as a tool for resolving investment disputes in Nigeria’s oil and gas sector, a critical industry that contributes significantly to Nigeria’s Gross Domestic Product (GDP), foreign exchange earnings and government revenues. This sector is marked by high-risk investments and complexity and often faces disputes arising from regulatory changes, fluctuating global prices, environmental concerns and contractual breaches. Arbitration, particularly in cross-border investments, provides a neutral, efficient and flexible mechanism for resolving such disputes. Using a doctrinal research methodology, the study analysed statutes, case law, international treaties, and academic sources. Findings revealed that while arbitration offers benefits such as neutrality and enforceability, there are still some challenges that must be addressed as a matter of urgency. Issues include resistance to enforcement of arbitral awards by Nigerian courts on grounds of national interest, high arbitration costs and biases favouring foreign investors. Nigeria’s legal framework, including the Arbitration and Mediation Act 2023 and the Petroleum Industry Act 2021, supports arbitration but lacks procedural clarity, leading to delays and inefficiencies. The paper concluded that legal reforms are essential to strengthen arbitration processes, enhance enforcement mechanisms and align Nigeria’s framework with international standards. Such reforms would foster investment stability and improve Nigeria’s attractiveness as an investment destination by reducing legal uncertainties. The paper recommended legislative and judicial improvements in order to achieve these goals.
Keywords: Dispute Settlement; International Arbitration; Investment Dispute; Oil and Gas Investment

Arbitration in the era of e-commerce: A comprehensive overview - Buhuri, Kristi (World Journal of Advanced Research and Reviews, 2024)
Technology is continuously evolving and has changed human interaction. It is consequently changing the ways disputes are solved. International dispute resolution procedures, and international arbitration, more specifically, are considerably influenced by the rapid expansion of innovative technologies. Years after the dot-com boom, Online Dispute Resolution (ODR) emerged and evolved considerably. Due to the digitalization of ODR methods, remote arbitration (or e-arbitration) is expanding. Arbitration is of particular interest due to its formal and binding nature, from a theoretical perspective. E-arbitration, as other ODR methods have attractive features as well as drawbacks, which are addressed in this document.  The purpose of this paper is three-fold: providing an overview of e-arbitration and the different considerations of this method, presenting the e-arbitration models of the European Union (EU), the United States (US), and the People’s Republic of China (PRC) and suggesting recommendations to improve international e-commerce arbitration, notably through a revision of the UNCITRAL Model Law on International Commercial Arbitration (UNCITRAL Model Law).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Digitalization; Innovative Technologies; ODR; Online Dispute resolution; e-Arbitration

Arbitration rules: In force as from 15 January 2024 - Cairo Regional Centre for International Commercial Arbitration (CRCICA, 2024)

Règlement d'arbitrage : En vigueur à compter du 15 janvier 2024 - Centre régional du Caire pour l’arbitrage commercial international (CRCICA, 2024)

التحكيم وفقًا لاتفاقية الأمم المتحدة بشأن نقل البضائع عن طريق البحر (هامبورغ، 1978) - Ghassan, ali; Haidara, jaber (Tishreen University journal of research and scientific studies -economic and legal sciences, 2024)
International maritime transport represents the backbone of international trade in our current era, for many reasons, such as low costs and the ability to transport large quantities of goods at once. The United Nations Convention on the Maritime Transport of Goods of 1978, known as the Hamburg Convention, represents a qualitative shift in regulating the rules of maritime transport of goods. Among the important topics regulated by the agreement is the subject of arbitration, as it is the most important means of settling disputes related to international trade contracts, especially the contract for the maritime carriage of goods. Accordingly, this research studies the rules of the Hamburg Convention related to arbitration as a means of settling disputes related to the contract for the maritime carriage of goods. يمثل النقل البحري الدولي عصب التجارة الدولية في عصرنا الحالي، ألسباب عديدة كانخفاض التكاليف والقدرة عمى والمعروفة 1978 نقل كميات كبيرة من البضائع دفعة واحدة، وتمثل اتفاقية األمم المتحدة لمنقل البحري لمبضائع لعام ىامبورغ، نقمة نوعية عمى صعيد تنظيم قواعد النقل البحري لمبضائع، ومن بين الموضوعات اليامة التي باسم اتفاقية نظمتيا االتفاقية، موضوع التحكيم، باعتباره أىم وسائل تسوية النزاعات المرتبطة بعقود التجارة الدولية، وخاصة عقد د اتفاقية ىامبورغ المتعمقة بالتحكيم كوسيمة لتسوية النزاعات النقل البحري لمبضائع، وبناء عميو يتناول ىذا البحث قواع ال
Keywords: Arbitration; Bill of lading; Bills of lading; Carriage of Goods by Sea (1978); Hamburg Convention; Hamburg Rules; International commercial arbitration; Maritime carriage contract; Maritime transport; UN Convention; اتفاقية ىامبورغ; التحكيم; سند الشحن; عقد النقل البحري

Bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta taraflar - Güngör, Tuba (Kırıkkale Üniversitesi, 2024)
Türk hukukunda, özellikle iş uyuşmazlıkları bakımından arabuluculuğun dava şartı olarak kabul edildiği tarihten bu yana, arabuluculuk kurumundan beklenen faydanın elde edilip edilmediği bir yana bırakılırsa öğreti ve uygulamada halen tartışıla gelen birçok konu bulunmaktadır. Bunlardan biri, çalışma konumuzu oluşturan bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta işçi ve işveren tarafların doğru ve tam olarak teşkilinin sağlanmasıdır. Alternatif çözüm yollarından biri olan arabuluculuğun dava şartı olarak düzenlenmesi, arabuluculuk faaliyetini yargılamanın ön şartı ve ayrılmaz bir parçası haline getirmiştir. Bu bakımdan arabuluculuk sürecinin doğru işçi veya işveren tarafla yürütülmemesi yargılamayı doğrudan etkileyecektir. İş uyuşmazlıkları bakımından işçi sıfatının belirlenmesi özellikle işçi olup olmadığı konusunda tereddüt yaşanan çalışanlar açısından önemlidir. İşveren tarafının doğru belirlenmesi ise, arabuluculuk faaliyetinin yanlış veya eksik işverenle yürütülmesinin ardından, yargılama sürecinde bu durumun tespit edilmesi halinde işveren tarafında değişiklik yapılamaması bakımından önem arz etmektedir. Arabuluculuk dava şartı olarak düzenlendiğinden, yargılama sırasında tamamlanabilmesi olanaklı değildir. Sürecin bu şekilde işlemesi ise mahkemeye erişim hakkının önünde engel teşkil edebileceği gibi, gerek iş güvencesi gerekse işçinin alacağına kavuşma noktasında hak kaybına ve mağduriyetine yol açabilecektir. In Turkish law, especially since the adoption of mediation as a condition for litigation in terms of labour disputes, there are still many issues that are still debated in the doctrine and practice, let alone whether the expected benefit of the mediation institution has been achieved. One of these issues is to ensure that the employee and employer parties are accurately and fully constituted in the mediation as a condition for litigation in terms of individual labour disputes, which is the subject of our study. The regulation of mediation as a condition of litigation, which is one of the alternative remedies, has made the mediation activity a prerequisite and an integral part of the proceedings. In this respect, failure to conduct the mediation process with the right employee or employer party will directly affect the proceedings. In terms of labour disputes, the determination of the employee party is especially important for employees who are in doubt as to whether they are employees or not. The correct determination of the employer party is important in terms of not being able to make changes on the employer side if this situation is detected during the proceedings after the mediation is carried out with the wrong or incomplete employer. Since mediation is regulated as a condition of litigation, it is not possible to complete it during the proceedings. This process may constitute an obstacle to the right of access to the court, and may lead to loss of rights and victimisation in terms of both job security and the employee's receivables.
Keywords: Dava şartı arabuluculuk; Employee; Employer; Iş uyuşmazlığı; Işveren; Labour dispute; Mediation; İşçi

ISDS 2.0: Time for a Doctrine of Precedent? - Jarrett, Martin (Journal of international economic law, 2024)

La mediación y la cultura del acuerdo - Lagones, Delcy de Anglim (Deconstruyendo la justicia, 2024)
Keywords: China; Dispute Settlement; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements resulting from Mediation (2018); UNCITRAL Model Law on International Commercial Conciliation (2002)

Climate Change Litigation in Civil Law African Countries: An Assessment of Barriers and Potentialities in Cameroon - Mbarga, Daniel Armel Owona (Climate Litigation and Justice in Africa, 2024)
It seems like a long time ago that there were only a handful of climate lawsuits. Since the first climate lawsuits were filed in the United States in 1990,² a myriad of litigation has emerged at the national, regional and global levels. According to the Grantham Research Institute on Climate Change and the Environment, as of May 2021 the databases on climate litigation around the world contained 1,841 cases that were either in progress or had already been decided.³ This shows the exponential development of the phenomenon through which civil society organizations, public law legal entities and private individuals are
Keywords: Africa; Cameroun; Civil Law; Climate change; Litigation

La bonne administration de la justice arbitrale en droit OHADA - Megou Ebock, Jocelyne Yvonne (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La résolution d’un litige passe généralement par la justice étatique habilitée à faire appliquer les lois, à corriger et réparer les injustices subies. Rendre justice suppose que certains moyens soient réunis afin de garantir une bonne administration de la justice. Mais de plus en plus la justice étatique est concurrencée par une forme de justice ayant pour principaux acteurs les parties : il s’agit de la justice arbitrale. Cette forme de justice semble être la parfaite incarnation d’une bonne administration de la justice dans la mesure où elle renvoie à un emploi équilibré des moyens de justice en conformité avec les objectifs de célérité de la justice arbitrale. Justice rendue sur la base d’une convention d’arbitrage, la justice arbitrale s’accommode bien du respect des exigences d’un procès équitable et garantie la bonne administration de la justice. S’agissant de la bonne administration de la justice arbitrale OHADA, tout parait plus simple dans la mesure où le législateur en a fait un mode privilégié de règlement des différends contractuels et un instrument juridique adapté aux exigences d’une justice de qualité. Ainsi, la préoccupation majeure de cette étude est celle de savoir dans quelle mesure la justice arbitrale pourrait être considérée comme la « pierre philosophale » de la bonne administration de la justice arbitrale en droit OHADA. C’est à travers l’analyse d’un corpus juridique entièrement rénové le 23 novembre 2017 que la justice arbitrale est considérée comme la pierre angulaire de la bonne administration de la justice. Ceci se justifie par la double assertion selon laquelle elle respecte les principes généraux de bonne administration de la justice et qu’elle demeure une justice ancrée sur le respect des principes spécifiques à la justice arbitrale.
Keywords: Administration; Arbitrage; Arbitragem; Arbitration; Arbitre; Good administration; Justice; Proceeding; Procès équitable

Jus Mundi Arbitration Review - Mistelis, Loukas; Fan, Kun (JMAR, 2024)
Articles The Seven Cardinal Sins of Investment Dispute Settlement Investment Arbitration in the New Era: Engine or Obstacle in the Fight Against Climate Change? The UNIDROIT Principles as a Tool for the Internationalisation of Contracts by Arbitral Tribunals AI: The Modern Tribunal Assistant – Impact on Enforceability of Arbitral Awards under the New York Convention Automation & Augmentation: Artificial Intelligence in International Arbitration The IBA Guidelines on Conflicts of Interest in International Arbitration 2024 CIETAC: Overview of Dispute Resolution in the Digital Environment in China Swiss Supreme Court rejects CJEU’s Komstroy ruling Romania’s Supreme Court Decides that Associations and Foundations Based in Romania Can Only Set Up Arbitral Institutions if Authorized by Law Book Review – On Arbitration: V. V. Veeder QC, Selected Writings and Contributions to the Development of Law (Wordsworth & Veeder (eds), OUP 2023) Book Review – Investment Arbitration and Climate Change (Ipp & Magnusson (eds), Kluwer 2024)

A comprehensive outline towards conciliation in the contemporary world of E-commerce - N, Vinod; Gupta, Poonam (World Journal of Advanced Research and Reviews, 2024)
Since the start of the millennial era, technical advancements have led to exponential growth in electronic commerce, or e-commerce. According to the United Nations Conference on Trade and Development (UNCTAD), e-commerce sales reached about US$25 trillion globally in 2021 [1] and are expected to grow at a compound annual growth rate of 9% through 2027, which is twice as fast as the 4% annual growth rate predicted for traditional in-person retail [2]. Online dispute resolution (ODR) techniques that aim to settle disagreements and lower the likelihood of expensive lawsuits are becoming more and more necessary as both individuals and corporations use online shopping platforms. Due of its legally binding nature, arbitration is the most formal method, as was briefly discussed [3]. Online arbitration is carried out using electronic methods, like email and digital tools designed to make the duties of arbitrators and parties to a dispute easier. It adheres to the same rules and processes as traditional arbitration. On the plus side of e-arbitration, advancements in technology allow for time and cost savings without sacrificing the ease of remote filing. The conclusion of e-arbitration agreements raises several negative issues, including privacy and data protection issues for the consumer signing the agreements and power imbalances between corporate entities and the consumer. The degree to which artificial intelligence (AI) is effectively and sufficiently analysing a dispute between parties is up for debate because it's unclear how new this adjudication process is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Artificial Intelligence; Conciliation; E-Commerce; Inteligência artificial; Intelligence Artificielle; ODR; OECD

Concurrent Investor-State Claims Before Domestic Courts and Investment Treaty Arbitration Tribunals: Philip Morris, Vattenfall and Beyond - Nottage, Luke; Stendel, Robert (Virginia journal of international law, 2024)
Keywords: Arbitrage; Arbitragem; Arbitration

La compétence du for de situation de l’immeuble face aux conventions de juridictions - Tchouankeu Djeuda, Claudia (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
L’admission d’une maitrise par les parties de la compétence internationale par des clauses de juridictions ; notamment des conventions d’élection de for, des conventions d’arbitrage ou de médiation, amène à s’interroger sur l’efficacité réelle de ces accords. Pour ce qui est de la matière immobilière, le fort attachement de l’Etat aux questions de territoire et les considérations de proximité entre litige et le for du situs ont pour effet d’empêcher toute dérogation à la compétence directe du for de situation de l’immeuble ; tant lorsque l’immeuble est situé sur le for du juge saisi que lorsqu’il est situé à l’étranger. Toutefois, l’observation d’un possible fléchissement de l’exclusivité de ce critère de compétence conduit à un plaidoyer en faveur de l’efficacité, quoique encadrée, des conventions juridictions en la matière.
Keywords: Autonomie de la volonté; Autonomy of will; Compétence internationale des juridictions; Convention de juridiction; Immovable property’s location; International jurisdiction; Jurisdiction agreement; Lieu de situation de l’immeuble; Matière immobilière; Real estate matters

Arabuluculuk faaliyetinin anlaşma ile sona ermesi - Terzi̇ Kahraman, Si̇bel (Kadir Has Üniversitesi, 2024)
Arabuluculuk kurumundan beklenen avantajların ortaya çıkabilmesi arabuluculuk faaliyeti sonunda anlaşmaya varılması ile mümkündür. Mevzuatta sürekli değişiklikler meydana gelmekte ve kurumun kapsamına aldığı uyuşmazlıklar hızla genişletmektedir. Uygulamanın yerleşmesi ve zaman zaman doktrinde görüş ayrılıkları yaşanması kaçınılmazdır. Mevzuatta daha detaylı ya da değiştirilerek düzenlenmesine ihtiyaç duyulan alanlar bulunmaktadır. Tez, mevzuatta yapılan son düzenlemeleri de kapsayarak anlaşmayı tüm yönleriyle ele almayı ve kurumun daha iyi anlaşılmasına hizmet etmeyi amaçlamaktadır. Yapılan bu çalışmanın ilk bölümde arabuluculuğun kurumsal çerçevesi ortaya konulmuştur. Bu bölümde amaç arabuluculuk kurumunu ve arabuluculuk faaliyetinin işleyişini anlatabilmektir. Bu amaçla arabuluculuğun kapsamı, türleri, arabuluculuğun karşılaştırmalı hukukta ve Türk hukukunda gelişimi, yargı ve tahkimden farkı, med-arb uygulaması anlatılmıştır. İkinci bölümde sona erme halleri tek tek ele alınmış, sona erme hallerinin mevzuatta dağınık halde düzenlendiği hususuna dikkat çekilmiş ve başkaca sona erme halleri de dikkate alınarak tek bir madde halinde düzenlenebilmesi hususu önerilmiştir. Arabulucunun, faaliyeti sona erdirme yönünde inisiyatif almasının sona erme hali olarak düzenlenmesi yönünde de öneri getirilmiştir. Üçüncü bölümde anlaşmanın terminoloji sorununa ve benzer kavramlardan farkına değinilmiştir. Arabuluculuk faaliyeti sonunda varılan anlaşmanın esaslı unsurları tespit edilmiştir. Bu kapsamda, sözleşme serbestisi, şarta bağlı edim düzenlenip düzenlenemeyeceği gibi önemli hususlara yer verilmiştir. Anlaşmanın nasıl düzenleneceğine ilişkin öneride bulunulmuştur. Anlaşmanın hukuki niteliği, anlaşılan hususlara karşı dava açılamayacağı, anlaşmanın hukuka uygun düzenlenmediği takdirde karşılaşılabilecek sonuçlar anlatılmış ve anlaşmanın arabuluculuğa elverişli olmamasına rağmen düzenlenmesi, dava şartı kapsamına girmeyen bir hususta faaliyetin yürütülmesi ve anlaşmaya varılması, yanlış dava türünden yapılan başvuru sonucu anlaşmaya varılması, arabulucunun uzmanlık alanına girmeyen bir konuyla ilgili anlaşma sürecini tamamlaması, hukuka uygun arabuluculuk faaliyeti yürütülmemesi sonucunda anlaşmaya varılması, arabulucunun arabuluculuktan çekilmesi gerekirken yine de anlaşma yapması gibi anlaşmadan kaynaklı sorunlara yer verilmiştir. Dördüncü bölümde anlaşmanın yerine getirilmemesi durumunda icra edilebilirlik şerhi alınması hususu, mahkemeye başvuru, yargılama usulü, mahkemenin incelemesi, şarta bağlı olarak yapılan anlaşmaya şerh verilmesi, icra edilebilirlik şerhi alınan anlaşmanın icrası, anlaşmayla ilamlı ve ilamsız takip yapılması gibi önemli hususlar ele alınmıştır. Son olarak, arabuluculuk sonucunda elde edilen uluslararası ticari anlaşmaların icra edilmesini kolaylaştırması amacıyla hukukumuzda da kabul edilen Singapur Konvansiyonu incelenmiştir. The expected advantages of the mediation institution can be realized through reaching an agreement at the end of the mediation process. There are continuous changes in the legislation, rapidly expanding the scope of disputes covered by the institution. The thesis aims to comprehensively examine the agreement reached at the end of the mediation process, including recent legislative amendments, to better understand the institution and its operations. The first part of this study outlines the institutional framework of mediation, explaining its scope, types, development in comparative law and Turkish law, differences from judiciary and arbitration, and the practice of med-arb. The second part discusses the various termination conditions, highlighting the scattered nature of these conditions in legislation and proposing their consolidation into a single provision. It also suggests granting mediators the initiative to terminate the process as a termination condition. In the third part, attention is given to the terminology issues and distinctions from similar concepts regarding the agreement reached through mediation. The essential elements of such agreements are identified, covering issues like contractual freedom and the regulation of conditional obligations. Recommendations are made on how agreements should be drafted. The legal nature of the agreement, restrictions on litigation concerning agreed-upon matters, consequences of improperly drafted agreements, and issues arising from inappropriate mediation activities are discussed. The fourth part addresses the issue of obtaining enforceability endorsements for agreements not fulfilled, court applications, trial procedures, court reviews, endorsement of conditional agreements, enforcement of endorsed agreements, and procedures for enforcement with and without judgments. Finally, the study explores the Singapore Convention, adopted in our legal system to facilitate the enforcement of international commercial agreements resulting from mediation.
Keywords: ADR; Agreement termination; Alternative dispute resolution; Anlaşmazlık; Arabuluculuk; Executability Annotation; Kanunlar 6325 sayılı; Laws 6325 numbered; Mandatory mediation; Mediation; Mediator; Médiation; Singapore Convention; Zorunlu arabuluculuk

Sermaye şirketlerinde zorunlu arabuluculuk - Ulusan, Banu (Galatasaray Üniversitesi, 2024)
Çalışma 06.12.2018 tarihinde 7155 sayılı Kanun ile Türk Ticaret Kanunu'na eklenen TTK m. 5A hükmüyle getirilmiş zorunlu arabuluculuğun, sermaye şirketleri çerçevesinde incelenmesini konu almaktadır. TTK m. 5A hükmüyle önce, ticari davalardan, konusu bir miktar paranın ödenmesi olan, alacak ve tazminat davalarının zorunlu arabuluculuğa tabi olduğu düzenlenmiştir. Daha sonra, 28.02.2023 tarihli ve 7445 sayılı Kanun ile yine ticari dava olmaları kaydıyla, menfi tespit, itirazın iptâlî ve istirdat davalarını da zorunlu arabuluculuk kapsamına almıştır. TTK lafzıyla dava şartı arabuluculuk olarak da nitelendirilen zorunlu arabuluculuk kavramı, Türk hukuku bakımından yeni bir kavram sayılabilir. İlk olarak 2017 yılında 7036 sayılı Kanun ile iş uyuşmazlıkları için düzenlenen zorunlu arabuluculuk kavramı, daha sonra ticari uyuşmazlıklar ve tüketici uyuşmazlıkları için de düzenlenmiştir ve Türk hukukunda zorunlu arabuluculuğun uygulama alanı git gide genişleme eğilimi göstermektedir. Bu sebeple, doktrinde pek çok eleştiriye de uğrayan zorunlu arabuluculuk kavramının, özellikle sermaye şirketleri bağlamında incelenmesi amaçlanmıştır. Her ne kadar Türk hukukunda yeni bir kavram olsa da, karşılaştırmalı hukukta zorunlu arabuluculuk uzun zamandan beri uygulanan ve tartışilânbir konu olagelmiştir. Karşılaştırmalı hukuk bağlamında bir inceleme yapıldığında öncelikle, özellikle zorunlu arabuluculuğun menşei sayılabilecek Amerikan hukukunda, konu özellikle doktrinde farklı açılardan ele alınmıştır. Çalışmanın birinci bölümünde bu çerçevede bir inceleme yapılmış, zorunlu arabuluculuğun tabi olması gereken kıstaslar ortaya konulmaya çalışılmıştır. Bu kıstaslar, çalışmanın ilerleyen bölümlerinde yapılacak değerlendirmeler için de önem taşımaktadır. Bunun yanı sıra zorunlu arabuluculuğun türleri ve zorunlu arabuluculuğa aykırı davranışlara bağlanan yaptırımlar üzerinde de durulmuştur. Zorunlu arabuluculuğun ve benzeri uygulamaların farklı hukuk sistemlerinde ne şekilde yer aldığı değerlendirilmiştir. Bu değerlendirmeler kapsamında Alman hukuku bakımından ZPO §278 ile EGZPO §15a incelenmiştir. İsviçre hukuku bakımından ise ZPO §197 vd. hükümleri incelenmiştir. Her iki hukuk sistemi de zorunlu arabuluculuğu düzenlememiş, bunun yerine medeni usûl kanunlarında davanın görüleceği mahkemeler nezdinde uyuşmazlık çözüm sürecini düzenlemiştir. İtalya ve Fransa'da ise zorunlu arabuluculuk uygulamaları mevcut ise de bu, Türk hukukunun aksine, son derece sınırlı bir şekilde gerçekleşmiştir. Zorunlu arabuluculuğun kaynağı olan Amerikan hukukunda ise arabuluculuk, zorunlu tutulan tek uyuşmazlık çözüm yöntemi olmamıştır. Ayrıca zorunluluk hususu kanunla değil, genellikle her bir dava için mahkemenin yönlendirmesiyle sağlanmaktadır. Tüm bu ülkelerin ortak özelliği ise ticari uyuşmazlıkları zorunlu arabuluculuğa ya hiç tabi tutmamaları ya da çok dar bir kapsamda tabi tutmalarıdır. Arabuluculuk her ne kadar bir yargılama faaliyeti olmasa da zorunlu arabuluculuk dava öncesinde yer alan bir aşama olduğundan, kanaatimizce medeni usûl hukukuna hâkim olan ilkeler bakımından da incelenmelidir. Bu kapsamda zorunlu arabuluculuğun öncelikle adil yargılanma ilkesi ve mahkemeye erişim hakkı kapsamında tartışmalara sebep olduğu görülmektedir. Bunun yanı sıra usûl ekonomisi ilkesi, aleniyet ilkesi, tasarruf ilkesi ve dürüst davranma yükümlülüğü bakımından da değerlendirmelere yer verilmiştir. Aleniyet ilkesi bağlamında arabuluculuğa hâkim olan ilkelerden gizlilik ilkesinin ticari uyuşmazlıklar bakımından bir avantaj oluşturduğu söylenebilir. Tasarruf ilkesinde yapılandeğerlendirme maddî hukuk ve usûl hukuku çerçevelerinde yapılmıştır. Ayrıca zorunlu arabuluculuğun menşei Amerikan hukukunda hâkimin ve avukatların rolleri de dikkate alınarak, zorunlu arabuluculuğun Türk hukukundaki hâkimin yargılamayı sevk ve idaresi ilkesiyle tamamen bağdaşmadığı sonucuna varılmıştır. Dürüstlük ilkesi bakımından yine maddî hukukla da bağlantı kurularak bir değerlendirme yapılmış, zorunlu arabuluculuk süreci sonunda varılacak anlaşmanın dürüstlük kuralına uygun yapılması için yeterli mekanizmaların bulunmadığı kanaatine varılmıştır. Bunun dışında HUAK m. 18A/11 hükmü uyarınca zorunlu arabuluculuk sürecinin ilk toplantısına mazeretsiz katılmayan tarafın her durumda yargılama giderlerinin tümünden sorumlu olması ve lehine vekalet ücretine hükmedilememesinin orantısız bir yaptırım olduğu, ayrıca bu sebeple hiçbir durumda yargılama giderlerinden sorumlu olmayacağını bilen tarafın, açılacak dava sürecinde davayı uzatacak veya yanlış yönlendirecek ve dürüstlük kuralına uymayacak her tür davranışı yapabileceği kanaatine varılmıştır. Çalışmanın ikinci bölümü TTK m. 5A hükmünün uygulama koşullarına yoğunlaşmaktadır. Bu kapsamda, ticari davalar bakımından karşılaştırmalı bir değerlendirme yapılmak istenmiştir. Türk hukukunda TTK m. 4 hükmüyle ayrıca düzenlenen ticari davalar, diğer hukuk sistemlerinde ticaret mahkemeleriyle ilişkili olarak düzenlenmiştir. Bu değerlendirmede dikkat çeken husus, davaların ucuz, hızlı ve etkin bir şekilde sonuçlandırılmasının amaçlandığı diğer hukuk sistemlerinde hukukçu olmayan hâkimlerin de görev yaptığıdır. Türk doktrininde ise böyle bir uygulamanın uygun olmayacağı haklı olarak belirtilmiş, bu bağlamda zorunlu arabuluculuk uygulamasının daha uygun olduğu kanaatine varılmıştır. Ticari davalarda dava şartını düzenleyen TTK m. 5A hem medeni usûl hukuku hem de ticaret hukuku bakımından incelenmiştir. Medeni usûl hukukun bakımından yapılanincelemede dava şartı kavramı ve hükmün dava türlerine göre gösterdiği özellikler incelenmiştir. Ticaret hukuku bakımından ise, arabuluculuk süreci sonucunda varılacak anlaşmanın bir maddî hukuk sözleşmesi oluşundan da yola çıkarak basiretli tacir kavramı incelenmiştir. Ayrıca zorunlu arabuluculuğun HUAK m. 5 hükmü ve gizlilik ilkesi nedeniyle göstereceği özellikler nedeniyle, ticari sırların korunması bağlamında da bir değerlendirme yapılmıştır. Çalışmanın üçüncü ve son kısmı sermaye şirketlerinde zorunlu arabuluculuğun incelenmesine ayrılmıştır. Bunun için öncelikle Alman hukukunda pay sahipleri davaları olarak adlandırilândavalar hakkında değerlendirme yapılmaya çalışılmıştır. Bu değerlendirmeyle adi şirketlerden farklı olarak pay sahipleri davalarının genel olarak ortağa değil şirket tüzel kişiliğine yöneltilmesi gerektiği, bunun yanı sıra pay sahiplerinin şirketin menfaatleri için dava haklarını kullanabildiği görülmüştür. Bu değerlendirmenin, sermaye şirketleri uyuşmazlıklarında zorunlu arabuluculuk sürecinde başvuru yapacak taraflar ve anlaşmanın etkileyeceği kişilerin tespitinde yararlı olduğu kanaatindeyiz. Bu değerlendirmenin ardından TTK m. 5A kapsamına girebilecek sermaye şirketi uyuşmazlıkları tespit edilerek, her biri için zorunlu arabuluculuğun göstereceği özelliklerin belirlenmesine çalışılmıştır. Bu belirleme yapılırken her bir uyuşmazlık konusu hakkında genel bir çerçeve sunulmuş, açılabilecek davalar hakkında bilgi verilmiş ve bu bilgiler ışığında zorunlu arabuluculuğun uygulama koşulları ile doğurabileceği sakıncalar üzerinde durulmuştur. Son olarak, yapılantüm değerlendirmeler ışığında sermaye şirketlerinde zorunlu arabuluculukla ilgili de lege ferenda görüşümüze yer verilmiştir. Bu kapsamda sermaye şirketleri uyuşmazlıklarının, dava konularının şirketler hukuku kısıtlarına ve emredici kurallara tabi olması sebebiyle, zorunlu arabuluculuğa her zaman uyumlu olmayabileceği sonucuna varılmıştır. Üstelik, bazı arabuluculuk türlerinde yapılması elzem hukuki denetimin ve arabulucunun bu denetimi yapamayacak olmasının yaratacağı sakıncalara da değinilmiştir. Bunun sonucunda İsviçre ve Almanya örneklerinde olduğu gibi mahkeme bağlantılı uyuşmazlık çözümlerinin düzenlenmesinin daha uygun olduğu kanaatine varılmıştır. İflas bakımından bir değerlendirme yapıldığında ise, İİK m. 226 hükmü nedeniyle doğabilecek sorunlara dikkat çekilmiş, bu bağlamda zorunlu arabuluculuğa başvuru kapsamında düzenleme yapılması önerilmiştir. Son olarak zorunlu arabuluculuk ile varılmak istenen amaçlar da dikkate alındığında, bu amaçlara ulaşmak için taraflara arabuluculuk dışında uyuşmazlık çözüm yollarına başvurabilmelerine imkân verilmesi gerektiği kanaatine varılmıştır. Bu şekilde hem çabuk ve ucuz bir şekilde uyuşmazlıkların çözümü amacına ulaşabilecek, hem de tarafların ihtiyaçlarına daha uygun bir yöntem seçmelerine imkân tanınacaktır. […] This study focuses on application of Turkish Commercial Code Art. 5A, which is amended with Code Nr. 7155 in 2018, to equity companies. TCC Art. 5A regulated mandatory mediation for commercial cases with monetary claims at the beginning. However, through amendment with Code Nr. 7445 in 2023, negative declaratory actions, actions for annulment of objections and actions for restitution were taken into scope of this regulation. Mandatory mediation, which can also be named mediation as cause of action according to TCC m. 5A, can be deemed as a new context in Turkish law. Regulated for the first time for some labour law conflicts with Code Nr. 7036 in 2017, mandatory mediation is regulated also for commercial conflicts as well as consumer law conflicts. Thus, it can be observed that scope of mandatory mediation in Turkish law has a tendency to spread within time. Therefore, as a concept subject to various critics, mandatory mediation is to be evaluated in context of equity companies within this study. Although mandatory mediation is considered to be a relatively new concept in Turkish law, in frame of comparative law, it has a long history of application and has been subject to critics for a long time. It is observed that in comparative law, especially in American law, which can be considered as the source, mandatory mediation has been taken into consideration with many aspects. The first chapter of this study conducts an evaluation within this frame and aims to set the criterias for a better application of mandatory mediation. These criterias are important for evaluation in following chapters of this study. In addition, the variations of mandatory mediations and sanctions applied to the acts contrary to mandatory mediations are observed. Mandatory mediation and similar applications in different law systems are also examined. Within light of this examination, ZPO §278 and EGZPO §15a in German law is taken into consideration, as well as ZPO §197 ff. in Swiss law. Both systems do not regulate mandatory mediation and instead, regulated dispute resolution process within their Civil Procedure Codes. Although mandatory mediation is regulated in Itâlîan and French law systems, these regulations have strictly limited scope. American law, the origin of mandatory mediation, applies other means of dispute resolution as well. Moreover, mandatory mediation in American law is not regulated by a code; it is court oriented in general. The common point of these countries is that none of them applies mandatory mediation within a wide scope on commercial disputes. Although mediation cannot be considered as an act of judication, since mandatory mediation is a step before courts, it should be evaluated with regard of principals of civil procedure law. In this context, it is observed that mandatory mediation gave reason to many arguments related to fair trial and access to court. In addition, evaluations on principals pf procedural economy, publicity, power of disposition and honesty are conducted. With regard of principal of publicity, it can be considered that principal of confidentiality of mediation is an advantage. The evaluations on principal of power of disposition are made in frame of substantial and procedural law. Furthermore, taking the features of American civil procedure law, it is concluded that mandatory mediation is not compatible with the role of judge in Turkish law. With regard of principal of honesty, an evaluation in the light of substantial law is also made and it is concluded that rules to maintain honesty in mandatory mediation are not sufficient in Turkish law. As an addition, it is also stated that sanction in Code of Mediation Art. 18A/11 is unproportionate in context of principal of honesty before courts. The second chapter of this study focuses on conditions of TCC Art. 5A. With this regard, a comparative evaluation on commercial actions is made. Commercial actions, regulated with TCC Art. 4 in Turkish law, are regulated in relation with commercial courts in other law systems. With this evaluation, it is noted that in commercial courts, which aims to solve disputes in a cheap, quick and effective manner, gives place to judges who have not a judicial notion in other law systems. In Turkish literature, it is rightly emphasized that such an application is not appropriate for Turkish law. TCC Art. 5A is also examined within frame of civil procedure and commercial law. Within civil procedure law frame, the concept of cause of action is examined, as well as features of TCC Art 5A in relation to claim in actions. Within commercial law frame, since the agreement concluded within mediation is a contract in context of substantial law, the notion of prudent merchant is evaluated. Furtermore, for mandatory mediation demonstrates features within light of Code of Mediation Art. 5 and principal of confidentiality, an evaluation of trade secrets are also conducted. The third and last chapter concentrates on examination of mediation as a cause of action in equity company disputes. Thus, an action named shareholders' action in German law, which is clarified using notion of actio pro socio, is evaluated. According to this evaluation it is concluded that, unlike simple partnerships, shareholders shall submit their claims against legal entity of equity companies and not against other shareholders. Neverthless, it is also observed that in some cases shareholders are entitled to submit the tools of defence of equity companies for interests of company. This evaluation is essential in order to determine the parties of dispute and the persons effected from the agreement reached at the end of mandatory mediation process. Following this evaluation, the kinds of disputes in equity companies, which fall into scope of TCC Art. 5A, are determined and the features demonstrated by them in context of mediation as a cause of action are defined. In order to comply with this evaluation, information on each subject of action is given, features of the relevant actions are explained and in the light of all evaluations, conditions of application of mediation as a cause of action are explained. Finally, in light of evaluations made within this study, our de lege ferenda opinions on mandatory mediation in equity companies are set. Within this frame, since dispute in equity companies are subject to limitations on equity company law and compulsory legal rules, it is stated that they might not always compatible with mediation as a cause of action. In addition, possible problems arisen from lack of legal supervision in mediation process are also mentioned. As a result, it is concluded that, it would be more convenient to regulate court annexed dispute resolution tools, similar with examples of Germany and Switzerland. With regard to bankruptcy proceedings, it is concluded that possible problems in relation to Turkish Code of Bankruptcy and Enforcement Art. 226 are highlighted and it is suggested that, in order to eliminate such problems, necesarry regulations by legislator should be made. Lastly, taking the goals of mediation into consideration, in order to reach these goals effectively, the importance of giving parties the opportunity to be able to choose other means of dispute resolution apart from mandatory mediation, is found to be essential. Thus, dispute resolution process will take place in a quick and cheap manner and parties will have the chance to be able to choose a dispute resolution method that suits their needs and interests.
Keywords: MARD; Mediación; Mediation; Mediação; Médiation

UNCITRAL Model Clause on Adjudication - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Confidentiality - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Highly Expedited Arbitration - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Technical Advisers - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

Blockchain and smart contracts: a game changer in mediation? - Mak, Charles Ho Wang; Mante, Joseph (Asian journal on mediaton, 2023)
In light of accelerating technological innovation and shifts in dispute resolution paradigms, this article elucidates the transformative potential of blockchain technology and smart contracts in mediation. The paper posits that these advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. The article critically assesses the inherent challenges and argues that overcoming these obstacles necessitates a multi-stakeholder approach, encompassing legislative measures, educational initiatives, and technological enhancements. It ultimately contends that blockchain and smart contracts hold the capacity to significantly reshape the landscape of mediation.
Keywords: Blockchain technology; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; Smart contracts

Arbitrage et modes amiables de règlement des conflits - Clay, Thomas (Recueil Dalloz, 2023)
Le hasard a voulu que la décision qui a été distinguée comme la plus importante de l’année 2023 corresponde à un arrêt annulant une sentence rendue par un tribunal arbitral que présidait l’auteur de ces lignes. Les usages académiques interdisant de commenter un tel arrêt, il sera renvoyé aux innombrables publications dont il a déjà fait l’objet (JCP E 2023. 1061, note D. Mainguy ; JCP 2023. 507, note D. Mouralis ; D. actu. 14 mars 2023, obs. J. Jourdan-Marques ; Rev. arb. 2023. 423, note F.-X. Train ; RTD com. 2023. 582, obs. E. Loquin ; Cah. arb. 2023. 501, note M. Henry ; Gaz. Pal. 16 mai 2023, p. 12, obs. L. Larribère ; JCP 2023. 221, § 4, obs. P. Giraud ; Lexis®PSL, 27 janv. 2023, obs. M.-L. Cartier et A. Meyniel ; Paris Baby Arbitration 2023, n° 59, p. 9, obs. G. Ghedjati et M. Villeneuve ; IA Reporter 12 janv. 2023, obs. L. Bohmer ; Global Arbitration Rev. 13 janv. 2023, obs. A. Ross), ayant même eu les honneurs de l’Agence France Presse (AFP) dans une dépêche du 20 janvier 2023 et… du Canard enchaîné (18 janv. 2023, p. 3). Les commentaires de doctrine sont d’ailleurs très majoritairement critiques sur cet arrêt inattendu, parfois avec des nuances, en dehors d’un seul, celui publié à la Revue de l’arbitrage, qui suit une approche univoque si singulière qu’elle interroge sur les motivations réelles de l’auteur : un professeur de droit ne devrait pas écrire ça. Il n’en reste pas moins que cet arrêt, aussi remarqué qu’il fût, ne sera donc pas commenté dans ces colonnes. Mais, pour que soit moins iconoclaste le paradoxe d’un panorama de droit de l’arbitrage qui n’évoque pas la décision la plus remarquée de l’année en droit de l’arbitrage, encore fallait-il qu’il en fût fait mention dans cet éditorial, lieu d’une licence académique plus libre, sous peine de laisser croire à une auto-censure, voire à une gêne du soussigné, qui, au contraire, assume pleinement d’user de sa liberté d’expression en toutes circonstances.
Keywords: Arbitrage; Arbitration; Convention d'arbitrage; Sentence arbitrale

La distinction entre recours en annulation et exequatur en droit français de l'arbitrage international - Alain, Alex (Université Paris 1, 2023)
S’interroger sur la distinction entre le recours en annulation et exequatur, c'est poser la question du régime juridique applicable à chacun de ces mécanismes de contrôle de la sentence arbitrale. Ces derniers paraissent, par hypothèse, différenciés puisqu’ils relèvent de deux catégories de procédures que le droit français ne confond pas : les voies de recours et l’exequatur. L’application des règles du droit processuel français commande donc en principe de ne pas confondre le recours en annulation, qui est une voie de recours, avec l’exequatur. Or, s’il est bien une notion qui innerve tous les pans du droit français de l’arbitrage international, c’est celle d’« autonomie ». Il en résulte que malgré la référence expresse à des notions bien connues du droit commun - i.e 1’exequatur et la voie de recours pour le recours en annulation -, celles-ci paraissent recevoir une acception spéciale en droit français de l’arbitrage international. Gommant les différences qui séparent traditionnellement les voies de recours de l’exequatur, le droit français de l’arbitrage international semble à bien des égards confondre le recours en annulation et l’exequatur. Émerge ainsi l’idée que les sentences arbitrales font l’objet d’une procédure de contrôle unique. Une confusion certaine entre le recours en annulation et l’exequatur existe en droit français de l'arbitrage international, elle est à l’origine de nombreuses incertitudes. Pour remédier à ce constat, l’étude propose l’application aux sentences arbitrales des règles du droit commun, relatives aux voies de recours et à l’exequatur.
Keywords: Action for annulment; Arbitrage international; Civil Procedure; Contrôle de la sentence arbitrale; Distinction; Droit international privé; Exequatur; International Arbitration Law; Jugements étrangers; Private International law; Procédure civile; Recours en annulation; Voie de recours; Voies d'exécution

Le développement du recours aux modes amiables en matière civile : étude comparée entre la France, les Etats-Unis et le Canada - Watrin, Geoffrey (Université de Strasbourg, 2023)
Darwin disait que « les espèces qui survivent ne sont pas les espèces les plus fortes ou les plus intelligentes, mais celles qui s’adaptent le mieux aux changements ». La justice n’échappe pas à cette règle. Sans cesse confrontée à de nouveaux défis, tels que l’encombrement judiciaire ou la pacification des relations entre les parties, cette dernière va devoir trouver les moyens qui lui permettront de fonctionner en accord avec les besoins de son temps. Les modes amiables de résolution des conflits pourraient bien en faire partie. Implantés de longue date et particulièrement appréciés aux États-Unis et au Canada, ces derniers semblent pour l’heure boudés par les praticiens et les justiciables en France. Le législateur montre néanmoins un intérêt de plus en plus important pour ces méthodes et pour cause : elles ont fait leurs preuves Outre-Atlantique. Dès lors, comment parvenir à les développer au sein de notre système ? C’est la question à laquelle nous essayerons de répondre dans cette thèse.
Keywords: ADR; Canada; Development; Droit comparé; Développement; France; MARC; Mediation; Modes amiables; Médiation; Procédure civile; United States; États-Unis

La mediación y el arbitraje laboral en el Procedimiento concursal: regulación y dificultades aplicativas - Dormido Abril, Julia (Trabajo, Persona, Derecho, Mercado: Revista de Estudios sobre Ciencias del Trabajo y Protección Social, 2023)
La declaración de concurso de una empresa no solo va a afectar al deudor concursado, pues tal calificación también tiene un efecto directo sobre los trabajadores. Sobre todo, si en el seno de un procedimiento concursal, para salvar la continuidad de la actividad empresarial, se decide adoptar alguna medida de reestructuración, tal y como pueden ser las modificaciones sustanciales de las condiciones de trabajo, el traslado, el despido, la suspensión de contratos o la reducción de jornada por causas económicas, técnicas, organizativas o de producción. Las decisiones que sobre cualquier de éstas se tomen pueden dar lugar a conflictos que tienen que solucionarse mientras el proceso judicial sigue su curso. Por ello, el legislador ha incorporado la mediación y el arbitraje en la norma mercantil como vías de solución extrajudicial de tales conflictos. Se trata de una fórmula jurídica no exenta de interrogantes, relacionados en este caso con aspectos como, la norma aplicable a tales mecanismos de solución extrajudicial, la incorporación de la solución al auto o el modo en el que impugnar el acuerdo o el laudo en materia laboral. The declaration of insolvency of a company will not only affect the insolvent debtor, as such a classification also has a direct effect on the employees. Particularly if, within the context of an insolvency procedure, in order to save the continuity of the business activity, it is decided to adopt any restructuring measure, such as substantial modifications to working conditions, relocation, dismissal, suspension of contracts or reduction of working hours for economic, technical, organisational or production reasons. The decisions taken on any of these may give rise to conflicts that have to be resolved while the judicial process is still underway. For this reason, the legislator has incorporated mediation and arbitration into commercial law as a means of extrajudicial settlement of such disputes. This is a legal formula that is not free of questions, related in this case to aspects such as the rule applicable to such out-of-court settlement mechanisms, the incorporation of the solution into the or-der or the way in which to challenge the agreement or award in labour matters.

Standing in international investment and trade disputes - Ossa, Ralph; Staiger, Robert W.; Sykes, Alan O. (Journal of International Economics, 2023)
International investment agreements employ dispute settlement procedures that differ markedly from their counterparts in trade agreements. A prominent and controversial difference arises with respect to the issue of “standing”: Who has the right to complain to adjudicators about a violation of the agreement? While trade agreements limit standing to the member governments (state-to-state dispute settlement), investment agreements routinely extend standing to private investors as well (investor-state dispute settlement). We develop parallel models of trade and investment agreements and employ them to study this difference. We find that the difference in standing between trade and investment agreements can be understood as deriving from the fundamentally different problems that these agreements are designed to solve. Our analysis also identifies some important qualifications to the case for including investor-state dispute settlement provisions in investment agreements, thereby offering a potential explanation for the strong political controversy associated with these provisions.
Keywords: Bilateral investment agreements; Investments; Investor-State Dispute Settlement; State-to-state dispute settlement; Trade agreements; Trade dispute

Legal Reconstruction of Dispute Settlement Between Importers and Exporters International Law Perspective - Pristha Utama, Wahyu; Tri, Lazarus; Setiyono, Joko (Journal of Xi'an Shiyou University, Natural Sciences Edition, 2023)
Reconstruction of dispute resolution law between importers and exporters from an international law perspective. The purpose of this study is to analyze: 1) How does the law of dispute resolution between importers and exporters perspective international law? 2) How is the implementation of the recommendations of the dispute resolution bodies of the World Trade Organization from an international law perspective? The research method used is normative juridical with a statutory approach, concept approach, and case studies. The results showed that: 1) Import export is a series of company activities that begin with an agreement. The agreement is the result of previous activities carried out by exporters and importers, namely in the form of supply and demand. The agreement is poured into a sales contract which is an agreement between exporters and importers to trade goods in accordance with mutually agreed conditions and each party binds itself to carry out all obligations incurred. 2) The series of processes undertaken in dispute settlement at the WTO consist of 4 processes, including: Mandatory Consultation between disputing parties to reach a settlement approved by the parties, Application for the establishment of a Panel, the Appellate Body, and the implementation and implementation of recommendations and provisions endorsed by the DSB.
Keywords: Dispute Resolution; Exporter; Importer; International Law; Reconstruction

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

Chronique de jurisprudence de droit de l’arbitrage - Larribère, Lilian (Gazette du Palais, 2023)
Dans la période récente, de nombreuses précisions viennent affermir le régime procédural des recours portés devant le juge français du contrôle. Ainsi, de l’article 1520 du Code de procédure civile qui ne liste que les griefs portant sur la sentence arbitrale elle-même, et qui autorise donc à se prévaloir des moyens d’irrecevabilité de la requête d’exequatur (Cass. 1re civ., 13 avril 2023, n° 21- 50053). Ainsi encore, de l’irrecevabilité du recours en annulation qui n’emporte pas exequatur de la sentence arbitrale (Cass. 1re civ., 7 juin 2023, n° 22-12757). On notera également les arrêts nombreux portant sur le régime de la convention d’arbitrage, et partant de la compétence arbitrale. Enfin, l’arrêt rendu par la Cour de Strasbourg dans l’affaire Semenya (CEDH, 11 juill. 2023, n° 10934/21, Semenya c/ Suisse) montre que le contrôle des droits fondamentaux devra être mené de manière scrupuleuse par le juge de l’annulation, et ce, même si la situation litigieuse ne présentait guère de liens avec les États parties à la CEDH.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Contentieux para-arbitral; Contentieux post-arbitral; Jurisprudence arbitrale

Les modes alternatifs de traitement des conflits familiaux : étude comparative des droits français et ivoirien - Ouattara, Tiégolo Fougniguéta (Université de Bordeaux, 2023)
La famille se fonde sur des liens qui ne sont pas nécessairement rompus par l'existence d'un conflit. De ce fait, la résolution des conflits familiaux nécessite l'usage de méthodes favorisant la restauration des relations familiale ou un vivre ensemble harmonieux entre les membres de la famille. Dans cette perspective, en droit français et ivoirien, les systèmes traditionnels de résolution des conflits familiaux étaient partagés entre la méthode amiable et la méthode judiciaire. En droit français, ce partage s'observe durant la période de l'Ancien régime et la période révolutionnaire. En droit ivoirien, cela s'observe durant la période coloniale. Cependant, dans ces deux ordres juridiques, dans le cadre légal, la méthode amiable a été reléguée au second plan au profit de la méthode judiciaire. Toutefois, ces dernières années, face au besoin de réduire la charge de travail du juge, d'apporter des solutions aux conflits dans des délais raisonnables et d'adapter la résolution des conflits à la conception sociale de la justice, se développent les modes alternatifs. Ceux-ci regroupent un ensemble de mécanismes ayant pour objet la résolution amiable des conflits. Le développement de ces modes varie d'un pays à l'autre. En France, ils font l'objet d'un développement accru. En Côte d'Ivoire leur développement est timide. Néanmoins, des méthodes similaires aux modes alternatifs sont utilisées par le justiciable ivoirien pour la résolution des conflits familiaux, mais dans un cadre informel. Eu égard à l'attachement du justiciable ivoirien à la justice informelle, aussi qualifiée de justice traditionnelle, se manifeste un besoin de sa reconnaissance légale. La justice traditionnelle ivoirienne étant par principe amiable tout comme les modes alternatifs, le développement de ces modes dans la législation familiale ivoirienne pourrait se faire dans le cadre d'une conciliation des règles les régissant avec celles régissant la justice traditionnelle ivoirienne. Mais cette conciliation devrait être faite en tenant compte des limites des modes alternatifs observées grâce à l'expérience française de ces mécanismes et des réalités sociales ivoiriennes. The family is founded on ties that are not necessarily broken by the existence of conflicts. Therefore, resolving family conflicts requires the use of methods that promote the restoration of family relationships or a harmonious living together among family members. In this regard, under French and Ivorian law, traditional systems for resolving family conflicts were divided between the amicable method and the judicial method. In French law, this division can be observed in the periods of the Old Regime and the Revolution. In Ivorian law, this can be observed during the colonial period. However, in both legal systems, the amicable method failed from a legal point of view in favor of the judicial method. This failure was due to the litigant and the legislator. However, in recent years, faced with the need to reduce the judge's workload, provide solutions to conflicts in reasonable timeframes, and adapt conflicts resolution to the social conception of justice, alternative methods of resolution are developed. These comprise a set of mechanisms aimed at amicably resolving conflicts. The development of these methods varies from one country to another. In France, they are subject to increased development. In Côte d'Ivoire, their development is modest. Nevertheless, similar methods to alternative modes are used by Ivorian litigants for the resolution of family conflicts, but in an informal setting. In view of the Ivorian litigants' attachment to informal justice due to the fact that it represents Ivorian traditional justice, there is a need for its legal recognition. Since Ivorian traditional justice is amicable by nature, just like alternative modes, the development of these methods in Ivorian family legislation could take place within the framework of a reconciliation of the rules governing them with those governing Ivorian traditional justice. However, this reconciliation should take into account the limitations of alternative modes observed through the French experience of these mechanisms and ivorian social realities.
Keywords: Alternative modes; Comparative law; Conflicts; Conflits; Côte d'Ivoire; Différends; Disputes; Droit; Droit comparé; Famille; Famille (droit); Family law; France; Justice traditionnelle; Litigation; Litiges; Modes alternatifs; Médiation familiale; Règlement de conflits; Traditional justice

Justice civile amiable, justice pénale négociée... vers une justice consensuelle ? (Revue Justice Actulaités, 2023)
Keywords: Conciliation; Conciliação (processo civil); Consentement; Justice amiable; Justice négociée; Médiation; Politique de l'amiable; Procédure pénale

Arbitrabilidade objetiva em contratos administrativos - Cardoso, Paula Butti (Universidade de São Paulo, 2023)
A Lei n° 9.307, de 1996, a Lei de Arbitragem, com a redação que lhe foi dada pela Lei n° 13.129, de 2015, passou a prever expressamente que a Administração Pública direta e indireta poderá utilizar-se da arbitragem para dirimir conflitos relativos a direitos patrimoniais disponíveis. Ultrapassadas as discussões em torno da arbitrabilidade subjetiva, a arbitrabilidade objetiva das disputas envolvendo a administração pública ganha papel de destaque. Divergências a respeito do que seriam os direitos patrimoniais disponíveis da administração pública faz com que a questão seja frequentemente levada ao poder judiciário, em atentado a valores informadores da arbitragem, como a segurança jurídica e a celeridade. Daí a necessidade de se buscar solução para a questão, o que pode ser feito a partir do direito administrativo contemporâneo, que valoriza cada vez mais a atuação consensuada em detrimento da atuação unilateral e impositiva da administração pública. Law No. 9,307, of 1996, the Brazilian Arbitration Law, amended by Law No. 13,129, of 2015, expressly provides that the direct and indirect public administration may use arbitration to resolve conflicts relating to renounceable patrimonial rights. Discussions relating to arbitrability regarding the parties in arbitration have given place to discussions regarding subject-matter arbitrability relating to disputes involving public administration. Different understandings about the renounceable patrimonial rights of the public administration frequently take the discussion to be ruled by judiciary courts, jeopardizing values that inform arbitration, such as legal certainty and celerity. The current scenario demands that a solution to the issue is provided. That can be done based on modern administrative Brazilian law, which increasingly values consensual action rather than unilateral action by public administration.
Keywords: Administrative contract; Administrative law; Arbitrabilidade objetiva; Arbitrability; Arbitrage; Arbitragem; Arbitration; Consensualidade; Consensuality; Contrat administratif; Contrato administrativo; Direito administrativo; Droit administratif

The impact of blockchain and smart contracts on dispute settlement: a case for mediation. - Mak, Charles Ho Wang; Mante, Joseph (2023 TIAC Journal of international dispute settlement inaugural annual conference (TJIDS 2023), 2023)
The research is premised on two important developments, accelerating technological innovation and shifts in dispute resolution paradigms. These advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. To make this case, we use blockchain technology and smart contracts as technological exemplars, and mediation as an example of dispute resolution mechanism that can be positively impacted by the use of the relevant technology. The potential of these technologies to promote dispute avoidance and the emerging legal frameworks for resolving blockchain technology and smart contract disputes were also explored. We also examine how blockchain technology and smart contracts can be integrated into the mediation process, the advantages, challenges, and possible solutions.
Keywords: Blockchain technology; Dispute resolutions; Disputes; Smart contacts; Technological innovation

L'unification des pratiques de médiation et de conciliation dans les pays membres de l'OHADA - Dah, Sègla Septime (Université de Toulon, 2023)
L’unification des pratiques de médiation et de conciliation s’inscrit dans une démarche centrée sur l’activité du médiateur ou du conciliateur et présente un intérêt double. D’une part, elle forge l’action du médiateur ou du conciliateur en répertoriant les critères afin d’instituer un référentiel qualité. Ce dernier servira à évaluer ses bonnes pratiques du médiateur ou du conciliateur. L’unification desdites pratiques n’entend pas instituer une bonne pratique de la médiation ou de la conciliation. Elle prône pour une identification desdites pratiques afin de constituer un socle commun à l’action et aux prestations de tous les médiateurs des pays membres de l’OHADA. D’autre part, elle est garante du droit à un médiateur compétent et de l’accès à un processus de résolution des conflits de qualité pour une médiation efficace. Le droit à un médiateur compétent et l’accès à un processus de résolution des conflits de qualité sont les deux composantes essentielles du recours effectif à la justice amiable en droit OHADA. Ce recours découle d’un droit de la médiation et de la conciliation qui est en codification dans les pays membres de l’OHADA. Ladite codification est un préalable à cette démarche d’unification. Ainsi, la construction du droit de la médiation et la conciliation doit être accompagnée d’une réelle politique d’unification des pratiques de médiation et de conciliation afin d’inscrire le recours à l’amiable dans l’habitude des justiciables.
Keywords: Amicable settlement; Appeals; Conciliation; Droit de l’amiable; Effectif; Effective; Efficace; Efficient; Evaluation; Justice; Justiciables; Litigants; MARD; Mediation; Médiation; Médiation internationale; Organisation pour l'harmonisation en Afrique du droit des affaires; Quality standards; Recours; Référentiel qualité; Unification; Évaluation

L'incompétence du juge étatique en présence d'une convention d'arbitrage en droit OHADA - Fofana, Modibo Mohamed; Diallo, Hamadi (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Le droit OHADA de l'arbitrage contient tous les ingrédients pour dissuader l’intervention du juge dans la procédure arbitrale soulevée par les plaideurs les plus récalcitrants. Face aux principes d’autonomie et de force obligatoire de la convention d’arbitrage, l’article 13 de l’Acte uniforme relatif au droit de l’arbitrage pose une obligation d’abstention à la charge du juge étatique à chaque fois qu’il est saisi d’un litige ayant déjà fait l’objet d’une compromission. À moins que la convention d’arbitrage soit manifestement nulle ou manifestement inapplicable, le juge étatique doit s’abstenir de toute intervention. Toutefois, en dépit du principe d’autonomie et de force obligatoire de la convention d’arbitrage, l’absence d’imperium qui caractérise la vie du tribunal arbitral nous amène à relativiser la posture de neutralité dont le juge étatique est contraint d’adopter. Ce dernier, dans le respect de la primauté reconnue à l’arbitre, se verra ponctuellement reconnaître le pouvoir d’assister l’arbitrage.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Convention d’arbitrage; Droit OHADA; Incompétence; Juge communautaire; Juge d’appui; Juge étatique

L’intervention du juge étatique dans l’arbitrage de l’Organisation pour l'Harmonisation du Droit des Affaires en Afrique (OHADA) : Une carence normative du droit communautaire - Fofana, Modibo Mohamed; Diallo, Hamadi (International Journal of Strategic Management and Economic Studies (IJSMES), 2023)
Les attributions du juge étatique sont confrontées à un flou juridique qui en résulte l’absence d’un régime juridique claire. A l’issue de cette réflexion, il convient de retenir que l’intervention du juge étatique à l’arbitrage dans l’espace OHADA est une œuvre particulièrement complexe car, si dans l’arbitrage spécifique de la CCJA, Il revient au juge communautaire la charge d’administrer la procédure et d’assurer le suivi durant la phase post-arbitrale, la détermination du juge étatique dans l’arbitrage de droit commun est une opération complexe et ses attributions ne sont pas claires. En effet, le flou lexical entourant l’expression générique désignant le juge étatique, entraîne un morcellement de son champ de compétence. Ce sont ses faiblesses qui justifient que des palliatifs soient proposés en vue de renforcer l’efficacité de l’intervention du juge national et de garantir par la même occasion la sécurité juridique dans l’espace OHADA.
Keywords: Arbitrage; Arbitragem; Arbitration; Juge communautaire; Juge d’appui; Juge étatique; OHADA

La transformation du Système de résolution des conflits entre État hôte et investisseur étranger : la conciliation des intérêts d’acteurs d’un système adaptatif complexe - Deligny Malchair, Marion (Université de Lorraine, 2023)
Les conflits entre État hôtes et investisseurs étrangers occupent, depuis une dizaine d’année le devant de la scène géopolitique. Le questionnement se porte aujourd’hui de façon globale sur l’articulation des méthodes de règlement de conflits particulièrement complexes en raison de leurs implications institutionnelles, juridiques et économiques. Cette thèse se consacre à appréhender le cadre de règlement des conflits d’investissements selon le modèle du système afin de déterminer les conditions nécessaires à la transformation profonde du Système de résolution des différends entre États-hôtes et investisseurs.L’analyse du Système de résolution des différends entre États-hôtes et investisseurs suppose d’abord d’en restituer le contexte historique et d’examiner les bases institutionnelles posées par le système CIRDI, celui-ci étant le fruit d’une idée, la substitution du droit à la force pour la résolution des différends d’investissement : « le paradigme juridictionnel ». Or, si des bases institutionnelles avaient été posées, celles relationnelles ne l’étaient pas. Il s’en suit un usage des mécanismes du Système de résolution des différends entre États-hôtes et investisseurs dans une logique défensive et adversariale. Cependant, la complexification croissante du monde et incidemment du système des investissements, conduit les acteurs de l’investissement à passer d’une logique adversariale à une logique de collaboration et de co-construction pour résoudre les inévitables problématiques auxquelles ils font face : « le paradigme consensuel ».Nous nous interrogeons alors sur les conditions nécessaires à la mise en œuvre de ce nouveau paradigme comme fondement du Système afin d’en provoquer la transformation profonde. L’application de concepts issus du champ d’étude de la complexité et des systèmes adaptatifs complexes permet de conclure que le consensualisme est tout à la fois le résultat et le moyen à mettre en œuvre pour faciliter cette transformation. Seule une démarche holistique, incluant l’ensemble des acteurs dans leur diversité, peut permettre de faire émerger des solutions innovantes à la hauteur des enjeux. Notre proposition est d’utiliser les outils et méthodes du Design Thinking appliqués au droit – le Legal Design- dont la démarche place les parties prenantes, et donc les éléments de culture et de contexte, au cœur du processus de conception de solutions, et susceptible de provoquer un changement dans la dynamique relationnelle des acteurs vers une logique de collaboration. Cette conclusion s’applique aux deux échelles retenues : celle de la transformation globale du Système de résolution des différends entre États-hôtes et investisseurs, et celle des projets d’investissement, dont une gouvernance participative doit être encouragée afin d’en permettre le succès et de permettre de réaliser une des vocations premières du système des investissements qu’est le développement des États d’accueil au bénéfice de leurs communautés. Conflicts between host states and foreign investors have been at the forefront of the geopolitical scene for the past ten years. Now the question is being raised on a global scale concerning the articulation of particularly complex conflict resolution methods because of their institutional, legal and economic implications. This thesis focuses on understanding the framework for resolving investment disputes based on the system model in order to determine which conditions are necessary for the profound transformation of the Dispute Resolution System between host states and investors.Before any analysis of the Dispute Resolution System between host states and investors can be undertaken, it is necessary to provide an insight into the historical context and to examine the institutional foundations of the ICSID system. These are the result of an idea, substituting international law to the use of force for the resolution of investment disputes: “the jurisdictional paradigm”. If institutional foundations were laid, relational ones were not. This resulted in the use of the Dispute Resolution System mechanisms between host states and investors in a defensive and adversarial logic. However, the increasing complexity of the world and, incidentally, of the investment system, has led investment players to move from an adversarial logic to one of collaboration and co-construction in order to resolve the inevitable problems they face: “the consensual paradigm”.We then question the conditions required for the implementation of this new paradigm as the foundation of the System in order to bring about its profound transformation. Applying concepts from the fields of study into complexity and complex adaptive systems leads to the conclusion that consensus constitutes both the outcome and the means to facilitate this transformation. Only a holistic approach, including all the actors involved and their diverse contexts, can make it possible to develop innovative solutions that meet these challenges. Our proposal is to apply Design Thinking tools and methods in a legal context – Legal Design. This approach places stakeholders, and therefore the elements of culture and context, at the heart of the process of designing solutions, and is therefore well suited to bringing about a change in the relational dynamics of the actors towards a logic of collaboration. This conclusion applies to both scales: that of the overall transformation of the Dispute Resolution System between host states and investors and that of investment projects, whose participative governance structure must be recognized as a crucial success factor and a means to support one of the primary purposes of the investment system, which is the development of host states for the benefit of their communities.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Complex Adaptive System; Dispute System Design; Droit international; Foreign investment; Investissements étrangers; Investment Conflits Resolution; Investment Mediation; Legal Design; MARD; Mediación; Mediation; Mediação; Médiation; Médiation d'investissement; Règlement de conflits; Résolution des conflits d'investissement; Système adaptatif complexe

Transparency in international arbitration: balancing the need for openness with the need for confidentiality - Mak, Charles Ho Wang; Rohatgi, Akshita (ACICA review, 2023)
International arbitration is often presented as an efficient and appropriate alternative to domestic court systems for resolving conflicts. For international arbitration to be effective, it is essential that the procedure adopted be open and accountable. This article will discuss the significance of openness in international arbitration and how it may promote justice, foster trust, and avoid corruption and misbehaviour.
Keywords: Corruption; International Arbitration; Justice; Misbehavour; Transparency; Trust

Reconstruction of CCMA Commissioners' Perceptions of Dispute Resolution in South Africa: a multi-perspective approach - Bendeman, H. M. A. (Potchefstroomse Univèrsiteit vir Christelike Hoër Onderwys, 2023)
A reconstruction of CCMA commissioners' perceptions of dispute resolution in South Africa: A multi-perspective approach This study focuses on the problems in the dispute resolution system in South Africa. The aim of this study is to explore the perceptions of commissioners of the Commission for Conciliation, Mediation and Arbitration (CCMA) regarding the capacity of parties to effectively deal with labour .conflict and disputes within the legal framework provided by the Labour Relations Act (LRA) (66/95). This includes an investigation into the reasons for the high referral rate of unfair dismissal cases to the CCMA and the influence of the case-overload on the effective functioning of the disputé resolution system. The · functionalist and conflict theoretical perspectives are used to study the structural aspects of the dispute resolution system and to explore structural strain. The interactionist perspective is used in the methodology of this study to reconstruct the perceptions of a group of CCMA commissioners. This study is predominantly of a qualitative nature and was conducted in an exploratory manner through in-depth interviews and e-mail questionnaires. Dunlop's open systems approach allowed for the conceptualisation of the major dispute resolution components of the labour relations system. T!Je analysis of the transformation of conflict formed the basis for understanding the background, the problem statement, the aims and assumptions of this study. lt was found that the guidelines in Schedule eight of the LRA (66/95) have become the norm for dealing with conflict within an enterprise, creating complex and technical processes for dealing with disputes. However, most of the employers and individual employees do not have the knowledge and skills to operate effectively in the system. This has led to a new type of adversarialism in the individual employment relationship, which is based on rights, rules and power. The very technical nature of the internai conflict resolution mechanisms, the incapacity of the parties and the adversarial nature of the labour relationship have resulted in the high referral rate and consequent problems that the CCMA is experiencing.
Keywords: Afrique du Sud; Arbitrage; Arbitragem; Arbitration; Conciliation; Conflict resolution; Conflits de travail; Dispute settlement; Industrial sociology; Labour dispute; Labour relations; MARD; Mediación; Mediation; Mediação; Médiation; Relations de travail; Règlement des différends; Résolution de conflit; Sociologie industrielle; South Africa

La pérennité du contrat international entre pacta sunt servanda et rebus sic stantibus : réflexions au regard du pouvoir interprétatif de l’arbitre - Bejeoui, Imed (UAEU Law Journal, 2023)

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

The efficacy of commercial arbitration, law and practice Lesotho - Thethe-Chitja, Makabelo (National University of Lesotho, 2023)
The success of commercial arbitration law and practice is achieved as a result of several factors. The purpose of the study was to investigate whether efficacy of commercial arbitration, law and practice in Lesotho is hindered by the legal framework which does not conform to the United Nations Commission Trade Law on International Commercial Arbitration, UNCITRAL Model Law. Examining such other factors as support of the courts and government, the study specifically investigated the impact of lack of education about commercial arbitration for the business community and unregulated arbitrators on the efficacy of the commercial arbitration, law and practice in Lesotho. With the use of the desk reviews and interviews as data collection methods for this study, the evidence obtained has revealed that efficacy of the commercial arbitration, law and practice in Lesotho is hampered by the law which is outdated and inconsistent with the UNCITRAL Model law. As such, support for the mechanism by the courts has been found to be at stake or adversely affected. Lack of support from the government and that of awareness campaigns about the mechanism for the business community have also been noted for constraining the efficacy of the commercial arbitration, law and practice in the country. Further noticeable from the findings include limited commitment from the legal profession and unregulated arbitrators, both of which could have significantly obstructed the mechanism. The study thus concludes that there is an urgent need for law reforms and concerted commitment from the relevant stakeholders to help towards achieving efficacy of the commercial arbitration, law and practice in Lesotho.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Lesotho

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

L’immunité des arbitres dans l’arbitrage OHADA - Diallo, Hamadi; Traoré, Abdramane; Traoré, Abdou Bougoury (International Journal of Strategic Management and Economic Studies, 2023)
Cet article, est une contribution à la réflexion sur le statut de l’arbitre en droit OHADA, entamée par plusieurs chercheurs africains, et au centre de laquelle se trouve la problématique de l’immunité en droit de l’arbitrage OHADA. Le débat sur le choix d’un système d’immunité et la définition d’un véritable statut pour l’arbitre est toujours d’actualité. Cet article fait le point global des approches et conceptions sur l’immunité diplomatique des arbitres de la CCJA. En effet, le débat sur la responsabilité touche de façon étroite celui du statut de l’arbitre : la responsabilité étant la résultante d’un statut, cela nous permettra d’aborder la question du statut juridique de l’arbitre en droit OHADA. Dans un contexte où les différentes législations, la jurisprudence ou encore les conventions internationales, n’abordent que très peu le statut de l’arbitre, la détermination des éléments permettant de préciser les contours des devoirs, droits et obligations de l’arbitre, contribuera de façon certaine à mieux appréhender la mission de l’arbitre.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitre; CCJA; Immunité; OHADA

Rights and Obligations of the Parties Against International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The position of international arbitration awards which is different from national arbitration awards and district court decisions causes differences in the rights and obligations of the parties to arbitral awards, especially those relating to legal remedies against awards. The formulation of the problem in this study is how are the rights and obligations of the parties to international arbitral awards in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the study state that the rights possessed by the parties to international arbitral awards in Indonesia are related to legal remedies against decisions, namely corrections to these international arbitral awards. The corrections to the decisions here are not only limited to administrative corrections but also corrections related to the principal international arbitral awards made before the request for execution was registered at the Central Jakarta District Court. While the obligations of the parties to international arbitral awards are to carry out international arbitral awards in good faith.
Keywords: International Arbitration Award; Rights and Obligations

Introduction: International Adjudication and the Legacy of the Mixed Arbitral Tribunals - Ruiz Fabri, Hélène (The Mixed Arbitral Tribunals, 1919–1939: An Experiment in the International Adjudication of Private Rights, 2023)
This introduction provides the reader with a general characterization of the 39 Mixed Arbitral Tribunals (MATs) created by the 1919-1923 peace treaties to address disputes between private persons and between private persons and states as a result of the First World War. Noting that the rich literature published on the MATs was followed by near-silence after 1945, it mentions the numerous questions that they still raise today, before explaining how the various contributions to the book edited by the authors address them.

L’ouverture du droit d’agir au système des règlements alternatifs des différends en droit OHADA et Camerounais : un procédé séduisant mais d’une efficacité incertaine - Njock, Luc Kevin Leny (Uniform Law Review, 2023)
The processes by which a model of social regulation channels its way of resolving conflicts make the strength of its conflict resolution system. Court justice has lost its exemplary function. The crisis of effectiveness and the crisis of legitimacy that the processual mode of dispute resolution is undergoing in our States, make it a justice system that is considered to have broken down. The need for justice thus directly raises the question of social regulation, the relevant model of social regulation. The call for a ‘right to sue’ open to the system of alternative dispute resolution rather than restrictively to the judiciary to resolve disagreements is the spearhead of the combinatorial approach to the administration of conflicts, the ferment of a plural approach to access to justice. Has Cameroonian law begun to renew its vision of the right to take legal action? Does it renew the dominant classical approach to the system of social regulation? The study notes the global and integral recognition of the alternative dispute resolution system, another, less contentious, way of dealing with disputes, the emergence within the traditional dispute resolution system of a right to amicable dispute resolution, but in an embryonic state. It then poses, in a prospective approach, the need for a unitary and global approach to private justice as challenges to be met to ensure the quality of this form of justice.

L'Arbitrage en matière des litiges contractuels - Ismail, Mahmoud (International Multilingual Journal of Science and Technology, 2023)
Le recours à l’arbitrage en matière des litiges contractuels entre des parties privées présente des avantages par rapport aux procédures devant les tribunaux. Les avantages de l’arbitrage qui a une valeur particulière en matière contractuelle se multiplient : les arbitres peuvent être choisis en raison de leurs compétences spéciales selon le sujet du contrat; la confidentialité peut être préservée; l’arbitrage peut être utilisé pour régler des questions sur le même sujet ou des sujets semblables mais survenant dans des pays différents, ceci peut présenter l'avantage de régler en une seule fois tous les différends entre les parties, surtout en matière de commerce.
Keywords: Arbitrage; Arbitrage Conventionnel; Arbitrage Judictionnel; Arbitragem; Arbitraje; Arbitration; Commerce; Droit civil; France; Jordanie; Litiges contractuels

La médiation en matière des litiges contractuels - Ismail, Mahmoud (International Multilingual Journal of Science and Technology, 2023)
Dans une économie de plus en plus globalisée, faute d’harmonisation juridique, les parties aux litiges contractuels n’hésitent plus à consulter les forums juridiques pour identifier les pays susceptibles de leur offrir le meilleur niveau de protection. Presque tous les litiges en matière contractuels se prêtent au début des conflits à la médiation. Il arrive souvent que lors d’un litige relatif aux droits contractuels, les parties recourent à la médiation. Cependant, pour pouvoir y recourir de manière utile, il est important d’éluder certains obstacles. Un litige ayant trait à un contrat, soulève des questions complexes de faits et de droit, peut nécessiter des dépenses importantes et exiger la présence de témoins experts. Puisque l’obligation contractuelle émise sera presque toujours un enjeu, un litige ayant trait au commerce, notamment international, commande une connaissance approfondie de la législation sur les objets de transactions, ainsi qu’une expérience des tribunaux qui traitent la plupart du temps de ces questions. En pratique, l’espace de rencontre entre la médiation et les litiges contractuels est le contrat lui-même. Or, le domaine contractuel est le domaine privilégié de la médiation. En réalité, la médiation peut avoir lieu dans les relations liée aux contrats de commerce, dans lequel une dévolution des droits contractuels est prévue. Ce mode alternatif fournit un moyen pour éviter les contentieux judiciaires.
Keywords: Approche comparée; Commerce international; Droit civil; France; Jordanie; Litiges contractuels; Mediation; Médiation

La place contestée de l'arbitrage international en droit de l'investissement - El Issa, Rayyan (Université Paris-Saclay, 2023)
La place de l'arbitrage en droit de l'investissement est discutée. Les réfutations à son encontre grandissent. De nombreuses problématiques édulcorent la définition même de la notion d'investissement. Les controverses doctrinales restent toujours nombreuses et débattues à ce sujet. De même, des doctrines s'affrontent sur la question de savoir s'il faut ou non élaborer un corps de règles cohérentes pour des sentences arbitrales homogènes. L'opposition à l'arbitrage dans le droit de l'investissement se retrouve aussi dans les problématiques liées à l'exequatur des sentences arbitrales liées à l'arbitrage d'investissement dans l'Union européenne. Un manque de soutien apparent au développement de l'arbitrage dans l'Union européenne s'est installé, comme le démontre le récent traité CETA conclu entre l'Union européenne et le Canada. L'arbitrage d'investissement ferait courir le risque d'un recul de la souveraineté. En effet, du fait l'arbitrage d'investissement, les Etats seraient moins incités à légiférer sur des matières pouvant avoir un impact sur l'activité d'une entreprise étrangère, par crainte d'une procédure arbitrale. Un lien délicat apparait alors, entre souveraineté et arbitrage d'investissement. Plusieurs doctrines se sont longtemps affrontées, notamment celle élaborée par Calvo et Drago en Amérique Latine entre 1870 et 1900, proposant de réduire les droits des investisseurs étrangers, face à une doctrine opposée, celle militant pour un standard minimum international de protection des investisseurs étrangers. Or, une renaissance de ces débats apparaît aujourd'hui, avec une problématique liée à la souveraineté de plus en plus ancrée dans les débats liés à l'arbitrage d'investissement. Pourtant, l'arbitrage d'investissement doit être perçu comme une méthode permettant à des investisseurs de bénéficier d'un arbitre indépendant et permettant de « dépolitiser » les contentieux. Mais des Etats admettent de moins en moins que leurs lois établies démocratiquement pour l'intérêt général puissent être contestées par des investisseurs étrangers devant un tribunal arbitral. Des auteurs parlent de « chilling effect », par lequel des Etats n'osent plus légiférer, par crainte de contentieux ultérieurs. De plus en plus d'Etats refusent que leur droit soit remis en cause par des juges privés. Plusieurs questions se posent. Est-il toujours concevable de protéger davantage un investisseur étranger qu'un investisseur national ? Est-il légitime de privilégier des juges privés, plutôt que des juges nationaux pour trancher les litiges en matière d'investissement ? L'utilité de l'arbitrage peut être comprise, dans des pays où la justice étatique est dite « corrompue » ou « biaisée ». En pareille situation, un investisseur étranger est légitime à vouloir saisir un arbitre neutre et indépendant. Mais la légitimité d'avoir recours à l'arbitrage dans des pays développés bénéficiant d'une justice étatique indépendante pose plus de difficultés. Dès lors, faudrait-il limiter l'arbitrage d'investissement aux pays souffrant d'un déficit d'indépendance de justice étatique ? Et donc d'exclure ce mode de règlement des litiges en la matière dans l'Union européenne ? La « politisation » du débat est en pleine renaissance. L'arbitrage d'investissement est un domaine relativement jeune et il convient de se demander s'il s'agit là d'un mode de règlement des litiges adéquat et d'un mode adapté au commerce international en général ? Assistera-t-on prochainement ou assiste-t-on déjà à ce que des auteurs qualifient de « fin de cycle » ? Il s'agit de questions ancrées dans l'actualité, que ce soit en France ou ailleurs dans le monde. The place of arbitration in investment law is discussed. The rebuttals are growing. Many issues water down the very definition of the notion of investment. The doctrinal controversies are still numerous and debated on this subject. Similarly, doctrines clash on the question of whether or not it is necessary to develop a body of coherent rules for homogeneous arbitral awards. The opposition to arbitration in investment law is also found in issues related to the exequatur of arbitral awards related to investment arbitration in the European Union. An apparent lack of support for the development of arbitration in the European Union has set in, as demonstrated by the recent CETA treaty concluded between the European Union and Canada. Investment arbitration would run the risk of a decline in sovereignty. Indeed, because of investment arbitration, States would be less encouraged to legislate on matters that could have an impact on the activity of a foreign company, because of the fear of arbitration proceedings. A delicate link then appears between sovereignty and investment arbitration. Several doctrines have long clashed, in particular the one developed by Calvo and Drago in Latin America between 1870 and 1900, proposing to reduce the rights of foreign investors, in front of an opposing doctrine, that campaigning for a minimum international standard of protection for foreign investors. A revival of these debates is appearing today, with an issue linked to sovereignty increasingly rooted in the debates linked to investment arbitration. However, investment arbitration must be seen as a method allowing investors to benefit from an independent arbitrator and allowing disputes to be “depoliticised”. But states admit less and less that their laws democratically established for the general interest can be challenged by foreign investors before an arbitration tribunal. Authors talk about the “chilling effect”, by which States no longer dare to legislate, because of the fear of subsequent litigation. More and more States refuse to have their rights challenged by private judges. Several questions arise. Is it always conceivable to protect a foreign investor more than a national investor ? Is it legitimate to favor private judges, rather than national judges, to settle investment disputes ? The usefulness of arbitration can be understood in countries where state justice is said to be “corrupt” or “biased”. In such a situation, a foreign investor is legitimate in wanting to seize a neutral and independent arbitrator. But the legitimacy of having recourse to arbitration in developed countries benefiting from independent state justice arouses more difficulties. Therefore, should investment arbitration be limited to countries suffering from a lack of independence of state justice ? And therefore to exclude this method of settling disputes in this area in the European Union ? The “politicization” of the debate is in full revival. Investment arbitration is a relatively young field and it is worth asking whether it is an adequate mode of dispute resolution and a mode suitable for international trade in general ? Will we soon witness or are we already witnessing what some authors describe as the “end of the cycle” ? These are issues rooted in the news, whether in France or elsewhere in the world.
Keywords: Arbitrage; Arbitragem; Arbitration; Contentieux; Contentieux de la concurrence; Droit de l'investissement; Droit et État; Investment Law; Investments; Litigation; Souveraineté; Sovereignty

Third Party Funding in International Arbitration: A Critical Appraisal and Pragmatic Proposal - Sweify, Mohamed (Edward Elgar Publishing, 2023)
The author of Third Party Funding in International Arbitration challenges the structural inconsistencies of the current practices of arbitration funding by arguing that third party funding should be a forum of justice, rather than a forum of profit. The author introduces a new methodology with an alternative way of structuring third party funding to solve a set of practical problems generated by the risk of claim control by the funder.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitral justice; Arbitration; Claim control; Dispute outcome; Financement; Funders; Third Party Funding; Tiers

Investigation of Investor-State Arbitration Problems in Afghanistan - Nikzad, Nezamuddin; Anwari, Gulaqa (International Journal of Social Science Research and Review, 2023)
The main purpose of this research is to explain and identify the major Investor-State Arbitration (ISA) problems in Afghanistan. Afghanistan's government is committed to providing legal security for the resolution of foreign investment disputes. The dispute resolution system's assessment is very important for foreign investors because they pay special attention to the dispute resolution system and consider it a criterion for their investments. This research will be the first comprehensive study about the Investor-State Arbitration problems in Afghanistan. In the writing of this research, the library method has been used. To extract reasons, laws, books, articles, and reliable scientific sources have been used. Afghanistan is a good market for foreign investment because it has good investment opportunities in different sectors. Foreign investors can choose the easiest and best mechanisms, such as arbitration in their contracts to deal with disputes. But the resolution of foreign investment through arbitration has some problems, and sometimes foreign investors are facing challenges with the settlement of their disputes through arbitration internationally and domestically in Afghanistan.
Keywords: Arbitration; Dispute; Foreign Investment; Investigation in Afghanistan; Problems

La Diplomatie juridique : Défense et illustration du droit français et du droit continental dans le droit global à travers les exemples de la médiation et de l'arbitrage international - Gontier, Jean-Yves (Université Paris-Saclay, 2023)
Dans la conception traditionnelle de la diplomatie, l'action extérieure des États est cantonnée aux domaines politique, économique et culturel. Le droit est plus rarement pris en compte comme outil d'influence dans l'action extérieure des États.Or, le droit joue un rôle fondamental dans la diplomatie économique. En effet, un pays qui n'est pas capable de défendre son système juridique est un pays qui économiquement est en péril, car c'est un pays qui ne peut pas s'exporter.Si la France par exemple, ou d'autres pays, se mettent à la remorque de l'Alternative Dispute Resolution jusque dans leur propre droit interne, ces pays ne pourront plus exporter leur système juridique au risque de ne plus pouvoir exporter tout court. Ils risquent alors de perdre une partie essentielle et substantielle de leur capacité de projection sur la scène internationale.De même, lorsque la francophonie économique perd du terrain, c'est tout un pan de la diplomatie économique qui perd de sa force de frappe.Avec les clauses compromissoires et clauses de médiation inspirées des modèles anglo-saxons qui se répandent dans les contrats internationaux, comment les juridictions des pays francophones qui ont été calquées sur le système judicaire français pourront-elles continuent à exister ? Les arbitres anglo-saxons finiront-ils par imposer lentement mais sûrement la Common law ? Il y a là un enjeu de diplomatie économique énorme.Nous verrons comment défendre au mieux la francophonie économique et juridique en évitant que l'Alternative Dispute Resolution ne devienne le cheval de Troie du droit anglo-saxon, avec à terme, le risque que des systèmes nationaux disparaissent.Ce sont là des questions légitimes et très graves, et l'on peut comprendre qu'elles soient posées avec une certaine persistance.Avec l'élargissement continu du champ des relations internationales, le droit doit devenir l'objet d'une politique extérieure stratégique à part entière. C'est pourquoi nous plaidons pour la mise en place d'une diplomatie juridique française et formulons des recommandations ainsi qu'une stratégie d'influence juridique extérieure.En prenant la défense et en illustrant le droit continental et le droit français dans le droit global à travers les exemples de la médiation et de l'arbitrage international, nous espérons contribuer à l'ébauche d'une théorie de la diplomatie juridique et à ouvrir des pistes nouvelles de réflexion en matière d'influence internationale, en particulier d'influence juridique internationale.Nous espérons contribuer ainsi modestement mais utilement à la défense du droit français et du droit continental pour que la confrontation et la compétition des système juridiques n'aboutissent pas à la domination d'un système juridique sur un autre mais que cette compétition aille au contraire dans le sens d'un meilleur équilibre entre les systèmes juridiques, dans le sens du progrès et de l'amélioration du droit français et du droit continental, mais aussi - s'il se peut -dans le sens des progrès dans la défense des causes et des valeurs universelles. In the traditional conception of diplomacy, the external action of States is confined to the political, economic and cultural domains. Law is more rarely taken into account as a tool of influence in the external action of States.However, Law plays a fundamental role in economic diplomacy. Indeed, a country that is not able to defend its legal system is a country that is economically in danger, because it is a country that cannot be exported. If France, for example, or other countries, follow the Alternative Dispute Resolution right up to their own domestic law, these countries will no longer be able to export their legal system at the risk of no longer being able to export at all. They then risk losing an essential and substantial part of their ability to project themselves on the international scene.Similarly, when the economic Francophonie loses ground, a whole section of economic diplomacy loses its strike force.With arbitration clauses and mediation clauses inspired by Anglo-Saxon models that are spreading in international contracts, how will the courts of French-speaking countries that have been modeled on the French judicial system be able to continue to exist? Will Anglo-Saxon arbitrators end up slowly but surely imposing the Common law? There is a huge stake in economic diplomacy here.We will see how best to defend the economic and legal Francophonie by preventing the Alternative Dispute Resolution from becoming the Trojan horse of Anglo-Saxon law, with the eventual risk that national systems will disappear.These are legitimate and very serious questions, and one can understand that they are asked with a certain persistence.With the continuous widening of the field of international relations, Law must become the object of a strategic foreign policy. This is why we plead for the establishment of a French legal diplomacy and formulate recommendations as well as a strategy of external legal influence.By defending and illustrating continental law and French law in global law through the examples of mediation and international arbitration, we hope to contribute to the sketch of a theory of legal diplomacy and to open new paths of reflection in terms of international influence, in particular international legal influence.We hope in this way to contribute modestly but usefully to the defense of French law and continental law so that the confrontation and competition of legal systems does not lead to the domination of one legal system over another but that this competition goes on the contrary in the sense of a better balance between legal systems, in the direction of progress and improvement of French law and continental law, but also - if possible - in the direction of progress in the defense of universal causes and values.
Keywords: Arbitrage; Arbitragem; Arbitration; Diplomatie; Diplomatie juridique; Diplomatie économique; Droit global; Economic Diplomacy; Global Law; Influence; Influence juridique internationale; International Legal Influence; Legal Diplomacy; MARD; Mediación; Mediation; Mediação; Médiation; Relations extérieures; Relations économiques internationales

The Pros and Cons of Third Party Funding in the International Investment Arbitration Regime - Mirveisi, Alireza; Zakerian Amiri, Mehdi; Abdollah Zadeh, Mohammad Ali (Public Law Researsh, 2023)
There is a growing stream of critics who see investment arbitration in favor of foreign investors and as a negative force as opposed to sustainable development. The phenomenon of third-party funding and its use in investment arbitration has increased such concerns. Third-party funding is basically the payment of all or a part of the arbitration costs of one of the parties of dispute by a third party funder which in return, the funder receives a percentage of the output of the award if successful. The purpose of this article is to explain and analyze the theoretical differences between pros and cons of third-party funding regarding the access to justice, screening mechanism for the claims, and the financial consequences on the host state. In this article, the advocates see third-party funding as a means of access to justice for aggrieved investors in investment claims, while the adversaries refering on the profitability of third-party funding, see this method in arbitration a form of wealth transfer from public sector to private corporations and also refer to the asymmetric structure of the investment arbitration regime as well as the risks arising from the transfer of management and control of arbitration process to the third party funders. یک جریان رو به رشدی از منتقدان وجود دارد که داوری سرمایه‌گذاری را به نفع سرمایه‌گذاران خارجی و بعنوان یک نیروی منفی در تضاد با توسعه پایدار می‌داند. پدیده تأمین مالی ثالث و بکارگیری آن در داوری سرمایه‌گذاری به این نگرانی‌ها افزوده است. تأمین مالی ثالث اساساً پرداخت تمام یا بخشی از هزینه‌های داوری یکی از طرفین دعوی توسط تأمین کننده شخص ثالث است که در ازای آن، تأمین کننده مالی درصدی از رأی صادره را در صورت پیروزی دریافت می‌نماید. هدف مقاله، تشریح و تحلیل اختلافات نظری موافقان و مخالفان تأمین مالی ثالث در خصوص دستیابی به عدالت، غربالگری دعاوی و تبعات مالی آن بر دولت است. در این مقاله موافقان، تأمین مالی ثالث را ابزاری جهت دستیابی به عدالت برای سرمایه‌گذاران زیان‌دیده در دعاوی سرمایه‌گذاری در نظر می‌گیرند در حالی که مخالفان با اتکا به اهداف سودآوری تأمین مالی ثالث، این روش را در داوری نوعی انتقال ثروت از بخش عمومی به بخش خصوصی می‌دانند و به ساختار نامتقارن رژیم داوری سرمایه‌گذاری و خطرات ناشی از انتقال مدیریت و کنترل فرایند داوری به تأمین کنندگان شخص ثالث نیز اشاره می‌نمایند.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitragem; Arbitration; Investment Arbitration Regime; Investments; Screening Mechanism for Claims; Third Party Funding; تأمین مالی ثالث; دستیابی به عدالت; رژیم داوری سرمایه‌گذاری; غربالگری دعاوی

Procedural powers of arbitrators in international arbitration- Real or perfunctory? - Mishra, Ajit Kumar (International Journal of Law, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; International Arbitration; Lex arbitri; Procedural powers; Tribunal power

The Dilemma of International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The final and binding nature of international arbitral awards results in the nullification of the rights of the parties to file legal remedies against the arbitral award, as is the case with decisions of national courts that can be appealed, appealed, or reviewed. However, Article 68 paragraph (2) of Law Number 30 of 1999 concerning arbitration and Alternative Dispute Resolution provides an opportunity for parties who refuse to recognize and implement an international arbitral award that can be appealed to, as well as Article 70 must also be explained that Article this applies only to national arbitrations. This of course creates legal uncertainty, disuse, and injustice for the parties. Therefore, what is highlighted in this research is what is the position of the final and binding international arbitration award in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the research show that the position of international arbitral awards in Indonesia is not the same as the decisions of national courts because they cannot be appealed, cassated, and reviewed. Therefore, it is necessary to completely amend international arbitration arrangements by removing Article 68 paragraph (2) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in order to provide legal certainty, benefit, and justice for the parties.
Keywords: Award; Final and Binding; International Arbitration

L'arbitrage à l'épreuve des procédures belges d'insolvabilité d'entreprises - Dantinne, Rouslan (Université de Liège, 2023)
Alors que deux entreprises sont liées par une convention d’arbitrage, une procédure d’insolvabilité est ouverte en Belgique à l’égard de l’une d’elles. De nombreuses questions émergent : L’instance arbitrale en cours doit-elle être suspendue ? Dans la positive, pourra-t-elle reprendre ? Les pouvoirs de l’arbitre sont-ils impactés ? L’instance n’a pas débuté, la validité de la convention d’arbitrage est-elle compromise ? La convention n’existe pas, les parties peuvent-elles la conclure ? L’entreprise en difficulté perd-elle sa capacité compromissoire ? Cette capacité est-elle transférée au praticien de l’insolvabilité ? La sentence a été rendue, peut-elle être exécutée ? Dans le présent exposé, nous mettons l’arbitrage à l’épreuve des procédures belges d’insolvabilité d’entreprises.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; Faillite; Insolvabilité; Insolvency; Procédures d'insolvabilité; Réorganisation judiciaire

L'unanimité de l'accord de conciliation en droit OHADA : une logique juridique irréaliste ? - Kourouma, Moussa Fanta (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2023)

Milletlerarası ticari tahkimde hakem kararlarının iptali - Ersari̇, Danyal (Marmara Üniversitesi, 2023)
Günümüzde ticaretin globalleşmesi ile birlikte tahkim, uluslararası uyuşmazlıkların çözümünde devlet mahkemelerine nazaran kişiler, şirketler ve devletler tarafından daha çok tercih edilir hale gelmiştir. Bu tercihin en önemli sebeplerinden biri tahkim yargılaması sonucunda verilen hakem kararlarının tıpkı mahkeme kararlarında olduğu gibi kesin ve bağlayıcı olmasıdır. Ancak aleyhine karar verilen taraf, ilgili hakem kararının adalete uygun olmadığını düşünebilir. Bu bağlamda hakem kararlarının devlet mahkemeleri tarafından denetlenebilmesi için neredeyse tüm milli hukuk sistemlerinde hakem kararlarına karşı denetim yolu olarak "iptal davası" öngörülmüştür. İptal talebinde bulunan taraf belirli sebeplerin olması halinde tahkim yeri mahkemesinde iptal davası açabilecektir. Hakem kararına karşı iptal talebinde bulunan tarafın amacı, kararın bir kısmını ya da tamamını geçersiz hale getirmek ve icrasını engellemektir. UNCITRAL Model Kanun ve ulusal hukuk sistemlerinde iptal sebepleri sınırlı şekilde sayılmıştır. Ancak bazen bu iptal sebeplerinin faklı şekillerde yorumlandığı görülmüştür. İptal sebeplerinin geniş yorumlanması hakem kararlarının iptal olasılığını orantısız şekilde arttıracaktır. Bu durum alternatif uyuşmazlık çözüm yolu olan tahkimin güvenirliğine zarar verdiği gibi uzun, meşakkatli ve masraflı tahkim yargılama sürecini de boşa çıkaracaktır. Ancak, iptal sebeplerin adaletsizliğe yol açacak şekilde çok dar yorumlanması da keyfiliğe, tutarsızlığa ve tarafların istemediği sonuçlara yol açacaktır. Bu çerçevede Türk kanunları dahil çeşitli ülkelerdeki kanunları ve mahkeme uygulamalarını dikkate alarak kanımızca iptal sebepleri bakımından doğru yaklaşımları ortaya koymaya çalışacağız. Çalışmamız üç bölümden oluşmaktadır. İlk bölümde milletlerarası tahkime ilişkin genel bilgiler, yabancı hakem kararlarının tabiiyetinin belirlenmesi ve iptal davasına konu olabilecek yabancı hakem kararlarının türleri yer almaktadır. Bunun devamında, ikinci bölümde, çeşitli ülkelerin tahkime ilişkin kanunları, tahkime ilişkin milletlerarası literatürde kabul gören hukuki metinleri de dikkate alınarak iptal sebepleri ortaya konulacaktır. Aynı zamanda, konu ile ilgili doktrindeki görüşlere yer verilerek çeşitli ülkelerde verilen mahkeme kararları çerçevesinde iptal sebeplerine ilişkin yaklaşımlara ver verilecektir. Çalışmamızın üçüncü ve son bölümünde ise iptal davasının tarafları, iptal davasında görevli ve yetkili mahkeme ve iptal davasından feragat konuları Türk hukuku ve karşılaştırmalı hukuk bakımından incelenmeye çalışılmaktadır. Along with the globalization of trade, arbitration has become more preferred by individuals, companies and states than state courts in resolving international disputes. One of the most important reasons for this preference is that the arbitral awards given after the arbitration proceedings are final and binding, just as the court decisions. However, the party rendered against the award may consider it unjust. In this context, in order for the arbitral awards to be audited by the state courts, "annulment case" is designed as a legal remedy in almost all national legal systems. The party requesting annulment may file an action for annulment in the court of the place of arbitration if there are certain reasons. The purpose of the party requesting annulment against the arbitral award is to invalidate some or all of the decision and to prevent its execution. Although the reasons for annulment are limited and similar in many legal systems, the interpretation of these reasons is of great importance. A broad interpretation of the grounds for annulment will disproportionately increase the possibility of annulment of arbitral awards. This situation will not only harm the reliability of arbitration, which is an alternative dispute resolution method, but will also nullify the long, laboursome and costly arbitration proceedings. On the other hand, much narrower interpretation of the grounds for annulment in a way that leads to injustice may lead to arbitrariness and inconsistency, as well as result in undesirable results by the parties. Considering these, we will try to put forward approaches that can be consistent in terms of the grounds for annulment, taking into account the laws and court practices in various countries, including Turkish laws. This study consists of three parts. In the first part, general information about international arbitration, determination of the nationality of foreign arbitral awards and types of foreign arbitral awards that may be subject to annulment proceedings are included. Following this, in the second part, the reasons for annulment will be presented considering the arbitration laws of various countries and the internationally accepted legal texts on arbitration. At the same time, we try to put forward the approaches regarding the reasons for annulment within the framework of the court decisions given in various countries by giving place to the opinions in the doctrine on the subject. In the third and final part of our study, the parties of the annulment case, the competent court in charge of the annulment case and the waiver of the annulment case are to be examined in terms of Turkish law and comparative law.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; International commercial arbitration

Les garanties du procès équitable à l’épreuve des modes alternatifs de règlement de conflits - Guedegbe, Igor Samson Bidossessi (Revue Béninoise des Sciences Juridiques et Administratives, 2023)

Bireysel iş hukukunda arabuluculuk - Gül Küçükkaya, Hande (Marmara Üniversitesi, 2023)
Arabuluculuk tarafların tarafsız bir üçüncü bir kişinin yardımı ile ihtilaflarını çözmeye yardımcı olması olarak tanımlanabilir. Türkiye'de özel hukuktan doğan ve tarafların üzerinde serbestçe tasarruf edebilecekleri uyuşmazlıkların arabuluculuk ile çözümüne ilişkin 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu'nun 2013 yılında kabulü ile arabuluculuk uygulamasına geçilmiştir. 7036 sayılı İş Mahkemeleri Kanunu ile 2018 yılı itibariyle dava şartı arabuluculuk kavramı Türk hukuk literatürüne girmiştir. 7036 sayılı İş Mahkemeleri Kanunu md.3 uyarınca kanuna, bireysel iş sözleşmesine, toplu iş sözleşmesine dayanan alacak, tazminat veya işe iade talebi ile açılan davalarda arabuluculuğa başvurulması dava şartıdır. İtalya, Almanya ve ABD'nin bazı eyaletlerinde iş hukukunda dava şartı arabuluculuk uygulaması yoktur. İngiltere'de iş mahkemelerine başvurmak için önce ACAS isimli kuruma başvurmak gerekir. ABD 'de ise iş ilişkilerindeki ayrımcılık iddiaları öncelikle EEOC'de görülmektedir. Bireysel İş Hukukunda Arabuluculuk başlıklı doktora tezi çalışmamız dört bölümden oluşmaktadır. Çalışmanın birinci bölümünde alternatif uyuşmazlık çözüm yöntemleri kavramı ve belli başlı alternatif uyuşmazlık yöntemleri irdelenerek incelenmiş, ikinci bölümde arabuluculuk kurumu, amacı, prensipleri, türleri, arabulucunun hak ve yükümlülükleri, arabulucu ve arabuluculuk sözleşmelerinin hukuki mahiyeti ve arabuluculuk etiği gibi konular çalışılmıştır. Mukayeseli İş Hukukunda Arabuluculuk başlıklı üçüncü bölümde, arabuluculuğun anavatanı olan Amerika Birleşik Devletleri, Birleşik Krallık gibi Anglo Sakson sistemindeki devletlerde, İtalya, Almanya, Fransa gibi Roma Cermen sistemindeki devletlerde ve Avrupa Birliği müktesabatında arabuluculuğun nasıl düzenlendiği ve son olarak dördüncü bölüm olan Türk İş Hukukunda Arabuluculuk başlığı altında, dava şartı arabuluculuk kavramına ilişkin konular yargı kararları da işlenerek ayrıntılı olarak irdelenmiştir. Mediation can be defined as helping parties resolve their disputes with the help of a third party. With the adoption of the Law No. 6325 on Mediation in Civil Disputes in 2013, mediation has been implemented regarding the resolution of disputes arising from private law and on which the parties can freely dispose of. As of 2018, with the adoption of the Labor Courts Law numbered 7036 the concept of mediation as a cause of action in employment disputes litigation introduced in our legal literature. Pursuant to Article 3 of Labor Courts Law numbered 7036, lawsuits filed with the demand for receivables, compensation or reemployment based on the law, individual employment contract, collective bargaining agreement are subject to mediation as a cause of action. In Italy and Germany mediation in employment disputes does not exist. In England, in order to apply to the labor courts, firstly it must be applied to ACAS. In the United States of America, for discriminatory allegations in the employment relation firstly EEOC must be addressed. The doctoral thesis titled Mediation in Individual Employment Law consists of four parts. In the first part of the study, the concept of the alternative dispute resolution methods is investigated by examining the main alternative dispute methods, in the second part, the mediation institution, its purpose, principles, types, rights and responsibilities of the mediator, the legal nature of the mediator and mediation agreemets and mediation ethics are studied. In the third part titled Mediation in Comparative Employment Law, the Anglo-Saxon countries such as the United States of America and the United Kingdom, which are the homeland of mediation, in the Roman Germanic system states such as Italy, Germany France and in European Union legal system are explained and lastly under the title of Mediation in Turkish Employment Law, which is the fourth part, the issues related to the concept of mediation as a cause of action are also discussed in detail adding judicial decisions.
Keywords: ACAS; Arabuluculuk; Cause of action; Comparative law; Danışma; Dava şartı; Karşılaştırmalı hukuk; Labour disagrement; Labour dispute; Labour law; Mediation; Uzlaşma ve Tahkim Servisi; İş hukuku; İş uyuşmazlıkları

Effective Conflict Management - International Chamber of Commerce (ICC Publication DRS, 2023)

The International Validity of Domestic Law in Investment-Treaty Arbitration - Jarrett, Martin (Arbitration international, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Investment arbitration; Investments

Milletlerarası ticari tahkimde delillerin değerlendirilmesi - Kesi̇kli̇, Ömer (Galatasaray Üniversitesi, 2023)
It is nowadays generally accepted that international commercial arbitration is the most popular method of resolving international disputes between commercial parties. This popularity is the cumulative result of many advantages that international commercial arbitration offers to the parties. It is suggested in the literature that one of these advantages is the freedom of parties and the resulting procedural flexibility. In virtue of this principle, the parties have the opportunity to establish a specific method of adjudication adapted to the nature of their dispute. This opportunity is provided by the fact that the arbitration regulations do not include detailed rules on the collection of evidence, thus leaving the parties and the arbitrators' range of motion. Therefore, we consider that this procedural flexibility has emerged as a possibility obtained at the expense of certainty in international commercial arbitration proceedings. This uncertainty is to such an extent that it also warrants the question as to whether there is an applicable law to take evidence in international commercial arbitration proceedings. Such procedural flexibility afforded to the parties, however, comes at a price of uncertainty with respect to arbitral procedure. International commercial arbitration developed as a reaction to the failings of proceedings in domestic courts, which were subject to detailed rules of evidence. Thus, the consensus in the arbitration community is that party freedom and the procedural flexibility that comes with it are fundamental attributes of arbitration. Although this presumption is theoretically correct; in other words, the parties are indeed able to craft such a procedure that would perfectly fit for adjudication of their disputes, mostly it does not reflect the practical reality. In practice, when parties are negotiating the terms of an agreement to govern their business relationship, they generally tend to avoid discussions as to what will happen if things go wrong. As a matter of fact, according to our practice experiences, when one of the parties' legal counsel tries to address such hypothetical scenarios, the parties generally prefer to suppress such "negative thoughts" and refuse to make in-depth discussions as to how a possible dispute is to be handled. Hereby, this leaves open the question of the procedure to be followed in arbitration proceedings in case of potential disputes. As a result, the provisions on how to resolve disputes that may arise between the parties, in other words, the "dispute resolution" provisions, are left to the very end of the negotiations and passed over in a few sentences. When the relationship between the parties becomes truly strained and a dispute comes to an unavoidable stage, it becomes even less likely that the parties will agree on how to gather evidence on the dispute in question. In a such situation, any suggestions made by one party regarding the procedure for the taking of evidence will be viewed with suspicion by the other party. In an environment of suspicion and animosity, it is often unrealistic to expect productive negotiations to take place on procedural matters. As a result, although the parties have a wide range of motions to make agreements regarding the method of collecting evidence in arbitration proceedings, they are often unable to exercise this authority in practice. As the parties are not exercising their rule-making powers, this important task, which is decisive for the resolution of the dispute, shifts to the arbitrators. Therefore, in our opinion, it would not be a wrong assessment to say that the freedom of the parties has turned into the freedom of the arbitrator in practice. Once appointed, arbitrators have to decide on many issues with respect to the taking of evidence as rules applicable to arbitration are generally silent as to these matters. Although arbitrators have the opportunity to be guided by some non-binding rules, such as the IBA Rules and the Prague Rules, which are considered to be effective and instructive in the arbitration community, they are ultimately left to make their assessments and reach an award based on their judgment. The above-mentioned non-binding rules can undoubtedly assist arbitral tribunals to a certain extent with regard to the taking of evidence. However, it is not possible to say that these rules are enforceable guidelines that can be blindly followed by arbitral tribunals. A closer look at these rules reveals that they leave many issues to the discretion of the arbitral tribunals. Of course, any decision regarding the taking of evidence in international commercial arbitration is already within the discretion of the arbitral tribunals, even in the absence of these rules. Therefore, these provisions, which have been drafted to allow the arbitral tribunals to decide as they see fit, are no more than general guidance on how to exercise their discretion. For these reasons, even if the parties have agreed on the application of these non-binding rules, the fact remains that the collection and evaluation of evidence are still left to the discretion of the arbitral tribunals. This study takes an inductive approach by analyzing the normative and non-binding rules of law applicable to evidence in international commercial arbitration. Firstly, this study examines whether there is a body of rules that can be characterized as the law of evidence in international commercial arbitration. It is determined that there is a law of evidence in international commercial arbitration; however, its content is rather composed of general principles. After determining that these rules have normative value, it is examined how and to what extent these general principles are concretized in terms of the types of evidence used in international commercial arbitration. Although the degree of concretization of these principles varies according to the types of evidence, as a general characteristic, it is determined that arbitral tribunals are left with a very wide discretionary power. It is concluded that arbitral tribunals have a wide latitude of action with respect to the submission of documents, the presentation of witness testimony, the use of expert testimony, the use of discovery and the extent of the res judicata effect of a prior award. Subsequently, the rules on the admissibility and evaluation of evidence are analyzed and it is concluded that the arbitral tribunals have wide discretion in international commercial arbitration, as in other matters relating to evidence and even the discretion regarding the evaluation of evidence is relatively wider. Since it is difficult to review the discretionary power exercised in these matters, it is observed that the arbitral tribunals' decisions on evidentiary issues fall outside the scope of judicial review. This leads to a further blurring of the already grey evidentiary issues in international commercial arbitration proceedings. This is because it is not possible to determine the extent to which the arbitral tribunal has relied on evidence that ostensibly played a role during the proceedings. In the last instance, although the arbitrators' discretionary powers are limited by general principles such as due process and opportunity to be heard, the limits of such discretionary powers are, generally speaking, somewhat blurred as these are general principles. Another issue is that arbitral tribunals are often subject to pressure from the parties when making their decisions on the taking of evidence during the arbitral proceedings. The parties are more interested in being the winner of the concrete proceedings than in the proper conduct of the proceedings in accordance with the law, procedure and rules. In this sense, a party whose request for evidence is likely to be rejected will often argue that the arbitral tribunal's decision violates the principle of a fair trial, even if this is not the case. It is in these circumstances that arbitral tribunals must strike a balance between a fair trial and an efficient trial and make appropriate decisions on evidentiary issues. If arbitral tribunals emphasize procedural efficiency and defer to the parties' presentation of their claims and defences, this may not in itself constitute an obstacle to legally correct decisions. However, this would violate the fundamental procedural safeguards of the participants in the proceedings and may even lead to arbitration proceedings becoming a mechanism for arbitrary and haphazard decision-making. If the opposite approach is taken, in other words, if the priority is to uncover the material truth at all costs and the procedural economy is put on the back burner, this will result in costly and protracted proceedings that will far exceed the limits of reasonableness. Given the limited scope of the guidelines available to arbitrators on the collection and evaluation of evidence, striking this balance is not an easy task. Therefore, it is quite understandable that arbitral tribunals, when deciding on evidentiary issues, may prefer the safer route and give precedence to claims of breach of the principle of a fair trial, even at the expense of the efficiency of the proceedings. Additionally, the confidential nature of the international commercial arbitral proceedings also amplifies the problem. As a result of this principle, the available knowledge as to the practice of arbitration becomes limited to anecdotal stories as to what has happened in certain individual international commercial arbitration proceedings. The arbitrators do not have sufficient opportunity to know about how their colleagues have dealt with certain issues that may have similarities with the issues that they have been trying to solve. In conclusion, in light of the foregoing, since the arbitral tribunals are the rule-makers of arbitration proceedings, the extent to which arbitration proceedings will function correctly and efficiently depends on the experience of the arbitral tribunals and their knowledge of the law, procedure and rules. Basing a correct and efficient arbitration procedure solely on the initiative of experienced arbitrators reduces the 'certainty' of the arbitral procedure. In the face of this situation, it may be tempting to argue that it is inappropriate for arbitrators to have so much freedom and that the rules applicable to arbitral proceedings should be revised to be more detailed. Indeed, there are those who argue that such a change should take place. In the final analysis, a good system should be able to function well regardless of how qualified (or unqualified) its participants are. It is obvious that an argument that sees detailed procedural rules as a remedy for this would contradict the historical development of arbitration and therefore would not be accepted by the international arbitration community. Likewise, from the other side of the coin, it could be argued that detailed procedural rules that are not appropriate to the nature of the individual dispute would prevent qualified and experienced arbitral tribunals from formulating rules that are appropriate to the resolution of the dispute in question, and that the hands of arbitral tribunals may be tied in this way. Although it may be argued that these counter-arguments are equally justified, they do not negate the fact that certainty should be ensured in international commercial arbitration proceedings. Therefore, this suggests that it may be appropriate to resort to alternative methods to ensure certainty. Indeed, it would be a mistake to assume that the only way to achieve certainty is through a detailed set of rules, as we, as legal practitioners in the Continental European legal system, are accustomed to. In the countries subject to the Common Law system, many branches of law do not have such a detailed set of rules and therefore it is not possible to claim that these legal systems lack certainty. Especially in the common law, certainty is provided by case law. If the same logic were to be applied to international commercial arbitration proceedings, it would mean that making information on arbitration proceedings more accessible could help to achieve the goal of certainty. In recent years, there have been some initiatives recognizing the benefits of this approach. While arbitral tribunals are under no obligation to follow the decisions of other arbitral tribunals, having the opportunity to see that there is a consistent pattern of decisions on a particular issue would undoubtedly provide valuable guidance for arbitral tribunals. As the pool of information available to arbitral tribunals and the parties expands, it is obvious that the grey areas regarding evidence in international commercial arbitration will diminish over time. In this way, it will be possible to achieve greater certainty without undermining the fundamental values of the arbitral procedure. Reducing the uncertainty caused by procedural flexibility on procedural certainty in this way will contribute significantly to the development of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Delil; Evidence; International Arbitiation Law; Milletlerarası Tahkim Kanunu; Proof (presentation); Tahkim; İbraz (İspat)

Regards sur l’intervention du juge étatique dans la constitution du Tribunal Arbitral dans l’espace OHADA - Mainibe Tchiombe, Calice Cléopâtre (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
Qu’il soit institutionnel ou adhoc, L’arbitrage est vu comme un mode de règlement des litiges qui a vocation à se dérouler, de la requête initiale à la sentence finale, sans l’intervention du juge étatique. Il arrive, cependant que, ce juge soit amené à intervenir dans le processus arbitral, pour une raison ou pour une autre. On a pu ainsi dire qu’il n’y a pas de bon arbitrage sans un bon juge. Bien que l’intervention du juge étatique doivent rester exceptionnelle en matière d’arbitrage, il importe que ledit juge soit identifié, d’autant qu’il n’est pas le mena selon la phase à laquelle il intervient et peut varier d’une organisation judiciaire à une autre.
Keywords: Juge étatique; Organisation judiciaire

L’encadrement juridique de la médiation dans l’espace OHADA : analyse critique de l’acte uniforme relatif à la médiation - Mukuamu, Prince (Université de Sherbrooke, 2023)
Aujourd'hui plus qu'hier, la médiation suscite l’intérêt tant des chercheurs, des praticiens, que des politiques. Cet intérêt se matérialise notamment par les différents cadres juridiques dont elle bénéficie dans plusieurs législations. Afin de promouvoir la médiation au sein de ses États membres, L’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a adopté le 23 novembre 2017 un Acte Uniforme relatif à la Médiation (AUM). Après avoir adopté depuis plus de deux décennies un Acte uniforme sur l’arbitrage, l’organisation régionale confirme sa volonté de promouvoir les modes alternatifs de règlement de conflits dans le domaine du droit des affaires. Cependant, l’AUM est un instrument juridique particulier attendu qu'il est le premier de son genre à s’appliquer également aux domaines non encore régis par le droit OHADA. Toutefois, si la médiation tend à se développer de plus en plus, il convient de prendre garde à ce que cette évolution, notamment en ce qui concerne son encadrement légal, ne conduise pas à sa dénaturation. Voilà l’un des défis auquel est également soumis le législateur OHADA.
Keywords: AUM; Acte uniforme; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; OHADA

Les principes directeurs du procès équitable en médiation OHADA - Ngono Yakam, Marie Joseph (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
L'image de l’alternative et de la souplesse de la médiation semble aux premiers abords exclure les principes directeurs du procès équitable de ce mode de règlement des conflits. Mais la réalité en est tout autre. Entant qu'instrument de justice, la médiation ne saurait s’affranchir des garanties d’ordre procédurales. Cette survivance va donc de soi puisque tout comme le procès, la médiation fait intervenir un tiers. La présente étude consiste donc à examiner la question des principes du procès équitable appliqués à la médiation OHADA.
Keywords: Fair trial; Guiding principle; MARD; Mediación; Mediation; Mediação; Médiation; OHADA; Principe directeur; Procès équitable

L'arbitrage international dans les contrats publics en droits marocain et français - Raissi, Imane (Revue du Droit Marocain, 2023)
Le recours à l’arbitrage, comme mode de règlement des différends commerciaux internationaux qui s’applique aux contrats publics reliant les Etats et leurs démembrements et avec des investisseurs privés, s’est étendu au fur et à mesure de l’interventionnisme croissant de l’Etat dans l’économie et de la multiplication des leviers juridiques qui lui sont dédiés (marchés publics, gestion déléguée, partenariat public-privé, etc.). Or, ces contrats ainsi soumis à l’hypothèse de l’égalité des parties posent la problématique de l’équilibre entre la portée de la clause compromissoire et la souveraineté des Etats en matière du régime juridique et de la compétence juridictionnelle. Dans une approche comparée entre les Droits marocain et français, cet article analyse les effets du recours à l’arbitrage international sur les règles applicables aux contrats publics à l’origine du différend, notamment, au niveau de la clause attributive de compétence, la compétence juridictionnelle et l’exequatur des sentences arbitrales.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Commande publique; Contrat public; Droit comparé; France; Maroc; Morocco

Arbitrability of Intellectual Property Dispute: A Pragmatic Dispute Resolution Mechanism - Singh, Vaishali (International Journal of Science and Research, 2023)
Conventionally, conflicts over intellectual property rights have been addressed primarily in national courts. Nonetheless, there has been a considerable inclination towards arbitration in recent years. For example, the number of cases decided under the WIPO Arbitration and Mediation Rules is constantly increasing, and the number of specific IP-related arbitral institutions is rising as well. This is due, in part, to the territorially limited reach of state court procedures, which no longer match the needs of modern international commercial processes. The transition to arbitration is appropriate since arbitration is particularly well suited to settling intellectual property conflicts. Arbitration is a private process, which is especially beneficial in IP issues due to the sensitive nature of the material involved. Furthermore, specific knowledge is necessary to properly settle technological disputes, a challenge that might be overcome by choosing adequately competent arbitrators.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Intellectual property; WIPO (World Intellectual Property Rights Organization)

La jurisprudence arbitrale : composante principale du droit international des investissements - Uranga, Paul (Les Cahiers de droit, 2023)
Le droit international des investissements résulte principalement d’une multitude de traités d’investissement, souvent bilatéraux, parfois régionaux et très rarement multilatéraux. Ce régime éclaté, ayant l’arbitrage comme moyen principal de règlement des différends entre investisseurs et État, ne favorise pas, en théorie, l’émergence d’une jurisprudence réellement cohérente et pertinente. Toutefois, la pratique arbitrale florissante en matière d’investissement s’est révélée constituer une véritable jurisprudence à l’importance non négligeable. Bien que le précédent n’ait pas de valeur juridique obligatoire, force est de constater sa valeur persuasive et la systématicité de son usage. Une telle utilisation des précédents arbitraux a pu permettre le développement d’une compréhension commune des normes des traités d’investissement et favoriser ainsi indirectement le développement conventionnel de ce droit. La jurisprudence arbitrale innerve de ce fait tous les pans du droit international des investissements, du discours des arbitres à l’évolution même des normes applicables. C’est en cela que la jurisprudence arbitrale peut s’entendre comme la composante principale du droit international des investissements.

Effective strategies for resolving labour disputes in the corporate sector: Lessons from Nigeria and the United States - Uzougbo, Ngozi Samuel; Akagha, Onyinyechi Vivian; Coker, Julie Olajumoke; Bakare, Seun Solomon; Ijiga, Amina Catherine (World Journal of Advanced Research and Reviews, 2023)
The relationship between an employer and employee though governed by various laws and regulations can still at some point witness some disagreements and dispute. Labour disputes are not uncommon neither are they peculiar to a particular industry in a country. Usually, trade disputes are hinged on agitation of employees for compensation, good working conditions, job stability and agitation against unlawful termination or dismissal of from service. Over the years, employees have adopted different ways to exhibit their discomfort and grievances in order to convey their message such as strike actions, peaceful protest and so on.  There’s no doubt that these disputes will drastically reduce the level of productivity and overall beneficial impact of the industries in the economic growth of the country. Hence, there’s a need to adopt strategies for resolving these labour disputes. Some industries have applied round table discussions, arbitration, mediation, collective bargaining as well as grievances remedial processes. This work will provide an overview of the causes of disputes in the corporate sector, examine the features of the Nigerian and United States disputes resolution system and also juxtapose the strategies for resolving labour disputes in the two countries. Furthermore, it will provide recommendations to effectively addressing labour issues within the business sector.
Keywords: ADR; Alternative dispute resolution; Industrial relations; Legislative Framework; Multi-door courthouse; Trade unions

Ticari davalarda arabuluculuk - Yildirimoğlu, Hakan (İstanbul Ticaret Üniversitesi, 2023)
Dünya genelinde, uyuşmazlıkların mahkeme dışında alternatif uyuşmazlık çözüm yolları ile çözülmesi konusunda artan bir eğilim bulunmaktadır. Alternatif uyuşmazlık çözüm yollarından biri de arabuluculuktur. Arabuluculuk gönüllülük esasına dayanan bir uyuşmazlık çözme biçimidir. Arabuluculuk sistemi, AB'ye üye bazı ülkeler başta olmak üzere birçok ülkede özellikle ticari uyuşmazlıklarda uygulanmakta ve sonuçları itibariyle tarafları memnun etmekte, yargının yükünün de ciddi şekilde azaltılmasına destek olmaktadır. Yargının iş yükünün hızla arttığı, yargılamadaki gecikmeler nedeniyle adalete duyulan güvenin azaldığı bir ortamda arabuluculuk uygulamaları birçok ülkeye örnek olmaktadır. Ülkemizde de arabuluculuk uygulanmaya başlanmış; hatta en sık karşılaşılan uyuşmazlıklardan iş uyuşmazlıkları, ticari uyuşmazlıklar ve tüketici uyuşmazlıkları dava şartı arabuluculuk kapsamına alınmıştır. Ticari davaların zorunlu arabuluculuk yoluyla çözülmesi uygulamada bazı sorunlara ve çelişkili yargı kararlarının ortaya çıkmasına neden olmuştur. Arabuluculuk, Ticari Davalar, Ticari Davalarda Arabuluculuk, Avrupa Birliği, Zorunlu Arabuluculuk, Alternatif Uyuşmazlık Çözüm Yolları, Dava Şartı Arabuluculuk, Uzlaşma. There is an increasing trend around the world related with the resolution of disputes through alternative dispute resolution methods out of court. One of the alternative dispute resolution methods' is mediation. Mediation is a form of dispute resolution on a voluntary basis. The mediation system is applied especially in commercial disputes in many countries, also in some member countries of European Union. The mediation not only satisfies the parties in terms of its results but also helps to reduce the burden of the judiciary. In a world where the workload of the judiciary increases rapidly and trust in justice decreases due to delays in the trial, commercial mediation practices in European countries set an example for many other countries. Mediation is not also practised in Turkiye but also mandatory in labor disputes, commercial disputes and consumer disputes. Contradiction and discrepancy between the court decisions and other judicial problems arised arised as a result of mandatory mediation. Mediation, Commercial Disputes, Mediation in Commercial Disputes, European Union, Mandatory Mediation, Alternative Dispute Resolution, Condition of Litigation, Commercial Mediation. Reconciliation, Voluntary Mediation
Keywords: Alternate dispute; Alternatif uyuşmazlık; Arabuluculuk; Avrupa Birliği; Commercial cases; Commercial disputes; European Union; Hukuk düzeni; Incompatibility; Judicial decisions; Law order; Mandatory mediation; Mediation; Ticari davalar; Ticari uyuşmazlıklar; Uyuşmazlık; Yargı kararları; Zorunlu arabuluculuk

L'opposabilité aux tiers de la convention d'arbitrage - Mhaoun, Jalal (Université de Bordeaux, 2022)
Il existe en droit commun et en droit de l’arbitrage deux mécanismes similaires ayant un objectif commun : rendre l’acte juridique apte à faire sentir ses effets à l’égard des tiers. Il s’agit, pour le droit commun, du principe de l’opposabilité et, pour le droit de l’arbitrage, de la règle de l’attraction des tiers à la procédure arbitrale. Ces deux techniques, qui procèdent de la même manière et partagent presque les mêmes conditions de mise en œuvre, ont en revanche une qualification distincte. En droit commun, l’opposabilité est connue pour être un principe à part entière dont la fonction principale, la fonction de sanction, est relativement offensive, puisqu’elle oblige les tiers, sujets auxquels l’opposabilité est habituellement attachée, au devoir général de respect, à l’obligation de ne pas nier l’existence des engagements d’autrui et de ne pas y porter atteinte au risque de subir les conséquences de leur immixtion. Le principe de l’opposabilité a également une fonction probatoire qui permet aux tiers d’opposer aux parties, ou aux autres tiers, l’existence d’un contrat pour apporter la preuve d’un fait. Alors qu’en droit de l’arbitrage, la règle de l’attraction permet une extension des effets de la convention d’arbitrage à l’égard des tiers qui se trouvent impliqués positivement ou négativement, directement ou indirectement à la négociation, la formation, l’exécution ou l’anéantissement du contrat dans lequel est insérée la clause d’arbitrage.Puisque les deux techniques partagent le même procédé et agissent sur les mêmes personnes, la présente thèse a pour but d’étudier la réception du principe d’opposabilité en droit de l’arbitrage. Cette réception passe par une intégration et un attachement de la règle de l’attraction au principe de l’opposabilité comme fonction nouvelle. L'objectif principal est donc de répondre à une question précise : comment faire en sorte que le principe de l'opposabilité soit accepté et transposé en matière arbitrale pour ainsi voir à l’œuvre toutes ses fonctions, y compris celle qu’il vient d’intégrer, sans que le système juridique ne subisse de profonds bouleversements.Notre analyse de la réception se déroule en deux étapes. Après avoir rappelé et établi le cadre théorique du principe de l'opposabilité, dans lequel avons-nous examiné les différentes conceptions, justifications et sujets de l’opposabilité ; cadre qui nous a offert une image plus claire et réaliste des applications de l'opposabilité en droit commun et nous a permis de voir si ces applications et fonctions étaient en mesure de justifier la règle de l'attraction. Nous avons donc conclu que l’opposabilité est parfaitement recevable en droit de l’arbitrage à condition d’y intégrer ladite règle de l’attraction comme fonction nouvelle. Convaincus de sa réception en droit de l'arbitrage, nous avons, ensuite, soumis la nouvelle fonction d’attraction à un ultime test, celui de l’efficacité. L’examen de l’efficacité aura permis de recenser les limites de la règle de l’attraction dont nous avons proposé un certain nombre de solutions de renouvellement, et ce, dans le but de mieux intégrer la fonction et pour que celle-ci puisse avoir un impact systématisé sur le droit de l’arbitrage.
Keywords: Arbitrage; Arbitrage multipartite; Arbitragem; Arbitraje; Arbitration; Convention d'arbitrage; Extension; Opposability; Opposabilité; Règle de l'attraction; Third parties; Tiers; Tiers (droit); Transmission

Reforming investor-state dispute resolution: Focusing on the roles of domestic courts - Ma, Wanli (Erasmus University Rotterdam, 2022)
While a universally applicable multilateral agreement on investment is not yet available, a broad network of BITs and investment chapters in FTAs has been put in place to protect foreign investors and their investments. Meanwhile, investment arbitration has become a defining feature of modern international investment law over the recent decades, enabling foreign investors to launch an investment arbitration against host states, often without the need to go through local remedies before that. With the caseload of investment arbitration increasing at a rather rapid speed, such a dispute resolution method has also attracted fierce criticism. Many commentators have alleged, among other, that the decision-making of investment arbitrators has been inconsistent and unpredictable, that investment arbitration has become a threat to public interest, that investment arbitration proceedings are not transparent enough, that the arbitrators involved are not independent nor diverse enough, that the lack of an applellate mechanism compromises the quality of decision-making, and that investment arbitration has become far too costly and time-consuming. Against such a backdrop, the global community has made joint efforts to reform the investment arbitration system, not least through various initiatives developed at ICSID and UNCITRAL. Almost at the same time, national states also seem to have started to reconsider the costs and benefits of including investment arbitration in their investment agreements as a method for the resolution of disputes with foreign investors. Although the caseload of investment arbitration continues to grow and national states keep concluding IIAs containing investment arbitration clauses, at least some countries in their more recent investment treaty making practice have demonstrated a policy trend to rein in investment arbitration and ramp up the role of domestic courts in resolving investment disputes. They often do so by exiting the ICSID system, terminating their investment agreements with economic partners, excluding investment arbitration from their investment agreements, and conditioning investment arbitration upon the prior use of litigation via domestic courts. While the state practice mentioned above surely does not suggest the global society has any intention to abandon investment arbitration any time soon, it prompts us to take a step back and reconsider the role that domestic courts may play in resolving investment disputes, instead of solely focusing on the piecemeal reform of investment arbitration. When it comes to investor-state dispute resolution, domestic courts can indeed play different roles along the process. Like investment tribunals, domestic courts can also adjudicate investment disputes between foreign investors and local authorities. Such a judicial role sometimes is also confirmed in investment agreements through, for example, the exhaustion of local remedies rule, the clause demanding pursuit of local remedies prior to investment arbitration and the fork-in-the-road provision. In the context of non-ICSID arbitration, disputing parties are often entitled to applying for the review by domestic courts loci arbitri of the rulings and awards rendered by investment tribunals. Domestic courts loci arbitri would thus assume a supervisory role with regard to arbitration proceedings and arbitral outcomes, as they may set aside arbitration awards in question according to the review grounds enumerated in local arbitration laws. Moreover, domestic courts in a broader sense may be called upon to support the conduct and / or authority of investment arbitration, by recognizing and enforcing the investment awards rendered by arbitral tribunals and issuing interim measures of a judicial nature to facilitate the arbitration process. Since litigation through domestic courts and investment arbitration are two primary remedies that foreign investors often rely on for the resolution of investment disputes, this study constructs three models of institutional design with regard to the allocation of jurisdiction over investment disputes between domestic courts and investment tribunals. While the reality may turn out to be more complicated, such three models roughly represent the institutional choices facing national states. These three models are: (i) utter reliance on domestic courts as the exclusive forum for investor-state dispute resolution, (ii) investment arbitration operating as a substitute for litigation via domestic courts, and (iii) investment arbitration working as a complement to litigation via domestic courts. In order to conduct a comparative institutional analysis of the three models to reveal their respective tradeoffs, this study employs a goal based approach which is increasingly used to analyze the effectiveness of international adjudicatory mechanisms. As a result of the employment of the goal-based approach, the goals of investor-state dispute resolution are recognized as achieving fair and efficient dispute resolution, promoting state compliance with investment treaty norms, facilitating the objectives of the investment law regime, and legitimizing the underlying investment treaty regime. While the quality of the national judiciaries of many developing countries is not the same as it was decades ago largely due to the judicial reforms launched around the world, fairness and efficiency in dispute resolution still cannot be fully guaranteed in the domestic courts of those countries without a robust legal system and a good record of the rule of law. However, there are certain institutional characteristics of court litigation that may facilitate the efficiency in the resolution of investment disputes, such as the unique advantage of domestic courts that they can work as a single forum for dispute resolution and the better knowledge of court judges of the domestic legal framework at issue. Domestic courts also hold great potential in promoting the compliance by national states with investment treaty norms not least because they have more flexibility in awarding both primary and secondary remedies, but that of course depends on whether domestic courts can adjudicate investment disputes in a fair and impartial manner. Moreover, while utter reliance on litigation via domestic courts may strengthen the domestic rule of law and improve the investment climate in the long term by pressing host states to improve their legal systems and judicial institutions, it may also invite the politicization of investment disputes and the diplomatic intervention from home states in investor-state dispute resolution. Furthermore, despite the risks created for foreign investors, reliance on domestic courts as the exclusive forum may enhance the legitimacy of the investment treaty regime by reducing the sovereignty costs incurred by national states and putting domestic investors and foreign investors on the same footing. Investment arbitration operating as a substitute for domestic courts, on the other hand, demonstrates certain advantages, which are typically affiliated with international arbitration, in achieving the fair and efficient resolution of investment disputes. Unlike domestic courts, which are an integral part of the state apparatus, investment arbitrators are often immune from the influence of domestic politics and are thus believed to be independent and impartial. Meanwhile, the specialization of arbitrators in a particular area of knowledge and the procedural flexibility of arbitration proceedings, among others, are expected to improve efficiency in the resolution of investment disputes. However, empirical evidence presented in the literature sometimes suggests that, in reality, investment arbitrators may not be that unbiased and investment arbitration proceedings often drag on with a bill of a massive amount. Besides, although investment tribunals have a broad scope of jurisdiction over the behavior of different government branches, the practical difficulties they face in awarding primary remedies may damage their ability in promoting state compliance with investment treaty norms. In addition, the introduction of investment arbitration grants to foreign investors a standing in international arbitration proceedings, to a large extent reducing the need for diplomatic protection and home state intervention. However, the positive impact of investment arbitration in facilitating the development of the domestic rule of law and the maintenance and increase of foreign capital is less certain. As for the preservation of the legitimacy of the underlying investment treaty regime, investment arbitration as an alternative to domestic courts cannot be relied on to produce much positive impact. For instance, the increasing sovereignty costs and financial burden imposed on national states would probably prompt more of them to turn against the investment treaty regime. The complement model, in which domestic courts assumes primary jurisdiction and investment tribunals secondary jurisdiction over investment disputes, stands a good chance in keeping the advantages of both court litigation and investment arbitration while avoiding their disadvantages. In the complement model, domestic courts will act as the first line of defense in adjudicating investment disputes, and the institutional advantages of court litigation will be enabled to release their potential. At the same time, even if foreign investors are not satisfied with the judicial outcome or regard the court proceedings as corrupt or unfair, they may escalate the specific disputes to investment tribunals for further consideration. Since court judges are more knowledgeable and experienced in the interpretation and application of domestic law, the legal analysis of court judges will also benefit the decision-making of investment arbitrators in the subsequent arbitration proceeding. Allowing domestic courts to have a first try at investment disputes will also increase the likelihood that primary remedies could be accorded, thus the unique advantages of primary remedies in promoting state compliance with investment treaty norms are not discarded in the complement model. Moreover, the complement model is also more promising in facilitating the achievement of the objectives of the investment treaty regime, and that is because domestic courts are not marginalized in the complement model, the antagonism between foreign investors and host states may be expected to decrease, and the depolicization of investment disputes will not be lost since investment arbitration is kept as an option. Furthermore, the complement model strikes a better balance among the interests of foreign investors, host states and other stakeholders, thus it is more likely to preserve and even enhance the legitimacy of the underlying investment treaty regime than the other two institutional choices. Although the complement model serves the goals of investor-state dispute resolution the best in theory, not any casual combination of court litigation and investment arbitration will do the job; instead, only a smart mix of the two dispute resolution methods can give full play to the advantages of the complement model. Now, we switch to the supervisory role of domestic courts in investor-state dispute resolution. While a systemic appellate mechanism has not been created for investment arbitration, disputing parties may rely on setting-aside proceedings in non-ICSID arbitration to challenge arbitration awards. In other words, domestic courts loci arbitri may conduct a judicial review of the rulings and awards made by investment tribunals. However, a theoretical analysis of the judicial review mechanism supported by empirical evidence has shown that the mechanism has several flaws, which include but are not limited to the points that follow immediately. Since there is only a casual link between the seat of arbitration and the investment dispute, it is inappropriate to subject the decision-making of arbitrators to the judges from the place where the arbitration proceedings took place. The very fact that review courts have been overwhelmingly located within the developed North could raise concern that the judicial review mechanism is inherently biased against developing countries which have already shown a somewhat negative sentiment towards investment arbitration. Given that judicial review proceedings could easily go through more than one instance of court proceedings in many jurisdictions, the dispute resolution process may consume more time and generate higher costs. From this point of view, the judicial review mechanism favors the richer party in investment arbitration and could become a weapon of dilatory tactics available for such a party. Considering the higher error costs relating to investment arbitration than that relating to commercial arbitration, limited review grounds and a copious amount of deference to arbitral tribunals may not prove to be as effective in the scrutiny of investment awards. Moreover, the idiosyncrasies as to review grounds and standards across jurisdictions indicate that inconsistency would also probably permeate the judicial review practices, which would then encourage forum shopping that leads to increased costs and decreased efficiency. In addition, as both review courts and enforcement courts may exercise control over investment awards, the setting-aside decision may be merely disregarded at the enforcement stage and the overall efficiency of investor-state dispute resolution may be reduced. In order to overcome many of the flaws mentioned above, a delocalized form of review should be introduced to take place of the current judicial review mechanism.

L’arbitrage des marchés publics - Sinclair, Kongni Ngoula (International Multilingual Journal of Science and Technology, 2022)
Les contrats administratifs, plus précisément les marchés publics, sont moyens par lesquels l’Etat assure sa mission d’intérêt général. Ainsi, il peut arriver que pendant la phase de passation ou d’exécution d’un contrat de marché public, que l’une des parties ne puisse pas accomplir les formalités, d’où la naissance d’un litige. De ce fait, pour résoudre ce litige, les parties peuvent décider d’un règlement à l’amiable du différend. L’arbitrage étant le mode par excellence de règlement à l’amiable des litiges, il est donc opportun en partant de ces spécificités, de mettre en œuvre la procédure d’arbitralité des marchés public et l’issue positive de cette procédure qu’est la sentence arbitrale.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; CEMAC; Commande publique; Contrats administratifs; GICAM; Marchés publics; Organes communautaires; Procédure arbitrale; Sentence arbitrale

La convention d’arbitrage : étude comparée de droit franco-marocain - Ajouby, Samia (Université Paris 2, 2022)
Terre attractive pour les investisseurs étrangers, le Maroc voit son économie muter au gré de l'implantation d'entreprises. Face à cette situation, l'adaptation du droit est essentielle. Il s'agit effectivement d'un instrument fondamental pouvant être mis à la disposition des entreprises pour leur offrir un cadre légal rassurant quant à la prospérité de leurs intérêts. Or la justice étatique inspire traditionnellement la crainte du fait de sa lourdeur administrative et de son incapacité à assurer des garanties procédurales suffisantes Pour résorber cela, le législateur marocain a tendu à développer les modes alternatifs de règlement des conflits, tel que l'arbitrage. C'est dans ce contexte que la loi intitulée "arbitrage et médiation conventionnelle" a été ratifiée, le 6 décembre 2007. Elle s'inspire du droit français pour modifier les articles 306 à 327 du Code de procédure civile marocain. Ce cadre procédural vise à insuffler une vigueur nouvelle aux modes alternatifs de règlement des conflits. Néanmoins, la souplesse du régime a pour corollaire des pathologies qui peuvent affecter les conventions d'arbitrage. La rédaction des clauses approximatives, et la formation insuffisante de certains arbitres se traduisent par des conventions d'arbitrage bancales, sources de nouveaux problèmes là où elles devraient faciliter la résolution des litiges. Dans ces conditions, une nouvelle réforme a donné naissance à un Code de l’arbitrage, ratifié le 24 mai 2022. Il s’agira d’étudier l’évolution de la législation marocaine de l’arbitrage, dans une dimension comparatiste avec le droit français, et à la lumière d’une recherche constante de l’efficacité de la convention d’arbitrage. [Abstract] The arbitration agreement : a comparative study of French and Moroccan law : Morocco is an attractive country for foreign investors, and its economy is changing as companies are setting up. Faced with this situation, the adaptation of the law is essential. Indeed, it is a fundamental instrument that can be made available to companies to offer them a reassuring legal framework for the prosperity of their interests. However, the state justice system traditionally inspires distrust because of its administrative cumbersomeness and its inability to ensure sufficient procedural guarantees. In order to solve this, the Moroccan legislator has tended to develop alternative methods of dispute resolution, such as arbitration. It is in this context that the law entitled "arbitration and conventional mediation" was ratified on December 6, 2007. It is inspired by French law to modify articles 306 to 327 of the Moroccan Code of Civil Procedure. This procedural framework aims at breathing new life into alternative dispute resolution. Nevertheless, the flexibility of the regime has as a corollary pathologies that can affect arbitration agreements. The drafting of unprofessional clauses and the inadequate training of arbitrators result in flawed arbitration agreements, which are a source of problems where they should facilitate the resolution of disputes. In these conditions, a new reform has led to an Arbitration Code, ratified on May 24, 2022. The aim is to study the evolution of Moroccan arbitration legislation, in a comparative dimension with French law, and in the light of a constant search for the efficiency of the arbitration agreement.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Comparative law; Contentieux international; Contract law; Contrats; Convention d'arbitrage; Conventions d'arbitrage international - Maroc; Dispute resolution; Droit comparé; Droit des contrats; Droit international; Efficacité; Efficiency; France; International law; International litigation; Maroc; Modes alternatifs; Procedure; Procédure; Règlement de conflits; Résolution des litiges

The Unilateral Arbitration Clause between Permissibility and Nullity - Mahmoud Jaradat, Nashat; JassimSarhan, Ghassan (Information Sciences Letters, 2022)
Researching the judicial applications of Arab countries to one of the issues that have occupied legal thoughts in the Western world for decades and still in one form or another, the so-called Unilateral Arbitration Clauses, we did not find a discussion of the applicability of this clause within the laws. Even though this condition takes a reasonable space of the legal arguments as previously mentioned, it has even become widely used in contracts, such as tenancy, contracting, and financial investments. The study showed that the above-mentioned clause has recently increased its use in financing contracts, especially with the increasing globalization of banking services and bank transfers. Although banks usually prefer to resort to traditional litigation, lack of similarity in the legal rules and judicial applications related to banking transactions and their difference from one country to another was a reason for the banks preference of resorting to arbitration. There is no examination of the legitimacy of an unequal or optional arbitration clause in Bahrain. Also, the Bahraini and Egyptian courts, to the best of our knowledge, did not decide whether it should be considered null or valid. The same case is applied to the French courts which have no cases that examined this type of clauses except for a case in 2006 and the other is a judgment close to the same issue on October 7, 2015, from the French Court of Cassation. The English and American courts were different; they examined this clause and had several judicial implementations due to the fact that most of the arbitration terms are either related to multinational companies operating within the framework of the Wall Street Stock Exchange in New York or those that stipulate the enforcement of British and Wales law on the provisions of the contract . However, many Arab countries, in general, as well as Bahrain and some Gulf countries, in particular, are seeking in their economic model to attract foreign investments and capital, especially those related to financial and banking industries, to diversify sources of income. The decision of investing or not investing the capital in a country is made by the judicial authority in terms of independence as well as the judicial application of legal texts as these factors are directly reflected in the desire to invest and show the possibility of protecting investors.

Settlement of Disputes Arising from Documentary Credit Under National and International Regulations - Nour, Hoda Magdy (UAEU Law Journal, 2022)
The need Settlement of disputes arising from bank credit between national and international rules, protecting the interests of the bank and ensuring its financial rights before the debtor. As the Bank faces different technical and legal difficulties, as well as the multiplicity of legal adaptation, we deal with the rules governing banking accreditation from the point of pleadings law, and the methods of amicable settlement of these disputes and following, and compulsory execution. International efforts are taking the lead in establishing the technical regulation of bank accreditation and setting rules "DOCDEX" in 1997, and the 2015 amendments, which still need more as they do not provide a legal way to implement them. It is necessary to find out legal regulation at the domestic and international levels, which calls for the legislator to intervene to organize its rules and procedures. We have sought in this study to weave the legal entity to seize bank credit within the legally acceptable limits based on a system of seizure of the debtor with third parties against the background of the legal system of documentary credit and the relationships arising from it, and its financial and economic effects that go beyond the parties to the beneficiaries of companies, bodies, and economic institutions, As the matter still requires the existence of special legislation regulating the seizure of bank credit, to ensure the effectiveness of the guarantees surrounding the appropriations by the national legislator and at the international level. This would expand the insurance of bank credit so that the creditors recover their full right directly or by seizing the value of the credit, which calls for organizing this seizure with rules that consider the privacy of this seizure and its rules and are consistent with the required speed in such transactions in a way that protects the creditor from abuse, in a manner that ensures the observance of confidentiality, due process, and the spirit of banking work, anticipate the possible future that will witness the decline of documentary credit and replace it with electronic transactions, the establishment of specialized banking courts that save time and effort.

Business Dispute Settlement Through Mediation in State Courts and Arbitration Institutions - Yuspin, Wardah; Aziz, Abdul (International Journal of Social Science Research and Review, 2022)
In social life, there are often differences in perceptions between humans, causing problems or disputes, whether minor or serious. Likewise in the relationship of economic activities or more commonly known as business relations. Not infrequently humans experience a clash and differences of opinion that lead to disputes. Various problems will always arise in business as long as humans run their business solely for profit, so there are often differences of opinion because the parties will not be harmed which will eventually lead to disputes. In the end, dispute resolution, especially business disputes, is often resolved through a trial in court through a lawsuit by one of the parties who feel aggrieved. However, what was expected from the settlement turned out to be unsatisfactory for the parties because the settlement through litigation sometimes took a long time to obtain legal certainty so that it actually harmed business people because of the loss of time, energy and materials. As an alternative to resolving business disputes, business actors have a tendency to avoid disputes in court and choose to use mediation or through arbitration institutions. This study will briefly describe the comparison of business dispute resolution through court mediation with settlement through arbitration institutions. The research was conducted through descriptive empirical legal research.
Keywords: Arbitration; Business; Dispute

Processo arbitral: a estabilização da demanda - Leão, Fernanda de Gouvêa (Universidade de São Paulo, 2022)
Esta tese trata da estabilização da demanda no processo arbitral. Ao se falar da estabilização da demanda no processo arbitral, são muito comuns as afirmações de que, no processo arbitral, o tratamento é diferente, pois é mais flexível. Também, comumente se afirma que a estabilização da demanda na arbitragem se daria no momento de assinatura do termo de arbitragem. No entanto, entende-se que o tema não foi analisado de forma aprofundada, e, inclusive, com base nas pesquisas realizadas, poucas foram as obras nacionais que trataram especificamente da estabilização da demanda arbitral. Diante disso, este trabalho buscará analisar como se dá a estabilização da demanda no processo arbitral e as hipóteses de modificação da demanda no decorrer do processo. Para tanto, inicialmente serão apresentadas considerações iniciais, necessárias ao desenvolvimento do trabalho, como a natureza jurídica da arbitragem e sua inclusão na teoria geral do processo. Após, analisa-se o processo arbitral, a formação da demanda na arbitragem e como se dá a definição das regras a serem observadas no processo arbitral, e como são definidos os poderes jurisdicionais dos árbitros. Ainda, ao se falar de estabilização da demanda, necessariamente deve ser estudado o conteúdo da demanda arbitral e sua individualização, ou seja, o que constitui o objeto litigioso do processo arbitral. Em seguida, será feita a investigação de quais são os elementos da demanda arbitral, as teorias que tratam de cada um deles e qual deve ser seu conteúdo mínimo. Ultrapassada essa investigação e fixados os conceitos necessários ao desenvolvimento do tema, serão analisadas as linhas gerais da estabilização da demanda, sua natureza jurídica e os fundamentos que embasam não só a regra da estabilização da demanda, mas também sua mitigação, do que decorre da análise dos sistemas rígidos e flexíveis. Definidos os conceitos gerais acerca da estabilização da demanda arbitral, analisaremos como outros ordenamentos tratam da questão, bem como as disposições no processo estatal brasileiro, para que se possa compreender o que o sistema processual entende como estabilização da demanda e as hipóteses de mitigação. Em seguida, trataremos do momento de estabilização da demanda arbitral, possibilidade de modificação dos elementos da demanda e consequências da violação da regra da estabilização da demanda. Por fim, todo estudo teórico deve mostrar seu viés prático, de modo que as análises que foram feitas possam ser aplicadas pelas partes e pelo árbitro. Por essa razão, o último capítulo é dedicado às recomendações sobre o tratamento da estabilização da demanda na arbitragem. This thesis addresses the stabilization of demand in the arbitral procedure. When discussing the demand stabilization in the arbitration procedure, it is widely asserted that in the arbitration proceeding the treatment is different since it is more flexible. Furthermore, it is commonly stated that the stabilization of demand in arbitration would occur when the terms of reference are signed. Nevertheless, it is understood that the issue has not been analyzed comprehensively and, based on the research conducted, few Brazilian studies have specifically addressed the stabilization of the arbitral demand. Thus, this study will analyze how the stabilization of the demand occurs in the arbitration procedure and the hypotheses of modification of the claim in the course of the procedure. For this purpose, the necessary initial considerations for the development of the study will be presented, such as the legal nature of arbitration and its inclusion in the general theory of procedure. After that, we will analyze the arbitration process, the formation of the demand in arbitration, and how the rules to be observed in the arbitration process are defined, as well as the jurisdictional powers of the arbitrators. Afterward, we will then proceed to the analysis of the arbitration process, the constitution of the demand in arbitration, and how the rules to be observed in the arbitration procedure are defined, as well as how the jurisdictional powers of the arbitrators are defined. Moreover, when discussing the stabilization of the demand, one must necessarily study the content of the arbitration claim and its individualization, i.e., what constitutes the litigious object of the arbitration procedure. Following that, an investigation of the elements of the arbitration claim, the theories that deal with each of them, and what the minimum content should be, will be carried out. Once this investigation has been concluded and the concepts necessary for the development of this thesis have been established, the general lines of the stabilization of demand will be analyzed, as well as its legal nature and grounds that support, not only the rule of stabilization of demand, but also its mitigation, which follows from the analysis of rigid and flexible systems. Once the general concepts concerning the stabilization of arbitral demand are defined, we will analyze how other legal systems address the issue, as well as the provisions in the Brazilian state process, so that we can comprehend what the procedural system understands as stabilization of demand and the hypotheses of mitigation. Next, we will address the moment of stabilization of the arbitral demand, the possibility of modifying the elements of the claim and the consequences of the violation of the rule of stabilization of demand. Finally, every theoretical study must reveal its practical side, so that the analyses that have been made can be applied by the parties and the arbitrator. For this reason, the last chapter is devoted to recommendations on the treatment of demand stabilization in arbitration.
Keywords: Alemanha; Arbitrage; Arbitragem; Arbitration; Arbitration procedure; Brasil; Direito Comparado; Direito Processual Civil; Espanha; Estados Unidos; Juízo arbitral; Litígio; Modification of the elements of the demand; Portugal; Procedimento especial; Stabilization of the demand

Desconsideração da personalidade jurídica na arbitragem - Ferraz, Renato de Toledo Piza (Universidade de São Paulo, 2022)
A presente tese se ocupa de analisar a possibilidade de vinculação de não signatário da convenção de arbitragem ao processo de jurisdição privada via desconsideração da personalidade jurídica no âmbito de arbitragens domésticas. Para tanto, no Capítulo 1, examinam-se premissas teóricas ligadas ao processo de aquisição da personalidade jurídica; de como ele opera limitando a responsabilidade dos integrantes do ente personalizado; e do embate entre autonomia da atividade societária e abuso de direito do qual pode resultar a desconsideração da personalidade jurídica. A teoria desconstitutiva é verificada desde sua criação até os dias atuais, enfatizando-se seu modo de funcionamento à luz dos pressupostos que autorizam sua incidência e os efeitos que se seguem desse reconhecimento segundo a concepção clássica da técnica desconstitutiva. No Capítulo 2, aborda-se o papel da autonomia da vontade para a teoria geral dos contratos e para a arbitragem, apontando-se o alcance e a classificação desta última para, a seguir, adentrar no tema da verificação do consentimento para arbitrar conflitos. Nesse contexto, são analisadas diversas teorias que fundamentam a participação de parte não signatária em arbitragens para se chegar à formulação daquilo que se denominou de consentimento suficiente para arbitrar conflitos. Ao ensejo do estudo das diversas teorias que embasam a extensão da cláusula compromissória, procura-se assinalar distinções, mas também semelhanças, que tornem viável apropriar seus argumentos, quando for o caso, para a específica hipótese de vinculação de terceiro via desconsideração da personalidade jurídica. No Capítulo 3, o epicentro da tese, são investigados os fundamentos que, segundo se defende, autorizam a hipótese. Para tanto, são levados em consideração implicações próprias da natureza jurídica da arbitragem e da regra do kompetenz-kompetenz; a equiparação entre árbitros e juízes togados no exercício de suas funções; o valor da efetividade para a jurisdição arbitral, com foco na análise econômica do direito e no impacto para os custos transacionais da arbitragem ao se rechaçar a hipótese defendida; a boa-fé objetiva como meio apto a identificar o consentimento suficiente; e, finalmente, uma análise individual de alguns trabalhos doutrinários que defendem a hipótese contrária, expondo criticamente seus motivos. Como resultado dos pontos abordados, procura-se responder se a análise da pretensão desconstitutiva por árbitros choca-se com o sistema por alargar os limites da convenção, seja em razão da matéria, seja em virtude dos sujeitos contratantes do pacto arbitral. A conclusão a que se chega é no sentido de que a conjugação desses fatores possibilita a vinculação de parte não signatária ao processo arbitral em razão da utilização abusiva da personalidade jurídica, sendo essa a solução mais consentânea com os propósitos da técnica desconstitutiva estampada no art. 50 do CC e conforme o que dispõe o sistema arbitral. This thesis is dedicated to analyzing the possibility of binding a non-signatory of the arbitration agreement to the private jurisdiction process via disregard doctrine in domestic arbitrations. To this end, Chapter 1 analyzes the theoretical premises linked to the process of acquisition of legal entity, the way it operates in limiting the liability of the members of the personalized entity, and the conflict between the autonomy of the companys activity and abuse of rights, which may result in the disregard of legal entity. The disregard doctrine is verified from its conception to the present days, emphasizing the way it works according to the requirements that allows its incidence and the effects from its recognition according to the classic doctrine of the corporate veil. Chapter 2 deals with the role of autonomy of the will in the general theory of contracts and arbitration, pointing out the reach and classification of the arbitration to then go into the theme of the verification of consent to arbitrate conflicts. In this context, the various theories that support the participation of a non-signatory party in arbitration proceedings are analyzed to formulate what is called "sufficient consent" to arbitrate disputes. In the course of analyzing the various theories on which the extension of the arbitration clause is based, an effort is made to point out distinctions as well as similarities that could make feasible to adopt their arguments, where appropriate, for the specific hypothesis of binding a third party through vail of legal entity. In Chapter 3, the epicenter of the thesis, the grounds by which, according to what has been defended, the arguments that authorizes the hypothesis are examined. To this end, the implications of the legal nature of arbitration are taken into consideration; the rule of kompetenz-kompetenz; the equivalence between arbitrators and judges in the exercise of their functions; the value of effectiveness for the arbitral jurisdiction, focused on the Economic Analysis of Law and the impact on the transactional costs of arbitration when the defended hypothesis is rejected; objective good faith as liable ground for identifying sufficient consent; and finally, individual analysis of some doctrinal works defending the contrary hypothesis, critically exposing their motives. As a result of all the points analyzed, an attempt is made to answer whether the analysis of the unconstitutional claim by arbitrators clashes with the system by extending the limits of the arbitration convention, whether due to the subject matter or to the contracting parties of the arbitration agreement. The conclusion is that the combination of these factors allows the binding of the non-signatory party to the arbitration process due to the abusive use of the legal entity, being this the most consistent solution with the purposes of the unconstitutional technique stamped in article 50 of Brazilian Civil Code and according to what the arbitration system disposes of.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Arbitration Law; Arbitration clause; Binding of non-signatories; Civil procedural law; Cláusula compromissória arbitral; Convenção de arbitragem; Direito arbitral; Direito processual civil; Limites subjetivos; Personalidade jurídica; Subjective limits; Vail of legal entity; Vinculação de não signatários

El principio de voluntariedad y la tenencia en mediación - Sarmiento, Mónica Piedra; Pazmiño, Esteban Polo (Polo del Conocimiento, 2022)
En los últimos tiempos la mediación se ha visto involucrada en varios conflictos y sucesos de la realidad actual, pues este procedimiento, como el resto de métodos alternativos de solución de conflictos siempre ha estado presente, sólo se tiene que acudir a los autores clásicos y observar que se hacía referencia a ellos. Sin embargo, la mediación ha tomado fuerza a través de su verdadero desarrollo hacia una cultura de paz. El principio de voluntariedad es una característica esencial en los medios alternativos a la solución de conflictos, en el que, las partes resuelven sus controversias en materia transigible, asistidos por un tercero neutral llamado Mediador/a, el mismo que, guía, y conduce a las partes a resolver de manera eficaz, eficiente, rápida, y legal los conflictos. Si bien es cierto, dentro de este procedimiento se presentan muchos problemas al momento de resolver esta situación, y se ha encontrado en el mismo con personas, situaciones, posiciones, intereses y necesidades diferentes, así también se evidencian sentimientos, que al momento de llegar a un acuerdo de tenencia, lo único que se prioriza es todo lo mencionado anteriormente, pero no de manera consciente y responsable el bienestar de los menores, y ante este escenario, las partes deciden, y como es lógico el tercero neutral (mediador) debe respetar esa voluntad. Para esta investigación se ha utilizado una metodología histórica - lógica, así como inductiva - deductiva y dogmática jurídica, con un tipo de investigación cuantitativo, y un nivel de investigación descriptivo, lo que permite detallar y caracterizar el fenómeno en estudio.
Keywords: Conciliación; Conciliation; Mediación; Mediation; Médiation; Relación padre – hijo.; Tenencia

The Right to Water in Investment Treaty Arbitration and Its Impact on Jurisdiction and Applicable Law - Geravand, Farshad (Public Law Researsh, 2022)
The right to water in investment arbitration has been one of the most contentious issues before investment arbitration tribunals in recent decades. The privatization of public services, including water and sanitation, and assigning them to foreign investors has caused the right to water as a vital benefit being repeatedly raised in investment arbitrations. However, due to tribunals’ narrow interpretation of jurisdiction and applicable law, this fundamental human right has been considered irrelevant and ignored, and this has fueled the legitimacy crises in investment arbitration. This research seeks to indicate the potentiality of more protection of the right to water through balancing the states international obligations in the two areas of investment law and human rights law. Proposed methods for integrating human rights with investment law include the correct interpretation of jurisdictional clauses and the applicable law based on the treaties interpretation principles, systematic integration and the inclusion of new clauses in investment agreements. طرح حق بر آب در داوری سرمایه‌گذاری یکی از مناقشه‌انگیزترین مباحث پیش روی دیوان‌های داوری در چند دهه اخیر بوده است. خصوصی‌سازی خدمات عمومی از جمله آب و فاضلاب و سپردن آنها به سرمایه‌گذاران خارجی موجب شده تا حق بر آب بعنوان یک منفعت عمومی و حیاتی بارها در داوری‌های سرمایه‌گذاری مطرح شود. با تفسیر مضیق محاکم از شروط صلاحیتی و قانون حاکم، این حق بنیادین بشری در برخی موارد نامربوط و نادیده تلقی شده و این امر به بحران مشروعیت در داوری سرمایه‌گذاری دامن زده است. این جستار می‌کوشد تا امکان حمایت بیشتر از حق بر آب را از طریق برقراری تعادل بین تعهدات بین‌المللی دولت‌ها در دو عرصه حقوق سرمایه‌گذاری و حقوق بشر نشان دهد و در پایان روش‌هایی را برای ادغام این دو از جمله تفسیر درست شروط صلاحیتی و قانون حاکم با تکیه بر اصول تفسیر معاهدات، تلفیق سیستمیک و گنجاندن بندهای جدید در موافقتنامه‌های سرمایه‌گذاری پیشنهاد کند.
Keywords: Applicable law; International Investment Arbitration; Jurisdiction; Right to Water; Systemic Integration; تلفیق سیستمیک; حق بر آب; داوری سرمایه‌گذاری بین‌المللی; شروط صلاحیتی; قانون حاکم

L'efficacité des mesures provisoires et conservatoires dans l'arbitrage interne : étude du droit français et du droit koweïtien - Alenezi, Ali (Université Jean Moulin Lyon 3, 2022)
En droits français et koweïtien, il existe une juridiction de référé quelque soit la matière. Cette juridiction a le pouvoir de prendre des mesures provisoires et/ou conservatoires pour régler momentanément une situation urgente ou pour sauvegarder provisoirement et rapidement un droit dans l’attente qu’un jugement au fond soit rendu. Toutefois, en matière arbitrale, le juge étatique n’est pas le seul compétent pour pouvoir prendre lesdites mesures. En effet, l’arbitre désigné dans la convention d’arbitrage dispose également de cette prérogative. À ce titre, les juges étatiques ou arbitraux français et koweitiens, bénéficient de points forts mais également de faiblesses lorsqu’ils rendent ces mesures. D’une part, les juges des référés français et koweïtiens disposent de toutes les prérogatives permettant de rendre leurs décisions provisoires d’une manière efficace et rapide. Toutefois, la lourdeur des règles procédurales applicables devant les juridictions de référé peut s’avérer dissuasif. Elles peuvent ainsi préférer se tourner vers l’arbitre puisque les règles de procédure propre à l’arbitrage sont souvent perçues comme étant modernes, simples et rapides. Toutefois, les arbitres de ces deux États ne disposent pas de l’impérium, qui garante garantissant l’efficacité et l’effectivité de leurs mesures. À ce titre, la substance de cette thèse résidera dans la comparaison entre le juge des référés et les arbitres français et koweitiens concernant l’efficacité et la célérité de leurs mesures provisoires et/ou conservatoires. La présente thèse s’attachera à démontrer, au travers de cette comparaison, que l’arbitrage est préférable au traitement du litige malgré l’absence de certaines prérogatives importantes qui aident les arbitres pour rendre leurs mesures provisoires et/ou conservatoires rapides et efficaces. In French and Kuwaiti national courts, the power of urgency exists regardless of the nature of the courts, civil or commercial. The power of urgency entitles to grant all provisional and precautional orders to address an emergency situation or to preserve the right of the parties without prejudice to the origin of the substantive right. However, in the case of an existence of an arbitration agreement, the judge does not have the right to grant these orders solely. In fact, the arbitrator appointed in the arbitration agreement also has the right to this privilege. In this regard, every French and Kuwaiti judge whether an arbitrator or a national judge has points of strength and weakness when granting these orders. On one hand, the French and Kuwaiti national judge has all the privileges that entitle them to grant provisional and precautional orders effectively and quickly. However, the nature of the procedures used to grant these orders can sometimes be stressful and exhausting to the parties involved in a way that affects the speed and effectiveness of these orders. On the other hand, the procedures followed before the arbitrators are easy, fast, and effective, but the arbitrators do not have the power to redress to ensure the execution of these orders, which affects the administration of justice. Therefore, the essence of this study lies in the comparison between the national judge and the arbitrator, French and Kuwaiti, in terms of the effectiveness and the speed of granting provisional and precautional orders. This study shows that arbitration is always preferred by disputants to obtain provisional and precautional orders more quickly and effectively than national courts.
Keywords: Arbitrage; Arbitral proceedings; Arbitration; Arbitrator; Arbitrator privileges; Arbitre; Astreintes; Célérité et efficacité des mesures provisoires et/ou conservatoires; Droits français et koweïtien; Imperium; Judicial expedited proceedings; Juge des référés; Mesures provisoires et/ou conservatoires; Pouvoir coercitif; Pouvoirs de l'arbitre; Pouvoirs du juge des référés; Référé arbitral et judiciaire; The French and Kuwaiti Laws; The power of redress; The provisional and precautional orders; The speed and effectiveness of provisional and precautional orders; Threatening fines; Urgent judge

La mise en question de l’arbitrage d’investissement et la réforme du règlement des différends entre investisseurs et États - Sucharitkul, Vanina (Université Paris 2, 2022)
Au cours des dernières décennies, le régime de règlement des différends entre investisseurs et États (« RDIE »), par le biais de l’arbitrage ad hoc, a été l’objet d’un examen approfondi et de critiques croissantes. Au fur et à mesure que les États défendeurs de diverses régions ont perdu des affaires d’arbitrage d’investissement, ils ont été comme désenchantés par ce type de mécanisme de résolution des litiges, dans ce qui est désormais connu comme le contrecoup de l’arbitrage d’investissement. Plus récemment, ces critiques se sont intensifiées au point que l’Union Européen a remplacé le RDIE contemporain par une cour permanente d’investissement pour régler ces différends. Une approche intermédiaire de la réforme du système par l’établissement d’un organe d’appel visant à donner de la cohérence aux nombreuses sentences arbitrales ad hoc est également envisagée. Cette thèse analyse les principales critiques du système du RDIE actuel afin d’examiner sa pertinence et effectue une comparaison entre les options de réforme, la manière dont elles sont censées résoudre les défauts du système, ainsi que les implications découlant de certaines des solutions les plus débattues. L’objectif de la thèse est de faire valoir qu’une refonte radicale ou révolutionnaire du système d’arbitrage des investissements ne fera que générer des incertitudes, susciter des problèmes juridiques et pratiques très complexes, et ne n’apportera finalement pas de meilleurs résultats. L’accent devrait plutôt être mis sur une indispensable évolution ou réforme substantielle au niveau des traités, afin de tirer les leçons des cas passés et de s’assurer que la rédaction des traités répond mieux aux défis actuels. = The dispute settlement regime between investors and States through ad hoc arbitration has come under heavy scrutiny and mounting criticism in the past few decades. As respondent States in various regions have lost investment arbitration cases, those States have become disenchanted with this form of dispute resolution mechanism in what has become known as the backlash against investment arbitration. More recently, these critiques have escalated to the extent that the European Union has replaced it with a completely new scheme that includes dismantling the investment arbitration system by replacing it with a permanent investment court to settle such disputes in its trade agreement. An intermediate approach to reforming the system, the establishment of an appellate body aimed at providing consistency to the numerous ad hoc arbitration awards, is also being considered. This thesis analyses the main criticisms of the current investor-State dispute settlement (“ISDS”) system to determine its validity and carries out a comparison between the policy reform options, how they are intended to solve the system’s purported flaws, as well as the implications arising from some of the hotly debated options. The aim of the thesis is to argue that drastic overhaul or revolutionary reform to the investment arbitration system will only lead to uncertainties, more complex legal and practical problems and would not yield better results. Instead, the focus should be on the evolution of substantive reform at the treaty level, to address the lessons learned from past cases and ensure that treaty drafting responds to current day challenges.
Keywords: Appellate Mechanism; Arbitrage; Arbitrage international; Arbitragem; Arbitration; Convention CIRDI; Cour Multilatérale d’Investissement; Droit et État; Groupe de travail III de la CNUDCI; ICSID Convention; INVESTMENTS; ISDS; ISDS Reform; Incohérence de sentences arbitrales; Inconsistent Arbitral Awards; Investissements étrangers (droit international); Investisseurs et État; Investment Court System; Investor-State Dispute Settlement; Multilateral Investment Court; Mécanisme d’appel; RDIE; Règlement des différends; Règles de transparence; Réforme du RDIE; Système de Cour d’Investissement; Transparency Rules; UNCITRAL Working Group III

La négociation dans le règlement des litiges internationaux d'investissement - Paredes Balladares, Francisco Xavier (Université Paris 1, 2022)
La négociation est une institution fascinante du droit de l’investissement, polyvalente et multifonctionnelle. L’étude systématisée de la négociation dans le droit de l’investissement fait ressortir que cette institution est plus qu’un simple moyen permettant de parvenir à des accords. En réalité, la négociation est partout dans le droit de l’investissement. Il s’agit de la seule institution véritablement transversale au droit des investissements, qui intervient de nombreuses manières dans les rapports entre les investisseurs et les États d’accueil. Nous pouvons attester de l’existence des négociations avec la négociation des accords internationaux d’investissement ou de contrats d’investissement entre l’État d’accueil et l’investisseur. De surcroît, la négociation est un instrument au service de l’instance juridictionnelle qui sert aux arbitres dans l’interprétation des accords ainsi que pour la détermination de la responsabilité des parties. Si les divers rôles de la négociation dans le droit de l’investissement ont fortement contribué à l’évolution du droit international, la négociation reste une institution peu connue. Sa nature, sa portée, et son contenu juridique restent peu étudiés et non systématisés dans le droit de l’investissement. De ce fait, cette recherche offre une analyse approfondie de la négociation afin de trouver sa place dans l’ordre juridique de l’investissement (en général) et dans le règlement des litiges (en particulier). Nous examinerons dans cette recherche les nombreux apports de la négociation au droit de l’investissement permettant d’affirmer que la négociation constitue le mécanisme essentiel dans la conclusion des accords ; qu’elle impose aux parties des comportements précis ; qu’elle est un instrument qui permet aux tribunaux internationaux de déterminer la responsabilité des parties en fonction de leurs actions et inactions ; enfin, qu'elle constitue un instrument qui aide la justice arbitrale à interpréter les accords ponctuels. Ainsi, cette recherche a pour ambition de comprendre la nature, la portée et les fonctionnalités de la négociation dans le règlement des litiges transnationaux d’investissement. Negotiation is a fascinating instrument of Investment Law, versatile and rich in legal content. The systematic study of negotiation in Investment Law reveals that this institution is much more than just an instrument for reaching agreements. In fact, negotiation is everywhere. It is the only institution of Investment Law that is truly transversal, intervening in many layers of the relationship between investors and Host States. We can recognize the existence of negotiations from the very beginning of an investment process (the negotiation of a contract between the investor and the Host State), as well as negotiations over the course of the life and operation of an investment, and negotiations at the termination of a transnational investment project. Moreover, negotiation is an instrument that serves arbitral tribunal as element for the interpretation of the agreements, and the determination of the parties’ liability. The various roles of negotiation in Investment Law have certainly contributed to the evolution of international law. Nevertheless, negotiation remains an unknown institution to lawyers, regarding its nature, scope, uses and legal content. Investment law requires a thorough analysis of this institution and a structure that adapts to the transnational legal order. In this research, we will examine numerous contributions of negotiation to Investment Law: as a necessary mechanism for the conclusion of agreements that impact Investment Law; as a mandatory rule that it imposes specific behaviors on the parties in respect to the principle of good faith; as an instrument that serves international tribunals to determine the parties’ liability for their actions taken over the course of negotiations, and as an instrument to assist the justice system to construe contracts. Thus, the ambition of this research is to comprehend the nature, scope, and the features of negotiation in International Investment Law. La negociación es un instrumento fascinante de Derecho de las inversiones, a la vez versátil y rico en contenido legal. El estudio sistematizado de la negociación en el Derecho de las inversiones revela que esta institución es mucho más que un instrumento para alcanzar acuerdos. En realidad, la negociación está en todas partes en el derecho de las inversiones. Es laúnica institución verdaderamente transversal al Derecho de las inversiones, que interviene de varias formas en la relación entre inversionistas y los Estados receptores de inversión. Podemos constatar la existencia de las negociaciones desde el inicio de un proceso de inversión (en la negociación de un tratado bilateral deinversión, o de un contrato entre el inversionista y el Estado anfitrión), negociaciones durante la vida y la operación de una inversión y negociaciones encaminadas a la terminación o liquidación de la inversión transnacional. Resalta, además, que la negociación es un instrumento al servicio de la instancia jurisdiccional, que sirve a los árbitros en su tarea de interpretación de acuerdos, y a la determinación de la responsabilidad de las partes. Los diversos roles que presenta la negociación en el Derecho de las inversiones ciertamente han contribuido a la evolución del Derecho internacional. Sin embargo, la negociación sigue siendo una institución poco conocida por los juristas, especialmente en lo tocante a su naturaleza, alcance, usos y contenido legal. ElDerecho de las inversiones requiere de un análisis exhaustivo de esta institución, acompañado de una estructura que se adapte al orden legal transnacional.En esta investigación examinaremos las diversas contribuciones que hace la negociación al Derecho de las inversiones, a saber: se muestra como un mecanismoinevitable para concluir acuerdos que terminan contribuir en la evolución del Derecho de las inversiones; impone a las partes comportamientos específicos enrespeto del principio de la buena fe; es un instrumento para que los tribunales internacionales determinen la responsabilidad de las partes en razón de sus accionesdurante la fase de negociación y se constituye en un instrumento que asiste al sistema de justicia en la tarea de interpretar los acuerdos. La ambición de esta investigación no es otra cosa que comprehender la naturaleza, el alcance y la funcionalidad de la negociación en el Derecho internacional de las inversiones.
Keywords: Accord; Arbitrage; Arbitrage d'investissement; Arbitration; Bonne foi; Buena fe; Contenido jurídico; Contract interpretation; Contrahendo; Contrato; Derecho Internacional Público; Derecho de las Inversiones; Droit de l’investissement; Droit international; Duty to negotiate; Estoppel; Good faith; Interpretación de acuerdos; Interprétation de l’accord; Investissements étrangers; Investment Law; Investments; Justicia; Negociación; Negotiando; Negotiation; Negotiation agreement; Négociation; Négociations; Obligación de negociar; Obligation de négocier; Pacto de negociación; Pactum; Período de negociación; Public International Law; Transnacional; Transnational

Visão Contemporânea da Jurisdição Arbitral - Bellocchi, Marcio (Universidade de São Paulo, 2022)
A questão fundamental que está por detrás da investigação feita para elaboração deste estudo consiste em saber se a arbitragem é jurisdição. A pesquisa foi conduzida de forma analítica de molde a que conclusões fossem alcançadas no sentido de se saber até que ponto a arbitragem é mesmo jurisdição. É claro que, para que isso fosse feito, isto é, para que esse caminho fosse percorrido, o primeiro tema a ser tratado deveria ser, necessariamente, a própria jurisdição. Trata-se de um conceito construído pela cultura humana cujo conteúdo, exatamente por isso, variou ao longo da história. Seguiu-se a mesma abordagem no que diz respeito à arbitragem. Assim, o primeiro objetivo desta tese foi o de acompanhar a evolução do conceito de jurisdição, ao longo do tempo, como forma de composição de conflitos, desde o direito romano, até a atualidade. Foi explorado o caminho pelo qual passou a jurisdição, com o fim de se investigar por qual motivo, em determinado momento, se começou a afirmar, de modo peremptório, que a jurisdição seria uma atividade realizada exclusivamente pelo Estado. O segundo objetivo consistiu em analisar a arbitragem, pondo-a lado a lado com a jurisdição estatal, explorando-se os pontos que ambos os fenômenos apresentam em comum, assim como os que diferenciam essas duas formas de exercício do poder-dever de julgar. Por isso, foi objeto de investigação e reflexão uma outra função da jurisdição estatal, recentemente assumida de forma clara pela jurisdição estatal, que é a de contribuir para a criação do direito. Procurou-se identificar em que contexto e extensão isso pode acontecer, tanto na jurisdição do Estado, quanto na jurisdição contratada pelas partes. Em um terceiro momento deste estudo, colocamos luzes sobre determinados institutos do processo civil, desenvolvendo-os, também, no terreno do procedimento arbitral. Num quarto e último momento, nossas reflexões se voltaram para o problema de se saber até que ponto a arbitragem seria mesmo jurisdição, equivalente à jurisdição estatal, em todos os seus aspectos, em toda a sua extensão, seus limites e suas funções. The fundamental question behind the research done to prepare this paper is whether arbitration is jurisdiction. The research has been conducted in an analytical manner so that conclusions could be reached in order to know to what extent arbitration is even jurisdiction. For this to be done, the first topic to be addressed should necessarily be jurisdiction itself. This is a concept constructed by human culture whose content, precisely for this reason, has varied throughout history. The same approach has been followed about arbitration. Thus, the first aim of this thesis was to follow the evolution of the concept of jurisdiction, over time, as a form of dispute resolution, since Roman law, until today. Jurisdiction has been explored, to investigate why, at a certain point, it began to affirm, peremptorily, that jurisdiction would be an activity performed exclusively by the State. The second aim was to analyze arbitration, placing it side by side with State jurisdiction, exploring points that both: state and arbitral jurisdiction have in common, as well as those that differentiate these two forms of judging. Therefore, another function, recently clearly assumed by the state jurisdiction, which is to contribute to the creation of law, has been object of investigation and reflection. It was sought to identify in what context and extent this can happen, both in the State and arbitral jurisdiction. In a third moment of this study, we shed light on certain institutes of civil procedure, developing them, also, in the field of arbitration procedure. In a fourth and last moment, our reflections turned to the problem of knowing to what extent arbitration would even be jurisdiction, equivalent to the State jurisdiction, considering all its aspects, its extent, limits and functions.
Keywords: Arbitrage; Arbitragem; Arbitration; Creation; Criação; Jurisdiction; Jurisdição; Procedure; Processo

Assessment Report of Arbitration Centre in Egypt (CRCICA) - SNFI (African Development Bank, 2022)

Arbitrage commercial international - Weiszberg, Guillaume (Arbitrage commercial international (seconde édition) (int), 2022)
La première version de cet article (datant de 2010), traitait largement de la jurisprudence et de la doctrine, parfois confidentielle, et le droit de l’arbitrage du commerce international (au moins dans sa conception et sa présentation françaises) était chaque jour davantage affiné , il complétait des formations internationales, les sources s’éclaircissaient, les commentaires foisonnaient et, aujourd’hui, nous vivons sans doute l’âge d’or de l’arbitrage commercial international[1]. Surtout, la première édition n’avait pu rendre compte de la réforme opérée peu après par ‘‘‘décret du 13 janvier 2011’‘‘. Un décret du Premier ministre français, autant dire tout de suite que le champ de l’étude présentée ici est à dominante principale franco-française, et que la principale préoccupation ici relèvera du ‘‘droit de l’arbitrage’’ dans une conception comparée, mais à partir du modèle français. Ainsi des réflexions seront menées dans le cadre du droit comparé et conventionnel international de ce type de résolution extra-judiciaire qu’est l’arbitrage commercial international, avec la présence à Paris de la Chambre de commerce internationale (CCI) et de sa Cour internationale d’arbitrage (CIA/CCI ci-après). La France est à l’avant-garde du sujet. Compte tenu de l’application de la loi dans le temps et pour une meilleure intelligibilité de la réforme, une réforme voulue par les acteurs et les juristes, ‘‘lato sensu’’, le droit antérieur à la réforme de 2011 est rappelé plus ou moins cursivement, qui montrera utilement les nombreux « progrès » de la discipline.

Role of Abuse of Rights Doctrine and Investment Arbitration Ratione Temporis in Limiting Nationality Planning - Saeedi, Niloofar; Askary, Pouria (Public Law Researsh, 2022)
Sometimes foreign investors after the dispute have arisen or when it is predictable and with the intention of bringing the dispute to arbitration, change their nationality or acquire new nationality. The phenomenon called Nationality Planning eases foreign investors’ access to a desirable treaty and increases the chance of bringing disputes against host states.So host states try to avoid these disputes by raising objections to Ratione Temporis or claiming abuse of rights. Arbitration tribunals’ approach towards their Ratione Temporis and abuse of rights is material in host states’ success in limiting Nationality Planning. So the question to be answered is that what requirements are considered by arbitrations in determining Ratione Temporis and abuse of rights and how these two are different. Arbitral precedent shows that these tribunals make distinction between cases of nationality planning contrary to their Ratione Temporis and cases that are considered as abuse of rights. However, in practice their strict approach results in limited acceptation of objections to Ratione Temporis or abuse of rights claims. گاه سرمایه‌گذار خارجی پس از بروز اختلاف یا زمانی که اختلاف قابل پیش‌بینی است و به قصد طرح دعوی در مرجع داوری، اقدام به تغییر تابعیت یا کسب تابعیت جدید می‌نماید. این اقدام که برنامه‌ریزی تابعیت نام دارد، دسترسی سرمایه‌گذار خارجی به یک معاهده سرمایه‌گذاری مطلوب را تسهیل کرده و احتمال طرح دعوی علیه دولت میزبان را افزایش می‌دهد. از این‌رو دولت‌های میزبان تلاش می‌کنند با طرح ایراد به صلاحیت زمانی یا سوء استفاده از حق، مانع پذیرش چنین دعوایی شوند. رویکرد مراجع داوری در احراز صلاحیت زمانی خود و تشخیص موارد سوء استفاده از حق، در موفقیت یا عدم موفقیت دولت میزبان در مقابله با برنامه‌ریزی تابعیت تعیین‌کننده است. بنابراین باید به این پرسش پرداخته شود که مراجع داوری چه شرایطی را برای احراز صلاحیت زمانی و سوء استفاده از حق در نظر می‌گیرند و چگونه میان این دو تمایز قائل می‌شوند. رویه مراجع داوری حاکی از آن است که این مراجع میان مواردی از برنامه‌ریزی تابعیت که مانع صلاحیت زمانی آن‌هاست و مواردی که سوء استفاده از حق تلقی می‌گردد، تمایز قائل می‌شوند. هرچند رویکرد سخت‌گیرانه آنها در عمل موجب می‌شود تنها در موارد محدودی ایراد به صلاحیت زمانی یا ادعای سوء استفاده از حق مورد پذیرش واقع شود.
Keywords: Abuse of rights; Bilateral Investment Treaty; Foreign Investment Arbitration; Nationality Planning; Ratione Temporis; برنامه‌ریزی تابعیت; داوری سرمایه‌گذاری خارجی; سوء استفاده از حق; صلاحیت زمانی; معاهده دوجانبه سرمایه‌گذاری

La notion de sentence arbitrale : étude de droit de l'arbitrage commercial - Merabti, Priscilla (Université Paris 1, 2022)
Qu’est-ce qu’une sentence arbitrale ? La sentence arbitrale est le résultat attendu par les parties qui se soumettent à une procédure arbitrale. Elle constitue le seul outil juridictionnel mis à la disposition de l’arbitre au cours d’un arbitrage. La sentence se voit revêtue d’un régime particulier, qui n’est pas ouvert aux autres types d’actes délivrés par l’arbitre, qui sont les ordonnances de procédures. La qualification en tant que sentence arbitrale d’une décision est donc une question primordiale, lorsqu’il est question d’arbitrage. La notion de sentence arbitrale n’est pas identique d’un droit à un autre et la définition française de la sentence arbitrale issue de l’arrêt Sardisud de la cour d’appel de Paris apporte son lot d’incertitudes en termes de qualification. En effet, la confrontation de cette définition à un certain nombre de cas d’objet d’étude suscite des interrogations. Ces interrogations poussent à l’analyse de chacun des critères permettant sa qualification, questionnant leur interprétation, mais aussi parfois leur nécessité. Certaines « zones grises » font naître des doutes de qualification de certaines décisions délivrées par l’arbitre en tant que sentence arbitrale : c’est le cas de la mesure provisoire, mais aussi de la sentence d’accord-parties. D’autres cas de figure posent des difficultés de qualification en deux temps, avec tout d’abord la question de la qualification de la procédure en tant qu’arbitrage et ensuite celle de la décision qui en découle en tant que sentence arbitrale. En effet, ces deux qualifications sont étroitement liées, d’une part puisque la sentence arbitrale ne peut exister sans arbitrage et d’autre part, car il existe une porosité des critères utilisés dans les définitions de l’arbitrage et de la sentence arbitrale. Ces difficultés de qualification en deux temps existent dans le cadre de la procédure d’arbitrage à deux degrés, la procédure devant un Dispute Adjudication Board en matière de construction, lors des procédures pré-arbitrales d’urgence, mais aussi lors d’une demande d’adaptation de contrat à un arbitre. L’étude de l’ensemble de ces cas de figure offre la possibilité de mettre à l’épreuve la définition actuelle de la sentence arbitrale, de souligner ses déficiences et de proposer une nouvelle approche de la notion de sentence arbitrale qui se décompose en deux propositions : d’une part, une interprétation plus élargie de certains critères utilisés dans la définition de la sentence arbitrale et d’autre part la disparition de certains critères qui apparaissent injustifiés.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; Arbitres (droit); Notion; Qualification; Sentence arbitrale

Effectiveness of the Recognition and Enforcement of the OHADA`S Arbitral Award - Juvelin, Rezara (International Journal of Social Science and Human Research, 2022)
OHADA is amongst an international organization consists of arbitral tribunal within regions in Africa to deal with international disputes on investment and commercial related. Henceforth, the purpose of the study examines the effectivity of arbitral awards enforcement under the perspectives of OHADA arbitration rules. The study axed through qualitative approach by interpreting legal rules, analyzing cases and commenting the weakness of the charter in terms of enforcement and recognition of arbitral awards. The decision of OHADA arbitral tribunal shall contain intrinsically legal effect to country members, however it leads problematics as the enforcement and recognition rules may be different in every country involved. Hence, the study interpreted the legal rules concerning enforcement and recognition of arbitral awards, effectiveness of the rules. In addition it exerted also the challenges and significant recommendation for improving the arbitration rules on enforcement of arbitral awards. It is found the weakness of the arbitral awards locates on refusal of concerned State to enforce the awards under the domestic law for undefinable conflict of interest
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Enforcement; OHADA; res judicata and exequatur

L’exécution des sentences arbitrales contre les personnes publiques de l’OHADA - Vodounon-Djegni, Comlan René (Université Côte d'Azur, 2022)
La thèse porte sur « L’exécution des sentences arbitrales contre les personnes publiques de l’OHADA ». Elle a pour but de démontrer comment mettre en œuvre ces sentences sans se heurter à l’immunité d’exécution des personnes qui en bénéficient. En effet, en l’absence d’une exception arbitrale, l’interdiction de l’exécution forcée et des mesures conservatoires à l’encontre de ces personnes semble s’étendre à l’exécution forcée des sentences arbitrales contre les personnes publiques de l’OHADA. Or, comme ces dernières, l’immunité d’exécution a également un fondement contractuel ; c’est une règle d’ordre public de protection à laquelle le bénéficiaire peut renoncer. Donc, son application ne serait requise que si son bénéficiaire n’y a pas renoncé. Mais, pour être valable, la renonciation à l’immunité d’exécution doit être expresse, au sens du droit international coutumier, dont fait partie la Convention des Nations Unies sur l’immunité juridictionnelle des Etats et de leurs biens du 2 décembre 2004, applicable en droit OHADA, pour raison de droit. Cette condition de validité de la renonciation pose le problème de l’efficacité des contrats soumis aux règles impératives du droit public ou des conventions et règlements d’arbitrage. Alors, faudrait-il envisager la réécriture des modèles habituels de conventions et règlements d’arbitrage pour y intégrer cette condition ? Cette approche garantirait l’effectivité des sentences arbitrales administratives, sur le fondement de la force obligatoire des contrats (Pacta sunt servenda) et de leur exécution de bonne foi. Aussi, pourrait-on renforcer cette renonciation par la mention de biens affectés à l’activité en cause ou à l’exécution de la sentence qui s’ensuivra sans lien avec l’activité qui y a donné lieu. En tout état de cause, l’immunité d’exécution ne s’oppose ni à l’identification des débiteurs des condamnations pécuniaires des personnes publiques, ni à l’exequatur des sentences arbitrales adm inistratives, ni même à l’exécution volontaire ou spontanée desdites sentences. Ainsi, en dépit de sa conception absolue ou stricte, l’immunité d’exécution de l’OHADA a des limites à l’égard des sentences arbitrales administratives.
Keywords: Administrative arbitration award; Arbitrage; Arbitrage (droit administratif); Arbitragem; Arbitration; Mandatory rules of public law; Organisation pour l'harmonisation en Afrique du droit des affaires; Personnes publiques; Renonciation à l’immunité d’exécution; Règles impératives du droit public; Sentence arbitrale administrative; Waiver of immunity from execution

L'attractivité de l'arbitrage au regard des nouvelles réformes de l'OHADA - Kounouho, Marcson Smile Geoffroy Tagnon (Université d'Abomey-Calavi, 2022)

Third Party Investment in International Commercial Arbitration - Ebrahimi, Seyed Sadegh; Boloori, Peyman; Solhchi, Mohammad Ali (Public Law Researsh, 2022)
International commercial arbitration imposes heavy costs to the parties involved. In this regard, one of the new phenomena in international commercial arbitration is "financing of court costs by a third party investor. There are several reasons for the emergence of a third party investor: 1- involved parties may not have the resources to pay for the costs of arbitration or they may be reluctant to use their funds to finance the litigation: 2. the uncertainty of receiving compensation as a result of paying the arbitration fees might encourage the parties to transfer this risk to a third party; 3. having its own advantages and disadvantages. Since the funder holds the power of the purse, TPF entails the risk of the control of the claim being transferred to the third party funder. We might ask whether international arbitration tribunals should examine the extent of the investor's influence in determining the allocation of costs or not. In addition, is it essential to disclose the third parties contracts confidential? Overall, it is concluded that those mentioned Tribunals should allocate and guarantee the arbitration cost and agree on disclosing of third parties fund contracts under urgent conditions by international arbitration tribunal. مراجعه به داوری تجاری بین المللی هزینه های کلانی را برای طرفین درگیر در فرآیند داوری به همراه دارد و تأمین این هزینه ها در خیلی از موارد به‌صورت مانع در مراجعه به داوری نمود پیدا می‌کند. در همین راستا یکی از پدیده‌های جدید در داوری تجاری بین المللی، «تأمین مالی هزینه دادرسی توسط سرمایه گذار ثالث» است. ظهور سرمایه گذار ثالث دلایل متعددی دارد؛ اولاً طرفین دعوی ممکن است فاقد امکانات مالی کافی برای هزینه های داوری باشند، ثانیاً ممکن است طرفین دعوی تمایلی به استفاده از منابع مالی خود برای تأمین مالی دادرسی پرهزینه نداشته باشند، ثالثاً عدم قطعیت ذاتی که در زمینه امکان اخذ خسارت در نتیجه دادرسی وجود دارد می تواند باعث تمایل طرف منازعه به انتقال این ریسک به شخص ثالث شود. پرسش این است که آیا محاکم تجاری بین‌المللی تعیین تخصیص هزینه‌ها بپردازد یا خیر؟ و آیا افشاسازی قراردادهای شخص ثالث ضروری می‌باشد؟ در نهایت این نتیجه حاص می‌شود که محاکم مذکور باید به تعیین تخصیص و تضمین هزینه‌های داوری پرداخته و از سویی با افشاسازی قراردادهای تامین مالی شخص ثالث در داوری تجاری بین المللی، در شرایط خاص و ضروری موافقت نمایند.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Cost Allocation; Disclosure; International Arbitration Tribunals; International commercial arbitration; Investments; Third Party Investment; Third parties; افشاسازی; تخصیص هزینه‌ها; داوری تجاری بین‌المللی; دیوان‌های داوری بین‌المللی; سرمایه‌گذاری شخص ثالث

A Legal Analysis of the Structure of Dispute Resolution Mechanisms of International Tax Agreements - Salehifar, Alireza (Public Law Researsh, 2022)
As international trade is expanding, international trade and tax disputes are increasing. Under international tax agreements, there are two mechanisms for the resolution of potential disputes between contracting States. These agreements mostly rely on a form of negotiation known as the “Mutual Agreement Process (MAP)” as the main mechanism for the settlement of disputes. During the last decade, the inclusion of “ad hoc arbitration” as a new dispute resolution mechanism in international tax treaties has become popular to augment the MAP. Iran has long concluded several international tax agreements with several countries for the avoidance of double taxation. Due to Iran’s macroeconomic policy for relying more on tax revenues as an alternative to revenues from the petroleum industry, it is important that the Iranian lawyers seek to focus more on tax law and tax dispute resolution mechanisms. The purpose of this article is to introduce and critically analyse the dispute resolution mechanisms of international tax agreements. In this article, to make some suggestions for the improvement of the dispute resolution system of tax treaties, the strengths and weaknesses of the MAP and ad hoc arbitration, will be scrutinised by adopting a descriptive-analytical approach. همسو با گسترش تجارت فراسرزمینی،‌ میزان دعاوی مرتبط با تجارت و مالیات‌های بین‌المللی نیز افزایش یافته است. در بسیاری از معاهده‌های مالیاتی بین‌المللی برای حل اختلافات، دو ساز و کار با عنوان «فرآیند توافق دوجانبه» و «داوری موردی» وجود دارد. فرآیند توافق دوجانبه که مبتنی بر مذاکره بین طرفین معاهده است بعنوان ساز و کار اصلی و داوری موردی هم که در یک دهه اخیر در این معاهده‌ها رواج یافته، بعنوان ساز و کار مکمل فرآیند توافق دوجانبه برای حل اختلافات استفاده می‌شوند. ایران از دیرباز جهت اجتناب از مالیات مضاعف، معاهده‌های مالیاتی متعددی را با کشورهای مختلف منعقد نموده است. همچنین سیاست کلان اقتصادی کشور در سال‌های اخیر مبتنی بر اتکای بیشتر به درآمدهای مالیاتی بعنوان جایگزینی برای درآمدهای نفتی بوده است. لذا اهمیت شناخت این نوع معاهده‌ها و‌ مکانیسم‌های حل و فصل اختلافات آنها برای حقوقدانان کشور بیش از پیش آشکار می‌شود. هدف این مقاله معرفی،‌ تحلیل و نقد ساز و کارهای موجود در معاهده‌های مالیاتی بین‌المللی برای حل اختلافات می‌باشد. در این مقاله نقاط ضعف و قوت فرآیند توافق دوجانبه و داوری موردی به شیوه توصیفی-تحلیلی بیان و راهکارهایی جهت بهبود این مکانیسم‌ها ارائه می‌شود.
Keywords: Arbitrage; Arbitragem; Arbitration; Dispute Resolution; International Tax Agreements; Mutual Agreement Procedure (MAP); Negotiation; داوری; فرآیند توافق دوجانبه; مذاکره; معاهده مالیاتی بین‌المللی; ‌ حل و فصل اختلاف

The Singapore Convention on Mediation: a commentary - Alexander, Nadja; Chong, Shouyu; Giorgadze, Vakhtang (Kluwer Law International, 2022)
Article-by-article commentary
Keywords: Dispute Settlement; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements resulting from Mediation (2018)

İslam borçlar hukuku açısından ticari ihtilafların çözümünde 'Arabuluculuk' - Almasri, Raed (Ankara Üniversitesi, 2022)
Bu tez, anlaşmazlıkları çözmede arabuluculuk konusunu ele almaktadır. Arabuluculuk konusu ticari mali muamelelerdeki anlaşmazlıklar ile sınırlıdır. Dolayısıyla tez ailevi anlaşmazlıklardaki nafaka gibi diğer mali anlaşmazlıklara değinmemektedir. Tez konusu fıkhi açıdan ele alındığı için, dört fıkhi mezhebin konuyla ilgili görüşleri, mukayeseli olarak işlenmiş, mezhepler arasında ihtilaf ve ittifak edilen noktalar ele alınmış ve görüşler arasında tercih yapılarak ortaya konulmuştur. Tez; bir mukaddime, üç bölüm, bir sonuç ve kaynakçadan meydana gelmektedir. Mukaddime de tezin planı, fihrist ve içerik ele alınmıştır. Tezin birinci bölümünde; arabuluculuk kavramının tanımı ve meşruiyeti, ikinci bölümde; arabuluculuğun rükünleri ve arabuluculukla ilgili hükümler ve şartlar, üçüncü bölümde ise; arabuluculuğun sonuçları ve etkisi ele alınmıştır. The dissertation aims to cover the subject of mediation in dispute resolutions exclusively in commercial disputes. Therefore, the research does not cover mediation in other disputes such as domestic disputes even when it's related to financial matters such as alimony. The research also studies mediation in commercial disputes from a jurisprudential perspective. Hence the jurists' opinions are presented and analyzed in a comparative approach to show its similarities, differences and present a jurisprudential preference. The dissertation is presented in an introduction, three chapters, a conclusion followed by the list of references and resources. The introduction provides an insight into the research contents and methodology. The first chapter discuss the definition of mediations and its legitimacy. The second chapter tackle the main pillars of mediations and clarify its ruling and conditions. Finally, the third chapter view the results of mediations and its expected impacts.
Keywords: Arabuluculuk; Borçlar hukuku; Commercial disputes; Incompatibility; Islamic law; Law of obligations; Mediation; Ticari uyuşmazlıklar; Uyuşmazlık; İslam hukuku

Dissenting opinions in international arbitration : More than an opinion? - Baltag, Crina (Principia, 2022)
Dissenting opinions have increasingly gained acceptance in international arbitration, with arbitration rules and laws allowing them, by either providing directly for such a possibility, or indirectly, by referring to ‘arbitral awards taken with majority of votes.’ Alan Redfern’s seminal 2003 Freshfields Lecture on dissenting opinions has highlighted the benefits, as well as the concerns with dissenting opinions, in particular, with those directed to alleged irregularities in the arbitral procedure. More recently, in the motion to set aside the arbitral award in Vantage Deep Water Co. v. Petrobras Am., Inc., the US District Court for the Southern District of Texas has rejected Petrobras’ argument that ‘the arbitral process was [so] “fundamentally flawed” … that “produced the extraordinary Dissent filed” by Mr Gaitis.’ While it is accepted that dissenting opinions have no legal effects, and in particular no legal effects similar to arbitral awards, they can have significant impact on the set aside and recognition and enforcement of arbitral awards. Las opiniones disidentes han ganado aceptación en el arbitraje internacional mediante reglas de arbitraje y leyes permitiéndolos, ya sea aceptando directamente la posibilidad de emitirlos, o indirectamente refiriéndose a ‘laudos arbitrales decididos por mayoría de votos’. El seminario del 2003 de Freshfields dictado por Alan Redfern sobre opiniones disidentes llamó la atención sobre los beneficios y las preocupaciones, en particular, aquellas opiniones disidentes dirigidas a señalar irregularidades en el procedimiento arbitral. Más recientemente, durante el procedimiento para anular el laudo arbitral de Vantage Deep Water Co. v. Petrobas Am., Inc., la Corte del Distrito Sur de Texas rechazó el argumento de Petrobras de que ‘el procedimiento arbitral había sido [tan] “fudamentalmente viciado…” que “produjo la extraordinaria opinión disidente consignada” por el Sr., Gaitis’. Mientras que es aceptado que las opiniones disidentes no tienen efectos legales, y en particular ningún efecto legal parecido a los laudos arbitrales, pueden lograr impactar significativamente a lograr la nulidad y el reconocimiento y ejecución de los laudos arbitrales.
Keywords: Anulación; Arbitral Awards; Dissenting opinions; Laudo arbitral; Recognition and enforcement; Reconocimiento y ejecución; Set aside; Voto salvado

Règlements d’Arbitrage en vigueur à compter du 1er janvier 2021 et de Médiation en vigueur à compter du 1er janvier 2014 - Chambre de commerce internationale (ICC Publication DRS, 2022)
Keywords: Arbitrage; Arbitragem; Arbitration; MARD; Mediación; Mediation; Mediação; Médiation; Règlement d'arbitrage; Règlement de médiation

COFOLA International 2022: Current Challenges of Resolution of International (Cross-Border) Disputes (Publications of the Masaryk University, theoretical series, editions Scientia, 2022)
- Bridging the Public-Private Law Divide in the Conflict of Laws; - New Practices in Alternative Dispute Resolution: New Pathways to Peace; - The Singapore Convention: A Giant Leap for Mediation or Just Too Good to Be True; - Potential Nexus Between the Enforceability of Foreign Judgments and the Quality of Civil Justice in ASEAN Did the Preliminary Objections Judgment Resolve the Chagos Archipelago Sovereignty Dispute? - The Order of Periodic Penalty Payments by the CJEU in Cases Filed by a State Against Another State; - The Dichotomy of Obligations of Conduct and Result in International Investment Law; - Investment Arbitration Reform: Third-Party Funding in Investment Arbitration; - Between Protection and Access to Justice: On the Regulation of Returns in Third-Party Litigation Funding; - Contract Adjustment in Arbitration : Should the Approach Be Adjusted? - Current Challenges of Enforcing Annulled Arbitral Awards; - Condifentiality of Arbitral Awards on National, International and Institutional Level; - Digitalisation of Judicial Cooperation in the EU: A Long Road Ahead; - Resolving Cross-Border Consumer Disputes: The Digital Experience in China; - Law Applicable to Non-Consumer Contracts Concluded at an Electronic Auction; - Can Robot Judges Solve the So-Called “Hard Cases”? - Current Challenges of Cross-Border Disputes in Slovakia : Is Slovak Law Anchored in the 21st century

Arbitration Rules In force as from 1 January 2021 and Mediation Rules In force as from 1 January 2014 - International Chamber of Commerce (ICC Publication DRS, 2022)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration rules; MARD; Mediación; Mediation; Mediation rules; Mediação; Médiation

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

Los medios jurisdiccionales de solución de las controversias internacionales : avances y nuevos retos - Petrova Georgieva, Virdzhiniya (Doctrina Jurídica, 2022)

A Closer Look at the Doctrine of Separability in Arbitration - Todorović, Ilijana (IUS LAW Journal, 2022)
In the ever-growing business world impacted by globalization, many commercial contracts nowadays contain an arbitration clause. This article focuses on the history behind arbitration as an alternative method of dispute resolution and its penetration to the forefront of mechanisms for resolving commercial disputes -with focus on England, France, and the United States. The article also delves into some of the key questions related to the relationship between an arbitration clause and the underlying contract in which it is contained. And those are the infamous separability and competence-competence doctrines. The author’s conclusion is that the efficiency of an arbitration clause is feasible only if its autonomy is entrenched and safeguarded from preventative and baseless court intervention. In that regard, the author addresses the consequences, current challenges, judicial and academic discourse, and the need for improvement when it comes to these two arbitral principles -all with the goal to provide contracting parties with forethought as to what to consider when drafting their contracts as to avoid unwelcome consequences.
Keywords: Arbitrage; Arbitragem; Arbitration; Competence-Competence; Doctrine; International Arbitration; Issues of Jurisdiction

الحق المعنوي للفنان العازف أو المؤدي في قانون الملكية الأدبية والفنية - دراسة مقارنة - - بعديد, دلال (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
يعتبر الفنان العازف أو المؤدي، الطائفة الوحيدة من أصحاب الحقوق المجاورة التي تتمتع بحقوق معنوية ومالية على أعماله. فالطابع الإبداعي الذي يكتسيه أداؤه يبرز شخصيته الأدبية والفنية، على خلاف أعمال أصحاب الحقوق المجاورة التي تتسم بالطابع الصناعي اولمادي. يتضمن الحق المعنوي جملة من الصلاحيات تمكن الفنان من الاستفادة من أعماله وحمايتها من مختلف أنواع الاعتداء. غير أنها وإن كانت تتشابه في البعض منها مع الحقوق المخولة للمؤلف لحماية مصنفات ه وشخصه، إلا أنها تختلف معها في البعض منها لاسيما الحق في تقرير النشر، والحق في السحب أو الندم، باعتبار أن التشريعات الوطنية الخاصة بالحقوق المجاورة والتي اعترف ت للفنان التمتّع بحق معنوي ، جاءت خالية من الإشارة إلى ذلك. لذا كان من الضروري تحديد مدى تمتع الفنان العازف بهذين الحقين، أمام الف ا رغ القانوني الذي أدى إلى مجادلات فقهية وتضا رب في الأحكام القضائية. L'artiste interprète ou exécutant est le seul des titulaires de droits voisins à bénéficier d’un droit moral et d’un droit patrimonial sur son interprétation. Le caractère original de sa prestation met en valeur sa personnalité littéraire et artistique, à l’inverse des oeuvres des titulaires de droits voisins qui se caractérisent par leur aspect industriel et matériel. Le droit moral dont dispose l'artiste-interprète, comprend un ensemble de prérogatives qui lui permettent de bénéficier de ses oeuvres et de les protéger contre les divers abus. Cependant, et bien qu’elles soient similaires, pour certaines d’entre elles, aux droits octroyés à l’auteur pour protéger son oeuvre et sa personne, elles se différencient de certains d’entre eux, en particulier le droit de divulgation et le droit de retrait ou de repentir, du fait que les législations nationales relatives aux droits voisins qui reconnaissent à l'artiste la jouissance d’un droit moral, sont dépourvues de toute référence à ce sujet. Dès lors, il était nécessaire de déterminer dans quelle mesure l'artiste-interprète jouit de ses deux droits, face au vide juridique qui a donné lieu à des controverses doctrinales et à des décisions de justice contradictoires. The artist, musician or performer, is the only one of the holders of related rights to benefit from a moral right and financial rights over his performance. The original character of his performance highlights his literary and artistic personality, unlike the works of holders of neighboring rights which are characterized by their industrial and material aspect. The moral rights available to the performer include a set of prerogatives that allow them to benefit from their works and protect them against various abuses. However, and although they are similar, for some of them, to the rights granted to the author to protect his work and his person, they are different from some of them, in particular the right of disclosure and the right of withdrawal or of repentance, due to the fact that national laws relating to neighboring rights which recognize the artist's enjoyment of a moral right, are devoid of any reference to this subject, Therefore, it was necessary to determine to what extent the performer enjoys both rights, in the face of the legal vacuum which has given rise to doctrinal controversies and contradictory court decisions.
Keywords: Arbitrage; Arbitration; Artist interpréter; Artist performer; Artiste exécutant; Artiste interprète; Contrefaçon; Counterfeiting; Droit moral; Intellectual property; International protection; Moral right; National protection; Piracy; Piratage; Propriedade intelectual; Propriété intellectuelle; Protection internationale; Protection nationale; Responsabilité; Responsibility

ال رقابة القضائية على أحكام ال ت حكيم دراسة مقارنة في القوانين العربية - زريفي, محمد (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
إن كان التحكيم طريقا بديلا للقضاء في حسم المنازعات، فإن عملية التحكيم تحتاج لكي تكتمل أسباب فاعليتها وانفاذ أحكامها لتدخل قضاء الدولة باعتباره سلطة عامة، تملك قوة إل ا زم الخصوم بتنفيذ أحكام المحكمين. ومن باب المفارقة، أن هذه الرقابة القضائية على أحكام التحكيم، تؤدي إلى إقحام القاضي الوطني في ن ا زع، أستبعد منه مسبقا بإ ا ردة المتنازعين، إلا أن المفارقة ظاهرية، حيث أن دور القاضي يبقى منحص ا ر في رقابة مدى مطابقة الحكم التحكيميي لمبادئ أساسية، أتت على سبيل الحصر، دون أن يكون له فحص وقائع وموضوع الن ا زع. غير أن تحديد سلطة القاضي لي س مطلقة، فبناء على المقاربة الجديدة المبنية على نوع المصالح المطلوب حمايتها، كمعيار لتحديد درجة وشدة الرقابة المسلطة على حكم لتحكيم، يستطيع هذا الأخير، تعديل رقابته بين مشددة ومخففة . وعلى هذا الأساس، فإن غالبية القضاءات العربية تبنت موقفا وسطيا بين مذهبي التوسع والتضييق من نطاق رقابة المحاكم على حكم التحكيم الدولي، تماشيا مع متطلبات التجارة الدولية ومقتضيات مصالحها الوطنية . If arbitration is an alternative means of resolving disputes, the arbitration process needs, for the reasons of its effectiveness and the application of its provisions, the intervention of the judicial power of the State, in order to oblige the parties to carry out the arbitral awards. Paradoxically, this judicial review of arbitral awards leads to involving the national judge in a dispute, which was previously excluded by the will of the parties in dispute. However, this paradox is apparent, because the role of the national judge remains limited to the strict control of the compliance of the arbitration award with the basic principles enacted in an exclusive manner, without having to examine the facts and the subject of the dispute. However, this limitation of judicial power is not absolute, because on the basis of the new approach, based on the type of interests to be protected, as the criterion for determining the extent of the control exercised over an arbitral award, the latter can modulate its control between strict and attenuating. On this basis, the majority of Arab jurisdictions have adopted a middle position between the two tendencies, so-called maximalist control, and minimalist tendency of the jurisdictions' control over the international arbitration award, in accordance with the needs of international trade and the requirements of their interests. Si l'arbitrage est un moyen alternatif pour de résoudre les différends, le processus d'arbitrage a besoin, pour les raisons de son efficacité et l'application de ses dispositions de l'intervention du pouvoir judiciaire de l'État, afin d'obliger les parties d'exécuter les sentences arbitrales. Paradoxalement, ce contrôle judiciaire sur les sentences arbitrales conduit à impliquer le juge national dans un litige, qui en était auparavant exclu par la volonté des parties en litige. Toutefois, ce paradoxe est apparent, car le rôle du juge national reste limité au strict contrôle de la conformité la sentence arbitrale aux principes de base édicté d’une manière exclusive, sans avoir à examiner les faits et l'objet du litige. Cependant, cette limitation de pouvoir juge n'est pas absolue, car sur la base de la nouvelle approche, fondée sur le type d'intérêts à protéger, comme critère de détermination de l'étendue du contrôle exercé sur une sentence arbitrale, ce dernier peut moduler son contrôle entre strict et atténuant. Sur cette base, la majorité des juridictions arabes ont adopté une position médiane entre les deux tendances, contrôle dite maximaliste, et tendance minimaliste du contrôle des juridictions sur la sentence d'arbitrage international, conformément aux besoins du commerce international et aux exigences de leurs intérêts.
Keywords: Arbitrage international; Arbitration; Commerce international; Contrôle des juridictions; International Trade; International arbitration award; Sentence arbitrale

L'intervention du juge étatique dans l'arbitrage : une approche de droit comparé - Ranjbari, Hiva (Université Paris Cité, 2021)
Aujourd'hui, l'arbitrage s'impose comme un mode indépendant de règlement des litiges. Même si l'arbitrage implique, par définition, l'exclusion de la compétence juridictionnelle des tribunaux étatiques, un lien existe entre la justice arbitrale et la justice étatique. Cette étude concerne l'intervention du juge étatique dans l'arbitrage international. Elle a été menée à partir des systèmes français, anglais et suisse. L'intervention du juge étatique dans l'arbitrage, obéit à deux principes directeurs : l'efficacité de l'arbitrage en tant qu'un mode définitif de règlement des litiges ; et le respect des droits fondamentaux et de l'ordre public international. En premier lieu, le juge peut être appelé à intervenir en soutien de l'arbitrage, complétant la compétence de l'arbitre pour des questions qui excèdent ses pouvoirs, avant et pendant la procédure arbitrale. En second lieu, il peut intervenir pour contrôler la sentence rendue. Avant le prononcé de la sentence, l'efficacité de l'arbitrage suppose l'appui du juge étatique dans certaines situations comme le commencement de la procédure arbitrale, la désignation des arbitres, ou le prononcé des mesures provisoires et conservatoires. Le juge apporte son soutien à l'arbitrage pour assurer le bon déroulement de la procédure. Après le prononcé de la sentence, l'intervention du juge prend la forme d'un contrôle judiciaire, l'idée directrice est d'assurer la protection des droits des parties et de l'ordre public international. Aujourd'hui, l'arbitrage s'impose comme un mode indépendant de règlement des litiges. Même si l'arbitrage implique, par définition, l'exclusion de la compétence juridictionnelle des tribunaux étatiques, un lien existe entre la justice arbitrale et la justice étatique. Cette étude concerne l'intervention du juge étatique dans l'arbitrage international. Elle a été menée à partir des systèmes français, anglais et suisse. L'intervention du juge étatique dans l'arbitrage, obéit à deux principes directeurs : l'efficacité de l'arbitrage en tant qu'un mode définitif de règlement des litiges ; et le respect des droits fondamentaux et de l'ordre public international. En premier lieu, le juge peut être appelé à intervenir en soutien de l'arbitrage, complétant la compétence de l'arbitre pour des questions qui excèdent ses pouvoirs, avant et pendant la procédure arbitrale. En second lieu, il peut intervenir pour contrôler la sentence rendue. Avant le prononcé de la sentence, l'efficacité de l'arbitrage suppose l'appui du juge étatique dans certaines situations comme le commencement de la procédure arbitrale, la désignation des arbitres, ou le prononcé des mesures provisoires et conservatoires. Le juge apporte son soutien à l'arbitrage pour assurer le bon déroulement de la procédure. Après le prononcé de la sentence, l'intervention du juge prend la forme d'un contrôle judiciaire, l'idée directrice est d'assurer la protection des droits des parties et de l'ordre public international.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitraje; Arbitral proceedings; Arbitral tribunal; Arbitration; Dispute settlement; Interim measures; International Arbitration; Mesures provisoires; Ordre public; Procédure arbitrale; Public policy; Sentence arbitrale; Tribunal arbitral

Les compétences exclusives en matière civile et commerciale : étude de droit international privé - Georgakoudi, Nikoleta (Université Paris 1, 2021)
La consécration des règles de compétence exclusive en matière civile et commerciale est largement admise en droit international privé comparé. Elles sont généralement présentées comme étant fondées sur l’implication de la souveraineté de l’État, soit parce que son territoire est physiquement en cause soit parce que le litige concerne le fonctionnement des services publics de l’État. À ces arguments juridiques, s’ajoute une série de considérations pratiques, comme la coïncidence nécessaire entre le forum et le jus. Toutefois, les arguments avancés, afin d’expliquer l’édiction de ces règles de compétence, sont-ils véritablement convaincants, surtout si on se place dans un espace judiciaire fortement intégré, fondé sur la confiance mutuelle et la coopération, comme celui de l’Union européenne ? Le caractère raisonnable des fors exclusifs est, en effet, critiqué dans certains domaines visés, puisque la prépondérance de l’élément étatique dans une matière ne requiert pas l’adoption d’une compétence exclusive. Les règles de compétence exclusive peuvent, par ailleurs, susciter des problèmes pratiques lors de leur mise en œuvre et on assiste à une profonde mutation, au niveau européen, du for exclusif prévu en matière de propriété intellectuelle. Dans ces conditions, il convient de s’interroger sur l’avenir et même la pertinence de la survivance de ces règles. Un système alternatif d’organisation des compétences, fondé sur la coopération et le dialogue fluide entre les juges, est envisageable, dans l’espace judiciaire européen, permettant d’échapper à l’exclusivité de la compétence juridictionnelle dans certaines matières visées. The establishment of exclusive jurisdiction rules in civil and commercial matters is widely accepted in comparative private international law. These rules are generally presented as being based on the implication of State sovereignty, either because its territory is physically involved or because the dispute concerns the functioning of the State public services. In addition to these legal arguments there is a series of practical considerations that support the justification of the court’s exclusive jurisdiction, such as the necessary coincidence between the forum and the jus. However, an open question is whether the arguments, put forward to explain the adoption of these rules of jurisdiction, are really convincing, especially in a highly integrated judicial area, based on mutual trust and cooperation, such as the European Union. The rationality of exclusive fora is indeed criticized in some of the concerned areas, since the preponderance of the state element in a matter does not require the adoption of an exclusive jurisdiction rule. Moreover, the rules on exclusive jurisdiction may give rise to practical problems when implemented, and we are witnessing a profound change, at European level, of the exclusive forum provided in intellectual property matters. Under these conditions, it is appropriate to question the future and even the relevance of the survival of these rules. An alternative system of jurisdiction, based on cooperation and fluid dialogue between judges, is conceivable in the European judicial area, making it possible to avoid the court’s exclusive jurisdiction in certain targeted matters.
Keywords: Arbitrage commercial international; Arbitrage international; Civil Procedure; Compétence exclusive en raison de la matière; Conflict of jurisdictions; Conflit de juridictions; Droit international privé; European Union law; European federalism; Exclusive subject matter jurisdiction; Fédéralisme européen; Hague Convention system; International Arbitration; Mechanisms of inter-jurisdictional cooperation; Mécanismes de coopération interjuridictionnelle; Principe de souveraineté; Principle of sovereignty; Private international law; Procédure civile; Procédure civile (droit européen); Système des conventions de La Haye; Union européenne (droit)

L'obligation de règlement des différends à la charge des organisations internationales - Weil, Elodie (CY Cergy Paris Université, 2021)
Le travail de recherche porte sur les modes et modalités de règlement des différends qui mettent en cause directement une organisation internationale. En fait très peu de mécanismes de règlement des différends sont prévus ou existent pour engager la responsabilité d'une organisation internationale ou mettre en cause la légalité de l'un de ses actes. C'est vrai qu'aujourd'hui il y a une prise de conscience sur la nécessité d'organiser le règlement des différends avec le nombre croissant des organisations internationales et des litiges. Si les mécanismes se développent ils restent encore à un stade sporadique à tel point que certains considèrent que les organisations internationales agissent en toute impunité. La question est alors de savoir si elles sont liées par une obligation de prévoir un mode de règlement des différends. Il n'existe pas réellement d'obligation générale de règlement des différends à la charge de l'organisation internationale les opposant à d'autres sujets de droit international. S'agissant des différends avec des personnes privées, la multiplication des clauses de règlement des différends dans les accords de siège ou protocole sur les immunités incitent à y voir l'émergence d'une norme coutumière à la charge des organisations internationales. Ce sentiment est d'autant plus grand que l'interdiction du déni de justice incite à ce que ce mode de règlement soit au surplus entouré de principes propres au règlement juridictionnel. Sans que l'obligation de règlement des différends ne se limite au règlement juridictionnel, il y a néanmoins un développement de la part des juges nationaux à sanctionner l'organisation internationale qui ne prévoit pas de mode de règlement alternatif en mettant à l'écart l'immunité de juridiction. The means and methods for resolving disputes involving international organizationsThe research focuses on the means and methods of dispute settlement which directly involve an international organization. In fact very little dispute settlement mechanisms exist to engage the responsibility of an international organization. Howether today there is an awareness of the need to organize the settlement of disputes with the increasing number of international organizations and litigation. The obstacles to the settlements of disputes are so huge that some consider that international organizations act with impunity. The question is whether international organizations are bound by an obligation to provide for dispute settlements mechanisms. The answer is probably negative when the dispute arises between an international organization and another subject of international law. The settlement of disputes is governed by sovereignty : that means subjects of International Law have to consent to the jurisdiction of a mechanism. The problems known for States are the same for international organizations, eventhough the laters don’t have any sovereignty. As far as disputes with private individuals are concerned, the proliferation of dispute settlement clauses in headquarters agreements or protocol on immunities encourage the emergence of a customary norm in charge of international organizations. This feeling is even greater than the prohibition of denial of justice urges that this settlement is in addition surrounded by principles specific to jurisdictional settlement. Enventhough the obligation is not limited to the jurisdictional settlement, there is a development from national judges to penalize the international organization which does not provide for alternative method, by waiving their immunity.
Keywords: Dispute resolution; Immunity; Immunités; International Organizations' Liability; International organizations; Organisations internationales; Responsabilité des organisations internationales; Règlement des différends

La responsabilité civile de l'arbitre - Moreau-Cucchi, Matthieu (Université Paris-Saclay, 2021)
L’arbitrage est une institution hybride qui mêle des aspects contractuels et juridictionnels. En effet, l’arbitre est contractuellement investi d’une mission juridictionnelle consistant à trancher un litige. Or, cette hybridité ne rejaillit aujourd’hui que partiellement sur la responsabilité de l’arbitre : la responsabilité qu’il engage dans l’exercice de ses fonctions est pleinement contractuelle, mais la faute génératrice de responsabilité est définie différemment selon que le manquement se rattache ou non à la mission de juger.La présente thèse propose de tirer toutes les conséquences de la nature duale de l’arbitrage sur la responsabilité de l’arbitre. Ainsi, seuls les manquements commis par l’arbitre en sa qualité de contractant devraient être de nature à engager sa responsabilité contractuelle. Les fautes commises dans l’exercice de sa fonction juridictionnelle, en revanche, devraient conduire à l’engagement d’une responsabilité délictuelle. Pour faire le départ entre ces différents manquements, il est proposé de classer les obligations l’arbitre en distinguant celles qui sont contractuelles de celles qui sont juridictionnelles. Le critère retenu pour procéder à cette classification tient dans la comparaison entre l’arbitre et le juge étatique. Sous réserve de quelques ajustements, les obligations qui pèsent à la fois sur le juge et sur l’arbitre seront qualifiées de juridictionnelles ; celles qui ne pèsent que sur l’arbitre seront qualifiées de contractuelles.Une fois identifié le régime applicable à la responsabilité arbitrale, il reste à dérouler les conditions de sa mise en œuvre. Cela passe, d’une part, par l’identification des règles de droit international privé applicables dans les cas où le litige portant sur responsabilité de l’arbitre présente un élément d’extranéité. Dans ces hypothèses, il conviendrait de retenir des critères identiques de désignation du juge compétent et de la loi applicable : à titre principal, c’est la volonté des parties qui doit prévaloir ; à titre supplétif, le lieu du siège de l’arbitrage paraît être le critère le plus adapté pour régir la compétence du juge et la loi applicable en matière de responsabilité arbitrale.La mise en œuvre de la responsabilité de l’arbitre passe, d’autre part, par une application des conditions d’engagement de la responsabilité prévues en droit français interne. A cet égard, les conditions de droit commun tenant au fait générateur de responsabilité paraissent devoir être repensées pour pouvoir s’adapter à la question de la responsabilité arbitrale. Ainsi, s’agissant de la responsabilité délictuelle qu’encourt l’arbitre en cas de faute juridictionnelle, le fait générateur pourrait être repensé autour de la notion de faute lourde juridictionnelle. Celle-ci serait définie comme un manquement de l’arbitre à ses obligations juridictionnelles essentielles, lequel suppose un défaut d’impartialité ou d’indépendance auquel s’ajoute la violation d’une autre obligation juridictionnelle. S’agissant de la responsabilité contractuelle qu’encourt l’arbitre en cas de faute contractuelle, la thèse propose d’identifier, pour chaque obligation contractuelle, le comportement qui peut être attendu de l’arbitre et, en miroir, celui qui pourrait être considéré comme un manquement. Sur cette question, en effet, la distinction classique entre les obligations de moyens et de résultat n’est d’aucun secours pour identifier les manquements générateurs de responsabilité.S’agissant ensuite de la question du dommage et du lien de causalité, les règles qui les entourent dans le droit commun de la responsabilité paraissent adaptées à la responsabilité arbitrale. Elles devraient donc pouvoir être mobilisées en l’état, sous réserve de préciser les types de dommages réparables, notamment en termes de perte de chance, et de trancher en faveur de la théorie de l’équivalence des conditions pour apprécier le lien de causalité, tant en matière contractuelle que délictuelle. Arbitration is a hybrid institution in which contractual and jurisdictional aspects are mixed. As a matter of fact, an arbitrator is invested by a contract with the mission to settle a dispute. And yet, this hybridity does only partially reflect on arbitral liability. The arbitrator’s liability is always contractual, but the misconduct that gives rise to his liability is defined differently when it is related to his jurisdictional mission.The present thesis tries to draw all the consequences from the hybrid nature of arbitration, concerning liability matters. Thus, the liability should be contractual only when the misconduct occurred while the arbitrator was acting as a contractor. By contrast, when he acts as a judge, his liability should be tortious. In order to distinguish those different situations, we offer to classify arbitrators’ obligations into two categories based on a comparison between arbitrators and judges. Overall, the obligations that lie with judge and arbitrators would be jurisdictional and would give rise to tort liability. On the contrary, the obligations that only weigh on arbitrators would be contractual and would give rise to contractual liability.Once one knows which set of rules to apply when it comes to arbitral liability, it remains to implement those rules. In this perspective, it is necessary, firstly, to know which court is competent and which law is applicable to international arbitral liability cases. Regarding jurisdiction as well as law applicable, it seems that same criteria should be used : parties’ will should be applied in the first place. On a suppletive basis, if there is no agreement between parties, the dispute regarding arbitral liability should be submitted to the courts of the State where the place of arbitration has been settled. Likewise, the law applicable to this dispute should be determined by the place of arbitration if the parties did not choose another law.Secondly, it is necessary to determine which conditions need to be fulfilled so that the arbitrator can be found liable, according to French internal liability law. In this regard, it appears necessary to adapt general law of liability to the specificities of arbitral liability. Concerning tort law, the misconduct giving rise to liability could be defined as jurisdictional gross misconduct. It would be characterized when the arbitrator has not been independent or impartial and has furthermore breached another jurisdictional obligation. As for contractual liability, misconducts should be defined on a case-by-case basis : different misconducts should be identified with each contractual obligations, for there is no general definition of contractual misconduct. The distinction between obligations of means and obligations of result is of no use when one tries to know precisely which behavior will give rise to contractual liability.Finally, concerning prejudice and causal link, general law of liability can be applied as it stands to arbitral liability without any modification. It only appears necessary to specify what damages can be remedied, notably regarding loss of chance. Moreover, the causal link should always be applied on the basis of equivalence of conditions rather than adequate causation, both in contractual and tort liability.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Arbitre; Civil; Civile; Liability; Responsabilité; Responsabilité (droit); Responsabilité contractuelle

Les demandes reconventionnelles de l’Etat en arbitrage transnational - Abonnat Ruggeri, Elise (Université Paris 2, 2021)
La demande reconventionnelle est une prétention du défendeur à l’instance qui revêt une finalité offensive et défensive. Reconnue en droit du contentieux international comme un droit dans le patrimoine du défendeur, elle est une demande incidente qui vise à contre-attaquer sur le plan substantiel le demandeur principal. Dans le contentieux transnational de l’investissement, l’appréciation de la compétence et de la recevabilité des demandes reconventionnelles par les tribunaux arbitraux est entravée par l’asymétrie des instruments de protection des investissements étrangers dont l’objet est principalement axé sur la protection des droits des investisseurs. Proposant une interprétation restrictive des conditions d’admission des demandes reconventionnelles, certains tribunaux arbitraux amenuisent l’effectivité du droit de contre-attaquer, notamment lorsque le traité applicable au différend prévoit des obligations réciproques limitées. Toutefois, l’objet du différend d’investissement que l’arbitre est appelé à trancher n’est pas toujours limité à l’ensemble normatif prévu par l’instrument servant de base à la demande de l’investisseur et peut couvrir une pluralité de normes. La diversité du droit applicable au différend d’investissement et l’étendue de la compétence matérielle des tribunaux arbitraux devrait ainsi permettre qu’un Etat mette en cause la licéité du comportement de l’investisseur au regard de l’ordre juridique interne et international. La demande reconventionnelle des Etats pose alors la question de la capacité de l’investisseur internationalement protégé à voir sa responsabilité engagée pour la violation du droit de l’Etat hôte et parfois aussi du droit international. Les demandes reconventionnelles peuvent alors servir d’agent révélateur des attentes légitimes de l’Etat à l’égard de l’investisseur internationalement protégé. Counterclaims are legal pretentions of the defendant with an offensive and a defensive character in relation to the claim of the other party. Recognized in international dispute settlement as a right of a defendant party, counterclaims are incidental claims aimed at pursuing substantial objectives rather than the mere dismissal of the main claim. In international investment arbitration, the establishment of jurisdiction over counterclaims is problematic because of the asymmetric nature of international investment agreements which are mainly dedicated to the protection of foreign investors’ rights. Adopting a restrictive approach of admissibility, arbitral tribunals have curtailed the effectivity of the right to counterclaim specifically when the applicable treaty contains limited reciprocal obligations. However, the subject- matter of an investment dispute may extend beyond the normative framework of the treaty, involving a plurality of norms. Thus, the diversity of the applicable law and the extended scope of material jurisdiction should enable States to allege violations of various obligations stemming from the domestic or the international legal orders. As a consequence, counterclaims raise the question of the investor’s capacity to be held responsible for breaches of domestic or international obligations, and can be deemed a vehicle to unveil the State’s legitimate expectations towards internationally protected investors.
Keywords: Admissibility; Compétence; Connection; Connexité; Counterclaims; Demande reconventionnelle; Demandes reconventionnelles; Diligence due; Domestic law; Droit international; Droit interne; Due diligence; Due diligence (droit international); Fondements juridiques; International law; Jurisdiction; Legal basis of claims; Objet du différend; Recevabilité; Responsabilité; Responsibility; Subject matter of the dispute

Pratique de l'arbitrage international en Algérie : enjeux et modernisation - Bouchelaghem, Saloua (Revue des Sciences Juridiques et Politiques, 2021)
A l’instar des autres pays, l’Algérie a adopté la conception dualiste de l’arbitrage, avec un régime juridique réservé à l’arbitrage interne et un autre destiné à réglementer l’arbitrage international par des dispositions particulières (Titre II Chapitre IV du CPCA). Ce qui laisse supposer une plus grande faveur pour l’arbitrage international dont le régime juridique est moins contraignante que celui de l’arbitrage interne. Ce droit de l’arbitrage parvenu certes à un stade en évolution vers la modernité ne comporte pas moins certaines lacunes que le législateur ne manquera pas de combler au gré de l’expérience de la pratique. Like the other countries, Algeria has adopted the dualistic conception of arbitration, with a legal regime reserved for internal arbitration and another intended to regulate international arbitration by specific provisions (Title II Chapter IV of the CPCA). This suggests a greater favor for international arbitration, whose legal regime is less restrictive than that of internal arbitration. this law of arbitration, which has certainly reached a stage in evolution towards modernity, nevertheless has certain shortcomings, which the legislator will not fail to fill with the experience of practice.
Keywords: Algérie; Arbitrage; Arbitrage international; Arbitragem; Arbitraje; Arbitration; Contrôle des sentences internationales; Etat; Examination of international awards; Juge étatique; Personnes publiques; State judge; public figures

Noms de domaine et modes alternatifs de règlement de conflits - Pavlenko Chapuis, Radmila (Université Paris 2, 2021)
Afin de régler les litiges relatifs aux noms de domaine, l’ICANN, entité gouvernant le DNS, crée en 1999 la procédure UDRP (Uniform Domain Name Dispute Resolution Policy, en français : règlement uniforme des litiges relatifs aux noms de domaine). Il s’agit du plus connu mais également du plus controversé des modes alternatifs de règlement de conflits en ligne. Il s'inscrit dans un millefeuille procédural au sein duquel l’ICANN superpose un grand nombre de procédures destinées à prévenir ou résoudre des litiges relatifs aux noms de domaine. Cette obscure et complexe matrice que l’ICANN qualifie d’ « administrative », n'organise cependant ni le rapport de ces procédures entre elles ni avec le droit étatique. Ces dernières années, une augmentation stratosphérique des litiges sur les noms de domaine est observée, résultant de la multiplication exponentielle de l'utilisation d'Internet par l'ensemble de la population mondiale suite à la crise sanitaire. Dans ce contexte, la sécurité juridique des titulaires de droits de propriété intellectuelle invite à repenser l'organisation du règlement des litiges relatifs aux noms de domaine en le faisant bénéficier d’une réforme unificatrice. Elle offre non seulement l'opportunité de créer un système de règlement de litiges unique mais également d’en préciser la nature et de clarifier les concepts à prouver. À cette fin, nous proposons de transformer le système actuel, historiquement extrajudiciaire et par nature privé, en un processus d'arbitrage avec l'objectif d'établir un lien procédural entre le système extrajudiciaire de l’ICANN et le droit étatique ainsi que d’assurer davantage de garanties procédurales aux parties. In order to settle disputes relating to the registration of internet domain names, ICANN, the governing body of the DNS, created the Uniform Domain Name Dispute Resolution Policy (UDRP) in 1999. This is the best known but also the most controversial of the alternative methods of online dispute resolution. UDPR is a part of the arbitration structure in which ICANN imposes a process intended to prevent or resolve disputes relating to domain names. The obscure and complex matrix that ICANN qualifies as ''administrative'', does not organize the relationship of these arbitration procedures to each other or to state law. In recent years, a stratospheric increase in domain name disputes has been observed, resulting from the ten-fold increase in Internet use by the entire world population following the Covid health crisis.In this context, the legal security of the holders of Intellectual Property (IP) rights invites a rethinking of the organization of the settlement of disputes relating to domain names by proposing a unifying reform. This offers an opportunity to create a new unique dispute resolution system, and also to specify its nature and clarify the concepts to be proven. Towards this end, we propose a full reform to transform the current system, which has been historically extrajudicial and is by its nature private, into a full arbitration process, pursuing the objective of establishing a procedural link of the extrajudicial system with state law as well as to provide more procedural guarantees to all parties.
Keywords: ADR; Alternative dispute resolution; Alternative methods; Arbitrage; Arbitrage (droit); Arbitragem; Arbitraje; Arbitration; DNS; Disputes; Domain names; Extra-Judicial system; Extra-judiciaire; ICANN; Internet Corporation for Asigned Names and Numbers; Litiges; Marques de commerce; Modes alternatifs de règlement des conflits; Noms de domaine; Noms de domaine (Internet) -- Droit; ODR; Online dispute resolution; Règlement de conflits; Système de règlement de litiges unique; UDRP; Unique dispute resolution system

Provas ilícitas e arbitragem - Avolio, Luiz Francisco Torquato (Universidade de São Paulo, 2021)
O presente estudo é dedicado ao tema da prova ilícita na arbitragem, com sua repercussão na formação do convencimento do árbitro, em consonância com as garantias que um processo justo e equitativo impõe às partes e aos julgadores. A tutela processual de supremos valores da Constituição, pela ampla e dogmática vedação à admissibilidade das provas ilícitas no sistema brasileiro, deve permear qualquer tipo de processo, evitando-se, assim, que o uso de provas vedadas se constitua em redobrada violação dos direitos fundamentais. Por outro lado, o mais aprofundado enfoque sobre a origem e natureza da prova supostamente inadmissível poderia ensejar o manejo de provas em menor grau ou não propriamente ofensivas a essas regras e princípios, evitando que se esvazie por completo o direito à prova, comprometendo-se, por consequência, o princípio da demanda ou da ampla defesa. Nesse caso, abre-se a discussão sobre se o aporte de provas ilícitas ao processo simplesmente as legitimaria à luz do princípio da comunhão (ou aquisição) da prova, ou se poderiam ser consideradas subjetivamente ilícitas tão somente quando deduzidas contrariamente ao titular dos direitos violados, mas ao mesmo tempo lícitas para demonstrar a ocorrência de uma violação a esses direitos. No tocante às consequências práticas, se a decisão, contaminada pelo acolhimento de prova ilícita, ou, ao revés, que deixou de considerá-la, no que pertinente, comprometer o livre convencimento do árbitro, pode ensejar ação de nulidade por violação do art. 32, inciso VIII c.c. art. 21, § 2º da LA, afetando, por arrasto, os princípios da igualdade das partes e da imparcialidade do árbitro. Excepcionalmente, nos casos em que se afigure a inexistência da decisão pela fundamentação exclusiva em prova ilícita, seria possível cogitar do manejo de ação declaratória, mesmo após decorrido o prazo decadencial da ação anulatória. The study is dedicated to the theme of illegal evidence in arbitration, with its repercussion in the formation of the arbitrator's conviction, in line with the guarantees that a fair and equitable process imposes on the parties and judges. The procedural protection of the supreme values of the Constitution, by the broad and dogmatic prohibition of the admissibility of illicit evidence in the Brazilian system, must permeate any type of process, thus preventing the use of prohibited evidence from constituting a redoubled violation of fundamental rights. On the other hand, a deeper focus on the origin and nature of the supposedly inadmissible evidence could lead to the handling of evidence to a lesser degree or not properly offensive to these rules and principles, preventing the right to proof from being completely emptied, compromising, consequently, the principles of demand and full defense. In this case, a discussion arises as to whether the provision of illicit evidence to the process would simply legitimize them in light of the principle of sharing (or acquisition) of evidence, or whether they could be considered subjectively illicit only when deducted contrary to the holder of the violated rights, but at the same time lawful to demonstrate the occurrence of a violation of these rights. With regard to practical consequences, if the decision, contaminated by the acceptance of unlawful evidence, or, on the other hand, which failed to consider it, as pertinent, compromises the arbitrator's free conviction, it may give rise to an action of nullity for violation of art. 32, item VIII c.c. art. 21, § 2 of the LA, affecting, by drag, the principles of equality of the parties and the impartiality of the arbitrator. Exceptionally, in cases where it appears that the decision does not exist on the exclusive basis of unlawful evidence, it would be possible to consider handling a declaratory action, even beyond the deadline for the annulment action.
Keywords: Acquisition of evidence; Admissibility; Arbitrage; Arbitragem; Arbitration; Arbitrator; Ação anulatória; Deadline; Declaratory action; Devido processo legal; Direito comparado; Direito de defesa; Equality of the parties; Evidence; Free knowledge; Full defense; Illicit proof; Impartiality of the arbitrator; Nullity action; Principles of demand; Prova ilícita

Arbitration as a Legal Mechanism in the Settlement of Disputes under Cameroonian Law - Tambe, Hans; Forbi, Nduah Esther; Epie, Mousinga Adele (Social Science Research Network, 2021)
Recently, commercial activities in the state of Cameroon are evolving and there is an inflow of investors from within the OHADA Zone and other regions of the world to Cameroon. This has led to the proliferation of commercial contracts such as concession contracts, production sharing agreements, risk contracts between the Republic of Cameroon and foreign investors, or contracts between individuals of foreign countries as well as with Cameroonian nationals. Commonly, contracts may be breached and disagreements surface among the contracting parties. The difficulties pose is in the manner to settle such disagreements in a friendly manner to maintain the relationship between the parties and to enables the contracting parties to resolve the disputes more cost-effectively and increase business efficiency in Cameroon. However, the state of Cameroon has a favorable attitude towards bilateral and multilateral investment treaties to guarantee protection to investors in the territory. This elucidates the reason why the government of Cameroon has enacted laws and ratified regional and international treaties, aimed at safeguarding a smooth atmosphere for investors and other commercial traders particularly in the domain of arbitration to help in resolving disputes in case of any disagreement among contracting parties. This article will present the authorities involved in arbitration with the experience regarding the application of the various law and institutions concerned with the arbitration. This will also help contracting parties or investors to understand the legal mechanisms in the settlement of disputes through arbitration in Cameroon.
Keywords: Arbitrage; Arbitragem; Arbitration; dispute; legal; mechanism; settlement

O acesso à justiça na era da automação, da inteligência artificial e da mineração de dados: o nascimento do devido processo digital (e-due process of law) - Mariano Junior, Raul (Universidade de São Paulo, 2021)
Trata o presente trabalho de aspectos da absorção da tecnologia, em especial a inteligência artificial e a automação no ambiente processual brasileiro. Discute-se aqui aspectos importantes da tecnologia ligada à computação, e a forma como já interfere e pode interferir, positiva e negativamente, no acesso à justiça (entendido como acesso à ordem jurídica justa). O conhecimento das tecnologias de machine learning, deep learning, processamento de linguagem natural, redes neurais, reconhecimento de fala, transcrições automáticas e conversão de texto em fala, já são largamente utilizados pelos tribunais, advogados e órgãos públicos, tudo num cenário transformador e disruptivo da tradição jurídica, sem qualquer ou muito pouca normatividade legal. O imbricamento da tecnologia com o princípio do devido processo legal, numa análise mais próxima, pode revelar que a tradição jurídica secular acumulada não mais se presta à finalidade de garantir decisões justas, esgarçando-se e perdendo importância e eficácia. O mundo jurídico precisa aproximar-se da tecnologia e das ciências da computação, para conformar sua aplicação e não ser conformado por elas. Por outro lado, a tecnologia computacional pode ser muito positiva no alargamento do acesso à justiça, se for adequadamente compreendida e utilizada especialmente para o tratamento de demandas repetitivas e para a aproximação da população mais carente do acesso à ordem justa. Isto se dá desde a organização e melhora das informações jurídicas disponíveis, até pelo desenho de novas formas, através do desenho de soluções de disputas, combinadas com a computação, criando vias de acesso como a ODR (Online Dispute Resolution). Pode, entretanto, esta mesma tecnologia, provocar efeitos nefastos ao estado de direito e aos direitos fundamentais se ignorada e não normatizada em tempo, traçando-se seus limites, usos, condições e responsabilidades, em velocidade equivalente ao desenvolvimento tecnológico, evitando-se, assim, lacunas de alto poder destrutivo, que certamente serão preenchidas pelo interesse econômico e político. This paper deals with aspects of technology absorption, especially artificial intelligence and automation in the Brazilian procedural environment. Important aspects of computing technology are discussed here, and the way it already interferes and can interfere, positively and negatively in the access to justice (understood as access to the fair legal order). Knowledge of machine learning, deep learning, natural language processing, neural networks, speech recognition, automatic transcriptions and text-to-speech conversion are already widely used by courts, lawyers and public bodies, all in a transformative and disruptive scenario of the legal tradition, without any or very little legal norms. The imbrication of technology with the principle of due process, in a closer analysis, may reveal that the accumulated secular legal tradition no longer lends itself to the purpose of guaranteeing fair decisions, fraying and losing importance and effectiveness. The legal world needs to get closer to technology and computer science, to conform its application and not be conformed by them. On the other hand, computational technology can be very positive in expanding access to justice, if it is properly understood and used, especially to deal with repetitive demands and to bring the poorest people closer to access to just order. This occurs from the organization and improvement of the available legal information, even through the design of new forms, through the design of dispute solutions combined with computing, creating access routes like the ODR (Online Dispute Resolution). However, this same technology can cause harmful effects to the rule of law and fundamental rights if ignored and not regulated in time, tracing its limits, uses, conditions and responsibilities, at a speed equivalent to technological development, thus avoiding gaps of high destructive power, which will certainly be filled by economic and political interest.
Keywords: ACCESS TO JUSTICE; ADR; AI; Accès à la justice; Acesso à justiça; Alternative dispute resolution; Applied computing (Law); Artificial Intelligence; Automatisation; Civil Procedure; Computação aplicada (Direito); Devido processo legal; Direitos fundamentais; Due legal process; Estado de direito; Fundamental rights; Inteligência artificial; Intelligence Artificielle; Jurisdiction; Jurisdição; Mégadonnées; ODR; Online Dispute Resolution; Processo Civil; Rule of law

Capacity of the International Investment Arbitration Mechanism in Environmental Protection - Habibi Majandeh, Mohammad; Gholami, Afife (Public Law Researsh, 2021)
Environmental considerations have always been a challenge for foreign investment. The need to observe environmental minimums from the beginning to the end of the investment is also a concern of environmental law activists. In the meantime, the host state faces sometimes conflicting commitments. State dual obligations to foreign investors on the one hand, and the whole citizens on the other, has in many cases led to disputes, rooted in environmental norms. The main question is how the arbitration mechanism can take an active stand in the face of such disputes? The main purpose of this study is to examine the reflection of these conflicts in investment arbitration and the importance and role of arbitration in improving the environmental status. The authors of this paper believe that the arbitration system has tools that it can use in resolving disputes to balance these conflicting obligations. Some of these legal tools are directly or indirectly related to investment agreements, and others are beyond the treaty and based on international principles, rules, customs and practices. ملاحظات محیط زیستی همواره یکی از چالش های پیشروی سرمایه گذاری خارجی بوده است. لزوم رعایت حداقل های زیست‌محیطی از آغاز تا پایان سرمایه گذاری، از دغدغه های فعالان حوزه حقوق محیط زیست نیز می باشد. در این میان دولت میزبان با تعهداتی بعضاً متعارض روبروست. تعهدات دوگانه دولت در برابر سرمایه گذار از یک طرف و عموم شهروندان از طرف دیگر، در موارد متعددی به بروز اختلافاتی منجر شده که ریشه در هنجارهای محیط زیستی دارد. پرسش اصلی این است که سازوکار داوری در مواجهه با این نوع اختلافات، چگونه می تواند فعالانه موضع گیری نمایند؟ هدف اصلی این مطالعه بررسی بازتاب تعارض ها در رویه داوری سرمایه گذاری و اهمیت و نقش داوری در بهبود وضعیت محیط زیستی است. نویسندگان این نوشتار بر این باورند که سیستم داوری، ابزارهایی در اختیار دارد که می تواند از آنها در جریان حل اختلاف برای ایجاد تعادل میان این تعهدات متعارض استفاده کند. برخی از این ابزارهای حقوقی مستقیم یا غیرمستقیم با معاهدات سرمایه‌گذاری مرتبط است و دستهای دیگر فرامعاهده ای و ناشی از اصول، قواعد، عرف ها و رویه های بین المللی است.
Keywords: Arbitrage; Arbitragem; Arbitration; Bilateral Treaties; Environmental Protection; International Arbitration; Investment Disputes; Legal Instruments; ابزار حقوقی; اختلافات سرمایه‌گذاری; حمایت از محیط ‌زیست; داوری بین‌المللی; معاهدات دوجانبه

Comparison of Egyptian and English Mediation Procedures in Construction - Swelam, Ahmed; Eldosouky, Adel Ibrahim; El Korany, Tamer Mostafa (Journal of Engineering Research, 2021)
The mediation process is the parties' will to the dispute to reach an amicable, non-binding settlement to end their dispute. The Egyptian legislature adopted the idea of issuing a draft law on mediation in civil and commercial matters to settle disputes between the parties, whether before the litigation stage or after appearing before the courts. The Egyptian Ministry of Justice held many community dialogue sessions to find the final version of the draft law. However, the concerned authorities have not issued the law until writing this paper. This research aims to compare and analyze the Egyptian mediation procedures and the British mediation procedures to improve, develop, and enhance the Egyptian ones especially the draft law as well as overcoming the obstacles that hinder the spread of mediation. On the one hand, presenting the Egyptian procedures in the draft mediation law and the rules of the Cairo Regional Center for International Commercial Arbitration, CRCICA. On the other hand, the British procedures represented in the Institute of Civil Engineers' mediation rules, ICE.
Keywords: Egypt; England; Mediation

Post award arbitral tribunal's mandate under the UNCITRAL Model Law and national laws based thereon - Al Hyari, Omar Hisham; Al Ani, Abdullah Rabee (Heliyon, 2021)
The UNCITRAL Model Law on International Commercial Arbitration provides for the extension of the mandate of the arbitral tribunal post issuance of the final award for the issuance of correction, interpretation, additional award, and remittance of the award back to the arbitral tribunal to remove grounds for challenging the award. Using a doctrinal approach, this paper examines the deviations of the national laws of adopting jurisdictions from the Model Law in regards to this extended mandate, and evaluates the improvements and drawbacks in these deviations. Mainly, the findings of this paper are that, of the many deviations, the positive changes are those that provide comfortable and lenient default provisions for the benefit of inexperienced parties, and since correction, interpretation, additional award, and remittance are useful provisions that are designed to help self-rectify the arbitral process, without adversely delaying it, then the changes that increase the efficacy of these provisions are welcomed. On the other hand, unnecessary deviations are seen as drawbacks that hinder the harmonization of national arbitration laws aimed at by the Model Law. The adopting jurisdictions shall be limited to those acknowledged as such by the UNCITRAL.
Keywords: Additional award; Arbitrage; Arbitragem; Arbitration; Arbitrators' mandate; Award; Correction; Interpretation; Model Law jurisdictions; UNCITRAL Model Law

Mediación y Cultura de Paz en los Objetivos de Desarrollo Sostenible 2030 - Gonzalo-Quiroga, Marta (Polo del Conocimiento, 2021)
El objetivo de la presente contribución es analizar el papel de la mediación como bisagra referencial entre dos de los Objetivos de Desarrollo Sostenible (ODS) para 2030: el núm. 4 -Educación- y el núm. 16 -Paz, Justicia, e Instituciones sólidas-. La metodología empleada parte de un estudio del panorama internacional para detenerse en la legislación española, tanto en mediación como en educación en cultura de paz, con las correspondientes novedades al respecto. Todo ello responde a una investigación analítica sobre distintas bases legislativas, documentales y bibliográficas que, como resultado, ha dado lugar a la creación de distintas tablas que resumen la investigación y, pretendemos, contribuyan a facilitar su difusión, en el marco de los ODS 2030. Se trata así de promover la mediación como una de las herramientas esenciales para fomentar la convivencia pacífica, la educación y la justicia en el contexto universal de la cultura de la paz.
Keywords: Cultura de Paz; Cultura de paz; Culture of Peace; Educación; Education; Educação; Justice; Justicia; Justiça; Mediación; Mediation; Mediação; Objetivos de Desarrollo Sostenible (ODS); Objetivos de Desenvolvimento Sustentável; Sustainable Development Goals

L’autonomie de la clause en droit privé - Tawk, Ghassan (Université de Montpellier, 2021)
L’autonomie un vocable recouvrant deux réalités : la « séparabilité » et « l’indépendance ». L’autonomie de la clause compromissoire se traduit par la SEPARABILITE de la clause et non pas par son indépendance puisqu’elle se trouve parmi les autres clauses du contrat de base. La séparabilité signifie que cette clause est différente des autres clauses dans son existence, son objet et sa portée et elle ne partage pas leur sort. Les effets de cette séparabilité se résument en une autonomie matérielle qui permet, d’une part, la survie de la clause compromissoire au contrat principal, l’absence de contagion des vices qui pourraient affecter le contrat et, d’autre part, elle l’autorise à être soumise à une loi différente de celle qui régit le reste du contrat et si les parties ont choisi la loi applicable à leur contrat, rien ne permet d’affirmer que cette même loi devrait régir la clause compromissoire, puisque celle-ci est fort différente dans son objet et sa nature du contrat qui la contient.En revanche, le principe de l’autonomie de la garantie autonome signifie L’INDEPENDANCE totale et ceci veut dire inopposabilité des exceptions contenu dans d’autres contrats ou instruments annexes s’y rapportant. Le mécanisme de la garantie autonome aboutit à la création d’une pluralité de rapports contractuels dont l’enchainement chronologique se présente par la création de deux contrats distincts et indépendants. L’appel de la garantie la rend irrévocable et exigible immédiatement sans contestations se rapportant au contrat de base et sans pouvoir lui opposer les exceptions qui pourraient s’appliquer à ce contrat.
Keywords: Arbitration clause; Autonomie; Autonomy; Clause compromissoire; Garantie autonome; Guarantees; Independence; Indépendance; Separability; Séparabilité; Sûretés (droit)

L'incidence de l'arbitrage et les situations triangulaires : Étude à la lumière de l'évolution du sort de la caution solidaire - El Hajj, Joyce (Université de Montpellier, 2021)
La Cour de cassation a mis fin aux controverses jurisprudentielles et doctrinales sur la qualité de la caution solidaire quant à la clause compromissoire, et cela en refusant l’application de la théorie de la représentation mutuelle des coobligés et en la qualifiant de « tierce personne », ouvrant par ce fait la porte à la tierce opposition. La transposition de la solution avancée par la Haute Cour, a été parfaitement appliquée à l’assureur non-signataire de la clause compromissoire insérée dans un contrat liant son assuré à une autre personne, même en présence de la clause de direction de procès dans le contrat d’assurance. Enfin, la possibilité de l’application de cette solution a été étudiée au cas par cas sur l’effet de la clause compromissoire statutaire à l’égard d’un futur ou ex- associé. The Court of Cassation put an end to the jurisprudential and doctrinal controversies on the quality of the joint and several sureties regarding the compromise clause, and this by refusing the application of the theory of mutual representation of the co-owners and by characterizing it as “third party”, thereby opening the door to the third-party opposition. The transposition of the solution proposed by the High Court was perfectly applied to the insurer who did not sign the arbitration clause inserted in a contract binding his insured person to another person, even in the presence of the trial management clause in the insurance contract. Finally, the possibility of applying this solution has been studied on a case-by-case basis on the effect of the statutory arbitration clause on a future or ex-partner.
Keywords: Arbitrage; Arbitragem; Arbitration; Assureur non-Signataire; Caution solidaire; Cautionnement; Clause compromissoire; Codébiteurs; Corporate law; Droit des sociétés; Joint and several sureties; Non-Signatory insurer; Third party; Tierce opposition; Tiers (droit)

Les centres d’arbitrage de l’espace OHADA face aux technologies de l’information et de la communication (TIC) - Ndongo Dimouamoua, Céline (Revue Juridique de la Sorbonne, 2021)
Depuis l’adoption de l’Acte uniforme relatif au droit de l’arbitrage, les centres d’arbitrage se sont multipliés dans la zone OHADA. Même si tous ces centres ne sont pas au même niveau de développement, les acteurs économiques leur confient de plus en plus le règlement de leurs différends. Toutefois, la fermeture des aéroports, la limitation des déplacements, l’impossibilité de se réunir, conséquences de la crise sanitaire mondiale apparue en mars 2020, ont perturbé le fonctionnement des centres d’arbitrage du monde entier, y compris ceux situés dans la zone OHADA. En abolissant les distances et les contraintes de temps, les technologies de l’information et de la communication (TIC) se sont révélées être des moyens efficaces de contournement des difficultés nées de la pandémie. En effet, les grands centres d’arbitrage en ont profité pour mettre en œuvre des solutions technologiques permettant de réduire l’impact de la crise sur les procédures arbitrales. Dans cet environnement hautement concurrentiel, la question de l’arbitrage en ligne dans les centres d’arbitrage de l’espace OHADA s’est alors de facto posée. La question de la place réservée aux TIC dans l’administration des procédures par ces centres et les moyens d’y développer l’arbitrage à distance est posée. Pour répondre à cette double interrogation, un état des lieux de l’arbitrage en ligne dans les centres d’arbitrage de la zone a été fait. Il en ressort que les règlements d’arbitrage des centres abordent le sujet de manière lacunaire. Bien plus, l’environnement économique et technologique dans lequel ils évoluent peut constituer un frein au recours aux TIC. La nécessité de compléter les règlements d’arbitrage sur des questions comme la cybersécurité, l’organisation des réunions virtuelles ou encore la signature électronique des documents est clairement apparue. Afin d’accélérer le développement de l’arbitrage en ligne, les centres d’arbitrage situés dans l’espace OHADA doivent aussi former leur personnel à l’usage des TIC, encourager les parties à signer des cyber-protocoles, et mettre à leur disposition des guides d’usage des TIC dans les procédures arbitrales. En pratique, la révolution numérique dans les centres d’arbitrage africains n’aura pas lieu sans les efforts combinés des centres, des parties et des arbitres. 22 ans après l’adoption de l’AUA, la compétitivité et la maturité des centres d’arbitrage de l’espace OHADA seront fonction de leurs capacités à intégrer les TIC dans leurs méthodes de travail.
Keywords: Arbitrage en ligne; Arbitrage institutionnel; Arbitration centres; Centres d’arbitrage; Cyber protocol; Cyber-protocole; Guides sur l’arbitrage en ligne; ICT; Institutional arbitration; OHADA; Online Dispute Resolution; Online arbitration guides; TIC; Vidéoconférence

La détermination du droit applicable à l’arbitrage - Lacreta, Isabela (Université Paris 10, 2021)
La détermination de la loi applicable à la résolution des crises juridiques entre les parties est la première étape de l’activité juridictionnelle dans les cas où un élément d’extranéité est présent. Il s’agit d’une étape essentielle pour assurer la protection juridictionnelle. Tout arbitrage est, du point de vue du système juridique du droit national, étranger à celui-ci. L’arbitre est l’autorité juridictionnelle du système juridique autonome de droit transnational, un système qui est déconnecté du système national, dans lequel le juge étatique est l’autorité juridictionnelle naturelle. L’État a le pouvoir de décider de la part de souveraineté à laquelle il souhaite renoncer en faveur de l’arbitre. En matière d’arbitrage, l’étendue de l’autonomie de la volonté des parties est largement reconnue, tant dans ses dimensions procédurales que matérielles. Rares sont les cas où les parties prévoient expressément les droits qui régiront leurs arbitrages. Droits, au pluriel, non seulement en raison de la nature transnationale des arbitrages, mais aussi en raison de la spécificité des questions soumises à la protection des arbitres. Chaque question doit être régie par son propre droit, conformément à la technique de dépeçage. Les méthodologies de conflit de lois propres au système juridique national, de nature interne et publique, ne sont pas adaptées et ne doivent pas être transposées en matière d’arbitrage. La multitude de questions pouvant être discutées dans un arbitrage exige une délimitation de l’objet de cette étude. Celle-ci est ainsi exclusivement consacrée au droit applicable à l’arbitrage, en particulier aux droits applicables à la convention d’arbitrage, au procès arbitral et à la validité et l’efficacité de la sentence arbitrale, en suivant les étapes classiques d’une procédure arbitrale. L’analyse de la détermination du droit applicable dans l’arbitrage, c’est-à- dire au fond, est exclue. Les conclusions de cette étude partent toujours du principe que l’arbitre est une autorité juridictionnelle non soumise aux règles d’organisation judiciaire et hiérarchique du système national ; ses actes sont soumis à un contrôle minimum d’internalisation, par le biais de conversations systémiques.
Keywords: Applicable law to arbitration; Arbitrage; Arbitragem; Arbitration; Autonomia da vontade; Autonomie (philosophie); Autonomie de la volonté; Conflict of laws; Conflit de juridictions; Conflit des lois; Conflito de leis; Direito applicável a arbitragem; Direito transnacional; Droit applicable à l'arbitrage; Droit transnational; Party autonomy; Soberania; Sociologia da arbitragem; Sociologie de l'arbitrage; Sociology of arbitration; Souveraineté; Sovereignty; Transnational law

L'arbitrabilité des litiges en droit des marchés financiers - Megam, Nadège Flore (International Multilingual Journal of Science and Technology, 2021)
Keywords: Arbitrage; Arbitration; Financial markets; Marchés financiers

The Role of Alternative Dispute Resolution (ADR) in Dispute Settlement of Logistics Activities - Quan, Gao (International Journal of Trend in Scientific Research and Development, 2021)
The Alternative Dispute Resolution (ADR) provides a non-litigation settlement mechanism for the parties of logistics activities. The advantages of ADR are highlighted in logistics dispute resolution due to the characteristics of logistics dispute and the difficulties faced in the litigation procedure. In the dispute resolution process, ADR means a simple, cost-efficient, and convenient method for the parties involved to settle disputes quickly, flexibly, and friendly. With its legitimacy and rationality, ADR should be the preferred choice for the parties involved in logistics dispute resolution.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Dispute settlement; Litigation procedure; Logistics activities; MARD; Mediación; Mediation; Mediação; Médiation

Le repli par les juridictions étatiques de leur jurisdictio - Bouhenic, Marcel-Gérard (Université Paris-Saclay, 2021)
Les juridictions étatiques rétractent volontairement leur jurisdictio pour favoriser les Modes Alternatifs de Règlement des Conflits (MARC) - notamment la médiation et l'arbitrage - et tendent ainsi à devenir un mode subsidiaire de règlement des litiges.Les techniques juridiques qui fondent la rétractation de la jurisdictio des juridictions étatiques au profit des MARC ont pour particularité d'être de source prétorienne et issues de raisonnements construits sur un a priori systématiquement favorable aux MARC, a priori qui n’est pas uniquement le reflet d’un système économique mais résulte de multiples influences idéelles (philosophiques, religieuses, sociétales).De fait, la subsidiarité des juridictions étatiques entraîne la subsidiarité de la loi en tant que norme de règlement des litiges. Parallèlement, les normes a-légales retenues par les MARC acquièrent une autorité assise sur la satisfaction tant des parties qui en font l'expérience que des juges étatiques qui constatent que la rétractation de leur jurisdictio ouvre le passage du juste général au juste particulier.Ainsi, progressivement, les institutions privées de MARC acquièrent un pouvoir politique en émettant des normes qui influent à la fois sur les règles que retiennent les juridictions étatiques et sur la stratégie des parties dans la défense de leurs intérêts.Au-delà de leur tendance à rétracter leur jurisdictio à l'égard des conflits privés en laissant se développer sous leur contrôle les MARC et les normes a-légales pour les conflits entre particuliers, les juridictions étatiques, en ce début du XXIè siècle, redéployent toutefois leur jurisdictio en endossant, le cas échéant, un rôle politique de création de normes et de suppléant du législateur lorsque les conflits s'expriment sous forme d'affrontements de Grands Principes, notamment lorsque les règles légales sont insuffisantes pour répondre à l'évolution de la société. State courts voluntarily retract their jurisdictio to favour Alternative Dispute Resolution (ADR) - notably mediation and arbitration - and are thus tending towards becoming a subsidiary means of dispute resolution.The legal techniques, on which the withdrawal of the jurisdictio of the State courts in favour of ADR is based, have the particularity of being of praetorian origin and the result of reasoning based on an a priori systematically favourable to ADR, an a priori that is not only the reflection of an economic system but the result of multiple "ideal" influences (philosophical, religious, societal). The subsidiarity of State jurisdictions leads de facto to the subsidiarity of the law as a standard for dispute settlement. In parallel, the non-legal standards adopted by ADR acquire an authority based on the satisfaction of both the parties to whom they are applied and the State judges who consider that the withdrawal of their jurisdictio opens the passage from what is just in general to what is just in particular. Thus, gradually, private ADR institutions are acquiring political power by issuing standards that influence both the rules adopted by State courts and the defense strategies of the parties.Beyond their tendency to retract their jurisdictio by allowing ADR and non-legal standards to develop under their control with regard to conflicts between private individuals, State courts, at the beginning of the 21st century, are nevertheless redeploying their jurisdictio by adopting, where appropriate, a political role as standard-setters and substitute legislators where conflicts take the form of confrontations between Great Principles, particularly where legal rules prove unable to respond to changes in society.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitrage international; Arbitragem; Arbitration; Consensualism; Consensualisme; Juridictio; Jurisdictio; MARC ( mode alternatif de réglement des conflits ); MARD; Mediación; Mediation; Mediação; Médiation; Médiation internationale; Repli; Règlement de conflits; Règlement pacifique des conflits internationaux; Withdrawal

Normas de aplicação imediata e arbitragem trabalhista: entre pluralismo e transnacionalidade - Guedes, Henrique Lenon Farias (Universidade de São Paulo, 2021)
O tema desta pesquisa é a lei aplicável ao mérito da arbitragem trabalhista com elementos estrangeiros, tendo, como problema, a determinação das normas brasileiras de aplicação imediata. Considerando que o direito do trabalho tem uma normatividade híbrida, dependendo tanto da produção legislativa estatal quanto da atividade normativa dos sindicatos, a hipótese é: o padrão normativo de aplicação imediata, em matéria trabalhista, deve ter critério pluralista, integrando regulamentos públicos e privados, ou melhor, produzidos pelo Estado, pelo sindicato e pelas empresas, de modo que as normas de aplicação imediata se encontrariam no direito transnacional. A pesquisa se insere em debates muito recentes na Academia e na sociedade civil estrangeiras, que tem proposto cláusulas e regras modelos para arbitragem nas cadeias produtivas; por outro lado, temas específicos de direito do trabalho não têm encontrado ressonância na doutrina brasileira de DIP, o que reforça a justificativa e a pertinência da pesquisa. Nesse sentido, a contribuição à ciência brasileira pretende-se original na articulação do marco teórico utilizado, a análise econômica do direito, ainda pouco explorada nos estudos brasileiros de direito internacional, com o ambiente decisório especial da arbitragem. A pesquisa será bibliográfica, normativa, jurisprudencial e documental, com uso do método hipotéticodedutivo. Para tanto, a tese é dividida em cinco capítulos. O primeiro oferece um resgate histórico da ideia de arbitragem comercial, opondo-o à evolução do direito internacional do trabalho e identificando uma dificuldade apriorística de se aproveitarem os conceitos da primeira na aplicação do segundo, especialmente diante de tratados de direitos humanos. O segundo identifica, na doutrina e na jurisprudência trabalhistas, que essa incompatibilidade é processada com razões que parecem equivocadas, isto é, com o uso hiperbólico ou inadequado dos conceitos de publicização e de ordem pública. O terceiro, portanto, identifica a potencial conveniência do conceito de normas de aplicação imediata, supostamente protetivo do trabalhador, mas o questiona no contexto de uma análise econômica do direito internacional, isto é, verifica sua sustentação à luz dos incentivos institucionais à captura dos fins do direito pelos Estados, ainda que estes sejam partes de tratados de direitos humanos. Funda-se, assim, um ceticismo quanto à qualificação de preceitos da legislação trabalhista nacional como normas de aplicação imediata. Ciente dessa limitação, o quarto tenta identificar as normas nacionais que verdadeiramente se deveriam aplicar, de forma imediata, ao mérito de uma disputa trabalhista plurilocalizada, com atenção transcultural à Convenção 169 da OIT. Estabelecidos os parâmetros do direito brasileiro, o quinto revisita a doutrina de Georges Scelle, para compreender a arbitragem como desdobramento funcional do direito internacional do trabalho e nela indicar um caminho mais adequado: as normas de aplicação imediata se encontrariam diretamente no regime transnacional do direito do trabalho. Assim, além da justificativa econômica para o afastamento de normas de aplicação imediata, especificamente nacionais, destaca-se uma proposta jurídica de reaproveitamento operacional desse conceito. O capítulo final faz a distinção entre os tipos de arbitragem que se relacionam com o direito da OIT (normativa) e com o direito transnacional (positiva).
Keywords: Arbitrage; Arbitragem; Arbitration; Direito Internacional Privado (análise econômica); Direito do Trabalho; Direitos Humanos; Droit du travail; Labour arbitration; Labour law; Legal pluralism; Overriding mandatory provisions; Pluralismo jurídico; Public policy; Transnational Law

L'arbitrage à l’épreuve des procédures collectives et de l’intervention du juge en droit de I’OHADA. - Kante, Souleymane (Université Jean Lorougnon Guédé, 2021)
Si l’on définit l’arbitrage simplement comme un mode de règlement des différends administré par les particuliers non investis de leur mission par l’Etat. Il n’en demeure pas moins que ce mode de règlement des différends ne saurait évoluer seul. C’est ainsi que l’ordre public des procédures collectives et l’intervention du juge étatique impact tant l’arbitrage. Il a paru important de jauger leur impact sur l’arbitrage. L’analyse effectuée à travers une méthode exégétique des textes communautaires et internationaux a permis de constater que les procédures collectives et l’intervention du juge étatique sont facteurs de désordre dans l’arbitrage. Toutefois, il convient de relever une certaine survie de l’arbitrage face aux procédures collectives et à l’intervention du juge étatique.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Juge étatique; OHADA; Procédures collectives; Survie

El principio de proporcionalidad en el derecho international económico - Reyes Sarmiento, Lina (Université Paris 10, 2021)
Le principe de proportionnalité a été récemment reconnu dans les traités et les accords internationaux du commerce et des investissements avec l’État. Cependant, peu d'études se concentrent sur la nature juridique, le contenu, la portée et les fonctions de ce principe dans le droit économique international. Cette thèse présente une analyse actuelle et détaillée sur ces questions.
Keywords: Arbitrage international; Arbitraje internacional; Dispute resolution; Droit international économique; International Arbitration; Inversiones; Investissements; Investments; OMC; Principes; Principios; Principles; Proporcionalidad; Proportionality; Proportionnalité; Proportionnalité (droit); Règlement des différends; Solucion de diferencias; WTO

Mediation: Is There a More Promising Future? The Case of the Cairo Business Community - Soliman, Cherine (Arab Journal of Administration, 2021)
In an era of economic distress, some organizations have found refuge and growth potential in cooperation. Mediation, a highly recommended cooperative concept, has been enabled in certain countries but not all. Some applications lacked local cultural support making it, despite government efforts, a failure to launch. In this article, we investigate attempts to launch mediation in the Cairo Business Community (CBC). This study enabled us to revisit how Egyptian culture was prototyped by Hofstede and to question its representativeness. Hofstede has consistently described Egyptian culture as being highly cooperative / collectivist but our observations indicate that this culture is now more of an individualistic / competitive type, due to the tremendous economic difficulties that Egyptian society is going through. These difficulties and their impact on culture are at the heart of the explanation of the failure to launch mediation in the CBC.
Keywords: Cairo Business Society; Conflict Resolution; Culture; Egypt; Mediation

Le réglement de litiges commerciaux en Afrique de l'Ouest - Traoré, Mandiou (Université Jean Moulin Lyon 3, 2021)
L’organisation du règlement des litiges commerciaux en Afrique de l’ouest notamment dans les États Parties au Traité OHADA est marquée à la fois par l’intervention des juridictions nationales d’instance et d’appel et de la Cour commune de justice et d’arbitrage. En effet, la mise en place d’une législation commune en matière de droit des affaires a nécessité l’institution d’une Cour de cassation unique pour unifier la jurisprudence. L’uniformisation de la jurisprudence a conduit à la mise à l’écart des juridictions nationales supérieures de tout enjeu de règlement de litiges liés à l’application du droituniforme excepté les décisions appliquant des sanctions pénales. Dès lors, les relations entre les deux ordres de juridictions supérieures sont plus empreintes de conflits que basées sur un véritable dialogue des juges. Eu égard à ce qui précède, pour assurer aux opérateurs économiques un meilleur règlement de leurs litiges en évitant les difficultés liées au règlement judiciaire, il convient de promouvoir d’autres outils alternatifs de règlement des litiges. Dès lors, l’adoption des actes uniformes relatifs à l’arbitrage et à la médiation ont permis de donner aux opérateurs économiques, d’autres lieux alternatifs pour régler leurs litiges. En outre, le développement des centres d’arbitrage, de médiation et de conciliation semble être une alternative aux juridictions judiciaires. Au regard, des multiples saisines du centre d’arbitrage, de médiation et de conciliation de Ouagadougou par les banques et établissements financiers, les sociétés d’assurances, de transports et de télécommunications, les entreprises minières et énergétiques, l’on peut en déduire que ce centre joue un rôle important dans le règlement alternatif des litiges commerciaux en Afrique de l’ouest. The organization of the settlement of commercial disputes in West Africa, particularly in the States Parties to the OHADA Treaty, is marked by the intervention of national courts of instance and appeal and the Common Court of Justice and Arbitration. Indeed, the establishment of common business law legislation has necessitated the institution of a single Court of Cassation to unify jurisprudence. The standardization of jurisprudence has led to the exclusion of the higher national courts from any dispute resolution issues related to the application of uniform law, except for decisions applying criminalsanctions. Consequently, relations between the two orders of higher courts are more marked by conflict than based on a genuine dialogue between judges. In order to ensure that economic operators have a better settlement of their disputes by avoiding the difficulties associated with judicial settlement, alternative dispute resolution tools should be promoted. Consequently, the adoptions of the Uniform Acts on Arbitration and Mediation have made it possible to give economic operators other alternative places to settle their disputes. In addition, the development of arbitration, mediation and conciliation centers seems to be an alternative to judicial jurisdictions. In view of the numerous referrals to the Ouagadougou Arbitration, Mediation and Conciliation Center by banks and financialinstitutions, insurance, transport and telecommunications companies, mining and energy companies, it can be deduced that this center plays an important role in the alternative settlement of commercial disputes in West Africa.
Keywords: ADR; Aide juridictionnelle; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Cassation; Development of arbitration, mediation and conciliation centers; Droit des affaires (régularisation); Développement des centres d’arbitrage, de médiation et de conciliation.; Judicial settlement of disputes; MARD; Mediación; Mediation; Mediação; Médiation; Organisation pour l'harmonisation en Afrique du droit des affaires; Règlement alternatif des litiges; Règlement de conflits; Règlement judiciaire des litiges; Standardization of jurisprudence; Uniformisation de la jurisprudence

L'Arbitrage familial international - Delobre, Anne-Sophie (Université Jean Moulin Lyon 3, 2021)
Comment évoquer un tel sujet sans s’émouvoir d’un antagonisme certain ? Les spécialistes du droit de la famille, conscients de l’importance de l’indisponibilité des droits, de la place de l’ordre public en la matière, des enjeux de protections des personnes concernées, sont souvent réticents à penser au concept de l’arbitrage familial international. A l’inverse, les spécialistes de l’arbitrage, habitués aux vertus du système, s’empressent de promouvoir « l’arbitrage pour tous » afin de conquérir un nouveau marché et répondre à une nouvelle demande. Ainsi, un dilemme naît : les litiges familiaux internationaux sont-ils arbitrables ? Dans une telle hypothèse comment pourrait être mis en œuvre l’arbitrage familial international ? C’est un sujet d’actualité, controversé, qui repose sur une idée qui n’est pas novatrice : sa vulgarisation sur la scène internationale ne serait pas une révolution. Il n’en demeure pas moins qu’une prudence s’impose dans une matière aussi sensible que le droit international de la famille. Face à la contractualisation croissante du droit de la famille, une voie médiane, pragmatique, d’un arbitrage familial international pourrait s’organiser par l’insertion d’une convention d’arbitrage dans les contrats internationaux de droit de la famille avant tout litige pour anticiper, organiser, les points épineux et éviter de douloureux procès. This dissertation addresses an issue that cannot be discussed without provoking concerns stemming from an indubitable antagonism. Family law specialists, who are aware of the importance of the unavailability of family-related rights, of the role of public policy rules in this area, and of the challenges involved in the protection of the persons concerned, are often reluctant to consider the concept of international arbitration in family matters. Conversely, arbitration specialists, who are familiar with the virtues of this procedure, are keen to promote “arbitration for all” in order to enter a new market and address a new demand. This gives rise to a dilemma: can family-related disputes be subject to arbitration? If so, how could arbitration procedures be implemented in this area? This is a current and topical issue, relying on an idea that is not novel: its general application on the international scene would not amount to a revolution. It remains however that caution must prevail in an area as sensitive as international family law. While family law is increasingly dominated by a contractual approach, a median and pragmatic solution might favour international family arbitration through the insertion of an arbitration clause in international family law contracts prior to any dispute in order to anticipate any thorny issue that might arise and organise its resolution, thus avoiding painful litigation.
Keywords: Arbitrability; Arbitrabilité; Arbitrage; Arbitrage international; Arbitragem; Arbitral court; Arbitration; Arbitration Agreement; Arbitration decision; Convention d'arbitrage; Disponibilité (droit); Droits indisponibles; Familial; Famille; Famille (droit); Family; International; Internationality; Internationalité; Litigation; Litige; Ordre public; Ordre public (droit international); Public policy; Sentence arbitrale; Tribunal arbitral; Unavailable rights

Les paradoxes de l'arbitrage institué par la Conférence Interafricaine des Marchés d'Assurances (CIMA) - Sindjui Siani, Brice Carlin (International Multilingual Journal of Science and Technology, 2021)
La constance dans l’arbitrage est sans doute la volonté dans le recours à ce mode de résolution de conflits. C’est parce que les parties trouvent un intérêt à l’arbitrage, qu’elles décident d’échapper à la compétence de principe des juridictions étatiques. Or, ce bel édifice est remis en cause par le législateur CIMA à l’article 276 par l’instauration d’une Commission Nationale d’arbitrage au sein des États membres dont les assureurs sont obligés de saisir lorsque nait un différend dans l’exercice des recours subrogatoires entre eux. Le paradoxe arbitral ainsi analysé comme ce qu’il est convenu d’appeler l’ « arbitrage forcé » n’empêche pas toute fois d’entrevoir dans ledit arbitrage institutionnel, un instrument au service de la justice et des assureurs tant les vertus sont variées.
Keywords: Arbitrage; Arbitration; Assureurs; CIMA; Commission Nationale d’Arbitrage; Insurers; National Commission of Arbitration; Recours subrogatoire; Recourse of subrogation

Proceedings of 2021 UNCITRAL Working Group III inter-sessional meeting: the use of mediation in ISDS - Asian Academy of International Law Limited (AAIL) (Asian Academy of International Law Limited, 2021)
Keywords: Dispute settlement; Investment disputes; MARD; Mediación; Mediation; Mediação; Médiation; UN Commission on International Trade Law; UN Convention on International Settlement Agreements resulting from Mediation (2018)

The arbitration of internal trust disputes in English law: Legal challenges and pathways - Clover Alcolea, Lucas (McGill University, 2021)
The arbitration of internal trust disputes has attracted significant attention in the arbitration and trust law communities in recent years with draft clauses and rules produced by arbitral institutions, several states undertaking legislative reform in order to provide such arbitrations with a statutory basis and numerous scholars as well as practitioners writing articles on the subject. Such enthusiasm is justified on the basis that arbitration has several advantages over litigation, such as confidentiality, international enforceability of judgments, the ability to choose one’s judge and the power to tailor the procedure. Notwithstanding these advantages, trust arbitration has failed to make any great inroad into trust disputes due to the many novel and complex points of legal practice and theory which it entails. For example, although arbitration does not typically involve minors or legally incapable parties’ trusts do, and thus trust arbitration raises numerous due process and human rights concerns. Similarly, court supervision and enforcement of trusts is sometimes considered essential to the very nature of trusts and questions therefore arise concerning the extent to which arbitral tribunals could supplant courts in that regard. Another complication is that trusts are not contracts and questions therefore arise about how to bind individuals to a trust arbitration agreement, particularly as regards beneficiaries who may be unascertained, minor or legally incompetent at the time the trust was created. The aim of this thesis is to analyse and present potential solutions to these complications from an English law perspective, although other common law legal systems will be analysed where relevant
Keywords: Arbitrage; Arbitragem; Arbitration; Internal trust disputes

Experimenting with international commercial dispute resolution - Erie, Matthew S; Bookman, Pamela K (AJIL Unbound, 2021)
In this essay, we describe the overlapping phenomena of new legal hubs (NLHs), international commercial courts, and arbitral courts. We survey their impact on the law and geopolitics of international commercial dispute resolution, identifying key issues these new dispute resolution institutions raise. While the rise of international commercial courts spans authoritarian and liberal states, Western and Asian states, common law and civil law traditions, it also highlights and builds upon regional differences. We question the assumption that the establishment of new courts is always consistent with an increase in the rule of law, particularly in non-democratic states. We close with thoughts about the potential influence and future role of these institutions. Some of the procedural innovations discussed here may lead to shifts in international commercial dispute resolution for years to come, but the question of whether there is sufficient demand for these new institutions lingers.

The Power of an Arbitral Tribunal to Determine Its Own Jurisdiction in International Commercial Arbitration - Kamanga, Patricia N. S. (Beijing Law Review, 2021)
Keywords: Arbitration Agreement; Competence-Competence; Jurisdiction; Party Autonomy; Power

Le financement de l’arbitrage par les tiers - Makhlouf, Amel (Revue internationale de droit comparé, 2021)
ruit de la pratique anglo-saxonne, le financement de l’arbitrage par un tiers financeur connaît un essor significatif tant à l’échelle nationale qu’internationale. Intervenu en France ces dernières années, ce mécanisme permet à un tiers (fonds d’investissement, société de financement spécialisée…) de financer une partie ou la totalité des frais relatifs à une procédure arbitrale tels que les frais d’avocats, d’experts, de témoins, d’arbitres ainsi que ceux liés à l’exécution de la sentence arbitrale. En cas de succès, le tiers financeur perçoit en contrepartie un pourcentage sur les dommages et intérêts alloués par la sentence arbitrale à la partie financée . Bien que dans une large majorité des cas le tiers financeur intervienne en faveur de la partie demanderesse, il peut aussi intervenir en faveur du défendeur ayant formulé une demande reconventionnelle. Le tiers financeur assume seul les risques financiers liés à la procédure. Si la partie financée n’obtient pas gain de cause à l’issue de la procédure arbitrale, le tiers ne percevra donc aucune rémunération et ne sollicitera auprès de son client aucun remboursement des frais qu’il aura avancés pour lui.

COFOLA International 2021: International and National Arbitration: Challenges and Trends of the Present and Future (Publications of the Masaryk University, theoretical series, editions Scientia, 2021)
- Virtual Arbitration Hearings in Times of COVID-19 (And Beyond); - International Arbitration and Blockchain: Current State, Types, Characteristics and the Future Perspective; - Use of Artificial Intelligence in Arbitration; - The Impact of Brexit on the Arbitration Procedure in Great Britain; - May Misapplication of EU Law Give Rise to International Responsibility of the Member State ... Under Investment Treaties? - International Investment Court System: The Future of Investment Dispute Settlement? - EU and Its New Mechanism for the ISDS in the Protection of FDI – What the Future Holds? - (Un)Clean Hands in International Investment Arbitration: Some Cleaning Required? - Challenges of Arbitrators in Inter-State Cases: A Different Cattle of Fish? - “Rules of Law” and Lex Mercatoria Determination Under the Auspice of ICC Arbitration; - Sources of Transnational Public Policy in International Commercial Arbitration; - Regulation of Arbitration Agreements Under New York Convention; - Comfortable Satisfaction Before the Court of Arbitration for Sport: Consistency Despite Differences? - Comparison of ICC Expert Report vs. ICC Arbitration Award; - Analysis of Civil Law Consequences of Corruption Under the Czech Law... in the Light of International Commercial Arbitration; - The Crime of Bending the Law From the Point of View of the Arbitrator ... of the Court of Arbitration and Application Practice; - The Arbitration Convention as One of the Measures to Eliminate Double Taxation ... in the European Union and in Slovak Republic; - Possibility of Resolving Individual Labor Disputes in Croatian Law by Arbitration; - What We Know, We Don’t Know About Macao’s Arbitration Framework and the Way Forward.

Yönetim kurulu krizleri ve çözüm yolları - Meti̇n, Umut (Kadir Has Üniversitesi, 2021)
YK farklı sorunlar veya uyuşmazlıklarla yüzyüze gelebilir. Sorunlar veya uyuşmazlıklar kriz halini alarak YK'nın işleyişine olumsuz etki edebilmektedir. Kriz derinleştikçe, YK işlevini yerine getirmekte zorlanabilir. Krizin bir adım ötesinde ise YK kilitlenebilmektedir. Pay sahipleri arasındaki menfaat çatışmaları, YK kriz ve/veya kilitlenmesinin en sık rastlanan temel nedenidir. Kilitlenme durumunda, YK toplantı yapamamakta veya karar alamamaktadır. Oysa ki, YK her daim çalışabilmesi gereken bir organdır. YK'nın kilitlenmesi, şirketin de kilitlenmesi sonucu doğurabilir. Bu durum öyle risklidir ki, şirketin feshi/tasfiyesi yakın bir ihtimal olabilmektedir. Bu aşamada kilidin olabildiğince hızlı açılması şirketten menfaati olan herkes için (pay sahipleri, YK üyeleri, çalışanlar, alacaklılar, kamu vb.) hayati önemdedir. Bu nedenle, şirket esas sözleşmesinde YK kriz ve kilitlenmelerine karşı önlemler planlanmalıdır. Tek kişiden ibaret YK modeli ve YK'ya danışma kurulu desteği kilitleme riskine karşı önerdiğimiz modeldir. Pay sahipleri sözleşmesi, aile şirketleri için aile anayasası gibi hukuki metinler kriz ve/veya kilitlenmeye ilişkin tedbirler içermelidir. Önlemlere, rağmen kilitlenme gerçekleşir ise, öncelikle YK içi ve şirket içi çözümler uygulamaya konulmalıdır. Bu tür yöntemler yeterli olmazsa, AUÇY'nin tatbiki, şirket dışından gelen çözümün ilk aşaması olarak kabul edilmelidir. Arabuluculuk ile YK kriz ve kilitlenmelerine karşı etkin, hızlı ve kalıcı çözümler sağlanabilmektedir. "Med-arb" veya "Arb-med" gibi yöntemlerden de faydalanılabilir. Tahkim de bir çözüm yoludur. Bu yolda "seri tahkim usulü" YK kilitlenmeleri için daha uygundur. Son çare olarak nitelediğimiz, dava yolu ise, bazı durumlarda içinde şirketin fesih ve tasfiye riskini barındırdığı için kilidi açmak ve hatta kilidi kırmak için uygulamaya konulabilir. Mahkemelerde, organ yokluğuna dayalı fesih davası ve özellikle haklı sebeple şirketin feshi davası çözüm sağlayabilecek dava tipleridir. Özellikle, haklı sebeple şirketin feshi davası, kriz ve kilitlenmelere daha uygun olup, stratejik sonuçlara da imkân vermektedir. Bunlar yanında, YK işleyişinde yapay zekâdan faydalanmanın mümkün olup olmadığı, yapay zekâya YK üyesi olarak kişi statüsü verilip verilemeyeceği, bu meselenin YK üyelerinin sorumluluğuna etkisi incelenmiştir. Board of Directors may face various disputes or disagreements. These disputes or disagreements may turn into crises which negatively affect the normal functioning of the board. As the crisis deepens, Board of Directors could have difficulties in fulfilling its function. Moreover, a step further from the crisis, Board of Directors might even be locked up. Conflicts of interest among shareholders are known as the most common cause of the board of directors crisis and/or deadlock. In event of a deadlock, Board of Directors, a body should always be able to function, cannot hold meetings or make decisions anymore. The deadlock of board of directors, may lead the entire company to be locked down whereas the company may encounter the possibility of dissolution and liquidation. At this point, unlocking the crisis as quickly as possible is vital for relevant competent persons of the company. Therefore, measures should be taken in the company's articles of association against Board of Director crisis and/or deadlock. One-person Board of Directors model and support of Advisory Board to Board of Directors is the model we recommend against the risk of locking. Legal texts such as shareholder agreements and family constitutions for family companies should include measures regarding deadlock. If a deadlock has occurred in spite of precautions, first of all, Board of Directors and internal remedies should be implemented. If such methods are not sufficient enough, Alternative Dispute Resolution (ADR) methods should be regarded as the first stage of external intervention. Effective and rapid solutions can be achieved against deadlocks via mediation. "Med-arb" or "Arb-med" could be also utilised. Arbitration is also a way and in this way; "expedited (fast-track) arbitration" procedure is more suitable for corporate deadlocks. Litigation, as the last possibility that we propose, could also be applied to unlock or even break the lock, since it contains the risk of dissolution and liquidation of company in some cases. In courts, termination action based on the absence of organs and especially termination of the company with a valid reason are the types of cases that may provide a solution. Especially termination of the company with a valid reason is more suitable for crisis and deadlocks, and also grants strategic results. In addition to these, it has been questioned in this study whether Board of directors possibly benefit from artificial intelligence in the operations and whether AI can be attributed a person-status as a member of Board of Directors. The effects of this issue on the responsibility of the members of Board of Directors have been analysed.
Keywords: Absence of body; Arabuluculuk; Arbitration; Artificial Intelligence; Board directors; Conseil d'administration; Crisis; Deadlock; Inteligência artificial; Intelligence Artificielle; Kilitlenme; Kriz; Mediation; Members of the board directors; Médiation; Organ yokluğu; Tahkim; Yapay zeka; Yönetim kurulu; Yönetim kurulu üyeleri

The prospective evolution of international commercial arbitration - Purqurian, Lily Leila (Revue libre de Droit, 2021)
“It is a curious fact that the Americanization of international arbitration is a topic that is often felt but is rarely discussed.” Roger P. Alford Similar to Alford’s sentiments, the shift towards arbitration in the United States alone is a phenomenon often felt, but feebly interrogated. Law schools across the nation continue to operate under the premise of judicial decision-making grounded in “rights protection.”[1] Yet, there is a clear shift towards arbitration as the preferred procedural process, with over 303,999 cases resolved by way of arbitration in 2019 alone.[2] While this brief note does not seek to interrogate the shift towards arbitration as much as it intends to examine the impact of American arbitration on international commercial arbitration generally, that shift, as you will see, looms in the background of any and all analysis of arbitration in the United States. I will begin by briefly noting the origins- and current regime of international commercial arbitration in the United States so to address the impact of its arbitration law and arbitral institutions on arbitration globally. I will then offer thoughts on the prospective evolution of international arbitration in the United States and how that may change the directions of legal procedural processes both in the United States and abroad. I. ORIGINS- AND CURRENT REGIME OF INTERNATIONAL ARBITRATION IN THE USA As arbitration flourishes as the choice for commercial disputes, there is no doubt that the United States has become a newfound hub for arbitration. It was not always this way, however. The Federal Arbitration Act (FAA) of 1925 established a steady road to an increasingly pro-arbitration policy, in three chapters, that shows itself in case-law as: when in doubt, favor arbitration.[3] The first chapter of the FAA establishes the framework for arbitration seated in the U.S. and provides the grounds for enforceable arbitration agreements and awards, while the second and third chapters implement the 1958 New York Convention and 1975 Panama Conventions, respectively. The strictly pro-arbitration policy does not lack in its own confusion, however, because of its basis in an otherwise federalist system. The FAA has largely remained unchanged since its nascence and has thus, left a substantive amount of discretion in interpreting arbitration law in the United States to the Supreme Court. One such source of confusion in U.S. arbitration law due to a lack of amendment lies in the term “arbitrability.” Arbitrability is the susceptibility of a case to be resolved by way of arbitration. In order to define the parameters of this susceptibility, the Supreme Court has distinguished between “procedural” and “substantive” arbitrability, wherein the former concerns itself with “prerequisites such as time limits, notices, laches, estoppel, and other conditions” and the latter, with a court’s decision.[4] The benefits to arbitration remain unmatched for commercial entities, however, which inspires the aforementioned pro-arbitration policy despite any real judicial framework. Arbitration allows parties to customize their dispute resolution by choosing the venue, applicable procedural law, and an expert adjudicator who may be more familiar with the intricacies of the dispute, among other benefits. There is a commitment to secrecy that is not found in the common court and the single, binding, and final resolution of a dispute through arbitration is the precise source of criticism that inspires the flock towards arbitration. Without the federal rules of civil procedure that would otherwise govern litigation, arbitration is governed by the procedural rules that each side agrees upon. The FAA paved the way for case law in the United States that would eventually shape a stronger pro-arbitration policy than ever—counseling against “even the mildest interference by courts in the conduct of U.S.-seated arbitrations.”[5] II. THE IMPACT OF U.S. ARBITRATION LAW AND U.S. ARBITRAL INSTITUTIONS IN THE WORLD OF ARBITRATION Assessing the impact of U.S. arbitration law begins by assessing what characterizes U.S. law: civil procedure. The adversarial form of litigation in which procedural tools are employed by advocates to advance arguments in a distinct style distinguishes the United States from other countries—and this feature inevitably slipped, in some capacity, into global arbitral institutions. Because the Rules of Arbitration for the International Chamber of Commerce are so brief,[6] American lawyers had tremendous flexibility in bringing American trial procedures with them. This came specifically in the form of document production for discovery and cross-examinations “to confront adverse witnesses.”[7] Critics refer to these added procedures as costly in both time and expense, defining them as the source of the “Americanization” of arbitration. Yet, while there is truth to such criticism, it may be more accurate to acknowledge the incorporation of aspects of American trial procedure as one country’s influence on arbitration. Far from inheriting solely American practice, global arbitral institutions maintain classic procedural tools while assimilating facets of each major country’s influence on arbitration.[8] III. THE PROSPECTIVE EVOLUTION OF INTERNATIONAL ARBITRATION IN THE USA Apart from being a source of revenue,[9] international arbitration is the natural response to the increase in “trade, investment, and supply-chain relationships” that hope to live free of potential biases from domestic fora.[10] The California Supreme Court may have briefly lost sight of this when deciding Birbrower, wherein attorneys not admitted to the bar of a certain state are not only ineligible to recover attorney’s fee but also, may be fined for unauthorizing practice of law.[11] Since Birbrower over two decades ago, however, the California Legislature unanimously passed Senate Bill 766. Under SB 766, non-California lawyers are able to represent parties in international arbitration proceedings in California, bringing California to the arbitration table. As home to Silicon Valley – and even aside from big technology, home to some of the largest companies in the world – California’s SB 766 will bring a swath of arbitration proceedings to its terrain. While California may certainly work in tandem with New York as the home to arbitration for technology and privacy concerns, reserving trade and investment disputes for New York, California may very well be the next major hub of arbitration. Already, it has received massive interest in being an arbitration destination. SB 766 will transform that interest into a revenue. It thus becomes all the more important, internationally, to understand and confront the ways in which the Americanization of arbitration would take place. [1] See, e.g. Thomas E. Carbonneau, Revolution in Law Through Arbitration, The Eighty-Fourth Cleveland-Marshall Fund Visiting Scholar Lecture, 56 Clev. St. L. Rev. 233, 233 n.3 (2008), available at https://engagedscholarship.csuohio.edu/clevstlrev/vol56/iss2/3 (“judicial decision-making has shifted from rights protection to guaranteeing access to some form of adjudication. As a result, law and adjudication have become less sacramental.”) [2] See American Arbitration Association, Adr.Org, https://adr.org/ (last visited Dec. 28, 2019). [3] See, e.g., Moses H. Cone Memorial Hosp. v. Mercury Construction Corp., 460 U.S. 1, 24-25 (1983) (“[A]ny doubts concerning the scope of arbitrable issues should be resolved in favor of arbitration …”). [4] See Howsam v. Dean Witter Reynolds, Inc., 537 U.S. 79, 85 (2002) (distinguishing between “issues of substantive arbitrability [which] are for a court to decide and issues of procedural arbitrability, i.e., whether prerequisites such as time limits, notice, laches, estoppel, and other conditions precedent to an obligation to arbitrate have been met, [which] are for the arbitrators to decide.”) (citations omitted). [5] See Laurence Shore, Tai-Heng Cheng, Jenelle E. La Chuisa, Lawrence Schaner, and Mara V.J Senn, International Arbitration in the United States 1, 320 (2018). [6] George M. von Mehrem and Alana C. Jochum, Is International Arbitration Becoming Too American?, 2 Global Bus. L. Rev. 47, 51 (2011) available at https://engagedscholarship.csuohio.edu/gblr/vol2/iss1/6. [7] Id. [8] Philip J. McConnaughay, Introduction to International Commercial Arbitration in Asia 1, xxix (2002). In support of his assertion, McConnaughay reports that from 1995 to 2000, China’s leading international arbitration commission, CIETAC, received 4,200 new international commercial arbitrations and the Hong Kong International Arbitration Centre (HKIAC) received 1,394, totaling 5,594. Id. Note: interrogatories and depositions are not included. [9] See ICC (International Chamber of Commerce), ICC Arbitration Figures Reveal New Record for Awards in 2018, https://iccwbo.org/media-wall/news-speeches/icc-arbitration-figures-reveal-new-record-cases-awards-2018/. [10] Daily Journal, International Arbitration Finally Comes to California, Howard B. Miller, https://www.dailyjournal.com/mcle/330-international-arbitration-finally-comes-to-california. [11] See generally, Birbrower, Montalbano, Condon & Frank v. Superior Court, 17 Cal. 4th 119 (1998).
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; International Arbitration

L'arbitrage en droit aérien et spatial - Soliveres, Théo (Aix-Marseille Université, 2021)
Keywords: Arbitrage; Arbitration; Droit aérien; Droit spatial

UNCITRAL Expedited Arbitration Rules - UNCITRAL (United Nations, 2021)

Chapter II: The Arbitrator and the Arbitration Procedure, An Arbitrator’s Imperative – How to Avoid Disappointing the Parties, Preventing Surprises and Enabling Efficient and Progressive Arbitral Proceedings - Welser, Irene; Mimnagh, Samuel (Austrian Yearbook on International Arbitration, 2021)

مراكز التحكيم البحري - بلقاسم, حبيب (Université d'Oran 2 Mohamed Ben Ahmed, 2021)
"Les centres d’arbitrage maritime." Résumé : Le sujet des centres d'arbitrage maritime concerne le processus de résolution des contentieux maritimes quand leurs parties optent pour soumettre leur différend à des instances d'arbitrage comme voie alternative. Les centres d'arbitrage maritime appliquent le règlement arbitral et ses règles dans le cas où le choix est fait en fonction de la clause compromissoire qui inclut ce choix ainsi que la loi applicable. Lacompétence de cet instance d'arbitrage convenue débute à la date de la soumission de la demande d'arbitrage, afin de lui confier le suivi des procédures d'arbitrage et de tout ce qui touche au litige arbitral et jusqu' à ce que la sentence (décision) arbitrale soit rendue. "Maritime arbitration centers." Summary: The subject of maritime arbitration centers concerns the process of resolving maritime disputes when their parties opt to submit their dispute to the arbitral tribunal as an alternative solution, and maritime arbitration centers apply arbitration regulations and its rules in case where the choice is made according to the arbitration clause which includes this choice as well as applying the law on all disputes. The arbitral tribunal function starts from the date of submitting the arbitration request to it to be entrusted with following up the arbitration procedures and everything related to the arbitration dispute and until the arbitral award is issued. : الملخص يتعلق موضوع مراكز التحكيم البحري بعملية فض المنازعات البحرية التي يختار أطرافها عرض النزاع على هيئات التحكيم كطريق بديل، و مراكز التحكيم البحري تعمل على تطبيق لوائح التحكيم و نظامها التحكيمي في حال وقوع الاختيار عليها وفقا لشرط التحكيم الذي يتضمن هذا الاختيار، إلى جانب القانون الواجب التطبيق على النزاع. و يبدأ اختصاص هذه الهيئة في التحكيم المؤسسي من تاريخ تقديم طلب التحكيم إليها، ليوكل لها متابعة إجراءات التحكيم و كل ما يتعلق بالمنازعة التحكيمية و إلى غاية صدور الحكم التحكيمي.
Keywords: Application for arbitration; Arbitral Awards; Arbitration; Centres d'arbitrage maritime; Clause d'arbitrage maritime; Demande d'arbitrage; Décision d'arbitrage; Maritime arbitration centres; Maritime arbitration clause

رقابة القضاء على أعمال المحكمين - غزيزات, دليلة (Université d'Oran 2 Mohamed Ben Ahmed, 2021)
رقابة القضاء على أعمال المحكمين من بين أوجه الرقابة التي أقرتها التشريعات الحديثة وقوانين التحكيم الوطنية و الإتفاقيات الدولية وكذا نظام التحكيم في ظل تطور الثقافة التحكيمية في الوقت الراهن. كما تعد ضمانا وحماية للمصالح وحقوق الأفراد والشركات التجارية من جهة وتُمكن القضاء من السيطرة على تصرفات المحكمين وحماية شخصهم في الدعوى التحكيمية لتحقيق فاعلية نظام التحكيم من جهة ثانية. Le contrôle des actes des arbitres est établi par les législations récentes et par la législation arbitrale nationale, ainsi que par les conventions internationales en la matière. Il participe à l’évolution de la culture arbitrale et constitue une garantie et une protection des intérêts des individus et des sociétés commerciales. Il permet d’avoir une vue sur les travaux des arbitres d’une part, et sur leur protection d’autre part, pour assurer l’efficacité de l’arbitrage. The review of the acts of the arbitrators shall be established by recent laws and national arbitral legislation and international conventions on the subject. It contributes to the evolution of the arbitral culture and constitutes a guarantee and protection of the interests of individuals and commercial company’s .It allows having a view on the work of the arbitrators on the one hand, and on their protection to ensure the effectiveness of arbitration
Keywords: Arbitral proceedings; Arbitration; Arbitrator; Arbitre; Contrôle; Judge; Juge; Procédure arbitrale

国际商事仲裁费用构成及合理控制仲裁费用探索 - 侯, 进才 (Journal of Oil and Gas Technology, 2021)
仲裁作为解决国际商事争议的主要方式之一，受到国际工程承包企业的青睐，然而当事人在决定一个案件是否要提起仲裁时，常会把仲裁费用作为一个重要考量指标，高昂的仲裁费用可能会限制国际商事仲裁制度的健康发展。本文以2017版国际商会仲裁规则下的收费标准为基础，从仲裁费用的构成、计算方法入手，探讨了仲裁费用影响因素，并给出了控制仲裁过程费用的合理化建议。 Arbitration, as one of the main ways to resolve international commercial disputes, remains a popular choice for international engineering company. The arbitration fees will be an important evaluating indicator when the parties considering apply for arbitration. Expensive arbitration fees may restrict the healthy development of international commercial arbitration system. Based on the arbitration cost and fees under the arbitration rules of the 2017 edition of the International Chamber of Commerce, characteristics, composition and calculation method of the arbitration fees are showed in this paper firstly; then, its influencing factors are discussed. Reasonable suggestions for controlling the arbitration fees are given in the end of this paper.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration Fees; Composition of Arbitration Fees; Controlling the Arbitration Fees; International Commercial Disputes; 仲裁费用; 国际商事; 控制费用; 费用构成

Foreign Investments in Disputed Maritime Zones: Maritime Disputes as Events of Force Majeure in International Law and International Investment Contracts - Kassem, Hazem (BAU Journal - Journal of Legal Studies, 2020)
Sovereign rights in Exclusive economic zones and Continental shelves are functionally limited to the economic exploitation of these zones. Moreover, in the case of disputed maritime zones these sovereign rights are neither exclusive nor necessarily constant. Nevertheless, states are still expected to provide the investments established in these zones the same treatment they should provide in their territories where they exercise full and constant sovereignty. If a host state agrees to the establishment of an investment in a maritime zone that become later contested, do the occurrence of the contestation and the hazards arising from such contestation relief the host state from its contractual and treaty obligations toward the investment by virtue of the force majeure concept. This paper argues that a traditional interpretation of the force majeure concept in respect of investment agreements and contracts, hampers states ability to de-escalate their maritime disputes, diminishes its capacity to conclude delimitation agreements and reduces the promotion of the UNCLOS III as well as its mechanisms for disputes settlement. It proposes a contextualist interpretation of the force majeure concept that is adapted to the exploitation of disputed maritime zones and states obligations under the international law of the sea. First, it examines the concept of force majeure as a doc-trinal hypothesis and its applications in international contracts and international in-vestment agreements. Second, it analyzes the legal act of maritime contestation as a force majeure event according to the possible interpretations of the concept of “force majeure”. Finally, it examines the recurrent legal implications susceptible of arising out of a contestation; provisional orders and unfavorable delimitation and their qualifica-tion as a force majeure event in the realm of investment agreements and contract.
Keywords: BIT; Disputed maritime zones; Force majeure; Foreign investment; Investment contracts; Maritime contestation; Maritime delimitation; Provisional measures

La portée de la conciliation préalable en matière de procédures simplifiées de recouvrement de l'OHADA dans la réalisation des droits du créancier - Tonda, Franck (International Multilingual Journal of Science and Technology, 2020)
Keywords: Conciliation; Créancier; MARD; Procédure simplifiée; Recouvrement de créances

L'arbitrage international et les contrats de transfert de technologie en droit comparé : France, Syrie, Égypte - Al Youssef, Omar (Aix-Marseille Université, 2020)
La France en tant qu’un pays développé possède une richesse juridique et judiciaire à propos de l’arbitrage et des contrats de transfert de technologie. Alors que la Syrie n’a pas jusqu’à ce moment un système juridique spécial à ces contrats. En plus, la loi syrienne de 2008 sur l’arbitrage a besoin d’être modifiée en raison des erreurs juridiques massives commises dans cette loi. S’agissant de l’Égypte, la loi de 1999 sur le commerce a mis en place un système juridique solide pour régir les contrats de transfert de technologie et l’arbitrage. Il faut mentionner que la jurisprudence égyptienne est très développée par rapport à la jurisprudence syrienne, ce qui me permet de faire une comparaison entre la France et les deux pays en développement. France as a developed country has a wealth of legal and judicial matters relating to arbitration and technology transfer contracts. While Syria does not yet have a special legal system for these contracts. In addition, Syria's 2008 arbitration law needs to be amended due to massive legal errors in that law. In Egypt, the 1999 trade law established a strong legal system to govern technology transfer contracts and arbitration. It should be mentioned that Egyptian case law is very developed compared to Syrian case law, which allows me to make a comparison between France and the two developing countries.
Keywords: Approche comparée; Arbitrage; Arbitrage international; Arbitragem; Arbitration; France; Syrie; Transfert de technologie; Égypte; Étude comparative

Limites da jurisdição e das decisões jurisdicionais estatais no âmbito da internet - Laux, Francisco de Mesquita (Universidade de São Paulo, 2020)
A tese tem como objetivo desenvolver as relações entre o exercício da jurisdição - especialmente, a limitação territorial de eficácia das decisões - e os conflitos vinculados à postagem de manifestações infringentes na internet. A hipótese central defendida pela tese é a de que a jurisdição e as decisões judiciais estatais, quando direcionadas a remover postagens na internet, têm seu espectro de eficácia limitado ao território do Estado em que proferidas. Isso significa dizer que pessoas que se conectam à internet a partir de outros Estados não podem ser diretamente impactadas pelo comando. A tese busca demonstrar, ainda, que o modelo de reserva de jurisdição estatal não é efetivo, independentemente de critérios de eficácia territorial, para solução de problemas especialmente vinculados à disseminação em massa de manifestações danosas. A tese foi dividida em três capítulos. No primeiro, o objetivo será o de estabelecer os princípios e regras vinculados às ideias de jurisdição internacional de acordo com a legislação brasileira de direito processual civil e direito internacional privado. Na segunda parte, será a vez de abordar os temas em referência a partir das perspectivas trazidas por ordenamentos jurídicos estrangeiros, especialmente recentes pronunciamentos advindos dos Estados Unidos da América e do Tribunal de Justiça da União Europeia a respeito dos limites territoriais de decisões judiciais destinadas a produzir efeitos na internet, além da apresentar uma breve contextualização de como outros países - como China, Brasil, Argentina e México - encaram fenômenos vinculados ao ambiente virtual. No terceiro e último capítulo, tais soluções serão compatibilizadas de modo a delimitar a amplitude territorial da jurisdição e das decisões jurisdicionais estatais nos casos que envolvem conflitos para retirada de postagens na internet. O capítulo abordará, também, a perspectiva de processos e decisões não estatais, adotados por gestores de redes sociais ou tribunais privados em um ambiente de autorregulação regulada, e de que modo isso pode ter reflexos no direito processual sob a ótica das noções de online dispute resolution (ODR). The thesis aims to reveal the relationship between jurisdiction (more specifically, its territorial scope/range) and the conflicts linked to posting abusive or illegal statements on the internet. The main hypothesis of the thesis is that jurisdiction and decisions rendered by the Judiciary, when directed to remove posts on the internet, have their scope/range limited to the territory of the State in which they are rendered. This means that people who connect to the internet from other States cannot be directly impacted by the decision. The thesis also seeks to demonstrate that the state jurisdiction reserve model is not effective, regardless of territorial effectiveness criteria, for solving problems especially linked to the mass dissemination of harmful manifestations. The thesis was divided into three parts. Part 1 aims to establish the principles and rules linked to the ideas of international jurisdiction in accordance with Brazilian legislation on civil procedural law and private international law. Part 2 discusses the issues in reference from the perspectives brought by foreign legal systems, especially recent pronouncements from the United States of America and the Court of Justice of the European Union regarding the territorial scope/range of judicial decisions aimed at produce effects on the internet, in addition to presenting a brief contextualization of how other countries - such as China, Brazil, Argentina and Mexico - face phenomena linked to the virtual environment. In the third and last part, such solutions will be compared in the objective of delimiting the territorial scope of the jurisdiction and of the state jurisdictional decisions in cases involving conflicts for the removal of posts on the internet. The chapter will also address the perspective of non-state processes and decisions, adopted by managers of social networks or private courts in an environment of "regulated self-regulation", and how this may have an impact on procedural law from the perspective of notions of online dispute resolution (ODR).
Keywords: Argentina; Brasil; Chile; China; Competência territorial; Direito Comparado; Direito Processual; Estados Unidos; Europa; Internet; Jurisdiction; Jurisdição; Jurisdição internacional; MARD; Mediación; Mediation; Mediação; Mediação e conciliação; Médiation; México; Mídias sociais; ODR; Online Dispute Resolution; Regulated selfregulation; Scope of jurisdiction; Social networks; Territory

International Commercial Arbitration - Kizi, Boratova Ziyoda Sobir (International Journal of Trend in Scientific Research and Development, 2020)
This article is devoted to the complex analysis of the English legislation of the international commercial arbitration. The author analyzed the commercial disputes and the bodies that proceed these disputes in England as well as main statutes regulating the international commercial arbitrations of England. The international commercial practices of the London International Court of Arbitration are described. Moreover, the author represents the main conclusions formed on the basis of the provisions of the national legislation on commercial arbitration and the regulations of the most well-known international arbitrations in England.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Act 1996; Arbitration institution; Commercial disputes; International commercial arbitration; The LCIA Rules; The London International Court of Arbitration (LCIA)

O recurso à arbitragem no âmbito das sociedades comerciais : os conflitos societários internos - Vaz, Juliana Touro Cerejo Rabaça (Universidade Católica Portuguesa, 2020)
A presente dissertação tem como objetivo analisar, à luz do ordenamento jurídico português, a possibilidade e adequação do recurso ao instituto da arbitragem como meio de resolução dos litígios intrassocietários, isto é, os litígios emergentes das relações entre os sócios de uma sociedade, os resultantes das relações entre os sócios e a própria sociedade, ou ainda no âmbito das relações entre os sócios ou a sociedade per si e os titulares dos órgãos de administração ou de fiscalização da mesma. Para tal, foi inicialmente adotada uma perspetiva comparatística com outros ordenamentos jurídicos. Posteriormente, foi adotada uma abordagem expositiva, do instituto da arbitragem em Portugal, analisando inicialmente de um modo geral, especificando depois o propósito principal da presente dissertação – a arbitrabilidade dos litígios intrasocietários, nomeadamente o regime da convenção de arbitragem, do tribunal arbitral e da própria sentença arbitral. Avaliadas as vantagens e os inconvenientes do recurso à arbitragem enquanto meio de resolução alternativa de litígios, e a sua aplicabilidade aos litígios intrassocietários, tomando como referência a escassa regulamentação deste instituto neste domínio no nosso ordenamento jurídico, conclui-se a presente dissertação com uma proposta de regulamentação legal e outra estatutária da arbitragem dos referidos litígios intrasocietários.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Entreprises commerciales; Litige interne

التحكيم رديفاً للقضاء في حل المنازعات - دراسة فقهية - Abu Lail, Mohammad (Jordan Journal of Islamic Studies, 2020)
Arbitration is considered as one of the basic means that has been legislated by Islam to resolve the people's disputes. Usually the resolutions of the arbitration are fast, guarantee the rights, respect the essence of justice and reduce the level of the controversy. Today, arbitration plays a vital role in resolving the international disputes such as the economic, political and local disputes as long as its effect upon the resolution of the internal disputes. This study highlights on the arbitration role in resolving the disputes as along with judiciary through showing the advantages of the arbitration and explain the relationship between arbitration and judiciary. And clarify its areas and its implications in jurisprudence. This study found out that the arbitration has a pivotal role in resolving the disputes resulting from the contractual and non-contractual relationships and the disputes resulting from the people in their natural and moral capacity, both internally as well as externally The study has shown the jurisprudence has taken the lead in explaining the terms and effects of the arbitration.

Le rôle de la confidentialité dans la procédure préventive de conciliation de l’OHADA - Nkouamo Ngnegue, Luc Norbert (International Multilingual Journal of Science and Technology, 2020)
La procédure de conciliation est l’une des innovations de la réforme de l’Acte Uniforme relatif aux procédures collectives d’apurement du passif. Le législateur OHADA l’a institué dans l’objectif de mieux gérer la prévention de la cessation des paiements des entreprises en difficulté financière. La conciliation est entrée dans la sphère des procédures collectives de l’OHADA avec un principe clé à savoir la confidentialité. Le principe de confidentialité constitue une pierre angulaire de la conciliation au regard de la place qu’elle occupe dans le dénouement de celle-ci. Le législateur communautaire fait intervenir ce principe dans tout le dénouement de la conciliation. La confidentialité se présente ainsi comme un aspect phare de la procédure. Cet état de chose nous a alors amené à s’interroger sur le rôle que peut bien jouer cette confidentialité qui anime l’ensemble de la procédure préventive. Selon notre point de vue, la confidentialité joue un double rôle dans la procédure de conciliation. Elle favorise d’une part la protection du débiteur soumis à la procédure en lui assurant la préservation de son crédit ainsi que les informations divulguées et d’autre part, facilite l’efficacité de la procédure à travers son imposition générale même si elle est un peu fragilisée par certaines atteintes. The procedure of conciliation is an innovation of the uniform Act organizing the legal treatement enterprises difficulties. The OHADA lagislator has institute it with the objective for the better manage in the suspension of payments prevention for enterprises in financial difficulty. The conciliation procedure has come in the sphere of OHADA legal treatement enterprises difficulties with a main principle which is confidentiality. The principle of confidentiality constitute a cornerstone of the conciliation procedure ending according to the Sport place it occupe. The Community legislator makes this principle to intervene in all the conciliation procedure. The confidentiality is present as a main aspect of the procedure. This situation brought us to question the role of the confidentiality witch lead all the preventive procedure. According to our point of view, the confidentiality plays a double role in the conciliation procedure. It favours firstly the protection of the debtor submit to the procedure insuring the preservation of his credit as well as divulgates informations and secondly, it facilitate the effectiveness of the procedure by his general using even it is fragilize by certains attacks.
Keywords: Cessation des paiements; Conciliation; Confidentiality; Confidentialité; Debtor protection; Efficacité de la procédure; Procedure effectiveness; Protection du débiteur; Suspension of payments

The Changing Paradigm of International Tax Dispute Settlement: What Are the Promises and Challenges of Mandatory Arbitration for China? - Ji, Xueliang (Oregon Review of International Law, 2020)
Through comparing dispute resolution methods under bilateral investment treaties (BITs) and bilateral tax treaties, this Article critically discusses the advantages of incorporating mandatory arbitration in bilateral tax treaties and demonstrates that national sovereignty will not be decreased by it. As a result, the Article argues that it would, in fact, be beneficial for China to adopt the mandatory arbitration method, which would further strengthen the global reform initiated by the OECD.
Keywords: China; Dispute resolution; International tax law

Reimagining the Framework for Resolving Intra-African Commercial Disputes in the Context of the African Continental Free Trade Area Agreement - Onyema, Emilia (World Trade Review, 2020)
This article examines the effectiveness of the framework for the resolution of intra-African cross-border commercial disputes, arising from the projected increase in intra-African trade in goods, services, and investments under the African Continental Free Trade Area. It examines the peculiar nature of intra-African trade and of the participating entities to provide the context to discuss the three major processes adopted in commercial dispute resolution (litigation, mediation, and arbitration) in Africa. It then argues for the promotion of arbitration as the dispute resolution process of choice for such disputes. It reimagined the framework for arbitration at the continental level and made two proposals targeted at the greater efficiency of the process: the designation of Regional Arbitration Centres across the African Union's eight recognized Regional Economic Communities, to administer such references; and the establishment of an African Commercial Court as a one-stop court for the enforcement or annulment of the final award.
Keywords: AfCFTA; Arbitrage; Arbitragem; Arbitration; Commercial dispute; Dispute Resolution; Litigation

Dos efeitos da falência sobre a arbitragem - Deccache, Antonio Carlos Fernandes (Universidade de São Paulo, 2020)
Esta tese analisa os efeitos da falência sobre a arbitragem. A falência constitui um regime complexo, formado por regras materiais e processuais, criado para lidar com o problema da insolvência empresarial. Tem natureza de execução coletiva, reunindo todos os credores do falido e todos os seus bens, que devem ser liquidados a fim de pagar os credores. Para a consecução dos seus objetivos, a decretação da falência opera efeitos diretos sobre a pessoa do devedor, seus bens, seus contratos e seus processos. O processo falimentar realiza-se mediante procedimento administrado pelo Poder Judiciário, centralizado, público, com a finalidade de lidar com os diversos interesses envolvidos. Diversamente, a arbitragem é meio privado de solução de controvérsias pelo qual partes capazes elegem um terceiro, da sua confiança, para resolver litígio versando sobre direitos patrimoniais disponíveis. Tem natureza jurisdicional e caracteriza-se por constituir alternativa privada, rápida, flexível e especializada de dirimir demandas que admitem transação. Seu procedimento tem natureza de processo de conhecimento, terminando com a prolação de sentença, e constitui processo descentralizado, privado, usualmente sigiloso, no qual as partes têm ampla liberdade para definir as regras materiais e processuais aplicáveis. Enquanto a falência constitui sistema que visa lidar com interesses de ordem pública -- sendo, portanto, controlado pelo Estado, centralizado, público e coletivo --, a arbitragem pauta-se na autonomia da vontade, na descentralização do sistema de resolução de litígios, lida com interesses privados e é usualmente sigilosa. Considerando as relevantes diferenças entre os dois institutos, questiona-se em que condições a falência e a arbitragem podem coexistir. O que se propõe neste trabalho é, portanto, analisar quais são os efeitos que a falência opera sobre a arbitragem e como esses efeitos impactam na convivência entre os dois institutos. Para tanto, este estudo organiza-se em duas partes: parte I, na qual são apresentadas noções introdutórias da falência e da arbitragem, que servem para assentar as premissas utilizadas na análise; e parte II, na qual são analisados os efeitos propriamente ditos da falência sobre a arbitragem. A parte I está dividida em dois capítulos, nos quais se trata, sucessivamente, da falência e da arbitragem. Já a parte II está dividida em três capítulos, nos quais se trata, sucessivamente: (i) dos efeitos da falência sobre a convenção de arbitragem; (ii) dos efeitos da falência sobre o procedimento arbitral; e (iii) dos efeitos da falência sobre a sentença arbitral. Ao final, conclui-se que, apesar de a falência operar efeitos sobre alguns aspectos da arbitragem, impondo-lhe limites no contexto falimentar, isso não as torna incompatíveis. Aduz-se que a falência não invalida a convenção arbitral celebrada antes da falência, nem impede sua celebração pelo administrador, que, entretanto, depende de autorização judicial. Comprovase, também, que o advento da falência não atrai nem suspende os procedimentos arbitrais, mas impõe condições para que o processo possa se desenvolver. Por fim, evidencia-se que a sentença arbitral, uma vez proferida, deve ser submetida a verificação no processo falimentar.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Arbitration Award; Arbitration Proceeding; Bankruptcy; Direito falimentar; Falência; Insolvency; Juízo arbitral; Procedimento especial

The Applicability of Mediation as an Alternative Dispute Resolution Mechanism under OHADA Law - Leinyuy, Kifemmabuh Antonia (Scholars International Journal of Law Crime and Justice, 2020)
Almost 20 years after it adopted the Uniform Act on Arbitration, OHADA revised its Uniform Act on Arbitration and adopted a new Uniform Act on Mediation along with the fresh set of arbitration rules of the Common Court of Justice and Arbitration in Abidjan. These three texts were revised with the assistance of consultants. Among other changes, with the 2018 Uniform Act on Mediation, a solid platform for the use of mediation in the region is now in place. The ability of mediators to carry out their adjudication function with judicial intervention remains a major challenge by parties under the OHADA zones. In this light, the worry which this article seeks to uncover is how the new mediation law is applicable and facilitates the amicable settlement of investment disputes. The article also highlights the legal basis regulating the mediation process as a whole. In attaining these objectives, we employ doctrinal research methodology. The article conclude with vigorous recommendations which if effectively implemented will go a long way to enhance business (investment) security.
Keywords: ADR; Alternative dispute resolution; Applicability; Dispute resolution mechanism; MARD; Mediación; Mediation; Mediação; Médiation; OHADA Uniform Act

Letztwillige Schiedsverfügungen : Geltungsgrund und Geltungsgrenzen - Gleim, Jakob (Studien zum ausländischen und internationalen Privatrecht, 2020)
Nach §1066 ZPO gelten die Vorschriften über vertraglich vereinbarte Schiedsgerichte entsprechend für "Schiedsgerichte, die in gesetzlich statthafter Weise durch letztwillige [...] Verfügungen angeordnet werden". Während solche letztwilligen Schiedsverfügungen im 20.Jahrhundert sehr selten waren, beschäftigen sie heute die deutschen Gerichte mit gewisser Regelmäßigkeit. Mit Zunahme der praktischen Relevanz rücken auch die dogmatischen Grundlagen letztwilliger Schiedsverfügungen in den Fokus: Warum darf der Erblasser nicht nur materielle, sondern auch prozessuale Verfügungen von Todes wegen treffen? Wie weit reicht die Zuständigkeit des letztwillig eingesetzten Schiedsgerichts? Und welches Recht ist anzuwenden, wenn der Erbfall grenzüberschreitende Bezüge aufweist? Jakob Gleim beantwortet diese Fragen und bezieht dabei im Rahmen eines Rechtsvergleichs auch das US-amerikanische Recht ein. Fürdie vorliegende Dissertation wurde Jakob Gleim mit der2020 der Max-Planck-Gesellschaft ausgezeichnet. Is it possible for the testator to mandate unilaterally that all disputes concerning the estate are to be arbitrated instead of litigated? While such a testamentary arbitration clause is an expression of the decedent’s freedom of disposition, it contradicts the beneficiaries’ right of access to a public court. In his dissertation, Jakob Gleim examines the tension between the decedent’s freedom of disposition and the rights of the beneficiaries, balancing these two positions against one another and thereby identifying the reasons and the limitations of the validity of testamentary arbitration clauses. While such clauses were rather rare in the 20th century, German courts have to deal with them more regularly nowadays. In his dissertation, Gleim explores the practical significance of testamentary arbitration clauses as well as their advantages and disadvantages. The author also addresses the questions of how far the jurisdiction of the arbitral tribunal extends and which law is to be applied in cross-border cases. The inquiry also includes insights gained from a comparative analysis of US-American law.
Keywords: Arbitaje; Arbitrage; Arbitragem; Arbitration; Arbitration clause; Bankruptcy; Clause d'arbitrage; Insolvency; Mediation; Negotiation

The Standards for Proving Damages and Its Amount: A Comparative Study under Transnational Instruments and International Arbitration Awards - Shoarian, Ebrahim; Sahebjam, Sara (Public Law Researsh, 2020)
Defining the applicable standards for proving and measurement of damages constitute one of the most significant issues under the law of damages. In principle, an aggrieved party, who claims compensation for damages based on contractual liability is responsible for showing the existence and the amount of losses suffered or to be suffered. Due to great importance of the issue, transnational instruments of contract law, such as UNIDROIT Principles of International Commercial Contracts (UPICC), Principles of European Contract Law (PECL) and Draft Common Frame of Reference (DCFR) have set out, explicitly or implicitly, special standards such as reasonable certainty, reasonably likely to occur and so on for proving damages; By contrast, the Iranian laws and regulations including the Civil Code do not set out such standards. The legal scholarship and jurisprudence have also failed to address the issue. Therefore, a comparative study of the issue with particular look at international instruments and arbitral awards could provide a reliable source of guidance. This paper analyzes the general and specific standards for proving damages and those situations that fall outside of ambit of the standards such as late payment damages. By doing so, the paper tries to open the debate in Iranian law. یکی از موضوعات قابل توجه در حوزه حقوق خسارت، تعیین استانداردهای قابل اعمال برای اثبات خسارات و میزان آنها است. علی القاعده، زیان‌دیدهای که به استناد مسئولیت قراردادی برای مطالبه خسارت اقامه دعوی میکند، بایستی اصل و میزان خسارتی را که متحمل شده یا خواهد شد، به اثبات برساند. نظر به اهمیت موضوع، اسناد فراملی مربوط به حقوق قراردادها از جمله اصول قراردادهای تجاری بینالمللی، اصول حقوق قراردادهای اروپا و پیشنویس طرح مشترک مرجع، به صورت صریح یا ضمنی، استانداردهای مشخصی مانند قطعیت متعارف، وقوع محتمل متعارف و غیره را برای اثبات خسارت پیشبینی کردهاند. در مقابل، مقررات موضوعه ایران از جمله قانون مدنی؛ چنین استانداردهایی را تنظیم ننموده و موضوع نیز مورد بررسی حقوقدانان و رویه قضایی قرار نگرفته است. بنابراین، مطالعه تطبیقی موضوع با نگاهی ویژه بر اسناد بینالمللی و آرای داوری می‌تواند منبع قابل اتکایی برای طرح بحث باشد. این مقاله، استانداردهای عام و خاص اثبات اصل خسارت و میزان آن و نیز مواردی مثل خسارت تأخیر تأدیه را که خارج از قلمرو شمول این استانداردها هستند، مورد تحلیل قرار میدهد و در نهایت تلاش دارد تا باب بحث را در حقوق ایران بگشاید.
Keywords: Arbitral Awards; Reasonable Certainty; Reasonably Likely to Occur; Standard for Proving Damages; Transnational Instruments; آرای داوری; استاندارد اثبات خسارت; اسناد فراملی; قطعیت متعارف; وقوع محتمل متعارف

Fall of Last Safeguard in Global Dejudicialization: The Problem of Protecting Public Policy in Private Business Disputes - Ghodoosi, Farshad (Oregon Review of International Law, 2020)
The importance of courts is shrinking. This is largely due to global dejudicialization: the process of outsourcing disputes to private dispute resolution. In the last several decades, along with the triumph of neoliberalism, privatization of the resolution of disputes has become the gospel of modern judiciaries. Courts have been pushed to the tail end of the private adjudication process and are used only as the last resort. The courts’ warm embrace of this structure along with practitioners’ push has led to a staggering expansion of private dispute resolution. The world therefore has witnessed an unprecedented growth of arbitration—the primary mode of private dispute resolution.
Keywords: Business law; Dejudicialization; Dispute resolution; Déjudiciarisation; Privatization; Public policy

La protection des secrets commerciaux dans l'arbitrage commercial international - Bitho, Théodore-Alexandre de Nika (Université Paris 1, 2020)
L'importance des secrets d'affaires dans l'essor de l'économie mondiale n'est plus à démontrer. Ils sont, selon les indicateurs les plus fiables, la partie la plus importante du patrimoine des sociétés qui détiennent les plus grandes fortunes du monde. Mais force est de constater que leur protection dans l'arbitrage commercial international est peu effective. Ils sont victimes de divulgations licites ou illicites qui les exposent. Pour une meilleure protection des secrets d'affaires durant une procédure arbitrale, des mesures correctives sont nécessaires. Ces mesures doivent concourir à redéfinir un cadre juridique pratique dont le fondement et la justification est la protection de l'information qui a une valeur commerciale et économique. Pour ce vaste chantier, la contribution des usagers et praticiens de l'arbitrage commercial international est indéniable mais celle des États est indispensable.
Keywords: Arbitrage; Arbitrage commercial international; Arbitrage international; Arbitragem; Arbitration; Confidentiality; Confidentialité; Discovery; Droit commercial (droit international); International Arbitration; Preuve (administration); Protection des secrets; Protection of secrets; Rôle de l'arbitre; Secret commercial; Secret d'affaires; Secrets d'entreprises; Trade secret

Investor-state arbitration and African states: a proposal for a Pan-African investment court - Ama, Obiajunwa (Canterbury Christ Church University, 2020)
This thesis proposed for the reform of Africa’s Investor-State Dispute Settlement (ISDS) landscape through the establishment of a Pan-African Investment Court (PAIC) as a mechanism for the resolution of Investor-State Disputes. This proposal is influenced by the findings of my investigation on the functioning of Investor-State Dispute Settlement (ISDS) through the deployment of Investor-State Arbitration to resolve Investor-State Disputes between African states and foreign investors. This research is motivated by the criticisms of the Arbitration mechanism by a broad spectrum of constituencies within international investment law. These criticisms are primarily anchored on the legitimacy crises of ISDS, a dissatisfactory notion that denounces the deployment of the private mechanism and privity of contract ingrained investment arbitration framework to resolve publicly-inclined investor-state disputes. Ancillary to this critical holy grail are further dissatisfactions on the practical functionality of investment arbitration in aspects of high volume of cases against developing states, lack of diversity in the appointment of arbitrators and curtailment of sovereignty of host states through the intrusion of provisions of International Investment Agreements on legitimate internal decision-making powers. Consequently, this thesis investigated the practical functioning of ISDS in African states. After the study of the experiences of Egypt, South Africa and Tanzania; it was found that the legitimacy crises of ISDS also impacts on African states, and does not support their socio-economic and sustainable developmental aspirations. As a remedy, I proposed for a reform to an Investment Court System (ICS) through the establishment of a Pan-African Investment Court (PAIC). An evaluation of this recommendation was conducted that evidenced potential challenges that may mitigate its feasibility, thus leading to the advancement of two secondary reform alternatives vis the reform and retention of the current investor-state arbitration framework and engagement in innovative treaty-making practices by African states. To the best of my knowledge, this thesis has not been previously submitted in any higher institution or published by another person. The contents of this thesis are my ideas. Where the materials of others were used, due acknowledgement and reference was provided. Acknowledgements
Keywords: Arbitration; Investment Court System; Investments; Investor-State Dispute Settlement; Investor-state arbitration

Les suites de l’accord amiable en afrique - Blanc, Gérard (L'accord amiable, 2020)

Guide de l'arbitrage de l'OMPI - Centre d’arbitrage et de médiation de l'OMPI (OMPI, 2020)

L’exécution forcée des décisions de la Cour commune de justice et d’arbitrage et des sentences arbitrales impliquant le droit de l’OHADA - Kangambega, Élisabeth L. (Revue Burkinabè de Droit, 2020)

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation

Arbitration related lessons: Insights from the supreme courts around the world - Nigmatullina, Dilyara; Vanlerberghe, Beatrix (b-Arbitra : Belgisch tijdschrift voor arbitrage, 2020)
In international arbitration, arbitrators have procedural powers that allow them to manage and conduct the arbitration proceedings in a fair and efficient manner. These powers are typically set out in the arbitration rules that the parties have agreed to, such as the International Chamber of Commerce (ICC) rules or the United Nations Commission on International Trade Law (UNCITRAL) rules. Arbitrators have the authority to determine the procedure to be followed in the arbitration, including the admissibility, relevance, materiality, and weight of the evidence presented. They can also decide on the language to be used in the arbitration and the location of the hearings. In addition, arbitrators can issue orders and directions as needed to ensure the fair and efficient conduct of the proceedings. This may include ordering the production of documents or witness testimony, or setting time limits for the submission of evidence. The present paper critically examines the lex arbitri, the law that governs the arbitral proceedings, and makes out a case that lex arbitri cannot be challenged in court, as the parties to the arbitration have agreed to resolve their disputes through arbitration rather than through the courts. However, if the tribunal exceeds its powers or acts in a manner that is inconsistent with the lex arbitri, the parties may have grounds to challenge the tribunal's decision on the grounds of lack of jurisdiction or due process. The paper summarises some key judgments in which Courts have upheld or quashed the Tribunals procedural orders. It will be concluded that the procedural powers of arbitrators in international arbitration are real and not perfunctory, though bounded within powers extended by Parties to the arbitral tribunal.
Keywords: Arbitrage; Arbitragem; Arbitration

Milletlerarası ticari tahkimde usule ilişkin konularda irade serbestisi - Takavut, İbrahim Doğan (İstanbul Üniversitesi, 2020)
Party autonomy is a well-accepted doctrine codified by national, international and supranational organizations that enables parties to be able to not only shape their contract but also their dispute resolution methods. It is believed that parties know their best interests; therefore, it is reasonable to give parties the freedom to decide whom they contract with and on what terms. This maximizes the autonomous freedom of the parties. Therefore, today it is well accepted that parties could waive their right to go to court and choose arbitration instead. However, through history, party autonomy has been seen as a direct threat to sovereign authority. States were always suspicious that arbitration hearings may not be as fair as court hearings since parties have the right to manipulate the arbitration processes. As a direct result of this, states regulated restrictions on party autonomy in international commercial arbitrations. Unfortunately, there is not an accepted definition of these restrictions and their effects on party autonomy have not been established or regulated internationally. Since party autonomy is the backbone of international commercial arbitration, it is important to crystalize the restrictions on party autonomy in procedural issues which directly affects the wellbeing of the arbitration process. Well accepted international regulations such as the New York Convention on Recognition and Enforcement of Foreign Arbitral Awards or UNCITRAL Model Law on International Commercial Arbitration helped to establish a unified system of restrictions on party autonomy but every state and state's courts interpret these restrictions differently. As procedural issues affect the result of international commercial arbitration, restrictions on party autonomy in procedural issues should be examined carefully. It is not an exaggeration that in international commercial arbitration the real and complicated questions most of the time originate from the issues of the boundaries of party autonomy. The tension between the party autonomy and efficiency of an arbitration process affects every decision which can be made by parties, arbitrators or courts. Therefore, this dissertation will investigate these problems in three parts by outlining; the source of party autonomy, the restrictions of party autonomy and the applications of these restrictions to party autonomy in procedural issues in international commercial arbitration. In the first part, the origin of party autonomy doctrine and how the doctrine developed throughout time will be examined. The law of arbitration, lex arbitri will be examined first. There are two accepted theories to determine lex arbitri. According to the territorialism theory, arbitration gets its power from the law of the place where the arbitration takes place. This theory suggests that the place where the arbitration takes place has control power over the procedure of arbitration. On the other hand, delocalization theory suggests that arbitral tribunals are detached from and not under the control of the law of the seat of arbitration. Although it looks like delocalization theory suits the needs of the international trade practice better because it assumes that arbitration is not in control of any law, it is still important to accept the power of the seat of arbitration since arbitration always needs a law to be controlled and get help. This section will also cover how different countries and international regulations determine lex arbitri and how it is determined in Turkish law according to the Turkish International Arbitration Law, Law no.4686. In the second part, restrictive measures of party autonomy will be examined. It will start with why party autonomy in procedural issues is needed to be restricted. Then the source of these restrictions will be mentioned. Afterwards, the common notions of the restrictions will be examined under the concepts of principles and rules. Under principles, the public policy and the common due process issues such as party equality, right to be heard, independence and impartiality of arbitrators will be examined in great detail. Then, mandatory rules which are based on these principles and their effect on party autonomy will be explained. The section will be closed with the examination of the circumstances where these principles and rules contradict each other. The main purpose of the second part is to look for commonly accepted problems of restrictions of party autonomy in procedural issues and how these common problems may evolve to a uniformed standard of the law, namely lex proceduralia. In the third part, the application of restrictions on party autonomy will be examined. The application of restrictions has different effects on parties, arbitrators and courts. Parties' autonomy is restricted while they are preparing their agreement on procedural issues, arbitrators are restricted during the arbitration processes and courts are restricted while helping the arbitration or controlling the awards. Before the arbitration process is initiated, parties' autonomy to shape their agreement looks like it is almost unlimited. However, parties' autonomy is always restricted by their choices. This situation is called the autonomy paradox. Therefore, the question of what parties can decide before the arbitrators join the processes is of the upmost importance. When the process starts and arbitrators start working, they balance the choice of parties and the restrictions of party autonomy. Since it is accepted that arbitrators are bound by the parties' choice and their power comes from the agreement of parties, it should be questioned whether they need to execute every choice of parties even if the choice is against mandatory provisions of lex arbitri or general accepted due process norms. Last but not least, courts' role on determining the party autonomy will be questioned. The power of courts to intervene in the arbitral process determine the practical limits of the autonomy of parties. During the arbitration process, the court may intervene in the process to help or control the arbitration; but real control power comes from when one of the parties asks courts to set aside or enforce the arbitral awards. While courts examine the arbitral awards, they also indirectly decide the limits of party autonomy. Therefore, this section will examine, which restrictions will affect the fate of the arbitral awards and how the courts should evaluate these restrictions. In conclusion, the dissertation will mainly investigate the topic of freedom of parties to determine the procedural issues in international commercial arbitration. It will aim to interpret and make use of the party autonomy doctrine as coherent as it can in the modern age. By illustrating the definition and limitations of the party autonomy in the procedural issues in international commercial arbitration, the dissertation will try to find a common international ground. This common ground may help to keep arbitration processes efficient while it provides fair hearings.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration boards; Commercial Arbitration; Commercial law; Free will; Hakem usulu; International Arbitiation Law; International Chamber of Commerce; Milletlerarası Tahkim Kanunu; Party autonomy; Procedural law; Tahkim; Tahkim kurulları; Ticaret hukuku; Uluslararası Ticaret Odası; Usul hukuku; Özgür istenç; İrade muhtariyeti

The Use of Mediation in ISDS - UNCITRAL Working Group III Virtual Pre-Intersessional Meeting (Asian Academy of International Law Limited, 2020)
Keywords: ISDS; Investor-State Dispute Settlement; Mediation; Médiation

La regulación del convenio arbitral y su implicancia en la institucionalidad del arbitraje comercial en el Perú - Vidal Ramos, Roger Pavletich (Universidad Nacional Mayor de San Marcos, 2020)
Estudia la regulación y los aspectos vulnerables del convenio arbitral, con énfasis a la necesidad de alcanzar una mejor institucionalidad del arbitraje comercial en el Perú. Determina los principios que fundamentan el arbitraje comercial. Identificar los supuestos de afectación al convenio arbitral. Analiza diversas sentencias de anulación de laudo respecto a la inexistencia de convenio arbitral. Analiza los diversos estudios teóricos y normativos en sede nacional e internacional respecto a los alcances del convenio y práctica arbitral. Identifica las instituciones jurídicas que brinden una protección del convenio en vía arbitral y judicial..
Keywords: Arbitrage; Arbitragem; Arbitraje industrial; Arbitraje y laudo; Arbitration; Convenios de arbitraje comercial; Convention d'arbitrage

The adaptation of China’s maritime arbitration system to international legal norms and practice - Xuan, Yan (The University of Queensland, 2020)
Maritime transport is essential to the world’s economy and maritime arbitration plays a crucial role in maritime dispute resolution. Nowadays, many coastal jurisdictions have set up their own maritime arbitration institutions such as those in the US, the UK, Germany, Australia, China, Japan, Hong Kong, and Singapore. Building a national world-advanced maritime arbitration system as soon as possible to suit China’s rapid developments in shipping and international trading does not permit of any delay. How should China improve her laws, rules and institutions, including those for the enforcement of maritime arbitration awards, having regard to leading international maritime arbitration systems? It is posited that selective adaptation from the successful experience of other maritime arbitration systems is the most convenient and effective way to achieve such a goal. This adaptation will follow from a comprehensive and comparative study of the maritime arbitration laws, rules and the maritime arbitration institutions, including the laws relating to the enforcement of maritime arbitration awards, from these main global maritime arbitration centres in order to make China’s maritime arbitration more competitive at the international level. This thesis does not purport to cover every research field relating to maritime arbitration. Instead, as previously stated, it will focus only on the comparative study of some selected key issues of international commercial arbitration among the selected jurisdictions. A comprehensive study of international commercial arbitration or international maritime law is not the subject of this thesis. It should be noted further that this research basically concentrates on the practical problems of maritime arbitration practices, rather than taking an overly theoretical approach. The thesis selects the UK, the US, Singapore and Hong Kong as the target jurisdictions for comparison. Through selective comparative analysis of the key issues of maritime arbitration systems in the selected jurisdictions, which are internationally recognised as significant by many arbitration scholars, this thesis proposes that all these issues could conveniently be categorised into four key criteria; namely, fairness, confidentiality, efficiency and enforceability. It follows that the adaptations of the Chinese maritime arbitration system should mainly focus on these four criteria, as these are the most critical factors for the development of Chinese maritime arbitration system. Moreover, these four criteria should also have significance for other underdeveloped maritime arbitration systems. Also, based on these four key criteria, the thesis provides some specific suggestions on how the Chinese maritime arbitration system can be adapted to reflect other selected jurisdictions in the respects of some key issues of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; Droit maritime; Efficiency; Enforceability; Fairness; Maritime arbitration

The enforceability of interim measures granted by an emergency arbitrator in international commercial arbitration - Zhang, Junmin (ProefschriftMaken, 2020)
The emergency arbitrator mechanism makes interim measures possible for parties involved in international commercial arbitration before the constitution of arbitral tribunals under urgent situations. However, with the development of the emergency arbitrator mechanism, the enforceability of interim measures made by an emergency arbitrator is questioned. This uncertainty leads to the hesitation of legal practitioners to apply the emergency arbitrator mechanism in practice. The research conducted two comparisons between different arbitration rules and between arbitration laws in jurisdictions. After discussing the legal status of an emergency arbitrator, the legal criteria to render interim measures, the potential barriers for the enforceability, and possible harmonization, it concluded that the interim measures granted by an emergency arbitrator in international commercial arbitration should be enforced and even harmonized through mandatory and non-mandatory methods.
Keywords: Arbitrage; Arbitragem; Arbitral Tribunal; Arbitration; Arbitration Law; Arbitrator; Commercial Arbitration; Emergency arbitrator; Enforceability; Interim measures; International commercial arbitration

基于国际商会仲裁规则下的国际工程项目仲裁管理 - 侯, 进才 (Journal of Oil and Gas Technology, 2020)
随着世界经济全球化，国内外企业之间的商贸往来迅猛发展，出现商事争议与纠纷的案件也呈现上升趋势，仲裁以其高效、快速等优点成为解决国际商事纠纷的最终方式之一。本文从仲裁的优点入手，首先阐述了完整仲裁过程中各个关键环节及注意事项，然后用流程图和横道图两种形式体现了一个完整的仲裁过程，最后就国际工程项目仲裁管理给出了具体建议。 With the globalization of the world economy, the commercial exchanges between domestic and foreign enterprises are developing rapidly, and the number of commercial disputes cases is growing quickly. Considering its advantages of high efficiency and speed, arbitration has become one of the final ways to solve international commercial disputes. This paper firstly presents the advantages of arbitration, then expounds the key stages and attention during the whole arbitration process. Flow chart and Gantt chart are drawn to show logics of the process. Specific suggestions on the arbitration management of international projects are given at the end of the article.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration Management; Arbitration Process; International Project; 仲裁程序; 仲裁管理; 国际工程

Essays on Economics of Litigation : an Application to Investor-State Disputes - Vu, Duy (Université Côte d'Azur, 2019)
International investment treaties often allow the foreign investor to sue the host country before international arbitration in case of breaches of treaty provisions. The number of investor-state disputes is growing so rapidly that some countries expressed their discomfort with the current international investment law regime. The first chapter gives readers a comprehensive view on the effectiveness and spillover effect of international investment arbitration. Based on a vast interdisciplinary literature, we reexamine recent criticisms and identify the root of the crisis faced by international arbitration. We conclude that it is possible for countries to adapt the current regime of international law to new situations without wholesale exit. The second chapter investigates the early settlement of investor-state disputes. Drawing on the rich economic literature and a new dataset related to treaty-based disputes, we find that the host state's experience, the case prospect, the nature of the regulatory measures, the identity of investors and Dutch investment treaties have significant impacts on the probability of early settlement. The third chapter focuses on an institutional dimension of arbitration: the effectiveness of ICSID in solving disputes. The time to resolution and the quality of the final judgment which is measured by the requirement of follow-on proceedings are used as performance indicators. We highlight how arbitrators' biographical and professional characteristics can impact the ICSID effectiveness. Les traités internationaux d'investissement permettent souvent à l'investisseur étranger de poursuivre le pays d'accueil devant un tribunal d’arbitrage international en cas de violation des dispositions du traité. Le nombre de différends entre investisseurs et États augmente si rapidement que certains pays expriment leur malaise à l'égard du régime actuel du droit international de l'investissement. Le premier chapitre donne aux lecteurs une vue générale sur l'efficacité et les effets de spillover de l'arbitrage international en matière d'investissement. En se basant sur une vaste littérature interdisciplinaire, nous réexaminons les critiques récentes et identifions la cause sous-jacente de la crise relative à l'arbitrage international. Nous concluons qu'il est possible pour les pays d'adapter le régime actuel du droit international à de nouvelles situations plutôt que de le quitter. Le deuxième chapitre étudie le règlement amiable des différends entre investisseurs et États. En nous fondant sur la riche littérature économique et sur une nouvelle base de données de différends relatifs à la violation des traités, nous constatons que l'expérience de l'État hôte, les perspectives du différend, la nature des mesures réglementaires, l'identité des investisseurs et les traités d'investissement néerlandais influencent significativement la probabilité d'un règlement rapide du différend. Le troisième chapitre se concentre sur une dimension institutionnelle de l'arbitrage : l'efficacité du CIRDI dans la résolution des différends. Le délai de résolution et la qualité du jugement final, représentée par la probabilité d'avoir des recours post-sentence, sont utilisés comme indicateurs de l'efficacité. Nous soulignons comment les caractéristiques biographiques et professionnelles des arbitres affectent l'efficacité du CIRDI.
Keywords: Analyse économique; Arbitrage international; Arbitrage international d'investissement; Centre international pour le réglement des différends relatifs aux investissements; Différends investisseur-Etat; Economic analysis; International Investment Arbitration; Investissements étrangers; Investor-state disputes; Médiation internationale

Arbitrage commercial international et politiques étatiques en matière commerciale : l'exemple du droit de la concurrence - Alhadidi, Ismaeel (Université de Bordeaux, 2019)
Il est admis que l’arbitrage international est impliqué dans l’assurance des politiques étatiques. Les droits nationaux contiennent des dispositions édictées en vue de protéger les intérêts étatiques et l’arbitre se trouve souvent amené à se prononcer sur une question qui met en jeu ces intérêts. Une telle opération n’est envisageable que si la matière en question est arbitrable. La question qui se pose est celle de savoir quelles sont les limites de l’arbitre dans la protection et l’assurance des politiques étatiques. En réalité plusieurs branches du Droit ont pour finalité d’assurer les politiques étatiques. A titre d’exemple, le droit de la propriété intellectuelle, le droit des sociétés, le droit de l’investissement et le droit de la concurrence peuvent être cités. Ce dernier constitue une bonne illustration des politiques étatiques. En effet, quand l’arbitre se charge de la mise en œuvre du droit de la concurrence, il est en train d’assurer le respect des politiques étatiques de l’Etat concerné.De ce fait, l’interaction entre l’arbitrage international et les ordres juridiques est devenue une réalité. Cette réalité procède de l’arbitrabilité des matières relevant de l’ordre public des Etats. Certains d'entre eux reconnaissent l’arbitrabilité des litiges intéressant l’ordre public comme le droit de la concurrence. D'autres n’acceptent pas que l’arbitre tranche ce type de litiges.La question de l’arbitrabilité objective nous conduit à étudier les différentes interactions entre l’arbitrage international et les politiques étatiques. Dans le cadre de cette étude, nous nous livrerons à l'étude des manifestations de cette interaction et des limites que l’arbitre doit considérer, du fait que la matière assurant des politiques étatiques, y compris le droit de la concurrence, n'est pas entièrement sujette à l’arbitrage.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Competencia; Competition law; Concurrence; Policies; Politiques; State; Étatiques

The contribution mediation can make in addressing economic crime in corporate and commercial relationships in South Africa - Hoffman, Cornelia Hendrina (Stellenbosch University, 2019)
Economic crime is complex and costly. It is costly because it harms victims, both directly and indirectly, as well as the broader economy. The cost is not only financial, but also to confidence and trust in corporate and commercial relationships in South Africa. Economic crime is complex because it includes offences from common-law fraud to statutory contraventions such as incorrect bookkeeping. There are several mechanisms in the South African legal justice system to address economic crime. The conventional legal models include adversarial criminal prosecution of the offender and civil compensation claims, the model of inquisitorial administrative investigations and sanctions like penalties and compensation orders. In 2001 section 105A of the Criminal Procedure Act, namely plea and sentencing agreements, was added as a model of negotiated justice. This mechanism allows the prosecution and the offender to negotiate and enter into an agreement regarding the charges and the sanctions, subject to approval of the court that the plea of guilty is proper and that the proposed sanction is a just sentence. This dissertation proposes that mediation be added to the existing alternative models to help combat economic crime. Mediation involves negotiated justice, as well as restorative justice. More specifically, mediation as a restorative justice process, constitutes a practical alternative to standard litigation as the affected parties themselves, with the facilitation of a third person, resolve the disputes between them. Mediation, a facilitative and flexible procedure, allows the voices of both the victim and the offender to be heard securely and meaningfully. Mediation is rehabilitative and allows for agreed restorative provisions for both the perpetrator and the victims of economic crime. The outcome is a proposed amendment to the Criminal Procedure Act 51 of 1977, namely the insertion of section 105B, “Mediated Settlement Agreements”, that will provide for mediation and a mediated settlement agreement to be incorporated into and form part of the criminal justice processes. It is envisaged that an accredited mediator will mediate between the parties, including the public prosecutor, the perpetrator, the victim and possibly members of the community. The mediated settlement agreement will include both compensation for the victims and a proposed sentence for the perpetrator. This mediated settlement agreement will then be tabled before the court for adjudication and approval to serve as an effective court order. The proposal is a logical legal development of section 105A of the Criminal Procedure Act on plea and sentencing agreements, as the process of mediation builds on the process of negotiation established in it. To put it bluntly, if a plea and sentence agreement can be negotiated between the prosecutor and the offender, a plea and sentence agreement can be mediated between the prosecutor, the offender and the victim. Mediation can integrate and expand the constitutional principles of reparation and ubuntu and curb economic crime by providing an effective restorative and just response to it.
Keywords: Alternatives to prosecution; Commercial law; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; South Africa

De la conciliación a la mediación: alternativas para la gestión de los conflictos - Bartolomé Cantalejo, Mª Yolanda (Universitat de Barcelona, 2019)
En nuestro país, hasta hace unas décadas se desconocía la existencia de métodos de gestión y resolución de conflictos reglados diferentes al procedimiento judicial, a excepción del arbitraje y de algunas buenas prácticas consuetudinarias en las que se utilizaba el buen oficio de terceros, como, por ejemplo, el Tribunal de las Aguas en Valencia; también existía la conciliación previa al desarrollo del juicio, que salvo en la jurisdicción laboral había quedado relegada a ser un recurso residual, y muy pocas veces tenía efectos de terminación del procedimiento tras haberse alcanzado un acuerdo. Ante este panorama, no había más remedio que acudir al sistema adversarial para resolver los conflictos jurídicos que se producían en las relaciones entre las personas en el desarrollo de la vida tanto en el ámbito individual como colectivo. Y desde hace algún tiempo el sistema jurisdiccional se revelaba insuficiente para “absorber” la totalidad de las situaciones de conflicto que se producían de forma habitual en la sociedad; la complejidad de las relaciones interpersonales y la abundancia de situaciones donde se producen los conflictos, dada la evolución y las grandes transformaciones sociales de los últimos años. La implantación de la mediación en el ámbito civil y mercantil a partir de la publicación de la Ley 5/2012, de 6 de julio, de mediación en asuntos civiles y mercantiles, como método alternativo y/o complementario de la gestión y solución de conflictos, debería mejorar la eficacia en la búsqueda de solución a los conflictos planteados y su gestión de un modo más eficiente y rápido, evitando todos los inconvenientes que se producen en sede judicial cuando no queda más remedio que acudir al procedimiento judicial. Las ventajas más importantes son: el ahorro de costes y tiempo en relación al procedimiento judicial tradicional; una solución que supone una menor carga emocional para las partes en conflicto y que redundará en la posible continuación de las relaciones en el futuro, y todo ello facilitará sentar los principios para cambiar la cultura litigiosa existente en nuestro país, por una más conciliadora que suponga una mejor convivencia y una transformación pacífica de la sociedad, sin olvidar la descarga de asuntos con el consiguiente alivio de los órganos jurisdiccionales. Todo ello garantizará que los ciudadanos puedan solucionar sus controversias de forma rápida y eficaz y contribuirá a un mejor funcionamiento del sistema generando un mayor dinamismo de nuestra economía. Aunque no podemos olvidar la urgente necesidad de adaptar y modernizar nuestras leyes procesales y de incrementar el número de órganos judiciales para agilizar un sistema jurisdiccional que adolece de falta de personal, lentitud excesiva por la escasez de medios y de la abundante burocracia para llegar a resolver las controversias planteadas ante los tribunales de justicia. La mediación, por lo tanto, es una alternativa diferente para la solución de los conflictos a todos los niveles que tienen que afrontar los ciudadanos; se pueden resolver los conflictos de forma dialogada y con una actitud proactiva encaminada a encontrar una solución a sus diferencias con un mayor grado de satisfacción y bienestar, puesto que serán los propios implicados quienes ideen la solución a su conflicto, creando menos fricciones y evitando las situaciones más dolorosas y conflictivas para ellos y para su entorno, buscando una salida pacífica y consensuada. Y esta forma de resolver los conflictos no acarrea solo beneficios a las personas que lo utilizan a nivel individual, por solventar sus controversias de una manera más útil, rápida y eficaz, sino que sirve para que las controversias se pacifiquen y esto redundará en unas relaciones más eficientes que implicarán una sociedad más pacífica y con una menor tendencia a la confrontación con la consiguiente reducción de la hostilidad en nuestra sociedad.
Keywords: Ciències Jurídiques; Conflict management; Econòmiques i Socials; Gestió de conflictes; Gestión de conflictos; MARD; Mediació; Mediación; Mediation; Mediação; Médiation

Jurisdictional challenges and enforceability of arbitral awards in the UAE - Badr, Ahmed Abdelhafez (Université Paris Cité, 2019)
The United Arab Emirates (UAE) is one of the major emerging markets in the world. The economy of the UAE is the second largest in the Middle East (after Saudi Arabia), with an estimated gross domestic product (GDP) of USD 1422 billion in 2017. In connection with this economic development, the UAE attempted to establish a modernized legal system to accommodate domestic and foreign parties demanding efficient and independent dispute resolution. Many local and international companies, as well as individual investors operating in the UAE, agreed to submit their disputes to arbitration in their contracts as a neutral, efficient, predictable, and easily enforceable dispute resolution mechanism. However, historically, and due to specific incidents that happened during the western occupation to the Arab world, arbitration was frequently perceived in the Middle East as a western process that is neither naturally nor culturally connected to the traditional judicial system that was rooted in the Middle East's more developed countries in the 1950s and 1960s. This historical background could explain, to some extent, the existing animosity of certain national courts in Arab countries to international arbitration. Further, this is demonstration is closely connected to issues being studied in this dissertation in relation to: - The frequent number of arbitral awards being annulled in the UAE, and - The jurisdictional challenges to arbitral tribunals in the UAE. Studying UAE jurisprudence on cases confirming setting aside arbitral awards is one of the main themes being studied in the first Part of this thesis; the span of the study extends from 1995 to 2018. In order to diagnose the root causes of setting aside arbitral awards, it was essential to study each case that confirmed setting aside arbitral awards by UAE courts. Out of several hundred case laws in the UAE included in the study, over one hundred thirty case laws confirmed setting aside both domestic and international arbitral awards; each of these case laws was analyzed and discussed with particular emphasis on the problematic issues or procedure causing annulment. In order to suggest solutions to this problem, the research takes a comparative approach to contrast the UAE recognition and enforcement process of arbitral awards with more developed jurisdictions. France, naturally, is the primary jurisdiction for this comparative research. France has an international reputation as being one of the most (if not the most) supportive jurisdiction to recognizing arbitral awards and arbitration in general as a dispute resolution mechanism. Despite consuming considerable time searching for cases where the French courts set aside arbitral awards, only twenty-two case laws were identified where the French courts upheld the setting aside of arbitral awards. This relatively low number confirms the worldwide reputation that annulment of arbitral awards by the French courts is factually a rare incident given the considerable number of awards seated and/or being enforced in France. The broader comparative perspective reflects a consistent pattern that most developed jurisdictions generally respect, support, and recognizes arbitral awards. This has developed a general perception among parties to arbitration that arbitral awards, once issued, should be enforced voluntarily before initiating the enforcement process, whereby award debtors do not seek annulment and voluntarily satisfy the arbitral awards before the commencement of the enforcement proceedings due to their prior knowledge that national courts are likely to recognize and respect to arbitral awards.
Keywords: Arbitral Awards; Contestations juridictionnelles; Enforceability; Exécution; Jurisdictional challenges; Opposabilité; Sentences arbitrales; United Arab Emirates; Émirats arabes unis

O Favor Arbitrandum : Ensaio de uma teorização - Diamvutu, Lino (Universidade de Lisboa, 2019)
A presente tese constitui um ensaio de teorização do favor arbitrandum. A tese, contrariamente a algumas posições doutrinárias sobre o tema, não encara o favor arbitrandum como sendo uma política legislativa ou judiciária visando a promoção da arbitragem. Antes, ela procura, a partir das suas manifestações legais e jurisprudenciais, identificar um princípio jurídico, determinando o seu conteúdo, os seus limites e os seus fundamentos. O princípio do favor arbitrandum revela-se plurifacetado e não apresenta um alcance idêntico nos diversos ordenamentos jurídicos estudados. O seu conteúdo pode ser apreendido em dois sentidos principais. Trata-se, por um lado, de um critério interpretativo-decisional em matéria de validade da convenção de arbitragem, da competência do tribunal arbitral e de validade ou reconhecimento da sentença arbitral. Por outro lado, o favor arbitrandum é um princípio jurídico supralegal que se expressa como directriz orientadora da actividade legislativa, e, do trabalho interpretativo e integrativo pelo julgador das normas relativas à arbitragem. O princípio do favor arbitrandum encontra fortes limitações que podem ser de carácter geral (v.g. a aplicação da reserva da ordem pública, a ofensa dos bons costumes, a fraude, etc.), inerentes ao procedimento arbitral (a falta pelo árbitro do jus imperium, as anti-arbitration injunctions ou a responsabilização civil do árbitro) ou relativas à qualidade das partes envolvidas na arbitragem (a impecuniosidade das partes e a imunidade de execução dos Estados). Quanto aos seus fundamentos, o princípio do favor arbitrandum assenta em fundamentos jurídico-políticos e dogmáticos. Os seus fundamentos jurídico-políticos relacionam-se com o desenvolvimento do comércio internacional, a necessidade de redução das pendências nos tribunais judiciais, a concorrência entre Estados no acolhimento das arbitragens internacionais e o favor accordandum. O verdadeiro fundamento dogmático do favor arbitrandum encontra-se no princípio da tutela da confiança.
Keywords: Conteúdo do princípio; Favor arbitrandum; Fundamentos; Limites; Manifestações

Le consentement étatique à la compétence des juridictions internationales - Marquet, Clément (Université de Genève, 2019)
Le consentement étatique à la compétence des juridictions internationales est un élément incontournable du droit international public. Il régit le le fonctionnement de la justice internationale. Cependant, malgré son ubiquité, la notion est mal comprise. Ce travail, à travers la jurisprudence de la CIJ, d'ITLOS, de l'OMC et du CIRDI, redéfinit ce consentement, à la lumière de son histoire, son rôle et ses enjeux. Cette re-contextualisation est accompagnée d'une présentation et d'une analyse des enjeux contemporains entourant la notion.
Keywords: Arbitrage; Arbitragem; Arbitration; CIJ; CIRDI; Compétence; Compétence de la compétence; Consentement; Cour internationale de justice; Droit international public; Forum prorogatum; ICSID; ITLOS; Interprétation; Investissements; Investments; Juridictions; MFN; NPF; OMC; Organisation mondiale du commerce; Recevabilité; TIDM

Problems of Enforcement of ICSID Awards: An Analysis of Micula Case - Hasankhani, Ali (Public Law Researsh, 2019)
In the case Micula A.O. v. Romania, the arbitration tribunal established under the auspices of the International Center for Settlement of Investment Disputes (ICSID) sentenced Romania to pay a compensation for the revocation of investment incentives and for the breach of fair and equitable treatment principle that had been laid down in a bilateral investment treaty between Sweden and Romania. Considering investment incentives as a breach of the EU regulations regarding state aids, the European Commission then rendered a directive, prohibiting the enforcement of the arbitration award by the member states. As articles 53 and 54 of ICSID emphasize that the awards are binding, the EU Commission’s act of rendering the aforementioned directive, and the member states refusal to comply with the award equals to giving the EU law primacy over international law, which should be considered as a breach of their international obligations. Using a descriptive-analytical method, this article seeks to explain the viewpoints of the parties and the courts which were asked to enforce the award, as well as to determine the nature of their acts.

A arbitragem internacional de protecção de investimentos e a dupla nacionalidade: dois pode ser igual a zero? - Duarte, Tiago (e-Publica, 2019)
The assessment of the investor’s nationality is of utmost relevance to determine the arbitral tribunal’s jurisdiction in Investor-State Arbitration. In treaty-based arbitration the investor must give evidence that is protected by the BIT, which means that he must have the nationality of the State party to the BIT that is not the host State. The case law considers irrelevant the fact that the investor possesses another nationality besides the nationality of the State party to the BIT and considers also irrelevant the fact that the invoked nationality is not the dominant one. Things get more serious if the investor has also the nationality of the host State (double nationality). In this scenario the investor cannot launch an ICSID arbitration against the host State because the Washington Convention forbids it. The possibility of an ad hoc arbitration is subject to the interpretation of the applicable BIT which has led to an unstable case law both because the BITs are not all equal and because different tribunals have analyzed the dominant nationality doctrine in different ways. A determinação da nacionalidade do investidor é um dos elementos mais importantes para a verificação da jurisdição dos tribunais arbitrais nas arbitragens de proteção de investimentos. Nas arbitragens baseadas em BIT (bilateral investment treaties) o investidor que inicia a arbitragem tem de demonstrar que está protegido pelo BIT que pretende invocar, pelo que terá de possuir a nacionalidade do Estado parte nesse mesmo BIT, que não seja o Estado onde o investimento foi realizado. A jurisprudência tem considerado irrelevante o facto de o investidor poder ter outras nacionalidades, para além da nacionalidade do Estado parte no BIT, desvalorizando igualmente o facto de essa nacionalidade não ser a nacionalidade dominante do investidor. Tudo se complica no caso de o investidor possuir igualmente a nacionalidade do Estado onde o investimento foi realizado. Nesse caso o investidor não poderá iniciar uma arbitragem com base no ICSID tendo em conta que a Convenção de Washington veda essa possibilidade. Já no caso de arbitragens ad hoc tudo dependerá da interpretação do BIT em concreto, o que tem levado a uma flutuação jurisprudencial, seja porque os BIT são diferentes, seja porque tem havido diferentes abordagens jurisprudenciais quanto à relevância da nacionalidade dominante.

Proceedings of 1st Annual Research Symposium on International Commercial Arbitration - Casoria, Maria (Royal University for Women, 2019)
Keywords: Arbitrage; Arbitragem; Arbitration; Convention on the Recognition and Enforcement; Foreign Arbitral Awards; International Commercial Mediation; International Settlement Agreements; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements; UNCITRAL Model Law

Causes of Delay in the Resolution of Commercial Disputes via Litigation Arbitration as a Way out within OHADA Laws - Sigala, Buma Roland (International Journal of Trend in Scientific Research and Development, 2019)
An essential requirement of justice is that it should be dispensed as quickly as possible. It is a well-known adage that, « justice delayed is justice denied». Delay in litigation is caused by a number of factors. For example in litigation the parties have the right to make a counterclaim, right to make appeal etc. Arbitration has been able to overcome the factors which cause delay in litigation because in arbitration, parties are given the right to exclude the possibility to make a counterclaim, the right to make appeal has expressly been prohibited by the Organization for the Harmonization of Business Laws in Africa (OHADA)1 legislator etc. But since the OHADA legislator has not expressly prohibited counter claim in arbitration, it is recommended that counterclaim should be expressly prohibited in arbitration as it is the case with appeal. This article aims at identifying the causes of delay in the disposal of commercial disputes via litigation and how these causes of delay have been combated in arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; Delay commercial; Disputes Litigation; Law and management

Arbitraje Comercial Internacional. Reconocimiento y Ejecución de Sentencias y Laudos Arbitrales Extranjeros - Paulsson, Jan; Opertti Badán, Didier; Santos Belandro, Rubén; Bouchenaki, Amal; Ojea, Mildred; Rivera, Irma; Caivano, Roque J.; Solís Zelaya, Román; Fernández López, Alberto; Fresnedo de Aguirre, Cecilia; Gosis, Diego B.; Gomm Santos, Mauricio; et al. (IIJ, 2019)
Keywords: Arbitraje Comercial International; Arbitration; Commercial arbitration agreements; Conflict of laws; International arbitration award; Sentences arbitrales étrangères

Interaction entre les Cours de justice communautaires et les juridictions suprêmes nationales : spécificités de la Cour Commune de Justice et d’Arbitrage (CCJA) de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) - Ondo Mve, César Apollinaire (La diffusion de la jurisprudence des Cours suprêmes judiciaires francophones au temps d’internet, 2019)

Règlement d'arbitrage en vigueur à compter du 1er mars 2017, règlement de médiation en vigueur à compter du 1er janvier 2014 - Cour internationale d'arbitrage; Centre international d'ADR (Publication ICC, 2019)
Keywords: Arbitration; Mediation

Médiation du champ pénal dans le monde francophone - Jullion, Daniel (La lettre des médiations, 2019)
Initiée au milieu des années 80, dans le contexte bien particulier de la politique de la ville mise en place par un nouveau pouvoir politique, la médiation pénale a bénéficié du contexte très favorable des relations mises en place entre le politique et le judiciaire lors de la création du CNPD (1), sous la présidence de Gilbert Bonnemaison (2), des CCPD puis, en 1988 de la DIV (3) et, enfin la circulaire du 10 juillet 1989 « ... participation de l’institution judiciaire à la politique de prévention ». Véritables instances de concertation sur les problèmes de société et de sécurité, élus et professionnels se sont rapprochés sur leurs préoccupations communes : apporter une réponse « sociale » à un « contentieux de masse » (constitué de « petits » actes de délinquance qui participent au sentiment d’insécurité) et que « ... la Justice traiterait mal ou pas du tout ... » selon l’expression de G. Apap (alors procureur de la République de Valence) qui a initié les premières expériences de médiation pénale (appelée à l’époque « conciliation pénale » ... !!).
Keywords: Droit pénal; Mediation; Médiation

Les rapports entre la justice étatique et la justice arbitrale : Etude comparative France-OHADA - Kouchanou, Balbine Léa Modukpé (Université de Perpignan Via Domitia, 2019)
L’arbitrage est un moyen de gestion de litige apprécié et privilégié par les acteurs du commerce international. Son bon fonctionnement dépend de la justice étatique. Ces deux appareils doivent entretenir un rapport tantôt fusionnel et tantôt concurrentiel. Le déroulement de cette relation peut réciproquement susciter des complications et de la méfiance. En France comme dans plusieurs autres États de l’Afrique subsaharienne, le juge étatique est le collaborateur de l’arbitre malgré l’envergure de leurs rapports. Ces États reconnaissent à la justice étatique son pouvoir explicite et implicite durant l’arbitrage. La présente recherche et étude aborde la mise en œuvre des compétences respectives attribuées à l’arbitre et au juge durant l’arbitrage. Afin d’accentuer et de pérenniser le bon déroulement de l’arbitrage en France et en Afrique francophone, cette étude s’est attardée sur la question de l’arbitrabilité et du développement économique. Après avoir énuméré des réalités freinant la floraison durable de l’arbitrage en Afrique, quelques solutions sont proposées pour le préserver de tout dysfonctionnement. Arbitration has been used to resolving cases appreciated by international trade actors. However, well-functioning depends upon state justice. Both devices should have maintain a fusional and competitive relationship. The unfolding of this relationship can reciprocally bring complications and mistrust. State judge is referee’s collaborator despite the spacing of reports in France and several other states in sub-Saharan Africa. These states recognize the explicit and implicit power of state justice during arbitration. This study approaches courts assigned to the arbitrator and judge during their challenge. In order to accentuate and sustain the smooth running of arbitration in France and Francophone Africa, this research has been focused on the issue of economic development. After listing realities hindering the flowering of arbitration in this part of Africa, some solutions have been proposed to preserve this method of dispute resolution of dysfunction.
Keywords: Approximation; Arbitrage; Arbitragem; Arbitration; Cases; Différents; France; Interstate; Interétatique; Justice (administration); Pays de l'OHADA; Proceedings; Procédures; Rapprochement

What the African Continental Free Trade Agreement Protocol on Dispute Settlement says about the culture of African States to Dispute Resolution - Akinkugbe, Olabisi (Articles, Book Chapters, & Popular Press, 2019)
An effective Dispute Settlement Mechanisms (DSM) upholds a rules-based trade regime; enunciates, clarifies and develops the jurisprudence of its constituent trade agreement; and also ensures predictability in the trading regime. Article 20 of the African Continental Free Trade Agreement (AfCFTA) establishes the DSM. The AfCFTA Protocol on Dispute Settlement (“Dispute Protocol”) provides for the rules and procedures for the settlement of disputes. Unlike the majority of the African regional economic community courts that are modelled after the Court of Justice of the European Union, the AfCFTA-DSM follows a handful of other regional judicial bodies – such as the Southern African Community Development Community (SADC) and the Tripartite Free Trade Area Agreement (TFTA) – that are modelled after the World Trade Organization (WTO) dispute settlement mechanism.
Keywords: AfCFTA; Dispute Settlement Mechanisms; Free Trade; Trade Agreement

La transparencia en el arbitraje internacional y en los tratados bilaterales de inversión - Febles Pozo, Nayiber (Universitat de Girona, 2019)
The thesis's main objective is the analysis of transparency in international arbitration. To this purpose, we start from a broad conception of the notion of transparency and its relevance in the current Bilateral Investment Treaties (BITs) and in the main international arbitration regulations: the ICSID, the ICC, UNCITRAL and its Rules on Transparency in Treaty-based Investor-State Arbitration, followed by a study of the most important issues of the arbitration procedure related to transparency, such as public hearings, the participation of third parties in the procedure (third-party funders and amicus curiae), the appointment of arbitrators and the conflict of interests and, finally, the analysis of transparency in the decisions (arbitral awards). The thesis proposes and bases, among other issues, the need to create an ICSID Court of Appeal and, if not, the most suitable mechanism for the implementation of an International Investment Tribunal
Keywords: Advertising; Arbitrage; Arbitragem; Arbitraje internacional; Arbitration; Bilateral Investment Treaties (BITs); Confidencialidad; Confidencialitat; Confidentiality; Ethical principles; International Arbitration; International Investment Tribunal; Investments; Investor-state arbitration; Preciding; Principios éticos; Principis ètics; Publicidad; Publicitat; Transparencia; Transparency; Transparència

Harmonização das Regras de Execução do Acordo de Mediação Comercial Internacional - Carvalho, David França Ribeiro de (Universidade de São Paulo, 2019)
O acordo mediado é aquele alcançado pelas partes como resultado de um procedimento de mediação. Diversamente das sentenças arbitrais estrangeiras, as quais gozam de um instrumento global para seu reconhecimento e execução, sob os auspícios da Convenção de Nova York, os acordos mediados transnacionais não possuem um instrumento harmonizado ou uniformizado que lhes conferem a mesma segurança. A mediação é um método de resolução de conflitos cada dia mais utilizado nas relações comerciais transnacionais e o resultado alcançado pelas partes precisa ser provido de maior reconhecimento e exequibilidade transnacional. Assim, são apresentadas algumas questões conceituais sobre o reconhecimento e a execução dos acordos mediados comerciais transnacionais para, na sequência, evidenciando o fenômeno da transnormatividade e pluralidade normativa, apresentar o arcabouço jurídico existente e seus limites no âmbito europeu com a Diretiva Europeia 2008/52/CE e transnacional, com a Lei Modelo da UNCITRAL sobre Conciliação Comercial Internacional de 2002. Essas normas reforçam a importância da elaboração de instrumentos que possam melhor assegurar o reconhecimento e a execução dos acordos mediados transnacionais. São apresentados e examinados argumentos sobre a necessidade e eventuais formas para o reconhecimento e execução dos acordos mediados transnacionais, proporcionando um melhor acesso à justiça. Ao final, são evidenciadas formas para a harmonização/uniformização e contextualizada a questão no âmbito do ordenamento jurídico brasileiro.
Keywords: Acordo mediado transnacional; Cross-border enforcement; Harmonization; Harmonização; International commercial mediation; MARD; Mediación; Mediation; Mediação; Mediação comercial internacional; Médiation; Reconhecimento e execução; Transnational mediated settlement agreement

Proceedings ISDS reform conference 2019: mapping the way forward - Asian Academy of International Law (2019)
Keywords: Dispute settlement; Investment disputes; LAW REFORM; UN Commission on International Trade Law

La déjudiciarisation de l'arbitrage OHADA - Massosso Benga, Cruse Hervé (Université de Perpignan Via Domitia, 2019)
Historiquement, l'arbitre et le juge sont un vieux couple. Cette union légale procède de l'assistance technique que ce dernier porte à l'arbitre. Les nombreux dysfonctionnements que connaissent les justices étatiques des États membres de l'OHADA poussent ces derniers à réorganiser cette institution phare des États. A l'instar des États-Unis, du Canada ou encore de la France, les États membres de l'OHADA peuvent également opter pour une déjudiciarisation qui, délesterait le juge étatique de toutes ses tâches supplémentaires, dont celles relevant de l'arbitrage, spécifiquement pour les États de cet espace juridique. Dans cette hypothèse, il s'agira de bâtir un système arbitral totalement affranchi de toute intrusion du juge étatique. Ces travaux s'inscrivent donc dans une logique de droit prospectif, l'objectif étant à terme de présenter un droit de l'arbitrage totalement émancipé de l'apport du juge et ainsi, véritablement conférer à cette justice privée son caractère indépendant tant vanté. Historically, the referee and the judge are an old couple. This legal union proceeds from the technical assistance that the judge brings to the referee. The numerous issues faced by the state courts of the OHADA member states are forcing them to reorganize this all important institution. Just like in the United States, Canada or France, the OHADA member states can also opt for a judicial injunction, which would relieve the state judges of additional duties, including those related to arbitration specifically for the member States of this legal environment. In regard to this, it will be useful to build an arbitral system completely free from any intrusion of the state judge. This work is therefore part of a prospective-law approach, the ultimate goal being to present a right for arbitration totally liberated from the contribution of the judge and thus, truly confer to this private justice it’s independent character.
Keywords: Arbitrage; Arbitrage OHADA; Arbitragem; Arbitration; Déjudiciarisation; Indépendance des arbitres; Indépendence of arbitrator; OHADA Arbitration; Organisation pour l'harmonisation en Afrique du droit des affaires; Simplification du droit

Financement de l'arbitrage par un tiers : une approche française et international - Mechantaf, Khalil (Université Paris 1, 2019)
Le financement des procès présente de nombreux avantages pour le développement de l'arbitrage international, auparavant inaccessible aux parties impécunieuses. Les systèmes anglo-saxons, traditionnellement contre le financement des procès, commencent à introduire des règlementations facilitant l'accès au financement et promouvant son développement. La sophistication des formes de financement et le statut du tiers financeur apportent cependant une certaine complexité à l'exercice par l'arbitre de son pouvoir et au déroulement de la procédure arbitrale. Cette dernière reste gérer par le consensus des parties et la confidentialité de la procédure. La divulgation de l'accord de financement et la détermination du statut du financeur sont parmi les questions que posent l'existence d'un tiers dans la procédure arbitrale. Third-party funding presents various advantages for the development of international arbitration, previously inaccessible for insolvent parties. Common law systems, traditionally against the funding of litigation, are recently adopting regulations allowing access to funding and promoting its development. The sophistication of the forms of funding and the status of third-party funder give rise to certain challenges with regard to the exercise by the arbitrator of his/her powers and the administration of the arbitration process. This process remains widely governed by the will of the parties and the confidentiality of the procedure. The disclosure of the funding agreement and determining the status of the funder are amongst the various questions triggered by the presence of a third-party in the arbitration process.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitration; Common law; Confidentialité; Droit -- Aspect économique; Extension contrat; Financement; Third-party; Tiers; Tiers (droit)

L'administration de la preuve en arbitrage international au regard des règles de l'International Bar Association ainsi que des règles de Prague - Gommé, Laurence (Université de Liège, 2019)
Ce travail traite principalement de l’administration de la preuve en arbitrage international. Cette question divise les praticiens du monde arbitral en deux camps : ceux issus de la tradition de common law et ceux issus de la tradition de civil law. Dans un premier temps, les règles de l’International Bar Association relatives à l’administration de la preuve ont tenté de concilier ces deux traditions juridiques différentes. Dans un second temps, les règles de Prague ont, récemment, été publiées ce qui nous permettra, dans ce travail, d’analyser les deux systèmes pour ensuite les comparer. Enfin, nous essayerons d’envisager l’avenir de ces nouvelles règles de Prague.
Keywords: Arbitrage; Civil law; Common law; Preuve; Production de documents; Règles de Prague; Règles de l'IBA; Soft law

L'intervention du juge étatique dans le cadre des mesures provisoires ou conservatoires en présence d'une convention d'arbitrage : analyse du droit belge - Sabatini, Fiona (Université de Liège, 2019)
L’arbitrage, en tant que justice privée, s’entend comme un mode de règlement des différends tant alternatif qu’antagoniste de la justice étatique. Dépourvu d’imperium, l’arbitre peut nécessiter le soutien et la coopération du juge pour traiter une procédure arbitrale. Divers droits contemporains de l’arbitrage envisagent explicitement le recours aux mesures provisoires et conservatoires lors d’un arbitrage interne ou international sans nécessairement apporter une définition de ces mesures. En matière d’arbitrage, les mesures provisoires et conservatoires détiennent un rôle capital préalablement ou durant l’instance arbitrale. Elles permettent le maintien d’une preuve, d’une situation de fait ou de droit et garantissent ou préparent une exécution efficiente et rapide de la sentence. La réunion dans le chef de l’arbitre de la compétence au fond et celle au provisoire peut être défavorable aux intérêts des parties, notamment lorsque le tribunal arbitral n’est pas encore saisi. Dès lors, prenant en considération les particularités de l’arbitrage et plus particulièrement du déroulement du procès arbitral, l’intervention du juge est indispensable pour résoudre temporairement une urgence sur le fondement de l’apparence d’un droit afin de conférer une force exécutoire aux décisions de l’arbitre. Le tribunal arbitral n’est pas seul à décerner ces mesures. Il est subséquemment légitime de se questionner sur la position du juge au sujet des mesures provisoires et conservatoires lors d’un arbitrage. Après analyse des diverses dispositions du Code de l’arbitrage, il résulte que le législateur met un point d’honneur à orchestrer la relation entre l’arbitre et le juge étatique. Pour ce faire, il opte pour une distribution de compétences entre le juge du provisoire et l’arbitre, une sorte de répartition qui implique un retrait de la compétence exclusive de l’arbitre en termes de mesures provisoires et conservatoires. Aussi, délibérément choisi par les parties, l’arbitre prononce le droit, mais sa décision est dénuée d’imperium. C’est la raison pour laquelle le recours au juge étatique est indispensable afin de soutenir sa décision. En matière de mesures provisoires et conservatoires, la compétence du juge judiciaire est à la fois partagée avec l’arbitre, mais aussi exclusive.

Médiation dans le domaine de la santé - Bonafe-Schmitt, Jean-Pierre (La lettre des médiations, 2019)
Depuis le milieu des années soixante-dix, la médiation s’est développée dans tous les champs de la vie sociale de l’entreprise à la famille, sans oublier le quartier ou l’école… et plus tardivement dans le champ de la santé, ce qui tend à démontrer qu’il existe un certain nombre de résistances à son développement1. Pourtant, au-delà du phénomène de mode, il convient de s’interroger sur ce renouveau de la médiation qui ne peut pas être réduit à une simple technique de gestion des conflits, car elle vise plus largement à (re)créer du lien social dans nos sociétés marquées par l’individualisation, la fragmentation, le délitement des rapports sociaux. Le domaine de la santé n’échappe pas à ce délitement des se caractérise à la fois par la montée des incivilités et de la violence dans les établissements hospitaliers, et plus largement par une crise de confiance entre le monde médical et les patients.
Keywords: Mediation; Médiation; Santé

May an employer dismiss an employee if the disciplinary chair imposed a lesser sanction? South African Revenue Service v Commission for Conciliation Mediation and Arbitration 2017 38 ILJ 97 (CC) - Calitz, Karin Beatrix (Stellenbosch Law Review, 2019)
In South African Revenue Services v Commission for Conciliation, Mediation & Arbitration, Kruger, the employee, called his superior a “kaffir” on more than one occasion. The employer unilaterally dismissed the employee after the chairperson of the disciplinary hearing had imposed a lesser sanction. In doing so, the employer disregarded the collective agreement which did not make provision for the sanction of the disciplinary chair to be substituted. The employee claimed that his dismissal was invalid and therefore unfair. The Commission for Conciliation Mediation and Arbitration (“CCMA”), Labour Court and Labour Appeal Court (“LAC”) agreed. However, in the Constitutional Court (“CC”) the employer no longer argued that it was entitled to substitute the sanction in the light of the breach in the trust relationship, but only alleged that reinstatement was a remedy that no reasonable decision-maker would order. The CC agreed and held that the dismissal was substantively fair but procedurally unfair. The CC did not answer questions of lawfulness, fairness and invalidity, but in Steenkamp v Edcon the CC held that employees claiming remedies for unfair dismissal in terms of the Labour Relations Act 66 of 1995 (“LRA”) should not rely on invalidity. However, employees still have the right to common-law remedies based on their employment contract. Considering the importance of collective agreements, negotiated disciplinary codes, certainty and consistency, and to avoid employers exercising unfettered power over employees, state organs should apply for a review of an unsatisfactory sanction by the disciplinary chairperson in terms of section 158(1)(h) of the LRA. Private employers could negotiate a disciplinary code which allows both the employer and employee to appeal against the decision of the disciplinary chair which should make provision that a more severe sanction can be imposed on appeal.
Keywords: Arbitrage; Arbitragem; Arbitration; Commission for Conciliation; Dismissal of employees; Labor discipline; MARD; Mediación; Mediation; Mediação; Médiation; South Africa; South African Revenue Services

La protection du tiers lésé par une sentence arbitrale - Do, Van dai (Revue internationale de droit comparé, 2019)
L’arbitrage est un mode de règlement des litiges convenu entre les parties mais il se peut que la sentence issue de ce mode de règlement porte atteinte au tiers, qui n’est ni partie, ni représenté à l’instance arbitrale. La présente étude comparative montre qu’il existe divers moyens de protection offerts au tiers lésé mais le meilleur instrument de protection est la tierce opposition contre la sentence arbitrale. Toutefois, une telle tierce opposition est encore peu connue dans le monde, de très nombreux systèmes, l’ignorent. En espérant que ce recours se développe au profit du tiers, cette étude montre ses avantages, sa consécration dans certains pays ainsi que son régime juridique. Arbitration is a mode of dispute resolution agreed between the parties but it is possible that the award resulting from this method of settlement infringes a third party’s right, who is neither a party nor represented in the arbitration proceedings. This comparative study shows that there are various means of protection offered to the injured third party but the best protection instrument is the third party opposition to the arbitration award. However, such a third party opposition is still not widely known in the world, many systems ignore it. Hopefully this remedy will be developed for the benefit of the third parties, this study shows its advantages, its recognition in certain countries as well as its legal regime.

L'avocat et la résolution des conflits - Dutoit, Nicolas (Anwalts Revue de l'Avocat, 2019)
Keywords: Arbitrage; Conciliation; Différends; Droit collaboratif; Litiges; Médiation; Négociation; Orientation préalable; Résolution de conflit

A Critical Look at the Mechanism for Challenge of Arbitrators Under ICSID Convention and Arbitration Rules - Gautama, Ivan (Juris Gentium Law Review, 2019)
Administered arbitrations under ICSID are amongst the most-utilized means to resolve investor-state disputes. Part of why it is so is because the ICSID as an institution is heavily affiliated with the World Bank. This affiliation serves as a double-edged sword in ICSID’s hands: while on one side such affiliation lends ICSID the credibility any successful arbitral institutions need, on the other side ties between the two institutions are proving to become too close for comfort. This paper explores what could go and has gone wrong in the past within the current ICSID arbitration system with regards to the mechanism for challenging arbitrator(s), and whether such mechanism allows ICSID to effectively deliver what it is expected to provide.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Conflict of interest; ICSID; Investor-State; World Bank

Online Dispute Resolution: Methods and Effects - Kumari, Poonam; Sood, Geetika (International Journal of Science and Research, 2019)
The concept of online dispute resolution came with the development of e-commerce. It is a branch which resolves the dispute between parties without interference of court. It includes arbitration mediation and negotiation. It also includes consumer to consumer disputes. With the emerging to globalisation the concept of online dispute resolution emerging day by day. The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. Thearticle is a study of ODR, online mediation and electronic arbitration. It includes their uses and their relationships with e-commerce. The paper is regarding primary aspects of online dispute resolution, its definition and its growth and development. It also includes the relationship between ODR and technology. Research paper isdiscussing the two forms of ODR: online mediation and electronic arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Online Dispute Resolution

El estatuto jurídico de los árbitros en el sistema CIADI - Soto-Díaz, David (Universidade da Coruña, 2019)
[Resumen] El arbitraje entre Estados y particulares extranjeros es un mecanismo de resolución de litigios a caballo entre el Derecho internacional público y el Derecho privado, que desde finales de la década de 1990 ha vivido un sorprendente auge a nivel mundial. Una modalidad de arbitraje institucional de inversiones es la del CIADI -Centro Internacional para el arreglo de Disputas sobre inversiones-, organismo dependiente del Grupo del Banco Mundial. El propósito de la tesis es llevar a cabo una investigación sobre la configuración de la independencia e imparcialidad de los árbitros del CIADI, sus derechos y deberes en tanto que tales y sus facultades procesales. La investigación se valdrá del Derecho comparado, tanto nacional como internacional, realizando una análisis de la doctrina, la práctica y la legislación que regula el sistema CIADI. A arbitraxe entre Estados e particulares estranxeiros é un mecanismo de resolución de controversias a cabalo entre o Dereito internacional público e o Dereito privado, que dende finais da década de 1990 viviu un sorprendente auxe a nivel mundial. Unha modalidade de arbitraxe institucional de investimentos é a do CIADI -Centro Internacional para o Arranxo de Desputas sobre Investimentos-, organismo dependente do Grupo do Banco Mundial. O propósito da tese é facer unha investigación sobre a independencia e imparcialidade dos árbitros do CIADI, os seus dereitos e deberes como tales e as súas facultades procesuais. A investigación valerase do Dereito Comparado, tanto nacional como internacional, realizando unha análise da doutrina, a práctica e a lexislación que regula o sistema CIADI. Arbitration between States and foreign investors is a dispute-resolution mechanism halfway between international public Law and private Law, which had surprisingly rised during the 1990's at the world level. In this work the following issues will be tackled: the legal nature of the aforementioned arbitrators. ICSID -International Centre for the Settlement of Investments Disputes- is a modality of institutional arbitration for investments. This institution is incarditated into the World Bank Group. The aim of this dissertation is to carry out a research on the configuration of the independence and impartiality of ICSID arbitrators, as well as their duties and rights as such and their procedural faculties. The research will be based on both national and international comparative Law, focusing in legal doctrine, in praxis and in the law governing the ICSIS system.
Keywords: Arbitrage international; Arbitragem; Arbitraje internacional; Arbitration; Derecho comparado; Mercado financiero-Derecho

Emerging Issues in Arbitration, Mediation and Conciliation - Sunil, Bhawna Bhelly (International Journal of Science and Research, 2019)
The resolution of disputes through alternative dispute resolution mechanisms has gained momentum over recent decades. It has increasingly occupied space in the academic literature as the “new” method to achieve “justice” for disputing parties. It is important to note that a variety of definitions of “justice” can be relied upon. However, in many cases, justice will mean the parties being able to resolve their dispute fairly, justly and amicably by applying law or legal principles. Traditional legal mechanisms for resolving disputes have been increasingly questioned as to whether they are actually capable of achieving justice in individual cases. Resolution in the courts is not only the method of resolving disputes . If the parties can resolve their own disputes then there will arise no need for court system in world. All though court system is good and fair way of dealing with civil disputes yet it might not be the best method to resolve the disputes. Basically there are four ways to of alternate dispute resolution. They are Negotiation, Mediation, Conciliation and Arbitration . The of ADR is to resolve the matters in a cost effective manner and foster long term relationship.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Conciliation; MARD; Mediación; Mediation; Mediação; Médiation; Méthodes alternatives de règlement de conflit

Milletlerarası Özel Hukukta arabuluculuk - Yarar, Güven (Akdeniz Üniversitesi, 2019)
Son yıllarda farklı hukuk düzenlerinde ve Türk hukukunda uyuşmazlıkların arabuluculuk yoluyla çözümü hususunda önemli gelişmeler kaydedilmesine rağmen bünyesinde yabancılık unsuru barındıran arabuluculuk faaliyetleri konusunda belirsizlik bulunmaktadır. Zira arabuluculuk faaliyetinin birden fazla hukuk düzeni ile irtibatlı olmasının arabuluculuk sürecine etkisine yönelik yasal düzenleme ve monografik çalışma eksikliği mevcuttur. Bu nedenle, arabuluculuk faaliyetinin yabancılık unsuru içermesi hâlinde meydana gelebilecek Kanunlar İhtilâfı ve Milletlerarası Usul Hukuku meselelerinin tespit edilip çözüm önerileri sunulması teorik ve pratik açıdan son derece önemlidir. Bu çalışma kapsamında ilk olarak, arabuluculuğa ilişkin genel bilgiler verilmiş ve arabuluculuğun hukuk sistemlerindeki yeri incelenmiştir. Akabinde arabuluculuğun Kanunlar İhtilâfı boyutu üzerinde durulmuş ve arabuluculuk faaliyeti kapsamında meydana gelebilecek Kanunlar İhtilâfı meselelerinin çözülebilmesi için terminoloji oluşturulması gereği anlaşılmıştır. Bu bağlamda, millî, milletlerarası ve milletlerarası ticarî arabuluculuğun çerçevesi genel hatlarıyla çizilmiştir. Ardından arabuluculuk faaliyetinin temel taşları niteliğinde olan arabuluculuk ve arabulucu sözleşmesine uygulanacak hukuka dair değerlendirme yapılmış, arabuluculuğa elverişliliğe ve arabulucunun hak ve yükümlülüğüne uygulanacak hukuka ilişkin muhtemel sorunlar tespit edilip çözüm önerilerinde bulunulmuştur. Arabuluculuğun Milletlerarası Usul Hukuku boyutu kapsamında ise arabuluculuk usulüne uygulanacak hukukun önemi ve bu hukukun tespitinde kullanılabilecek kriterlere yer verilmiştir. Daha sonra, birden fazla hukuk düzeni ile irtibatlı bulunan arabuluculuk faaliyetinin başarıyla sonuçlanmasıyla oluşan milletlerarası anlaşma belgesi ele alınmıştır. Bu bağlamda, milletlerarası anlaşma belgesinin mevcudiyeti için kabul edilebilecek koşullara yönelik değerlendirme yapılmıştır. Son olarak, milletlerarası anlaşma belgesinin tanınması ve tenfizine yönelik ihtiyaç tespit edilmiş, milletlerarası anlaşma belgesinin tanınması ve tenfizine ilişkin kabul edilebilecek ön ve aslî şartlar ile tanıma-tenfiz usulüne yer verilmiş ve sonuç ve değerlendirmelerde bulunularak çalışmamız tamamlanmıştır. Although significant progress has been achieved in different legal systems and Turkish law in terms of settlement of disputes through mediation for last years, there is uncertainty regarding mediation activities that include foreign elements. The reason is that there is not much legal regulation and monographic studies on the effect of mediation activity being linked to more than one legal order over mediation process. For this reason, it is very important theoretically and practically to identify the issues of Conflict of Laws and International Procedural Law that may occur in case of mediation activity involving foreign elements. In this study, first of all, general information concerning mediation is given and the legal aspect of mediation is examined in legal systems. Subsequently, the legal aspect of mediation in conflict of law was emphasized and it was understood that the terminology should be established in order to solve the Conflicts of Laws that may occur within the scope of mediation activity. In this context, the framework of national, international and international commercial mediation is outlined. Then, the assessment of the law to be applied to the mediation and mediation agreement which is the cornerstones of the mediation activity was made, possible problems related to the mediability and mediation of the mediator's rights and obligations were identified and solutions were proposed. Within the scope of mediation law aspect of International Procedural Law, the importance of the law to be applied to mediation procedure and the criteria that can be used in determining this law are included. Following this, the international agreement document which was formed by the successful completion of the mediation activity which is connected with more than one legal order was emphasized. In this context, an assessment was made on the conditions acceptable to the existence of the international convention. Finally, the need for the recognition and enforcement of the international agreement document was determined and our study was completed making results and evaluations by including the prerequisite and essential conditions for the recognition and enforcement of the international agreement document and the recognition-enforcement procedure.
Keywords: Arabuluculuk; Droit international privé; International law; International private law; Mediation; Médiation; Uluslararası hukuk; Uluslararası özel hukuk

La collaboration entre la CCJA et les juridictions nationales de cassation dans le cadre du droit OHADA - Assi N'Guessan, René Marcel (Université de Perpignan, 2018)
La collaboration entre la CCJA et les juridictions nationales de cassation, s’effectue dans le contentieux des Actes uniformes. Il met en oeuvre la supranationalité judiciaire de la CCJA qui se manifeste par sa substitution aux juridictions nationales de cassation soulevant des questions liées aux Actes uniformes. Il faut reconnaître que la complémentarité de la collaboration entre la CCJA et les juridictions nationales de cassation dans le recours en cassation devant la CCJA fait ressortir différents des problèmes : une inconstitutionnalité du Traité ou des Actes uniformes dans le processus d’intégration, des inquiétudes dans la procédure de recours en cassation (pas d’auto-saisine de la CCJA, absence de cas d’ouverture à cassation devant la CCJA, formule exécutoire sur les arrêts de la CCJA), l’évocation, la substitution des juridictions nationales de cassation créent devant la CCJA, une controverse dans l’identification du juge compétent dans les procédures de l’AUPSRVE, un risque de conflit de compétence et de lois avec des organisations régionales surtout (UEMOA). Cette collaboration se poursuit entre le juge étatique et la CCJA dans l’arbitrage, c’est le mode de règlement des litiges dans le système OHADA, à cause de l’éthique de l’arbitrage. Ce mode de règlement des litiges dans le mode des affaires ne répond plus au critère du monde des affaires. Même si l’arbitrage OHADA est dual (ad hoc et CCJA), il faut trouver des moyens dans divers droits plus adéquats pour pallier aux divers problèmes évoqués dans le monde des affaires.
Keywords: Arbitrage; Arbitration; Arbitration Agreement; Auto-saisine; CCJA; Connectedness; Controverse; Controversy; Inconstitutionnalité; Litispendance; Organisation pour l'harmonisation en Afrique du droit des affaires; Self-referral; Unconstitutionality

Règlement des différends relatifs à l'investissement dans le système de règlement des différends de l'Organisation Mondiale du Commerce (OMC) : Étude comparative entre l'arbitrage investisseur-Etat et les mécanismes de règlement des différends de l'OMC - Al Jehni, Rania (Université Paris-Est, 2018)
Les investisseurs étrangers dans les secteurs de services occupent une position particulière dans le droit économique international : ils sont couverts par des accords internationaux d'investissement ainsi que par des disciplines multilatérales sur le commerce des services. Contrairement à ce que la pratique actuelle suggère, les deux principales composantes du droit économique international, à savoir le droit commercial et le droit des investissements, fusionnent. Ils partagent non seulement des principes et des règles essentiellement équivalents, mais leurs disciplines s'appliquent également aux mêmes sujets et situations. Les accords internationaux d'investissement et les règles de l’OMC sur le commerce des services (disciplines de l'AGCS), bien que de nature très différente, présentent des principes communs qui favorisent l'investissement international dans les secteurs de services. En particulier, les deux ensembles d'accords consacrent des obligations de non-discrimination entre les investisseurs étrangers et nationaux dans les secteurs de services. Dans cette situation, les investisseurs étrangers profitent également des obligations que les deux ensembles d'instruments imposent aux États contractants. Ces instruments prévoient de solides mécanismes de règlement des différends en cas de violation de leurs obligations. Les investisseurs étrangers dans les secteurs de services peuvent donc avoir recours à deux mécanismes alternatifs de règlement des différends pour contester les mesures de leurs pays hôtes qui enfreignent les obligations internationales.L’OMC, contrairement au CIRDI, est beaucoup plus qu’un simple système de règlement des différends : l’OMC possède un élément institutionnel important qui a la capacité de fournir et d’appliquer les valeurs systémiques. Cette différence fondamentale entre le système de règlement des différends de l’OMC et d’arbitrage du CIRDI fournit une perspective analytique à travers laquelle l’étude évalue et compare la portée précise du chevauchement entre les disciplines du commerce et de l'investissement, ainsi que la capacité des parties privées à recourir à ces mécanismes de règlement des différends.Du point de vue méthodologique, deux approches sont concevables. Une analyse comparative et contextuelle : l'accent est mis sur les accords internationaux accordant la qualité pour les parties privées dans les procédures internationales de règlement des différends. L'attention est attirée sur le droit international du commerce et d'investissement, en comparant les principes, les règles et les mécanismes de règlement des différends du cadre de l'investissement international (y compris les accords qui définissent les relations d'investissement internationales) et le cadre d'investissement assez limité de l'OMC, principalement les dispositions pertinentes de l'AGCS. Une approche inductive, la jurisprudence est également pertinente. Un examen approfondi de la jurisprudence existante sur chaque sujet, afin de clarifier le sens de règles par ailleurs vagues et ambiguës et de répondre finalement à la question de savoir si les procédures de règlement des différends de l'OMC pourraient constituer une alternative valable pour le règlement des différends entre l'investisseur dans le secteur de services et l'État.
Keywords: CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Commerce international; Différends; ICSID; Investissements; Investissements étrangers; Investment; Investments; OMC; Organisation mondiale du commerce; Réglementation; Settlement; WTO; Échanges internationaux de services

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

L'unité fondamentale des accords amiables - Poli, Catherine (Aix-Marseille Université, 2018)
Les processus de résolution amiable des différends – conciliation, médiation, procédure participative ou droit collaboratif – présentent une unité d’objectif. Leur mise en œuvre permet une tentative de conclusion d’un accord amiable : un contrat consacrant la solution du différend construite par les parties. Sans se départir d’une approche procédurale, cette étude propose une analyse contractuelle de la résolution amiable des différends. Au-delà d’une procéduralisation de la formation de l’accord amiable, le droit commun des contrats sert en effet de manière unitaire les négociations et la conclusion de l’accord amiable. Ce dernier présente néanmoins une certaine diversité au regard des qualifications contractuelles qu’il peut revêtir. Si le contrat de transaction apparaît comme un référent à l’accord amiable, tout accord amiable ne consiste pas nécessairement en une transaction. Mais au-delà du jeu des qualifications possibles, le droit commun des contrats fédère les conditions de validité et les forces de l’accord amiable. Une unité fondamentale des accords amiables se révèle ainsi, garantissant la résolution effective des différends. The amicable settlement process - conciliation, mediation, collaborative procedure or law - present the same aim. Every amicable settlement process permits the conclusion of an amicable agreement: a contract consecrating the solution built by the parties. Without distracting from procedural approach, this study offers a contractual analysis of the amicable dispute resolution. Beyond a proceduralisation of the negotiation and the amicable settlement formation, it is the general law of contract that insure a support to the amicable settlement process. However, the amicable settlement presents some diversity due to peripheral qualifications. If the transaction contract is a reference to the amicable settlement, every amicable settlement is not necessarily a transaction. Beyong the choice of qualifications, the general contract law unites the validity conditions and the forces of the amicable settlement. A fundamental unity of amicable settlements reveals, safeguarded the effective dispute resolution.
Keywords: ADR; Accord amiable; Alternative dispute resolution; Amicable settlement; Amicable settlement process; Collaborative law; Conciliation; Conciliation process; Droit collaboratif; MARD; Mediación; Mediation; Mediação; Modes alternatifs de résolution des différends; Médiation; Processus de résolution amiable des différends; Procédure participative; Résolution amiable des différends; Transaction; Transaction (droit); Transaction agreement

Arbitraje y propiedad intelectual: consideraciones procesales y desafíos para un arbitraje eficiente - Gil Seaton, Ayllen (Universitat Pompeu Fabra, 2018)
En el presente trabajo se propone estudiar al arbitraje en materia de propiedad intelectual desde una perspectiva procesal, con miras a contribuir a la eficiencia y eficacia de su procedimiento. La especial idoneidad del arbitraje como mecanismo de resolución de estas controversias, muestra la fuerte conexión entre los derechos de propiedad intelectual y el arbitraje. Sin embargo, del estudio empírico realizado se revela una disonancia entre el desarrollo de los derechos de propiedad intelectual y la evolución del arbitraje en la materia. A partir de esta primera constatación, se profundiza en la identificación de tres obstáculos clave en el funcionamiento del arbitraje y se sugiere recurrir al derecho procesal como método de solución de los mismos. Finalmente, se proporcionan herramientas concretas de solución en materia de arbitrabilidad, intervención de terceros y efectos del laudo. Todo lo anterior con el objetivo de consolidar al arbitraje como un mecanismo de resolución de disputas en materia de la propiedad intelectual.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Intellectual property; Propriedad intelectual; Propriedade intelectual; Propriété intellectuelle

Modes alternatifs de résolution des conflits – droit des affaires - Conférence internationale des barreaux CIB (2018)

Le procédé de passerelle entre la conciliation et la sauvegarde - Approche comparative droit français/droit OHADA - Kourouma, Moussa Fanta (Université de Toulon, 2018)
Cette thèse porte sur le procédé de passerelle entre la conciliation et la sauvegarde, dans une approche comparative droit français, droit OHADA. Le procédé de passerelle permet au chef d’entreprise d’élaborer un plan de redressement dans le cadre de la conciliation, avant de le faire adopter lors d’une sauvegarde accélérée. La présente thèse se subdivise en deux parties. Dans la première partie, un diagnostic est posé pour comprendre les raisons de l’adoption de ce mécanisme de traitement des difficultés des entreprises en droit français, et celles qui pourraient ou non justifier sa reconnaissance en droit OHADA. Il ressort de cette partie que, dans les droits français et OHADA, la rigidité du régime de la cessation des paiements ainsi que l’unanimité obligatoire de l’accord de conciliation constituent un handicap au redressement des entreprises, car le principe d’unanimité donne un droit de véto à chaque créancier. Le procédé de passerelle permet de passer outre l’opposition des créanciers minoritaires qui utilisent ce droit de véto pour faire adopter le projet de redressement du chef d’entreprise par vote majoritaire sur le terrain judiciaire. Dans la deuxième partie, une étude prospective est menée ; le procédé de plan pré-négocié joue un rôle à la fois préventif et curatif : il permet, d’une part, la libre négociation, entre un débiteur et ses créanciers, d’un plan conventionnel de restructuration et, d’autre part, l’anticipation de l’intervention du tribunal pour optimiser l’actif et maîtriser le passif. Le procédé de passerelle est adopté en droit français ; la présente thèse propose une étude de son régime juridique. Il n’est pas reconnu pour le moment en droit OHADA ; son applicabilité y est analysée. Pour l’amélioration de la prévention et du traitement des difficultés des entreprises dans les droits français et OHADA, des pistes sont proposées. Il en est ainsi notamment, d’un côté, de l’adoption des comités de créanciers dans la procédure de conciliation française et, de l’autre, de la reconnaissance du mécanisme de plan pré-négocié, de la réforme du régime de la cessation des paiements et de la spécialisation des tribunaux connaissant des contentieux régis par l’AUPC en droit OHADA. La présente étude, en plus d’apporter une contribution scientifique à l’étude des nouvelles procédures de sauvegarde accélérée en droit français, vise à lancer le débat sur l’opportunité de l’adoption du procédé de passerelle en droit OHADA. L’organisation de la cession pré-arrangée dans le cadre du mandat ad hoc en droit français et l’opportunité de l’adoption d’une telle cession en droit OHADA sont des problématiques qui pourraient faire l’objet d’une recherche. This thesis focuses on the bridging process between conciliation and safeguarding, in a comparative French law approach, OHADA law. The gateway method allows the entrepreneur to develop a recovery plan in the context of conciliation, before adopting it during an accelerated backup. This thesis is divided into two parts. In the first part, a diagnosis is made to understand the reasons of the adoption of this mechanism of treatment of the difficulties of the companies in French law, and those which could or could not justify its recognition in OHADA law. It appears from this section that, in the French and OHADA laws, the rigidity of the system of cessation of payments and the compulsory unanimity of the conciliation agreement constitute a handicap to the recovery of the undertakings, since the principle of unanimity a veto right to each creditor. The gateway process makes it possible to override the opposition of the minority creditors who use this right of veto to get the project of recovery of the head of enterprise adopted by majority vote on the legal ground. In the second part, a prospective study is conducted; The pre-negotiated plan process plays both a preventive and curative role : it allows, on the one hand, the free negotiation, between a debtor and its creditors, of a conventional restructuring plan and, on the other hand, the anticipation of court intervention to optimize assets and control liabilities. The gateway method is adopted in French law; this thesis proposes a study of its legal regime. He is not recognized for the moment in OHADA law ; its applicability is analyzed. For the improvement of the prevention and the treatment of the difficulties of the companies in the French rights and OHADA, tracks are proposed. This is notably the case, on the one hand, of the adoption of the creditor committees in the French conciliation procedure and, on the other, of the recognition of the pre-negotiated plan mechanism, of the reform of the cessation of payments and specialization of courts dealing with disputes governed by the AUPC under OHADA law. This study, in addition to making a scientific contribution to the study of new accelerated safeguard procedures in French law, aims to launch the debate on the appropriateness of the adoption of the OHADA gateway process. The organization of the pre-arranged assignment under the ad hoc mandate in French law and the advisability of adopting such an assignment in OHADA law are issues that could be the subject of research.
Keywords: Cessation des paiements; Cessation of payments; Conciliation; Contractualisation; Contractualization; Droit du travail; Entreprises; Entreprises en difficulté; Etude comparative; Expedited backup; Faillite; France; Gateway process; Labour law; MARD; Mediación; Mediation; Mediação; Médiation; Negociation; Négociation; Pays de l'OHADA; Plan pré-négocié; Pre-negotiated plan; Prepack-cession; Prevention; Preventive regulation; Procédé de passerelle; Prévention; Règlement préventif; Sauvegarde accélérée; Transmission

Les émanations de l'État à vocation économique dans l'arbitrage des investissements et dans le contentieux de l'O.M.C - Cortesi, Giulio Alvaro (Université Paris 1 ; Università degli Studi di Padova, 2018)
L'idée de cette thèse sur le droit international des investissements concernant les entreprises d'État trouve son origine dans l'impressionnant développement économique de ces dix dernières années. D'une part, ce dernier donne une pertinence considérable à ce thème compte tenu de son actualité. D'autre part, il existe un intérêt considérable pour les problèmes juridiques laissés en suspens par ces entités. Cette thèse commence par un chapitre préliminaire dans lequel la forme juridique de ces institutions est analysée, à la fois avec une évaluation empirique et du point de vue du droit national et international applicable à ces sujets. L'analyse empirique approfondie qui n'a pas encore été réalisée dans les recueils de contributions examinés s'est révélée fondamentale, car certaines des questions juridiques concernant les entreprises d'État ne pourraient vraiment pas être abordées sans une telle approche. Le corps plus juridique de la thèse, consacré uniquement à l'analyse juridique, est composé de trois parties et présente deux principaux pôles d'intérêt : le premier est lié à la compréhension des implications juridiques de ces entités et le second, plus large, vise à comprendre le traitement qui a été réservé à ces organes dans les différends examinés. Ce traitement peut nous renseigner au niveau systémique sur le droit international des investissements, qui a également nécessité une comparaison ciblée avec l'arbitrage commercial et avec le droit commercial international. The idea of a thesis on state enterprises in international investment law finds its roots in their impressive economic development during the last decade, which, on one hand, gives considerable relevance to this theme given its inherent actuality and, on the other hand, there is a considerable interest in the juridical problems that these entities leave open. The thesis consists of a preliminary chapter, were the legal form of these institutions has been analyzed, from both an empirical assessment and the standpoint of national and international law applicable to these subjects. The empirical, in-depth analysis, not yet reached in the collections of examined contributions, turned up as fundamental, because some of the legal issues concerning state enterprises cannot really be tackled without such an approach. The more juridical body of the thesis, devoted only to legal analysis is composed of three parts and has two main poles of interest: the first linked to the understanding of the legal implications of these entities and a second, and, wider one, aimed at understanding what the treatment of these bodies, occurred in the dispute cases examined, can tell us at a systemic level about international investment law, which has required also a targeted comparison with commercial arbitration and international trade law.
Keywords: Contentieux d'investissement; Contentieux fiscal; Contentieux économique; Economic litigation; Entreprises publiques; Finances publiques; Fond souverain; Investment arbitration; State enterprises

Problématique de la compétence et de la procédure devant la Cour Commune de Justice et d’Arbitrage de l'OHADA : cas de recours dans les litiges commerciaux congolais - Banza Ilunga, Aimé; Mwansa Kalunga, Jean-Pierre (KAS African Law Study Library, 2018)

Exécution des sentences arbitrales étrangères en République Démocratique du Congo - Kangaseke Mbaka, John; Tshizena Tshinate, Céline (KAS African Law Study Library, 2018)

Pour une justice contractuelle efficace : la médiation OHADA - Kenfack, Hugues (La Lettre, 2018)
Pendant longtemps, la médiation a été le parent pauvre de la justice contractuelle dans le monde. Depuis quelques temps, un vent de faveur souffle sur tous les modes alternatifs de règlement des différends (MARD) parmi lesquels la médiation occupe une place importante.
Keywords: Mediation; Mediação

La renonciation ponctuelle à la mise en œuvre d’une clause compromissoire rend-elle cette dernière manifestement inapplicable dans d’autres contentieux ? - Posocco, Laurent (La Lettre, 2018)

Le litige du travail a-t-il une nature réfractaire à l'arbitrage - Posocco, Laurent (La Lettre, 2018)

Les parties à un arbitrage international sont-elles solidairement tenues de la rémunération due aux membres du tribunal arbitral ? - Posocco, Laurent (La Lettre, 2018)

Médiation de la consommation dans le monde francophone - Thomas, Vincent (La lettre des médiations, 2018)
Le litige de consommation est souvent modeste. Il appelle de ce fait une solution rapide à moindre coût. Sauf exception, l'action en justice ne convient ni au consommateur, ni à l'entreprise, nommée « professionnel » par Code de la consommation. En effet, l'action judiciaire est longue, son résultat échappe à la prévisibilité des parties et les frais induits sont sans commune mesure avec les montants en jeu. Le législateur en a conscience. C'est l'une des raisons pour lesquelles il expérimente depuis quelques années des alternatives à la justice ordinaire. Le juge de proximité a ainsi été créé en 2002 pour les litiges inférieurs à 4 000 €, taux de compétence qui a permis de régler bon nombre de contentieux de la consommation. Malgré son utilité, ce juge spécial n'a pas survécu aux critiques du monde judiciaire et a été supprimé en 2017. Parallèlement, les modes amiables – c'est à-dire par l'accord des parties – de résolution des différends se sont développés. Le Code de procédure civile consacre depuis 2012 un titre complet à la médiation et à la conciliation conventionnelles dont dispositions s'appliquent en dehors de toute procédure judiciaire.
Keywords: Consommation; Mediation; Médiation

Defragmenting Investment disputes: Multilateral Court of Investment Disputes as a Panacea? - Kidane, Brook Bekele (Revue juridique des étudiants de la Sorbonne, 2018)
Never was there a time whereby investment dispute settlement came to the forefront of every possible communication outlet, from academia and mainstream news to civil societies and an outright protest of the public. TTIP and CETA brought ISDS to a broad daylight scrutiny in many parts of Europe getting the attention of law and policy makers at EU and national level. The criticisms and anxiety over ISDS relates to divergent interpretation of similar or identical International Investment Agreements (IIAs) provisions that lead to inconsistency and unpredictability of decisions, lack of transparency in investment disputes, lack of independence and impartiality of arbitrators, the elite group of arbitrators, costs, diversions of public money from public goods and services, ‘chilling effect’ on state regulatory powers and bypassing national judicial systems.; With a view to establish and tackle the problem with a meaningful solution to the legitimate concerns and anxieties, the EU, with its competence to conclude the Investment Agreements, attempted to create two mechanisms. The inclusion of Investment Court System (ICS) in newly concluded IIAs and the creation of a multilateral investment court.; This article will assess the three systems together, i.e. the ISDS, ICS, and the multilateral investment court, in terms the pros and cons and attempt to envisage the policy shortcomings or benefits under any of the systems. Jamais il n'y a eu une époque où le règlement des différends en matière d'investissement a été au premier plan de tous les moyens de communication possibles, qu'il s'agisse d'universitaires, de la presse grand public, de la société civile voire d’actions publiques. La TTIP et la CETA ont permis à l'ISDS de faire l'objet d'un examen minutieux dans de nombreuses parties de l'Europe, attirant l'attention des législateurs et des décideurs politiques au niveau européen et national. Les critiques et l'anxiété à l'égard de l'ISDS ont trait à l'interprétation divergente de dispositions similaires ou identiques des accords internationaux d'investissement (AII) qui conduisent à l'incohérence et à l'imprévisibilité des décisions, au manque de transparence dans les différends en matière d'investissement, au manque d'indépendance et d'impartialité des arbitres, à l'élite des arbitres, aux coûts, aux détournements de fonds publics des biens et services publics, à l'"effet paralysant" sur les pouvoirs réglementaires des États et au contournement des systèmes judiciaires nationaux. En vue d'établir et d'aborder le problème avec une solution significative aux préoccupations et aux inquiétudes légitimes, l'UE, avec sa compétence pour conclure les accords d'investissement, a tenté de créer deux mécanismes. L'inclusion de l'Investment Court System (ICS) dans les AII nouvellement conclus et la création d'un tribunal multilatéral de l'investissement. Cet article évaluera les trois systèmes ensemble, c'est-à-dire le SIPDS, le SCI et le tribunal multilatéral de l'investissement en termes d'avantages et d'inconvénients et tentera d'envisager les lacunes ou les avantages de l'un ou l'autre des systèmes.

Political risk in energy-related investment disputes - Sahin, H. (The World Arbitration and Mediation Review (WAMR), 2018)
The energy industry is a key source of growth stimulation for developing states. This is true not only in terms of economic growth, but also in terms of the transfer of knowledge and skills as well as the provision of employment opportunities. Understandably, developing states are well-disposed towards international investors, and are eager to enter into petroleum investment contracts with the expectation that this will bring the aforementioned benefits to their countries particularly where the host state is less able to act as a provider of such resources autonomously. On a global scale, regardless of their type, all investments face risks. These risks are volatile in nature and reach as the world economy globalises. It is, of course, true that political risk phenomena per se are potentially destructive to all industries. However, it is fair to say that due to its high stakes, the energy industry is more acutely exposed and subject to political risk than most sectors. The purpose of this article is to examine political risk, particularly direct expropriation risk, in long-term energy investment projects. This paper will refer to arbitral decisions with regard to expropriation cases, as well as the valuation techniques applied by the investment arbitration tribunals in unlawful expropriation cases.

International Arbitration Practices in Nigeria: A Construction Industry Appraisal - Ewa, O. O.; Haytham, B.; Okon, E. E.; Enang, O. P.; Emiri, D. A. (World Journal of Innovative Research, 2018)
This paper aims to investigate Corporate Alternative Conflict Management and Dispute Resolution compliance through an appraisal of International Arbitration practices in Project-based Organizations in the Nigerian Construction Industry. In this study, simple percentages and frequencies of occurrence were used to analyse data derived through subject matter interviews and a questionnaire survey. Using the Survey Monkey tool, 85 questionnaires were distributed to key players in the AEC (Architecture-Engineering-Construction) Industry including Engineers, Project Managers, Architects and Quantity Surveyors and 53 were returned complete. The survey indicated that 66% preferred a more private Construction Arbitration to a public Litigation as a preferred method of dispute resolution, with 65% agreeing that a lack of proper project funding hinders the arbitration process in the Nigerian Construction Industry. 66% agree that Arbitration Time contributes more to project delays while 32% believe that Cost of the arbitration process is the greater source of project delays. We recommend that issues of confidentiality be carefully managed in dealing with outside counsels, while Project-based Organisations in Nigeria should ensure to develop master plans compatible with long-term strategies, including setting aside adequate funding for the timely resolution of project disputes through the implementation of only Arbitration-friendly contracts. This paper contributes to knowledge by bringing to bear the current compliance levels of project-based organisations in the practice of Arbitration in the Nigerian Construction Industry.

Who is in? Who is out? How the Uncitral Transparency Rules Can Influence the Upcoming Amendments of the ICSID Arbitration Rules - Yu, Hong-Lin (Contemporary Asia Arbitration Journal, 2018)
The International Center for Settlement of Investment Disputes (hereinafter "ICSID") has started its fourth amendment of its Arbitration Rules since 2016. The issue of transparency has been highlighted as a delicate issue in ICSID ongoing current amendment. It is also listed in the topics that have been identified for potential amendment. This article analyses how the issues of access to hearings and confidentiality over information arising from arbitration is treated under the current framework. A comparison is made against the Transparency Rules. The analysis is also made against the comments received from the public whose views are analysed as a possible direction the amendment may take.

L'ineffectivité du droit du travail à l'orée de la réforme OHADA - Bitsamana, Hilarion Alain (Université Côte d'Azur, 2018)
Cette thèse est un condensé de différentes irrégularités ou violations des droits dont sont victimes les travailleurs africains par leurs employeurs, en dépit des diverses législations en matière du travail qui existent dans tous les Etats parties. Au point où ils paraissent vivre une autre exploitation après l’esclavage et le colonialisme, cette fois-ci par leurs propres compatriotes. Ces maux sont constatés à la fois dans les rapports individuels de travail comme dans les rapports collectifs. C’est ainsi que certains salariés sont recrutés à la suite des tests de complaisance, sinon par la corruption, sans un document de travail ; d’autres travaillent pendant des années pour percevoir des salaires de misère, dans des conditions de travail affreuses. Quant aux irrégularités relatives aux rapports collectifs, pour mieux les duper, ces travailleurs sont exclus de la gestion de l’entreprise, ne bénéficiant ni du droit d’expression, ni du droit de participer aux performances de l’entreprise ; encore moins d’une représentation collective exemplaire par les délégués du personnel et les syndicalistes. En cas de litige, ils n’ont pratiquement pas une bonne protection étatique par les inspecteurs du travail et les magistrats. Ainsi pour sortir de cette crise aigüe dans le secteur du travail privé qui fait des ravages depuis plusieurs années après les indépendances, bien qu’il existe une réforme en vue à travers l’OHADA, les autorités nationales et internationales doivent veiller à la bonne application du droit du travail en prenant les mesures qui s’imposent. A défaut, la réforme du droit du travail envisagée par l’OHADA sera elle aussi vouée à l’échec. This thesis is a compendium of various of rights which are currently victims of African workers by their employers despite various legislations in the work that exist in all states parties ; to the point where they appear to live another operation after slavery and colonialism. They live poverty on a daily basis. These evils are recognized both in the individual employment relationship as in public reports. This is how some employees are recruited following tests of complacency, if not corruptly there, without a working document ; others work for years to collect wages, without bonus, without leave, in terrible working conditions. As for collective reporting irregularities, to better trick these workers are excluded from the management company born with the right of expression or of the right to participate in the performance of the company still less than exemplary collective representation by the staff representatives and trade unionists. In case of dispute they have virtually no state protection by labor inspectors and judges. So out of this acute crisis in the sector private work that wreaks havoc for many years after independance, well there is a view through the OHADA reform, national and international authorities to ensure the correct application of the right to work by taking the measures that are necessary. Otherwise the reform of the labour law envisaged by the OHADA of the Right Business is also doomed to failure.
Keywords: Arbitrage; Arbitragem; Arbitration; Droit du travail; Employeur et employé (droit); Irregularities; Irrégularités; Job; Labour law; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'OHADA; Recruitment; Recrutement; Sécurité du travail; Travail

L’arbitrage international dans l'OHADA : évolution vers l’arbitrage des investissements en Afrique - Dalil, Mustapha (Journal of Strategic Affairs, 2018)
En vertu des dispositions de l’article 53 Al. 1 du Traité de création de l’OHADA (l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires) : « Le présent traité est, dès son entrée en vigueur, ouvert à l’adhésion de tout Etat membre de l’Union Africaine et non signataire du traité. Il est également ouvert à l’adhésion de tout autre Etat non membre de l’Union Africaine invité à y adhérer du commun accord de tous les Etats Parties ». Cette action d’harmonisation du droit des affaires, tout en s’inspirant d’autres législations telles que le droit français et la common law, les Etats-membres de l’OHADA ont à leur disposition un arsenal législatif efficace et approprié à leur développement économique communautaire. Ce droit revêt un intérêt particulier pour les entreprises marocaines actives dans l’espace OHADA. Le Maroc, par le renouvellement de son adhésion à l’Union Africaine (UA) et en procédant à une demande d’adhésion à la Communauté Economique des Etats de l’Afrique de l’Ouest (CEDEAO) dont le but est de « promouvoir la coopération et l’intégration dans la perspective d’une Union économique de l’Afrique de l’Ouest », (le Maroc) a réaffirmé sa détermination d’intégrer les espaces économiques africains de référence
Keywords: Arbitrage international; Droit des affaires; Développement économique; Relations internationales; Union africaine; الاتحاد الإفريقي; التحكيم الدولي; التنمية الاقتصادية; العلاقات الدولية; قانون الأعمال

Guide de l'arbitrage de la CCJA-OHADA - Cour Commune de Justice et d'Arbitrage (CCJA) (OHADA, 2018)

Médiation des relations de travail dans le monde francophone - Housty, Françoise (La lettre des médiations, 2018)
La médiation pour déminer les conflits au travail » : c’est ainsi que fut annoncée une grande vague de réforme judiciaire et des institutions du travail en France par les lois Macron dès 2016, afin d’introduire de la « médiation » dans le monde du travail1. L’objectif déclaré est de développer le dialogue au sein de l’entreprise et de prévenir le recours à une justice lente parce que engorgée.
Keywords: Mediation; Médiation; Relation de travail

60 Years of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958: Are We There Yet in Sub-Saharan Africa? - Okubote, Abayomi (Social Science Research Network, 2018)
Sub-Saharan Africa has, in recent years, been classified as a natural-resource play for foreign investors. These investment potentials have made the region one of the most attractive investment destinations in the world. The region is also diverse, with a mix of different legal systems and legal traditions. While investors are constantly seeking to understand the different legal regimes, international arbitration offers comfort by providing a framework for the enforcement of rights in a neutral forum and on a different platform. According to the World Bank, the ability to enforce an arbitral award is an important factor for investors considering potential markets in which to invest.Given the sixtieth anniversary celebration of the New York Convention (NY Convention), this article examines the enforcement regimes for arbitral awards in sub-Saharan Africa. It considers the momentous developments in the enforcement regimes in the region, due to the implementation of the NY Convention. It examines the proposed amendments to the enforcement provisions in the Nigerian Arbitration Act (Repeal and Re-enactment) Bill 2017, recently passed by the Nigerian Senate. It also examines the important provisions in the revised Uniform Act on the Law of Arbitration and the revised Rules of Arbitration of the Common Court of Justice and Arbitration – both recently adopted by the OHADA Council of Ministers. It attempts a comparison between the enforcement regimes in the OHADA Member States, the NY Convention Member States, and in countries that do not belong to any of the two regimes.A chart of the legal regimes on enforcement of foreign arbitral awards in sub-Saharan Africa is attached as appendix.
Keywords: ACA; Annulment; Arbitral Awards; CCJA; Commercial Arbitration; Convention; Enforcement; Enforcement of Arbitral Awards; Foreign Awards; ICSID Convention; Judiciary; New York Convention; OHADA; Reciprocity; Reservations; Sub-Saharan Africa; Treaty; UAA; UNICTRAL Model law

Guide pour le développement des services de médiation et arbitrage - Centre du Commerce International (ITC, 2018)
Keywords: Centre d'arbitrage; Centre de conciliation; Centre de médiation; Gestion; Management

L’arbitrage comme mode alternatif de règlement des litiges en RDC : cas de l’arbitre du CENACO - Kapinga K. Nkashama, Symphorien (KAS African Law Study Library, 2018)
Cette étude s’intéresse à l’arbitrage comme mode alternatif de règlement des litiges en RDC. L’auteur y analyse les règles juridiques qui s’appliquent à la compétence et à la sai- sine du Tribunal arbitral, au mode de désignation des arbitres qui le composent et à la pro- cédure arbitrale à suivre. Il étudie aussi la sentence arbitrale ainsi que les voies de recours offertes aux parties, avec un coup d’œil particulier sur l’arbitrage organisé par le centre Na- tional d’Arbitrage, de Conciliation et de médiation de la Fédération des Entreprises du Congo et en comparaison avec la procédure usitée devant les juridictions civiles étatiques
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitre; MARD; MARL; RDC

Les efforts de la CNUDCI pour accroitre le niveau de transparence dans l’arbitrage d’investissement - Belhadj, Miriana (Revue de l'ERSUMA, 2018)
Récemment, la Commission des Nations Unies pour le Droit commercial international (CNUDCI) a adopté deux instruments sur la transparence dans l’arbitrage entre investisseurs et États fondé sur des traités. Un Règlement adopté en 2013, prévoit des règles spécifiques pour compléter tout règlement d’arbitrage choisi pour régir un arbitrage conduit sur la base d’un traité d’investissement. Ces règles prévoient notamment, et sous certaines conditions, la publication d’informations et de documents relatifs à l’affaire. Elles permettent aussi que des observations soient présentées par les tiers ou par une partie au traité non partie au litige. Une Convention adoptée en 2014 met en place un mécanisme efficace permettant aux États de prévoir l’application du Règlement sur la transparence à leurs traités d’investissement antérieurs à l’entrée en vigueur du Règlement. À la date de cet article, la Convention compte cinq États parties, dont deux États africains (18 autres États, dont 3 États africains, l’ont signée) et est entrée en vigueur le 18 octobre 2017. Ces efforts de promotion de la transparence dans l’arbitrage d’investissement ont été suivis de discussions au sein de la CNUDCI aboutissant à ce qu’un nouveau groupe de travail au sein de la CNUDCI soit chargé de réfléchir à une possible réforme du système de règlement des différends entre investisseurs et États (RDIE). Dans le cadre de ces réflexions politiques et techniques de haut niveau, la question de la place de la transparence – autre que la transparence procédurale – est récurrente à plusieurs égards et inévitablement au cœur des débats.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; CNUDCI; Investissements; Investments; Transparence; Transparency

Arbitrage commercial international - Besson, Sebastien (Arbitrage, médiation et autres modes pour résoudre les conflits autrement, 2018)

La médiation et l'arbitrage dans l'espace UEMOA : recueil des lois et pratiques - Centre du Commerce International (ITC, 2018)
Keywords: Arbitrage; Arbitration; Mediation; UEMOA

La médiation et l’arbitrage de litiges commerciaux dans l’espace UEMOA - Centre du Commerce International (ITC, 2018)
Keywords: Arbitrage; Arbitration; Mediation; Médiation

Revista PLMJ Arbitragem : Jurisprudência comentada de 2017 - Coimbra Trigo, Ana; Monteiro, António Pedro Pinto; Heidrich Jaques, Betyna; Góis Coelho, Carla; Carrera, Iñaki; Schmid Moura, Joana; Tornada, João; Júdice, José-Miguel; Caldeira, Leonor; Carvalho, Mariana; Gouveia, Mariana França; Ziegler, Pacôme; et al. (PLMJ Advogados, 2018)

An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

Kroniek Internationale Arbitrage - De Ly, Filip (Tijdschrift voor Arbitrage, 2018)

L’arbitrage comme mode de règlement des différends dans les codes d’investissements des Etats membres de l’UEMOA - Djigle, Doundongue (Revue de Recherches en Economie et en Management Africain, 2018)
Dans le but d’attirer les investissements directs étrangers, les Etats membres de l’UEMOA ont adopté des codes d’investissements destinés à régir les relations entre investisseurs et Etats. Ces codes privilégient l’arbitrage comme mode de règlement des différends. Mais le fondement de cet arbitrage n’est pas le même dans chacun des codes. Certains codes comportent directement dans leur corpus la clause d’arbitrage que l’investisseur peut activer en cas de survenance d’un litige, tandis que d’autres renvoient à des sources extérieures, tel un contrat d’investissement ou un traité bilatéral d’investissement liant l’Etat d’accueil avec l’Etat d’origine de l’investisseur. En outre, dans leur pratique, les Etats de l’UEMOA donnent souvent le choix aux investisseurs entre différentes instances arbitrales. Pourtant, peu de procédures d’arbitrage sont engagées contre ces Etats sur le fondement des codes nationaux d’investissement.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Code des investissements; Etats membres.; Investissements; Investments; Offre d’arbitrage; UEMOA

Arbitration cost : a short comparative view of the schedule of fees of arbitration centers within the OHADA zone - Dogué, Karel Osiris Coffi (Revue de l'ERSUMA, 2018)
Amongst the seventeen OHADA member states there are over fourteen arbitration centers or institutions that handle disputes arising from contractual agreement without going through the courts of the state. The arbitration cost within the various arbitral centers differs from one arbitration center to another. The schedule or method for calculating fees are regulated by the rules of the various arbitration centers or by the OHADA Uniform Act Arbitration Rules pertaining to arbitration fees annexed to the rules of arbitration for the Common Court of Justice and Arbitration and for arbitration centers without arbitration rules. This contribution describes and contrast the various schedule of fees applicable with the arbitration centers under the OHADA zone in particular and also makes a comparative view of the arbitration fees out of the OHADA zone.
Keywords: Arbitragem; Arbitraje; Arbitration; Arbitration cost; Arbitration fee; Arbitration proceedings; Coût de l’arbitrage; Frais d’arbitrage; OHADA Arbitration's Center; Procédure arbitrale

Les MARD (modes alternatifs de résolution des différends) au prisme des droits fondamentaux substantiels - Dumas, Romain (Revue des droits et libertés fondamentaux, 2018)
La loi pour la justice du XXIème siècle a renforcé le recours aux MARD (modes alternatifs de résolution des différends) en incitant, voire en obligeant les parties à les utiliser pour tenter d’aplanir un nombre croissant de différends. Si la prise en compte des droits fondamentaux processuels par les MARD ne fait plus guère de doute, la question se pose néanmoins de savoir quel niveau de garantie ces processus accordent aux droit fondamentaux substantiels des parties qui les mobilisent.
Keywords: Arbitrage; Liberté contractuelle; Liberté d'expression; Médiation; Vie privée

Les fondements de la circulation de la convention d’arbitrage - Faye, Ousmane (Revue de l'ERSUMA, 2018)
« Il n’y a pas de contrat sans consentement des parties ». Tel est formulé le principe sacro-saint du consensualisme contractuel. Toutefois cette règle générale reconnue par tous les systèmes juridiques d’obédience romano-germanique ne finit pas de montrer des réserves. Ces exceptions se retrouvent dans tous les types de contrats même dans ceux qui portent sur le règlement alternatif des litiges. C’est cette dernière situation que traduit la problématique de l’application du contrat d’arbitrage à des tiers non-signataires, encore connu sous le terme de la circulation du contrat d’arbitrage. En principe la théorie de la relativité des conventions impose que l’engagement soit source d’obligations pour son auteur, mais pas pour les tiers auxquels l’acte ne peut ni profiter ni nuire. Malgré cette restriction, la jurisprudence et la doctrine restent largement favorables à la circulation de la convention d’arbitrage. Les fondements avancés pour justifier cet élargissement du contrat d’arbitrage à des tiers non-signataires sont assez divers. Certains sont tirés du droit des obligations notamment de la théorie de la représentation et des groupes de contrat. D’autres ont pour fondement le droit des sociétés, particulièrement la théorie des groupes de sociétés et celle de la levée du voile social ou l’alter ego.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Contrat d'arbitrage; Convention d'arbitrage; Corporate law; Droit des sociétés

La preuve dans la médiation commerciale - Kpako, Valentin V. V. (Revue de l'ERSUMA, 2018)
En considération de ce que la médiation commerciale entendue comme un processus par lequel des personnes physiques ou morales, demandent à un tiers de les aider à parvenir à un règlement amiable d’un différend découlant d’un rapport juridique, contractuel ou autre ou lié à un tel rapport, il est aisé de percevoir qu’il s’agit d’un mode de résolution non judiciaire de litige. A la différence du règlement judiciaire des conflits, la médiation commerciale tend à solutionner les points d’oppositions entre les parties, et à maintenir et soigner leurs relations d’affaires. Elle s’oppose à l’arbitrage qui tranche le litige par une sentence, qui s’impose aux parties, qu’elles la veuillent ou non. Elle ne génère donc pas de perdant, mais les deux parties doivent avoir fait des concessions, et gagner en temps. De ce fait, l’on est tenté d’affirmer que la médiation commerciale pourrait se passer de l’exploitation des moyens de preuve. D’ailleurs, l’Acte uniforme de l’OHADA relatif à la médiation ne fait aucune mention du principe de preuve dans la conduite de la médiation commerciale pas plus que l’ensemble des textes qui organisent la matière. L’on se pose même a question de l’opportunité d’avoir à prouver les faits dans une telle discipline si tant est que toutes les parties en sortent gagnantes. Mais à y voir de près, la médiation commerciale ne semble pas totalement exclure le système de la preuve tel que pratiqué dans la procédure judiciaire de résolution des conflits. Au contraire, elle en a fortement besoin pour à la fois justifier le fondement des prétentions des parties ainsi que la solution au litige. Précisément, la preuve dans la médiation commerciale participe à la détermination des points à discuter et à la justification tant des propositions formulées par le médiateur que des concessions à faire par les parties.
Keywords: Espace OHADA; MARD; Mediation; Médiation; Médiation commerciale; Procédure de médiation

La médiation civile : alternative ou étape du procès ? - Leborgne, Anne (Droit privé, 2018)
Initialement pensé comme une alternative à la solution judiciaire, le recours à la médiation, processus structuré, par lequel deux ou plusieurs parties tentent de parvenir à un accord en vue de la résolution amiable de leurs différends, avec l’aide d’un tiers le médiateur, choisi par elles ou désigné avec leur accord par le juge saisi du litige, apparaît aujourd’hui, dans de nombreux procès de droit privé comme une étape du règlement judiciaire. Il en est ainsi, en droit de la famille, en droit de la consommation, en droit commercial mais également désormais, en droit social. Depuis 2015 en effet, le Code de procédure civile impose aux parties à un litige de justifier, lors de l’introduction de l’instance, des diligences entreprises en vue de parvenir à une résolution amiable de leur litige et le juge est lui-même invité à leur proposer une mesure de conciliation ou de médiation à défaut de justification. Un pas de plus a été franchi avec la loi de modernisation de la justice du 18 novembre 2016, dite « Justice 21 », qui a rendue obligatoire la tentative de conciliation ou de médiation pour les petits litiges du quotidien, avant la saisine du juge d’instance. On pouvait dès lors se demander si ce mode de résolution d’un conflit participait de la justice ou s’il s’en distinguait et comment il était accueilli par les justiciables et les praticiens du droit. C’est à ces questions que le colloque des 28 et 29 avril 2017 a cherché à répondre, à partir de l’examen du droit positif et prospectif français et en utilisant le droit comparé, européen et international. Les résistances comme les initiatives pour promouvoir la médiation ont été examinées lors de la première journée de la manifestation. Le deuxième jour a permis de faire point sur l’actualité de la médiation civile dans les différentes branches du droit privé et de mesurer l’influence des règlements européens et de la jurisprudence de la Cour européenne des droits de l’homme sur le développement de ce processus.
Keywords: Code de procédure civile; Cour européenne des droits del'homme; Droit de la consommation; Droit privé; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; Médiation familiale; Recours

L'avocat et la médiation - entrez dans la danse ! - Lévy, Cinthia (Arbitrage, médiation et autres modes pour résoudre les conflits autrement, 2018)

L'arbitrage international et la place réservée à l’ordre public dans les pays du golfe persique - Mazidi, Sépideh (Revue de l'ERSUMA, 2018)
La notion de l’ordre public est l’un des concepts les plus complexes des systèmes juridiques. Dans les pays arabo-musulmans la difficulté est encore plus grande, car cette notion se rapproche de celle de la Chari’a. En effet, l’ordre public des pays de la région du golfe trouve sa légitimité dans l’Islam et dans les Constitutions de ces pays. Les Constitutions du Koweït, Bahreïn, Qatar et les Émirats Arabes Unis considèrent la Chari’a comme la source principale de la législation. A l’échelle internationale, la présence indirecte de la Chari’a se manifeste à travers l’arbitrage international, mode efficace et rapide de résolution des conflits du commerce international. Dans la procédure arbitrale, la Chari’a peut intervenir à tous les niveaux : elle peut jouer un rôle fondamental pour la conclusion de la convention d’arbitrage, le choix de la loi applicable ainsi que pour l’exécution et les recours contre la sentence. Dans le cadre de notre étude, nous étudions le choix de la loi applicable et la phase exequatur. Cependant le stade de la conclusion de la convention d’arbitrage est en dehors des limites de ce travail.
Keywords: Arbitrage international; Arbitration; Charia; International arbitration; Islam; Légitimité; Région du golfe

Vers des partenariats inter-états africains, gages d’équité en faveur des investissements économiques en Afrique - Nguemdom, Ruth Carelle (Revue de l'ERSUMA, 2018)
Est-il essentiel de créer de véritables et solides couloirs juridiques entre les régions et les Etats africains pour encourager les investissements économiques ? La question mérite d’être posée. Un tel partenariat implique que soit mise en place une stratégie commune autour des investissements économiques. Il va ainsi permettre de créer une dynamique industrielle et commerciale encore plus forte que celle observée aujourd’hui au sein de l’OHADA. L’UA ou l’OHADA doivent être dotées de moyens réels car l’union fera la force pour les africains trop faibles pour agir et compter seuls face aux puissances étrangères (l’UE, la Chine, l’Inde, la Russie, les USA…). Pour ces Etats, l’Union serait la négociatrice privilégiée pour de nouveaux partenariats plus équitables. Avec cette stratégie de coopération rentable, les Etats africains pourront parler d’une même voix et passer du statut de « perfusés » à celui de « partenaires ». Si ce vœu pieux semble loin de portée, il est malheureusement une des clés de la réussite africaine en matière de développement économique et social, de croissance durable par le biais des investissements économiques. Ceci au même titre que l’intégration régionale car, comme le rappelle si bien la CEA, l’approfondissement de l’intégration régionale permettra d’améliorer de façon significative l’attractivité du continent africain comme destination pour les investissements économiques.
Keywords: Afrique; Coopération Sud-Sud; Investissements; Investments; Partenariat inter-Etats

Vers la contractualisation de la justice : Cas de la médiation en droit OHADA - Ntumba Musuka, Zacharie-Richard (Annales de la Faculté de Droit, 2018)

La justice étatique à l’épreuve de l’avancée des modes alternatifs de règlement des différends en droit OHADA - Soumaïla, Sounon Tamou Abdou (Revue de l'ERSUMA, 2018)
La « raison d’être » de l’OHADA est de faciliter l’activité des entreprises et garantir la sécurité juridique et judiciaire des activités économiques. A cette fin, la justice ou « la juridiction compétente dans l’Etat Partie » selon les termes du législateur de l’OHADA, est d’une grande contribution. Mais, en marge de cette justice, on voit se développer remarquablement les Modes Alternatifs de Règlements des Différends (MARD) en Droit OHADA. Le législateur est parti de l’arbitrage pour en arriver aujourd’hui à la médiation, sans oublier la conciliation. Le souci du législateur est sans doute d’assurer la célérité dans le traitement des conflits, garantie que n’offre pas toujours la justice étatique. Que devient alors le juge étatique au milieu de ces «nouveaux» modes de règlement des différends dans le droit OHADA ? La réponse à cette interrogation est apportée en considération des deux Actes uniformes récemment adoptés (le 23 novembre 2017 à Conakry) par le Conseil des Ministres de l’OHADA sur la Médiation et l’Arbitrage. Dans l’un ou l’autre de ces textes, le juge n’est pas traité de la même manière, conséquence de la nature de chaque procédure. La nature contractuelle de l’accord de médiation s’impose au juge tandis que la sentence arbitrale doit faire l’objet de reconnaissance et d’exequatur. En conséquence, le juge qui semble s’effacer lors du déroulement des procédures d’arbitrage et de médiation, réapparaît à l’occasion de l’exécution des décisions qui en résultent, mais là encore, son intervention est nuancée. Dans l’exécution de la sentence arbitrale elle est obligatoire et exclusive ; dans la mise en œuvre de l’accord de médiation elle est facultative. Au final, l’on peut souhaiter que le législateur fasse interagir les différentes procédures de règlement des différends en droit OHADA.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Conciliation; Droit OHADA; MARD; Mediation; Médiation; Règlement des conflits

Quelle médiation dans l’espace OHADA sans professionnalisation des médiateurs ? Les inspirations du contexte belge - Tadjudje, Willy (Revue de l'ERSUMA, 2018)
Le 23 novembre 2017, le dixième Acte uniforme de l’OHADA sur la médiation a été adopté au cours de la 45e session du Conseil des Ministres tenue à Conakry (Guinée). Selon le communiqué final de ladite session, cet Acte uniforme a pour objectif « de combler le vide législatif existant en la matière dans la plupart des Etats membres de l’OHADA et promouvoir ce procédé amiable de règlement des différends ». Le but de cette réflexion est de jeter un regard critique sur ce texte dans une approche comparative avec le contexte belge. L’analyse sera focalisée sur la question de la professionnalisation des médiateurs. En Belgique, la médiation est une « profession réglementée », alors que dans l’espace OHADA, l’accès à la médiation semble libre, ce qui peut laisser des doutes sur la crédibilité de cet outil de règlement amiable des litiges.
Keywords: Belgique; Espace OHADA; Mediation; Médiateur; Médiation; Médiation et négociation; Procédure de médiation; Professionnalisation

Ex Aequo et Bono as a Response to the ‘Over-Judicialisation’ of International Commercial Arbitration - Teramura, Nobumichi (UNSW Sydney, 2018)
Ex aequo et bono is a long-lived legal concept that enables arbitrators to decide a dispute based on notions of fairness instead of a strict application of legal norms. Jurists generally agree that arbitrators authorised to decide commercial disputes ex aequo et bono can more easily tailor arbitral procedure to achieve an efficient and fair dispute resolution process. They therefore agree that ex aequo et bono arbitration maximises procedural flexibility. However, this flexibility is now perceived more as a negative rather than a positive, despite the potential of ex aequo et bono to mitigate growing concerns about the ‘over-judicialisation’ of arbitration – the increasing formalisation and inefficiency of arbitral procedure. Commentators usually assert that ex aequo et bono introduces excessive unpredictability into arbitration and encourages arbitrators to abuse their discretion. As a result, ex aequo et bono has remained unpopular to this day. This thesis challenges this overly negative conception of ex aequo et bono. It does so particularly under the UNCITRAL Model Law, as an important foundation stone of the global commercial arbitration regime. The thesis investigates significant divergence in the understanding of ex aequo et bono across state jurisdictions and international arbitration institutions. It also analyses the core trends in actual legal practice and in thinking about the principle. The thesis thereby demonstrates that the Model Law requires arbitrators to ensure that their arbitral awards are based on three objective elements: contract terms, trade usages, and mandatory rules of law. Accordingly, while the Model Law allows arbitrators deciding ex aequo et bono to invoke their subjective conceptions of fairness as the ultimate gap-filler when discerning the intention of the parties, the scope for doing so is not unduly expansive. Further, the refinement of various legal theories underpinning international commercial arbitration has enabled parties to determine and challenge more readily the arbitrators’ subjective ideas of fairness. The thesis therefore concludes that the flexibility inherent in ex aequo et bono needs to be both re-evaluated and rejuvenated. It urges the international arbitration community to adopt a revitalised conception of ex aequo et bono to counter-balance the encroaching ‘over-judicialisation’ of arbitration.
Keywords: AI; Amiable composition; Arbitrage; Arbitragem; Arbitration; Arbitration theory; Artificial Intelligence; Blockchain; Cryptocurrency; Ex aequo et bono; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; Trade usages; UNCITRAL Model Law

Médiation et arbitrage dans les services financiers : conseil en placement et gestion de fortune - Thévenoz, Luc (Arbitrage, médiation et autres modes pour résoudre les conflits autrement, 2018)
Dans le contexte actuel d'échange automatique de renseignements en matière fiscale, quelles sont les perspectives de la médiation et de l'arbitrage comme modes de résolution des litiges relatifs aux services financiers - spécialement la gestion de fortune et le conseil en placement - que la place financière suisse offre à sa clientèle privée et institutionnelle suisse et étrangère? Cet article commence par un rapide tour d'horizon international de la situation. Il examine ensuite le développement de la médiation qui résultera de la mise en oeuvre de la loi sur les services financiers et s'achève par quelques réflexions sur l'arbitrage et les actions collectives dans ce domaine.
Keywords: Conseil en placement; Gestion de fortune; Médiation; Services financiers

Without Silence, There Is No Golden Rule; Without Dissent, There Is No Progress - Uluc, Inan; Sutton, Kristi R. (Oregon Review of International Law, 2018)
The frequency of dissenting opinions accompanying arbitration awards in international arbitration has multiplied, particularly in international investment arbitration. Accordingly, dissenting opinions are now inevitable companions to majority awards. Notwithstanding the fact that dissenting opinions neither form part of an arbitral award nor constitute a separate award, the escalation of dissenting opinions spawns anxiety in scholars and practitioners. This trepidation ignited a crusade whereby those opposed to the practice of rendering dissent challenge the role and usefulness of these opinions. In this respect, this Article initially considers and critiques specific arguments raised by those opposed to dissenting opinions in international arbitration. Following analysis of the criticisms, this Article explores the beneficial and constructive aspects of dissenting opinions. Evident from this discussion is that dissenting opinions are not only integral to supplement an arbitrator’s quasi-judicial capacity, but also encourage issuance of well-reasoned awards. Clear from the benefits of dissenting opinions in international arbitration, any departure from the present clemency espoused toward the practice will eventuate in the field’s regression.
Keywords: Civil law; Common law; International arbitration

The Impartiality and Independence of Arbitrators and Its Implication on the Validity of Arbitral Awards - Yoga, I. Ketut Dharma Putra (Juris Gentium Law Review, 2018)
Arbitration is a way to resolve disputes outside the courts as a form of an alternative dispute resolution. The submitted dispute will be decided by one or more arbitrators, who will then render an arbitral award. One of the most fundamental principles of arbitration that must be adhered to by all arbitrators worldwide is the impartiality and independence of arbitrators, which have been regulated in various International laws. Arbitrators are not allowed to communicate with any party related to the case they are hearing. Further, arbitrators should not be influenced by others in making their decision and drafting the arbitral award to ensure objectivity and prevent any bias. An arbitrator's failure to act impartial and independent can lead to the invalidity or annulment of an arbitral award.

O.E.C.D. promotion for arbitration as an additional tool of settling disputes in the field of international taxation - Zeyen, Gaëtan (Revue de l'ERSUMA, 2018)
In a globalized world, arbitration plays an increasing role in settling international disputes. Almost all areas of Law are or might be concerned. Until very recently, [international] taxation was - as a rule - seen as a not ‘arbitrable-friendly’ matter. As the ‘classical’ method of settling international tax disputes - i.e., based on the so-called ‘Mutual Agreement Procedure’ (shortly, ‘M.A.P.’) - has shown its limits (mainly: lack of efficiency and involvement from the taxpayers themselves), arbitration became a subject of study for well-known and established academics and even an appropriate method of settling such international tax issues. As a result, both on international (O.E.C.D.) and European levels, legal initiatives have been taken, in order to promote arbitration as an additional tool of settling disputes in the field of international taxation. The purpose of the present article is, therefore, to describe and scrutinize these [very] recent legal initiatives and raise some potential issues that, at least in the author’s view, need to be addressed. One of these issues concerns the enforcement of such arbitral decisions.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration proceedings; Dispute settlement; International taxation; O.E.C.D; OCDE

الاطار القانوني للاستثمار العربي في الجزائر - عبد الصدوق, حفيظة (Université d'Oran 2 Mohamed Ben Ahmed, 2018)
للاستثمار العربي في الج ا زئر أهمية خاصة لسببين: أحدهما يتعلق بأهمية الاستثمار في حد ذاته لما يلعبه من دور لا يستهان به في التنمية الاقتصادية للدولة، مؤث ا ر على كل جوانب الحياة في المجتمع بما يوفره من تطور اقتصادي وازدهار واستق ا رر، وثانيهما يرتبط باتخاذه وسيلة لتجسيد التعاون العربي المشترك وتحقيق التكامل المنشود منذ عقود، والذي تأكد عدم تحققه الا بالاعتماد على المدخل الإنتاجي من خلال توظيف رؤوس الأموال العربية في الدول العربية. بدافع هذين العاملين وجذبا لرؤوس الأموال العربية وضعت الج ا زئر اطا ا ر قانونيا ا زخ ا ر بالضمانات والامتيا ا زت بعد تحديد مفهوم الاستثمار العربي، هذا الإطار يتألف من الاحكام الاتفاقية السامية على التشريع الوطني الواردة في الاتفاقيات المبرمة بين الج ا زئر والدول العربية بعد المصادقة عليها، ومن احكام التشريع الوطني الذي يعد آلية قانونية تنفذ بها الدولة است ا رتيجياتها. ت ا زمن ذلك مع تهيئة مناخ الاستثمار بصفة عامة من خلال الإصلاحات التي طالت مختلف التشريعات المتعلقة بإقامة الاعمال اولاستثمار في الج ا زئر. جاءت هذه الد ا رسة لتبين معالم هذا الإطار القانوني، مكوناته ومدى تأثيره في رفع مست وى الاستثمار العربي في الج ا زئر كما ونوعا، ضمن مشاريع التكتل الإقليمي والجهوي او المبادلات الثنائية مع الدول العربية.
Keywords: Accords bilatéraux; Algeria; Arab Nationality; Arbitrage; Arbitration; Bilateral Agreements; Blocage; Blocking; Business Establishment; Compensation; Création d'entreprise; Encouragement; Garanties; Guarantees; Investissements; Investment Protection; Investments; Nationalité arabe; Privileges; Privilèges; Protection des investissements

L’arbitrage des litiges relatifs à la finance islamique - Alyaqout, Yousef (Université de Lorraine, 2017)
L’essor de la finance islamique moderne va poser logiquement la question de la résolution des litiges. En effet, le recours à la justice étatique aboutit à des impacts négatifs sur la réalisation des objectifs de la finance islamique et sur le développement de ce secteur d’activité. Dans cette optique, l’application de la législation nationale par le juge étatique aboutit à la requalification des contrats de financement islamique en des contrats de financement conventionnel. En outre, ce recours au juge étatique conduit à la neutralisation de la Charia en tant que droit applicable. Tout cela conduit à la dénaturation de la finance islamique. Cette dénaturation est une source de contradictions. On sait bien que les institutions financières islamiques reposent sur une obligation fondamentale, selon laquelle toutes les opérations financières effectuées doivent être conformes à la Charia. De plus, les personnes ayant recours à la finance islamique visent principalement à exercer des activités financières en toute conformité avec leurs principes religieux et éthiques issus de la législation islamique. L’étude a également montré que les modes amiables de règlement des litiges contribuent à prendre en considération la particularité de la finance islamique. Cependant, cette prise en compte reste insuffisante. En effet, ces modes ne présentent pas un mécanisme complet, homogène et cohérent de règlement des litiges relatifs à la finance islamique. Leur contribution à la construction d’un système juridique propre à la finance islamique est très limitée. De ce fait, ils ne peuvent pas participer efficacement à la promotion de l’industrie financière islamique. De plus, ils souffrent d’un défaut majeur au niveau de la force de la solution proposée : l’efficacité de cette solution dépend en principe de la bonne volonté des parties. Face à ce dysfonctionnement de la justice étatique et des modes amiables, la solution a été recherchée du côté de l'arbitrage. En effet, l’arbitrage connaît une expansion spectaculaire dans le monde actuel au point de devenir le mode normal de règlement des litiges. Cet essor exceptionnel de l’arbitrage se constate notamment dans la vie économique et financière. A l’heure actuelle, cette vie est devenue inconcevable sans l’arbitrage. En matière de finance islamique, l’arbitrage en tant que mécanisme reposant sur la liberté et la volonté apparaît comme la meilleure voie permettant la prise en considération de la spécificité de cette activité, l’application de la Charia dans le domaine de la résolution des litiges. C’est pourquoi, ce mode alternatif de règlement des litiges s’adapte parfaitement aux exigences des litiges relatifs à la finance islamique et pourrait contribuer à la promotion de ce secteur d’activité. Grâce aux avantages qu’il offre aux opérateurs de la finance islamique, l’arbitrage s’affirme comme la justice naturelle des litiges relatifs à la finance islamique. Pour renforcer le rôle de l’arbitrage dans le domaine de la finance islamique, un projet de réforme a été présenté. Ce projet vise à moderniser l’arbitrage dans toutes ses étapes. Dans cette optique, l’accent a été mis sur la convention d’arbitrage, le statut de l’arbitre, le droit applicable et la sentence arbitrale. Tout cela a été achevé par l’élaboration d’un projet de charte éthique de l’arbitrage en matière de finance islamique. Une fois modernisé et renouvelé, l’arbitrage peut devenir un pilier essentiel de l’industrie financière islamique, en participant efficacement à la promotion de cette activité. Avec une justice équitable, pratique, efficace, conforme à la Charia et adaptée, la finance islamique se trouve renforcée et consolidée. The rise of modern Islamic finance will logically raise the issue of dispute resolution. Indeed, recourse to state justice leads to negative impacts on the achievement of the objectives of Islamic finance and on the development of this sector of activity. In this context, the application of national legislation by the state judge results in the reclassification of Islamic financing contracts into conventional financing contracts. In addition, this recourse to the State Judge leads to the neutralization of Shariah as an applicable law. All this leads to the denaturation of Islamic finance. This denaturing is a source of contradictions. It is well known that Islamic financial institutions are based on a fundamental obligation that all financial transactions must conform to Sharia law. In addition, people who use Islamic finance primarily aim to conduct financial activities in accordance with their religious and ethical principles derived from Islamic legislation. The study also showed that amicable dispute resolution modes help to take into account the peculiarity of Islamic finance. However, this consideration remains insufficient. Indeed, these modes do not present a complete, homogeneous and coherent mechanism for resolving disputes relating to Islamic finance. Their contribution to the construction of a legal system specific to Islamic finance is very limited. As a result, they can not participate effectively in promoting the Islamic financial industry. In addition, they suffer from a major flaw in the strength of the proposed solution: the effectiveness of this solution depends in principle on the good will of the parties. Faced with this dysfunction of state justice and amicable modes, the solution was sought on the side of arbitration. Indeed, arbitration is expanding dramatically in today's world to the point of becoming the normal mode of dispute resolution. This exceptional growth of arbitration can be seen in particular in economic and financial life. At present, this life has become inconceivable without arbitration. In the area of Islamic finance, arbitration as a mechanism based on freedom and will appears as the best way to take into account the specificity of this activity, the application of Shari'a in the field of the resolution of litigation. For this reason, this alternative dispute resolution method is perfectly suited to the demands of Islamic finance litigation and could contribute to the promotion of this sector of activity. Thanks to the advantages it offers to operators of Islamic finance, arbitration is asserting itself as the natural justice of disputes relating to Islamic finance. To strengthen the role of arbitration in the field of Islamic finance, a reform project was presented. This project aims to modernize arbitration in all its stages. From this perspective, the focus was on the arbitration agreement, the status of the arbitrator, the applicable law and the arbitration award. All this has been completed by the elaboration of a draft ethical charter of arbitration on Islamic finance. Once modernized and renewed, arbitration can become an essential pillar of the Islamic financial industry, effectively participating in the promotion of this activity. With fair, practical, effective, Sharia-compliant and responsive justice, Islamic finance is strengthened and consolidated.
Keywords: Arbitrage; Arbitragem; Arbitration; Droit commercial; Droit financier islamique; Droit procédure; Litiges; Marché financier; Règlement de conflits

Le règlement des litiges survenant des contrats de partenariats public-privé (PPP / PFI) : recherche d’une meilleure gestion des sources des litiges dans les contrats de PPP : enjeux et conséquences pour l’Egypte - Eissa Zakaria Abdelsalam, Nora (Université Lille 2, 2017)
Le partenariat public privé est un instrument pour la réalisation des objectifs du développement en Egypte. Sur le plan international, le recours aux PPP soulève des difficultés compliquées à résoudre. La nature complexe de ce type de projets augmentent la probabilité de litiges entre les parties. L’analyse comparée des expériences britannique et française, permet d’élaborer une référence pour le gouvernement égyptien en matières des réformes juridique et économique. Dans le cadre d’améliorer la gestion des projets de PPP en Egypte, deux approches peuvent être adressées dans notre recherche. En premier lieu, le développement d’une méthodologie de gestion efficace des risques par l’analyse de types des risques attachés aux PPP pendant le cycle de vie du projet. En deuxième lieu, la présentation des mécanismes les plus efficaces de résolution des litiges découlant des projets de PPP. Public-private partnership is an instrument for achieving development objectives in Egypt. On the international level, the use of the PPP model raises complicated challenges and difficulties. The complex nature of such projects increase the probability of disputes between the parties. The comparative analysis of the British and French experience allows the elaboration of a reference for the Egyptian government in the legal and economicreforms. In order to improve the management of PPP projects in Egypt, two approaches can be addressed in our research. First, the development of an effective risk management methodology through the analysis of the types of risk associated with PPP during the life cycle of the project. Second, the presentation of the most effective mechanisms for the resolution of disputes arising from PPP projects.
Keywords: Egypte; Gestion des risques; PFI; PPP; Partenariat public-privé; Pays en développement; Projets d’infrastructures; Étude comparative

La réception par le droit Iranien de la loi type de la CNUDCI sur l’arbitrage commercial international - Pour, Mohammad Mehdi (Université de Lorraine, 2017)
De nos jours, les activités et les relations d'affaires sont beaucoup plus larges et complexes qu'auparavant. L'extension de cet espace, nécessite que les différends relatifs aux affaires commerciales soient réglés dans des systèmes efficaces adaptés à la nature des litiges de ce domaine, c'est-à-dire, rapidement, de manière précise et par des experts. C'est pour quoi, au cours des dernières décennies, les législations des pays relatives à l’arbitrage ont été actualisées, et les conventions internationales dans ce domaine connaissent une large réussite. Les pays recherchant à transformer leur législation sur l’arbitrage commercial disposent d’un modèle législatif apprécié et intéressant fourni par la loi type sur l’arbitrage commercial international ; il a été adopté en 1985 par la CNUDCI et constitue aujourd’hui une référence pour réaliser une unité juridique dans le domaine de l’arbitrage commercial international. Les transformations des régimes juridiques nationaux ont débuté assez tôt dans certains des pays développés tels la France, la Suisse et la Belgique, tandis qu’elles ont été entamées assez tardivement dans d’autres pays, tels ceux en voie de développement dont l’Iran. En Iran, l’arbitrage a toujours été admis et pratiqué ; néanmoins, la procédure civile iranienne présentait encore des insuffisances, et dévoila encore davantage de défauts concernant l’arbitrage international. En conséquence, les parties iraniennes aux contrats internationaux ne pouvaient convaincre les parties étrangères à accepter l’Iran en tant que place d’arbitrage. C’est en accord avec les évolutions législatives mondiales que l’Iran aussi, tout en se joignant à la Convention de New York de 1958, réforma sa législation sur l’arbitrage commercial international, en adoptant en 1997 une loi sur l’arbitrage commercial international rédigée en adoptant le modèle législatif proposé par la CNUDCI. Cette loi marqua une évolution marquante dans la législation iranienne vu qu’elle institua d’importantes règles alignées sur les tendances récentes du droit de l’arbitrage international. Malgré cela, certains praticiens y découvrirent des défauts et des lacunes, réclamant ainsi une réforme nécessaire pour rendre le droit iranien réellement attractif. Néanmoins, la loi iranienne de 1997 n’a jamais fait jusqu’à ce jour l’objet d’une étude scientifique systématique. L’examen des droits d'autres pays tels que : la français, la belge et l'anglais sur l’arbitrage commercial international, ainsi que l’étude d’autres sources pertinentes, permettra d’identifier et d’analyser en profondeur les lacunes et de proposer des remèdes. Nowadays, the business relations are much broader and more complex than before. The extension of this area of activities requires the disputes arising out of business relationships to be resolved through the effective systems aligned with the nature of this area, i.e. the promptness, accuracy and expertise. Hence, over the last few decades, the national laws relating to the arbitration have been developed, and international conventions in this field achieved a great deal of success.The countries seeking to reform their legislation on commercial arbitration can adopt the well-known model law provided by the UNCITRAL Model Law on International Commercial Arbitration which has been adopted in 1985 by UNCITRAL and is now a reference for the realization of a legal system in the field of international commercial arbitration. Changes in national legal regimes began relatively early in some of the developed countries such as France, Switzerland and Belgium, while they were initiated fairly late in other countries, such as developing world, including Iran.In Iran, arbitration has always been admitted and practiced; nevertheless, the civil procedure in Iran was inadequate in this area, and revealed even more defects concerning international arbitration. Consequently, Iranian parties to international contracts could hardly convince their foreign parties to accept Iran as the seat of arbitration.It was in line with global legislative developments that Iran, while joining the 1958 New York Convention, has reformed its legislation on international commercial arbitration by adopting a law on commercial arbitration in 1997 in accordance with the model law proposed by UNCITRAL. This law marked a significant development in Iranian legislation as it established important rules aligned with recent trends in the law of international arbitration. Despite this, the practitioners discovered some defects and shortcomings. That’s why they call for a reform necessary to make Iranian law truly attractive. Nevertheless, the Iranian law of 1997 has never been subject of a comprehensive study so far. Examination of the laws of other countries such as French, Belgian and English on international commercial arbitration, as well as the study of other relevant sources, will pave the way to identify and analyze in depth the gaps and propose remedies.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; Convention de d'arbitrage; Droit commercial; Iran; Loi de l'arbitrage; Loi type de la CNUDCI; UNCITRAL

Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

La pratique de l'arbitrage OHADA selon le règlement d'arbitrage CCJA - Bebohi Ebongo, Sylvie (Revue juridique de l'Océan Indien, 2017)
L’arbitrage OHADA repose sur un régime dual. Le régime dual de l’arbitrage OHADA est constitué, d’une part, par l’arbitrage de droit commun régi par l’acte uniforme OHADA relatif au droit de l’arbitrage qui réglemente l’arbitrage de droit commun dans l’espace OHADA et, d’autre part, par l’arbitrage spécifique CCJA qui repose sur le titre IV du Traité OHADA et le règlement d’arbitrage de la Cour commune de justice et d’arbitrage. Qu’est-ce qui caractérise dès lors l’arbitrage OHADA selon le règlement d’arbitrage CCJA et le distingue de l’arbitrage de droit commun de l’acte uniforme OHADA relatif au droit de l’arbitrage ? Comment fonctionne l’arbitrage selon le règlement d’arbitrage CCJA ? Pour mieux comprendre comment se pratique l’arbitrage OHADA selon le règlement d’arbitrage CCJA, il est nécessaire d’appréhender ses spécificités tant dans sa mise œuvre (I) qu’en matière d’exécution des sentences arbitrales qui en sont issues (II).
Keywords: Arbitrage; Arbitragem; Arbitration; Clause compromissoire; Compromis d'arbitrage; Convention d'arbitrage; Espace OHADA; Exequatur; Exécution; Investissements; Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA); Promotion; Protection; Règlement d'arbitrage; Sentence arbitrale; TBI; Traités Bilatéraux; lois nationales

Le règlement par voie d'arbitrage des litiges relatif aux investissements dans l'espace OHADA - Kenfack Douajni, Gaston (Revue juridique de l'Océan Indien, 2017)
Keywords: Arbitrage; Arbitragem; Arbitration; Clause compromissoire; Commission des Nations Unies pour le droit commercial international (CNUDCI); Contrat; Convention d'arbitrage; Exequatur; Investissements; Investments; Jurisprudence arbitrale; Loi nationale; Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA); Règlement des litiges; Sentence arbitrale; Traité de protection des investissements

Les ambigüités de la voie de cassation en matière de droit pénal des Actes uniformes, (A propos de l'arrêt de la CCJA n°143/2016, du 14 juil. 2016 Ibrahima Aboukhalil c/Etat du Sénégal et le ministère public et a) - Lekebe Omouali, Daphtone (Revue de l'ERSUMA, 2017)
L'interprétation des Actes uniformes est un défi pour son application. L'harmonisation des règles de droit des affaires dans l'espace OHADA s'est accompagné d'un objectif d'unification de la jurisprudence et la Cour Commune de Justice et d'Arbitrage joue à cet égard un rôle essentiel. L'articulation des compétences judiciaires entre la CCJA et les juridictions nationales statuant en cassation offre cependant, en matière pénale des Actes uniformes, l'image d'une option pathologique. Alors que la CCJA proclame la compétence exclusive des cours suprêmes nationales en cas d'application des sanctions pénales, la nécessité d'assurer une répression uniforme en cas de violation du droit uniforme milite en faveur d'un partage de compétence entre celle-ci et celles-là.
Keywords: Droit de l'arbitrage; Droit pénal des affaires

La médiation : une approche constructive à la hauteur des conflits de notre temps : un pont possible entre la justice et la paix dans un monde pluraliste - Graf, Kathrin (Université Paris 2, 2017)
Ce présent travail a pour vocation de fournir une approche multidisciplinaire – historique, socio-politique, économique, et psychologique – pour comprendre l’intérêt général de la gestion constructive de conflit, et en particulier les opportunités liées à la méthode de la médiation. La thèse reflète le chemin parcouru - de la déconstruction à la reconstruction du sujet – débutant par une analyse théorique (les origines, les spécificités, les différences avec d’autres méthodes, les valeurs et principes), passant par une prise en considération des phénomènes individuels et collectifs inhérents au conflit et à sa gestion (les niveaux de conflit, les dimensions de la gestion, les fondements psychologiques individuels, les opportunités d’une démarche intégrative mais aussi les limites et risques liés à la méthode de médiation). Le travail tient également compte de l’évolution personnelle du chercheur, de sa pratique de médiateur, des échanges avec d'autres professionnels ainsi que ses constats de réalisabilité (conseils de mise en pratique, organisation logistique, outils concrets pour les différentes phases, et restitution des étapes clés d’un cas pratique).Mots clés : accompagnement, arbitrage, compréhension mutuelle, confidentialité, consensus, dialoguer, doubler, écoute active, empathie, facilitation de communication, gestion de conflit effective et constructive, impartialité, médiation, méthodes alternatives de règlement de conflit, modération, négociation intégrative, prévention/traitement auto-responsable de futures conflits, résolution créative de problèmes, solutions « pareto optimales », rétablissement de la paix, gestion des processus, rapprochement, réconciliation, science décisionnelle, supervision, zone d’accords possibles This work aims to provide a multidisciplinary approach - historical, socio-political, economic, and psychological - to understand the general interest of constructive conflict management, and in particular the opportunities related to the method of mediation. The thesis reflects the path taken - from deconstruction to reconstruction of the subject - beginning with a theoretical analysis (origins, specificities, differences with other methods, values and principles) and considering the individual and collective phenomena inherent to each conflict and its management (levels of conflict, management dimensions, individual psychological foundations, opportunities of integrative bargaining, but also the limits and risks associated with the method of mediation). The present work also takes into account the personal evolution of the researcher, her practice as a mediator, exchanges with other professionals on this behalf and her personal findings of feasibility (practical advice, logistical organization, concrete tools for the various phases, and the restitution of the key steps of a practical case). Key words : active listening, alternative dispute resolution, arbitrary, communication facilitation, conciliation, confidentiality, consensus, constructive and effective conflict management, creative problem-solving, decision science, dialogue, empathy training, empowerment, Harvard negotiation model, impartiality, integrative bargaining, looping, mediative solutions, moderation, negotiation, “pareto optimal” solutions, peacemaking, process management, reconciliation, reframing, settlements, supervision, therapy, understanding, zone of possible agreements
Keywords: Arbitrage; Arbitrage (droit européen); Arbitragem; Arbitrary; Arbitration; Conciliation; Creative problem-solving; Ecoute active; Gestion de conflit effective et constructive; Gestion des crises; Impartiality; Impartialité; Integrative bargaining; MARD; Mediación; Mediation; Mediative solutions; Mediação; Moderation; Modération; Médiation; Méthodes alternatives de règlement de conflit; Negotiation; Négociations; Pays de l'Union européenne; Peacemaking; Réconciliation; Résolution créative de problèmes; Rétablissement de la paix; Understanding

L’arbitrage en cinq idées reçues - Couturier, Jean-Pascal (La Lettre, 2017)
Les pouvoirs publics n’ont de cesse de vouloir orienter les justiciables (entreprises comme particuliers) vers des modes alternatifs de règlement des différends (MARD). L’arbitrage est le plus ancien d’entre eux ; le grand public l’a (malheureusement) découvert à travers les nombreux rebondissements de l’affaire Bernard TAPIE / CREDIT LYONNAIS.

Regards croisés sur l’arbitrage et sa perception par l’usager - De La Chapelle, Antoine; Heraud, Cindy (La Lettre, 2017)
L’affaire dite « Tapie », résolue par une sentence arbitrale en date du 7 juillet 2008, a placé l’arbitrage sous le feu des projecteurs médiatiques et a fait couler beaucoup d’encre, alimentée par un certain nombre de représentations erronées et de préjugés vis-à-vis de la justice arbitrale. D’aucuns ont ainsi dénoncé une justice arbitraire, au service d’intérêts privés et au fonctionnement opaque, invitant à une défiance généralisée.

La médiation interentreprises dans le monde francophone - Henry, Sophie (La lettre des médiations, 2017)
Concurrence déloyale, inexécution contractuelle, rupture brutale, conflit entre associés… Autant d’exemples de litiges qu’une entreprise peut être amenée à connaître au cours de son existence. La longueur et le coût des procédures, l’aléa et le carcan d’une décision de justice obligent les entreprises à repenser leur politique de gestion des conflits, Leurs contraintes économiques favorisent progressivement les modes amiables de règlement. Elles optent de plus en plus pour la médiation, dans une perspective d’efficacité, d’optimisation des coûts et délais et de maîtrise de leur image. Dans une étude réalisée en 2016 par le CMAP (Centre de Médiation et d’Arbitrage Paris) en partenariat avec Squaremic et Baro Alto, il apparait que 90% des entreprises interrogées ont eu recours à la médiation au moins une fois sur les douze derniers mois et 77% d’entre elles jugent ce mode de résolution efficace.
Keywords: Gestion de conflits; Mediation; Médiation

Les provisions pour arbitrage face à l’impécuniosité d’une partie - Posocco, Laurent (La Lettre, 2017)

Rejet de l’annulation de la sentence rendue par un arbitre ayant divulgué une hypothétique cause de partialité - Posocco, Laurent (La Lettre, 2017)

The Admissibility of Shareholder Claims: Standing, Causes of Action, and Damages - Bottini, Gabriel (University of Cambridge, 2017)
This thesis addresses risks of multiple recovery, prejudice to legitimate interests of third parties, and inadequate consideration of the applicable law in shareholder claims in investment treaty arbitration. It challenges the application by investment tribunals of two basic premises: i) that shareholders are entitled to claim for damages vis-à-vis measures against the company in which they hold shares and ii) that ‘contract claims’ are to be distinguished from ‘treaty claims’. The central argument is that the failure to recognize substantive overlaps between shareholder treaty claims and contract claims risks more than one recovery, potentially prejudices third parties, and can lead to an incomplete application of the applicable law. The foundations of standing and the cause of action in shareholder treaty claims involve two complementary ideas of independence, i.e., independence of shareholder treaty rights vis-à-vis the local company’s contractual/national law rights and independence of treaty claims vis-à-vis contract claims. However, the substance of shareholder treaty claims, defined as the state measure and particularly the losses involved, is often identical to or at least overlaps considerably with related contract/national law claims. Prevailing ideas on shareholder standing and the cause of action in international investment law have provided useful conceptual tools for jurisdictional determinations. Yet they have not allowed tribunals and the literature to fully consider the implications of shareholder indirect claims. The thesis argues, first, that investment tribunals should acknowledge substantive overlaps between contract and treaty claims. Second, shareholder claims may be inadmissible when such overlap exists and there is a risk of double recovery or prejudice to third parties. Third, the substantive coincidence of treaty and contract claims calls for an integrated approach to the applicable law, where proper weight is given not only to IIA provisions but also to general international law and the national law governing the investment.
Keywords: Admissibility; Admissibility and jurisdiction; Applicable law; Arbitrage; Arbitragem; Arbitration; Contract claims; Contract-treaty distinction; Double recovery; Investment arbitration; Investment claims; Investments; Mixed claims commissions; Prejudice to third parties; Shareholder claims; Shareholder standing; Treaty claims

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

Usages et arbitrage - Sanchez Saëz, Crystelle (Université de Montpellier, 2017)
Alors même, qu’au sein de l’arbitrage, les usages sont omniprésents, un grand nombre d’acteurs ne sont pas conscient de leur existence. Pour autant, ils sont retrouvés tout au long de l’instance arbitrale. En amont de la prise de décision, les usages processuels permettent une règlementation précise et efficace de la procédure arbitrale. Au moment de la prise de décision, le recours aux usages substantiels est un bon moyen de parvenir à la décision la plus adéquate et ainsi mettre un terme au litige. Ils constituent ainsi un outil efficace, mais surtout alternatif aux Droits nationaux. Although, in arbitration, usages are everywhere, many practitioners are not aware of their existence. However, they are involved in every step of the arbitral proceeding. Before the making of the decision, procedural usages enable the organization of a sound and precise regulation of the arbitral proceeding. At the time of the making of the decision, substantial usages ensure to come to the most adequate decision, in order to put an end to the dispute. Hence, they can be a very useful tool, that would be an alternative to national Laws
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Dispute resolution in the oil and gas industry: an appraisal of mediation and litigation procedures. - Mohammed, Jamilu Ibn (Journal of private and business law, 2017)
The Oil and Gas Industry Resolution originally recognised negotiation and concede to the alternative dispute resolution rather, their litigation. The paper analysed appraised the different alternative dispute resolution, formulae including mediation the doctrinal method of research which analyses all legal in others as applied. All methods relating to the dispute resolution were analysed from the library and it has formed that mediation which involves the process of resolution dispute weather the involvement of litigating is prefer for being use costly and time consuming. Litigation been so expensive and time wasting is not recommence for oil and Gas Industry.
Keywords: Dispute Resolution; Gas; Industry; Litigation; MARD; Mediación; Mediation; Mediação; Médiation; Oil

فعالية اتفاق التحكيم التجاري الدولي - تعويلت, كريم (جامعة مولود معمري, 2017)
استند الفقه والقضاء على فكرة فعالية اتفاق التحكيم مجال التجارة الدولية، لتبرير الأخذ ببعض القواعد، كاستقلالية هذا الاتفاق ومبدأ "الاختصاص بالاختصاص"، التي كيفت على أنها قواعد مادية ومبادئ راسخة في قانون التحكيم التجاري الدولي. غير أن اللجوء إلى هذه المبادئ في مفهومها الليبرالي الحالي ، الذي وصل إليه خاصة القانون الفرنسي ، يسمح من الناحية العملية بانفلات هذا الاتفاق ليس فقط من حكم القانون الوطني، بل أيضا من إرادة الأطراف، التي جاءت هذه المبادئ لحمايتها، لذا نرى أنه من الأجدر الأخذ بالحلول التي وضعها القانون النموذجي للتحكيم التجاري الدولي، الذي سنته لجنة الأمم المتحدة للقانون التجاري الدولي في سنة 1985. L’efficacité de la convention d’arbitrage en matière de commerce international a été évoquée pour justifier le recours à certaines règles telles que l’autonomie de ladite convention et la « compétence-compétence ». Ces dernières sont qualifiées de règles matérielles et de principes indiscutables du droit de l’arbitrage international. Toutefois, le recours à ces principes dans leur sens actuel permet en pratique, et selon la conception du droit français notamment, de soustraire la convention d’arbitrage non seulement à toute loi étatique, mais aussi à la volonté des parties que ces principes sont sensés préserver. Par conséquent, nous pensons qu’il est préférable de recourir aux solutions consacrées par la loi type sur l’arbitrage commercial international de la CNUDCI de 1985
Keywords: Arbitrage; Arbitrage commercial international; Arbitration; Commerce international; Compétence-compétence; Convention d'arbitrage; اتفاق التحكيم; التجارة الدولية; التحكيم التجاري الدولي; مبدأ الإختصاص بالإختصاص

Le rôle historique et actuel de la francophonie dans le règlement des conflits - Dramé, Omar (Université Toulouse 1 Capitole, 2017)
Cette thèse porte sur le rôle historique et actuel de la Francophonie dans le règlement des conflits. L'objectif est d'étudier la contribution de l'Organisation internationale de la Francophonie dans les processus de résolution des conflits qui secouent l'espace francophone qui est devenu un théâtre de guerre civile et de guerre ethnico-religieuse, affaiblissant le développement économique et social de plusieurs pays, particulièrement ceux d'Afrique francophone. Devenu un acteur incontournable sur la scène internationale, l'Organisation internationale de la Francophonie, regroupant des ayant le français en partage, décide de contribuer activement à la résolution des conflits. Du point de vue méthodologique, cette thèse est basée sur une approche évolutive, centrée sur la particularité de l'approche francophone dans les processus de règlement des conflits en tenant compte de son historique et l'utilise au service de la paix et de la stabilité de ses Etats membres. Dans la première partie, la thèse met l'accent sur l'approche préventive de l'OIF dans les processus de maintien de la paix en exhortant ses Etats membres à promouvoir la culture de la paix et la gouvernance démocratique. Elle met en exergue la politique de prévention de cette organisation, qui repose sur la volonté de promouvoir l'Etat de droit, le respect des droits de l'homme, considérée comme la meilleure stratégie de maintien de la paix. Elle expose la stratégie adoptée la l'Organisation internationale de la Francophonie pour accompagner ses Etats membres dans la promotion de la démocratie, de la paix, de la bonne gouvernance qui sont des leviers importants pour assurer une gouvernance démocratique synonyme de stabilité d'un pays. Ce travail de recherche démontre la spécificité de l'approche francophone dans la résolution des conflits qui repose aussi sur le renforcement des institutions judiciaires visant à assurer la paix, la justice sociale, la sécurité et la lutte contre la corruption. Dans un second temps, la thèse fait porter l'analyse sur le rôle que l'Organisation internationale de la Francophonie joue dans les opérations de rétablissement et de la consolidation de la paix et démontre comment cette organisation est devenue un acteur tant sollicité sur la scène internationale grâce à son influence, à son capacité de mobilisation, ses stratégies de médiation et de facilitation ainsi que sa politique d'accompagnement pour faciliter la justice transitionnelle et favoriser l'effectivité de la justice pénale internationale visant à punir les auteurs de guerre.
Keywords: Francophonie; Maintien de la paix; Organisation internationale de la francophonie; Règlement de conflits

Le recours aux modes alternatifs de règlement des litiges en matière de propriété intellectuelle - Tankeu, Jean (Université de Nantes, 2017)
Compte tenu de la complexité et de la dimension sensible de la gestion des affaires de propriété intellectuelle ainsi que de la diversité des modalités de protection et d’application des droits de propriété intellectuelle dans différents ressorts juridictionnels, les MARL sont aujourd’hui un moyen efficace de régler les litiges de propriété intellectuelle. Cela est particulièrement vrai en ce qui concerne les affaires de propriété intellectuelle qui impliquent des considérations commerciales. En effet, la propriété intellectuelle fait désormais partie intégrante du commerce international et de l’économie mondiale. D’où le développement du contentieux non juridictionnel international de la propriété intellectuelle avec pour fondement la création de plusieurs centre internationaux d’arbitrage et de médiation de droit commun et d’un centre spécialisé en arbitrage et médiation des litiges de propriété intellectuelle : le centre d’arbitrage et de médiation de l’OMPI. Cette montée en puissance des MARL en matière de propriété intellectuelle se justifie par l’émancipation de ces derniers par rapport à l’ordre public qui ne joue plus son rôle limitatif voir perturbateur. Il se voit aujourd'hui cantonné dans un rôle lui permettant d'assurer sa fonction naturelle de défense des intérêts légitimes de l'État, mais sans entraver les activités privées qui s'y conforment. Given the complexity and the sensitive dimension of the management of the Affairs of intellectual property as well as the diversity of methods of protection and enforcement of intellectual property rights in different legal jurisdictions, MARL today are an effective way of resolving disputes of intellectual property. This is especially true with regard to the intellectual property cases that involve commercial considerations. Indeed, intellectual property is more territorial in terms of application. She is now an integral part of international trade and the global economy. Where international no jurisdictional litigation of intellectual property development with based on the creation of several international center of arbitration and mediation of common law and a Center who specializes in arbitration and mediation of intellectual property disputes: WIPO mediation and Arbitration Center. This rise of ADR in intellectual property is justified by the emancipation of these compared to public order which no longer plays its role limiting see disruptive. He is now confined in a role enabling it to ensure its natural function of defence of the legitimate interests of the State, but without impeding private activities that conform.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; MARD; Propriedade intelectual; Propriété intellectuelle; Règlement de conflits

Desenho de sistemas de disputas : criação de arranjos procedimentais consensuais adequados e contextualizados para gerenciamento e resolução de controvérsias - Faleck, Diego (Universidade de São Paulo, 2017)
A tese aborda a técnica de desenho de sistemas de resolução de disputas, entendida como a organização deliberada e intencional de procedimentos ou mecanismos processuais, que interagem entre si, e, quando aplicáveis, de recursos materiais e humanos, para a construção de sistemas de prevenção, gerenciamento e resolução de disputas. A delimitação do objeto da presente tese se justifica pela lacuna existente na análise convencional, direcionada a apenas um ou outro mecanismo de resolução de disputas, consubstanciados nos métodos formais mais familiares para os operadores do direito: adjudicação por um tribunal estatal, arbitragem, conciliação ou mediação e negociação. A tese argumenta que a utilização de uma nova lente sistêmica poderá ampliar substancialmente, para o operador do direito, a sua capacidade de invenção e implementação de estratégias adequadas à resolução de disputas. Tais lentes compreendem a mudança do enfoque de análise de um mecanismo particular para o reconhecimento de toda a ordem de mecanismos processuais e canais disponíveis às partes em um determinado contexto, como estes funcionam e principalmente como eles interagem - uma análise de sistemas. Sob esta perspectiva, a tese explora um outro importante pressuposto para a construção de arranjos procedimentais: a adequação. O trabalho argumenta que o fator que incrementará as chances da adequação da resposta processual ao contexto será o processo de concepção, construção e implementação do arranjo procedimental, sob a perspectiva sistêmica. O processualista deve estar atento aos passos inexoráveis que a tarefa de desenhar sistemas de resolução de disputas requer ; esses passos serão abordados detalhadamente no trabalho. A tese sustenta que, sem a devida reflexão e ação sobre os temas identificados em cada uma das etapas necessárias para o desenho de um sistema, o trabalho de construção da resposta processual será mais difícil e o risco de inadequação será agravado. The thesis addresses the topic of dispute systems design, regarding the intentional organization of resources and procedures, which interact with each other, to prevent, manage and resolve disputes. The investigation is important due to the gap in the conventional analysis in dealing with dispute resolution, that aims at one or other dispute resolution mechanism, related to the most familiar formal methods used by lawyers and parties: court adjudication, arbitration, conciliation, mediation or negotiation. The thesis argues that a systemic approach could substantially improve the means for invention and implementation of adequate strategies for dispute resolution in the context of the myriad of situations in which this is necessary. Such an approach requires that the focus of attention be shifted from a particular mechanism of dispute resolution to the broad array of available channels and mechanisms in a given context, how they work, and mainly, how they interact with each other and the people involved: a systems level analysis. Under such perspective, the thesis addresses another important aspect of dispute design: the adequacy. The thesis argues that the element that will increase the chances of adequacy of the procedural response to the context is the process of thinking, building and implementing the procedural scheme, under the systemic approach. The designer should be mindful of the inexorable steps that the dispute systems design initiative requires, which are addressed in detail in the work. The thesis demonstrates that, without careful and structured planning and execution regarding the main issues that lay at every necessary step of the dispute design process, the work of building an adequate procedural response may prove difficult and risky
Keywords: ADR; Alternative dispute resolution; Amicable Dispute Resolution; Arbitrage; Arbitragem; Arbitration; Conciliation; Direito processual; Dispute Resolution; Dispute Systems Design; Hybrid Methods; MARD; Mediación; Mediation; Mediação; Mediação e conciliação; Multi-step Clauses; Médiation; Negotiation; Procedural Mechanisms; Procedural Methods and Processes; Resolução de conflitos

Les enjeux de la déjudiciarisation - Cimamonti, Sylvie; Perrier, Jean-Baptiste (Mission de recherche Droit et Justice, 2017)

Dissenting Opinions in International Commercial Arbitrations - Mohanty, Gautam (Central European University, 2017)
A dissenting opinion with reference to International Commercial Arbitrations elementarily denotes the expression of disagreement by an Arbitrator in relation to both the reasoning and the result of the award granted by the majority of the Tribunal. Though still at a nascent stage, the practice of delivering dissenting opinions is one which needs to be duly noted and taken into due consideration because of the incidental and collateral questions that it nurtures. Fundamentally, a dissenting opinion raises concerns related to the effect, the nature and the rectitude of such opinions. One such collateral question is the enforceability of such dissenting opinions and the repercussions that follow in the context of an arbitral award delivered by the majority. In addition to the above raised question, through this thesis the author will also address other questions such as whether the act of delivering a dissenting opinion is an indicator of the increased sense of maturity of arbitrators in international commercial arbitration? Whether the dissenting opinion possesses any precedential value to the arbitration cases arriving prospectively? and How do such opinions contribute to the development of arbitration jurisprudence. Moreover, through this thesis the author will also attempt from a comparative perspective to examine and make an incisive analysis of the governing rules of arbitration across various arbitration regimes such as ICSID, LCIA which already have a wellestablished arbitration jurisprudence.

Le droit non-étatique dans les rapports internationaux privés : contribution à l'étude des fonctions du droit international privé - Heyraud, Yann (Université Paris 1, 2017)
La production de règles d'origine non étatique se développe dans les rapports internationaux privés. L'analyse de ces règles dans les activités commerciale et sportive construit progressivement une définition unifiée de la notion de droit non-étatique : ensemble des règles écrites et unilatéralement élaborées par des acteurs privés et/ou publics, ayant vocation à s'appliquer eu égard à l'activité considérée, indépendamment des frontières étatiques. Cette proposition est mise à l'épreuve des diverses interactions entretenues par le droit non-étatique, visant à en expliquer le fonctionnement. L'arbitrage atteste sa réception, la fréquence de son application, voire sa promotion, jusqu'à l'exclusion de législations nationales impératives. L'ordre juridique français, par principe, refuse la réception de ce droit, hormis action exceptionnelle des juges, du législateur ou d'organes auxquels il est reconnu compétence. À un niveau supra-étatique, la Cour de justice contrôle directement les règles non-étatiques susceptibles d'entraver les libertés garanties par l'Union européenne, dont la libre circulation des travailleurs. La Cour européenne des droits de l'homme a la possibilité de contrôler indirectement les règles non-étatiques transposées par des États, en raison d'atteintes potentielles aux libertés individuelles, dans le cadre de la lutte contre le dopage par exemple. Le droit international privé, par ailleurs, contribue à rendre compte de l'application du droit non-étatique, en renforce l'efficacité, et participe, potentiellement et à titre prospectif, de la résolution de conflits de normes produits par des règles non-étatiques. The production of non-state norms is growing in private international relations. The analysis of these norms in commercial and sporting activities is progressively building a unified definition of the notion of non-state norms: set of rules written and unilaterally drawn up by private and/or public actors, has intended to be applied with regard to the activity concerned, regardless of State borders. This proposal is put to the test of the various interactions maintained by non-state norms, in order to explain how these norms work. Arbitration attests to its receipt, the frequency of its application and even its promotion, up to the exclusion of imperative national rules. The French legal system, as a matter of principle, refuses to accept these non-state norms. Exceptionally, this principle is contradicted by the action of judges, legislators or bodies whose competence is recognized by the French legal system. At a -supra-state level, the Court of Justice directly controls non-state norms which may hamper the freedoms guaranteed by the European Union, including the free movement of workers. The European Court of Human Rights has the possibility of indirectly controlling non-state norms transposed by States, due to potential breach of individual freedoms, for example in the fight against doping. Moreover, Private International Law helps to explain the application of non-state norms, enhances their efficiency, and potentially and prospectively participates in the resolution of conflicts of norms produced by nonstate norms.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitration; Conflicts of norms; Conflit de normes; Droit international privé; Droit non-étatique; Lex mercatoria; Lex sportiva; New Law Merchant; Non-State Law; Private International Law; Private Regulation; Régulation privée; Transnational

Arbitrage et éthique : causes du mal, évolution récente et pistes d’amélioration – Regards sur le monde et sur l’océan Indien - Anilha, Fernande; Magamootoo, Julien (Revue juridique de l'Océan Indien, 2017)

Suggestions pour promouvoir la place de l’arbitrage en Afrique. Madagascar et la Tunisie comme illustration - Ben Hamida, Walid (Revue juridique de l'Océan Indien, 2017)

Alternative Dispute Resolution (ADR) and access to justice: An introduction - Betancourt, J. (Arbitration, 2017)
Text of a talk given by the author at the University of West London on 8 March 2016 on the topic of Alternative Dispute Resolution, its relation to the concept of access to justice and the idea of practising law in the interest of justice.

Juge judiciaire, acteur de l'essor de l'arbitrage : cas français, malgache et mauricien - Chuk Hen Su, Lalaina (Revue juridique de l'Océan Indien, 2017)

The Application of CISG in International Arbitration - Cisár, Ivan (FIRST BRNO ARBITRATION CONFERENCE 2017, 2017)
International arbitration allows great flexibility of the parties to structure their whole relationship. One of the key factors is the choice of the law applicable to the substance of the relationship. CISG is intended for the regulation of such relations between international businessmen. This paper builds on the empirical evidence of the International Arbitration Surveys conducted among various groups of practitioners on their reasoning con cerning choice of law applicable to the substance of the relationship and argues that although CISG is not chosen by them frequently (or arguably not chosen at all), this “omission” is not warranted.
Keywords: CHOICE OF APPLICABLE LAW; CISG; INTERNATIONAL ARBITRATION

Disqualification Decisions under the ICSID Convention and Arbitration Rules - Cleis, Maria Nicole (The Independence and Impartiality of ICSID Arbitrators, 2017)
This Chapter aims to distill a consistent approach to arbitrators’ independence and impartiality from past decisions on disqualification requests. In a first part, the interpretation of the manifest lack requirement provided for in Article 57 icsid Convention is scrutinized. The definition of this threshold (i.e. the burden of proof imposed on the challenging party) is crucial, because it determines the effectiveness of the right to an independent and impartial decision-maker. The second part of the Chapter inquires how specific categories of alleged conflict are dealt with. It seeks to derive consistency and predictability from the outcome or reasoning of disqualification

The Independence and Impartiality of ICSID Arbitrators: Current Case Law, Alternative Approaches, and Improvement Suggestions - Cleis, Maria Nicole (Nijhoff International Investment Law Series, 2017)
In The Independence and Impartiality of ICSID Arbitrators, Maria Nicole Cleis examines the standard of independence required under the ICSID Convention, as evidenced in existing disqualification decisions, and makes novel suggestions for reforms to ensure unbiased decision-making. Readership: All interested in International Investment Law and investor-State arbitration in particular. Readership includes academics, lawyers and arbitrators involved in investment-related disputes (including in-house counsel), treaty negotiators and NGOs.
Keywords: Arbitrage; Arbitragem; Arbitration; Civil procedure; International Arbitration; International disputes; International law

Guide du secrétariat de la CNUDCI sur la Convention pour la reconnaissance et l’exécution des sentences arbitrales étrangères (New York, 1958) - Commission des Nations Unies pour le Droit Commercial International (Nations Unies, 2017)

First Brno Arbitration Conference 2017: Current Issues of International Commercial Arbitration (Publications of the Masaryk University, theoretical series, editions Scientia, 2017)
Content research papers : - The Application of CISG in International Arbitration; - CISG and Arbitration in the Hungarian Legal Practice; - Time Limits in Arbitration Agreements : What Can We Expect, if We Fail to Meet Them? - Interpretation Hardships Regarding the CISG, in Particular Article 7; - Awarding Punitive Damages in Czech Arbitration Proceedings; - Award of Legal Costs in Arbitration with Focus on Regulation in the Slovak Republic; - Advantage or a Disadvantage? The Costs of Arbitration Court Proceedings in Hungary.

La déontologie de l’arbitre - Dupeyré, Romain (Revue juridique de l'Océan Indien, 2017)

Analyse comparative entre Maurice et Madagascar sur les spécificités liées à l’arbitrage international et à l’arbitrage institutionnel - Gunnoo, Dipna (Revue juridique de l'Océan Indien, 2017)
Les lois mauricienne et malgache relatives à l’arbitrage international s’inspirent toutes deux de la Loi type de la CNUDCI. En dépit de cette source d’inspiration commune, ces deux pays présentent plusieurs aspects divergents. Ces divergences, liées à l’arbitrage international, se retrouvent, non seulement, au sein des caractéristiques législatives et juridictionnelles de chacun de ces États, mais également au sein des caractéristiques des institutions arbitrales promues par ces deux pays. International arbitration laws in Mauritius and Madagascar are both largely inspired by the UNCITRAL Model Law. Despite this similar source of law, these countries have various differing aspects. In the field of international arbitration, discrepancies between these two States can be found, on one hand, in the legislative and jurisdictional features and, on the other hand, in the features of arbitration institutions showcased by these two countries.

Repenser la procédure civile : les enjeux théoriques de l'accès à la justice et l'hypothèse de la régulation sociale par l'intégration des modes extrajudiciaires de prévention et de règlement des différends (PRD) - Hountohotegbè, Sèdjro Axel-Luc (Université Laval, 2017)
La thèse analyse en théorie du droit l’évolution de la procédure civile sous l’angle des enjeux de l’accès à la justice. Elle formule l’hypothèse d’un modèle de régulation sociale qui opère un renversement de la perspective moniste positiviste classique par l’intégration des modes extrajudiciaires de PRD. La thèse répond à la question de recherche suivante : Quels fondements théoriques à l’évolution de la procédure civile pour l’amélioration de l’accès à la justice ? D’un point de vue méthodologique, la thèse opte pour une démarche théorique et documentaire. Elle emprunte aux principales Écoles de théories du droit, en particulier à l’École sociologique. Le cadre théorique s’appuie alors sur les théories du pluralisme juridique, des systèmes et du réseau. Ces théories irriguent la thèse tout entière et servent de grille analytique aux deux parties principales de celle-ci. Dans la première partie, la thèse délimite et précise le concept d’accès à la justice. En trois chapitres, cette première partie s’attèle méthodiquement à déconstruire les acceptions dominantes institutionnelles et restrictives du concept. Elle aboutit à l’élaboration d’une définition innovante à valeur théorique et pratique de l’accès à la justice. Dans la seconde partie, l’analyse porte sur l’évolution des paradigmes de la procédure civile. En trois chapitres, elle pose une critique du système dominant de règlement des conflits en général et de la procédure civile en particulier qui reposent sur le droit selon les principes de hiérarchie des normes. La thèse déconstruit cette vision, puis propose une théorie générale supportant la légitimité des modes extrajudiciaires de PRD. Finalement, la recherche suggère une évolution de la procédure civile et soumet à cet effet un modèle de système de justice alternatif intégrant les modes extrajudiciaires de PRD. Le modèle de régulation proposé est non antinomique et complémentaire au modèle dominant. Le modèle de régulation sociale construit dans la thèse s’articule autour de trois paradigmes fondamentaux à savoir la décentralisation, la multipolarité et la complémentarité. La thèse constitue un compendium d’analyses et soumet un cadre de référence des paradigmes de base d’un système de justice renouvelé pour l’amélioration de l’accès à la justice.
Keywords: Accès à la justice; Arbitrage; Arbitragem; Arbitration; MARD; Mediación; Mediation; Mediação; Médiation; Procédure civile; Règlement de conflits

Arbitrage et sécurisation juridique des investissements : l'arbitrage comme moyen de sécurisation des investissements à Madagascar - Jakoba, Raphaël (Revue juridique de l'Océan Indien, 2017)
Madagascar s’est doté d’un arsenal juridique cohérent et attractif relatif aux investissements. La panoplie de mesures est étoffée allant d’une loi spécifique sur les investissements (loi 2007-036 sur les investissements à Madagascar), à un cadre institutionnel tel que l’EDBM, et enfin des engagements internationaux (adhésion à la convention de Washington de 1965, ratification de plusieurs APPI (Accords pour la promotion et la protection réciproques des investissements) avec la France, le Benelux... À la lumière de cet arsenal en faveur des investissements, il est permis de dire que l’arbitrage, mode de règlement des différends pour les investissements, est placé au cœur d’une politique d’attraction et de sécurisation des investissements. Toutefois, la pratique malgache de l’arbitrage international tant commercial qu’en investissement révèle un certain nombre de dysfonctionnements et de défaillances qui impactent sur l’environnement des affaires. Madagascar has developed a coherent and attractive legal arsenal for investment. The range of measures was refined ranging from a specific investment law (Law 2007-036 on investments in Madagascar) to an institutional framework such as the EDBM, and international commitments (accession to the Washington convention of 1965, Ratification of several APPI [Agreements for the Promotion and reciprocal Protection of Investments] with France, the Benelux...). In the light of this arsenal in favor of investments, it can be said that arbitration, the method of settlement of Investment Disputes, is at the center of a policy of attracting and securing investments. However, the malagasy practice of international arbitration, either for commercial or investment arbitration reveals a number of dysfunctions and failures, impacting significantly the investment climate.

Alternative Dispute Resolution in Oil and Gas Contracts Law: An Analysis - Kareem, Kareem Kawa (Near East University, 2017)
The industry of oil and gas is not peculiar to question anymore, inferable from the global condition as well as its various dimensions. While trying to complete an agreement procedure, it would barely be clear to expect the thing that could happen in the emergence of a debate. Hazard moving and fragmented contracting lie at the heart of the organization relationship innate in the obtainment and financing of extensive scale undertakings, such as power plants, oil and gas pipelines, and condensed natural gas facilities. An examination of gas bonds gives exact proof of the hazard moving results of legally binding inadequacy. This thesis is a basic examination of the discipline we call the law of oil and gas. A number of the imperfections connected with this "specific" status. Jurisprudential with its "uncommon" status. Jurisprudential imperfections have created as courts leave from essential contract, property, or tort law in quest for natural resources ideas. The marvel isn’t restricted to natural resources law but instead can occur in any "law of" setting. This article delineates the issues connected with oil and gas law by dissecting legal ways to deal with perceiving and applying "inferred agreements" under the oil and gas rent. By contrasting the experience and results under the oil and gas lead to the result under an agreement law investigation, it is conceivable to assess whether a specific "oil and gas" govern is vital or prudent. In the past quarter-century, huge changes have happened in the ways legal advisors approach strife. There have been uncommon endeavors to create systems went for more proficient, not so much expensive, but rather more fulfilling determination of contention, including more broad and suitable utilization of intercession and other " alternative dispute resolution " (ADR) approaches. This review analyzes what is known and not considered about the development and effect of ADR in government and state courts, in the business division, and in work and shopper settings. The investigation inspects the relationship amongst ADR and court trial, additionally underlines the more extensive employments of and method of reasoning for intercession and different process decisions. This study concentrates on the oil and gas contract with question by ADR.

Le règlement par voie d'arbitrage des litiges relatifs aux investissements dans l'espace OHADA - Kenfack Douajni, Gaston (Revue juridique de l'Océan Indien, 2017)

Réflexion sur la notion et le régime de la médiation au sein des modes amiables de résolution des différends : à partir des expériences de médiation dans les ressorts des Cours d’appel d’Aquitaine (Agen/Bordeaux/Pau), de Paris et de Lyon - Larribau-Terneyre, Virginie; Lecourt, Arnaud; Brus, Florence; Alvarez Elorza, Alexis; Drouiller, Camille; Sane, Claude MIchel (Mission de recherche Droit et Justice, 2017)

International Arbitration - Liatowitsch, Manuel; Rosenthal, Jeffrey; Forneret, Martine; Scherker, Emily; Ashford, Peter; Janzik, Sabrina; Weldon, Matthew; Houston, Robert; Boog, Christopher; Gottlieb, Benjamin; Meijer, Gerard; Verberne, Valerie; et al. (The Year in Review, 2017)
Keywords: Arbitration; Dispute resolution; International Law

L'arbitrage et la lutte contre la corruption - Ligneul, Nicolas (Revue juridique de l'Océan Indien, 2017)

Primera ejecución en España de un laudo OHADA ¿Por qué tiene un juez español que forzar su cumplimiento? - Linares Rodríguez, Enrique (Arbitraje: revista de arbitraje comercial y de inversiones, 2017)
El Convenio de Nueva York de 1958 permite se busque el reconocimiento y la ejecución de un laudo OHADA en terceros Estados. Sin embargo, admite el empleo de la normativa interna para regir el procedimiento y deja a salvo cuestiones relacionadas con la inmunidad soberana de los Estados. Las nuevas leyes adoptadas en España en materia de cooperación jurídica internacional e inmunidad soberana, establecen la intervención del MAEC cuando un Estado extranjero sea demandado ante tribunales españoles como es el caso Commercial Bank / Guinea Ecuatorial. Esta previsión puede implicar un giro de la jurisprudencia hacia posturas más cercanas a la inmunidad absoluta. Como se verá en este artículo, aunque CBGE haya obtenido el execuátur del laudo en España y logrado el embargo del avión titularidad de Ceiba, las medidas coercitivas de ejecución podrán ser recurridas en revisión por el Estado, quien podrá plantear una estrategia fundamentalmente en dos direcciones: (i) bien demostrando la finalidad soberana del aparato embargado, para defender así su carácter inmune a la ejecución, o (ii) bien alegando que la persona jurídica afectada por el embargo no ha sido parte en el arbitraje y por tanto no es la deudora del laudo. La práctica jurisprudencial internacional ha demostrado que existen gran des posibilidades de que el tribunal termine levantando el embargo si se demuestra fehacientemente alguna de estas dos defensas.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Ejecución; Embargo; Guinea Ecuatorial; Inmunidad; Laudo arbitral

The notion of award in international commercial arbitration-lessons from French and English law - Marchisio, Giacomo (McGill University, 2017)
For the past twenty years, international commercial arbitration scholarship has mainly focusedon the private dimension of international arbitration. Part of a greater movement toward the privatization of justice and law, this understanding of the discipline has obscured arbitrators'adjudicative role. By reflecting on different adjudicative models and by analyzing the form andcontent of arbitral decisions, new light can be shed on our understanding of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Award; Commercial Arbitration; English law; French law; International Arbitration; International commercial arbitration

L'arbitrage de droit commun régi par l'Acte uniforme relatif à l'arbitrage - Ngwe, Marie-Andrée (Revue juridique de l'Océan Indien, 2017)
L’arbitrage de droit commun est régi par l’Acte uniforme relatif à l’arbitrage, véritable loi de procédure harmonisée applicable dans les 17 États membres de l’OHADA. Aux côtés de l’arbitrage CCJA dont il est complémentaire, il a sa légitimité et sa vocation propre qui est de permettre le développement d’un arbitrage de proximité. Conforme aux standards internationaux, qu’il soit ad hoc ou institutionnel, il met au cœur du processus les parties, afin de créer une véritable culture locale de l’arbitrage. À ce titre, il donne un rôle essentiel aux institutions nationales d’arbitrage dont la connaissance de terrain et la proximité des acteurs permettent l’enrichissement de la lex arbitri, jusqu’à permettre aujourd’hui d’inspirer une réforme de cette loi uniforme de l’arbitrage OHADA qui tend vers toujours plus d’efficacité et de modernité. Il nous sera donné en particulier de faire part de l’expérience du Centre d’arbitrage du GICAM, Douala (Cameroun). The Uniform Act on arbitration is the ordinary law that governs arbitration. This Uniform Act is a harmonized procedural enactment that is applicable in the 17 member states of OHADA. It exists alongside, and is complementary to CCJA arbitration. But it has its own legitimacy and its own vocation, which is to allow the development of an arbitration of proximity. Whether considered from an ad hoc arbitration viewpoint, or an institutional arbitration viewpoint, the Uniform Act complies with international arbitration standards. It places the parties at the heart of the arbitral procedure in order to create a local culture of arbitration. In this regard, it provides an important role to national arbitration institutions whose understanding of the field and proximity to stakeholders permit the enrichment of the lex arbitri. Today, this role given to national arbitration institutions has inspired a reform of the Uniform Act on arbitration, which aspires for more efficiency and modernity. We shall, in particular, share the experience of the GICAM Arbitration Centre in Douala Cameroon.

Document Production and Disclosure in Investor-State Arbitration - Oepangat, Dioputra Ilham; Janet, Janet (Juris Gentium Law Review, 2017)
It is not uncommon for states to engage in arbitration proceedings with their investors (“Investor-State Arbitration” or “International Investment Arbitration”) administered under the International Centre for the Settlement of Investment Disputes. When these parties engage in document production during evidentiary proceedings, there arises an issue with regards to documents requested by the investor, which is considered as a “state secret” by the state. Based on the IBA Rules on the Taking of Evidence in International Arbitration (“IBA Rules”), states may have particular interest to refuse the production of a document. This is based on the argument that a document may be exempted from production if the document qualifies as a state secret by virtue of Article 9 of the IBA Rules. This paper will discuss appropriate measures to be taken by tribunals in order to allow for material and relevant evidence to be produced during proceedings, which may be crucial in being able to prove the case of the investor in the case of a conflict pertaining to the production of documents containing state secrets.
Keywords: Arbitrage; Arbitragem; Arbitration; Disclose; Document; IBA; ICSID; International; Investments; Prove; Secrets; Sensitive

La Charte confiance du Centre d’arbitrage et de médiation de Madagascar (CAMM) - Ramangaharivony, Gérard (Revue juridique de l'Océan Indien, 2017)
Les litiges font partie intégrante du monde des affaires. Les gérer efficacement constitue un défi majeur pour le maintien de la paix sociale et l’accroissement du business. Dans sa mission de sensibilisation aux Marl, le Centre d’arbitrage et de médiation de Madagascar (CAMM) a élaboré et proposé une Charte confiance de règlement des litiges. Cette Charte a pour objectif la continuité des affaires, le respect de la loi et un marché sain et prospère.

L'Etat dans l'arbitrage d'investissement - Ranjeva, Hery Frédéric (Revue juridique de l'Océan Indien, 2017)

Règlement alternatif des litiges commerciaux et économiques dans la zone francophone - Ravaloson, Johary (Revue juridique de l'Océan Indien, 2017)

Can third party funding deliver justice in international commercial arbitration? - Yu, Hong-Lin (International Arbitration Law Review, 2017)
Third party funding arrives at international commercial arbitration without clear guidelines. The recognition and acceptance of its legality is hampered by the omissions of all stakeholders' rights involved in international commercial arbitration. In balancing the funder’s contractual rights to gather information under the third party funding agreement and stakeholders' rights to know, the current research examined how non-disclosure of the third party funding agreement would prevent the arbitrators from fulfilling procedural justice required for the integrity of arbitration on their part and impede the opposing party’s right to know during the proceedings. The research highlights the issues from the delivery of procedural and substantive justice as well as suggesting legal and jurisprudential grounds in third party funding governance. It also points out that all issues examined will ultimately contribute to the failure in delivering justice in international commercial arbitration if third party funding is left to self-governance.
Keywords: Arbitration; International commercial arbitration; Third Party Funding

Composantes multidimentionnelles de l’arbitrage : de la considération locale à l’interculturalité internationale - Wehbe, Fatima Sara (Normandie Université, 2016)
La mondialisation a permis l’instauration de plusieurs institutions d’arbitrage. Cette multitude de choix offerte aux investisseurs pourrait induire les parties à choisir une institution défavorable quant à la résolution de leur litige. L’objectif de la thèse est de présenter un modèle de gestion pour les juristes qui facilite le choix de la juridiction la plus efficace ceci avec la mise en œuvre d’un tableau de notation associant des critères multidimensionnels accordant une notation selon le degré d’importance vue par les parties. A ce sujet, le tableau mis en place regroupe les quatre juridictions les plus connues internationalement qui sont les juridictions étatiques, la CCI, le CIRDI et la CNUDCI. L’arbitrage est composé de plusieurs fondements qui lui accordent sa spécificité. L’analyse multidimensionnelle permettrait donc de faire une analyse arithmétique des valeurs comparatives des composantes juridiques et extra-juridiques de l’arbitrage qui forment le tableau de notation afin de faciliter la prise de décisions des investisseurs. Afin de vérifier l’efficacité du tableau de notation, un questionnaire a été adressé aux investisseurs ainsi que des interviews effectuées avec des juristes ont permis de déceler l’impact de l’expérience sur le choix du centre le plus efficace. L’étude de cas de l’affaire COMMISIMPEX est un exemple de l’effet du choix inefficace sur la résolution du litige et explique comment l’expérience pourrait affecter la décision de l’institution d’arbitrage le plus efficace à la résolution du litige. Pour en conclure qu’il n’y a pas de juridiction intrinsèquement meilleure que les autres. Il faut donc procéder au cas par cas et selon ce que les parties recherchent suite à leur litige, pour en déduire la juridiction ou l’institution qui leur serait la plus favorable afin de leurs garantir le plus de droits lors de la résolution de leur litige. Globalization has established several arbitral institutions. They offer a multiple of choices to the investors that could induce the parties to choose an unfavorable institution.The aim of this thesis is to present a management model for jurist which facilitates the choice of the most efficient jurisdiction in resolving their dispute, with the implementation of a scoring table combining multidimensional criteria, giving a rating according to the degree of importance for the parties. In this regard, the table regroup four of the most well-known internationally jurisdiction, the State court, the ICC, the ICSID and the UNICITRAL. Arbitration is composed of several fundaments that give it its specificity. Multidimensional analysis thus would make an arithmetical analysis of the comparative values of the legal and extra-legal components of arbitration which form the scoring table to facilitate decision making of investors. To verify the effectiveness of the scoring table a questionnaire was sent to investors as well as an interview conducted with lawyers have identifies the impact of the experience on the choice of the most efficient arbitral center. The Case study of COMMISIMPEX is an example of the effect of inefficient choice on the resolution of the dispute and how the experience may affect the decision of the most effective arbitration institution to the resolution of the dispute. To conclude none of the jurisdiction is inherently better than the others. We must proceed case by case and according to what the parties are looking after their dispute, to deduce the court or institution that would be most favorable to them by guarantying more rights in the settlement of their dispute.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Interculturality; Interculturalité; International commercial arbitration; Pluralisme juridique; Règlement de conflits

L’arbitrage institutionnel OHADA : Instrument émergent de sécurisation juridique et judiciaire des activités économiques - Diakité, Moussa (Université Toulouse 1 Capitole, 2016)
Devant le ralentissement des investissements en Afrique, il s’est avéré incontournable de reconstruire un ensemble juridique moderne adapté à l’exigence de protection des activités économiques. Les Présidents des pays, essentiellement de la zone franc, ont ainsi signé le 17 octobre 1993 le Traité relatif à l’harmonisation du droit des affaires en Afrique visant à garantir la sécurité juridique et judiciaire. Le droit issu de ce traité a donné naissance à divers Actes uniformes dont l’Acte uniforme relatif à l’arbitrage. L’objectif de notre étude a été d’analyser, principalement à partir de ce texte et sa pratique, dans quelle mesure les opérateurs économiques bénéficient, par l’arbitrage, d’une meilleure garantie d’encadrement de leurs activités. Si l’arbitrage apparait comme étant un instrument pertinent en termes de protection des investissements, c’est qu’il allie deux exigences fondamentales : la liberté ainsi que la sécurité. En effet, la liberté des parties et des arbitres est au fondement de la procédure arbitrale, garantissant aux opérateurs économiques l’assurance d’une justice plus adaptée aux exigences internationales. L’arbitrage doit également offrir une sécurité juridique dans la résolution des conflits permettant de sauvegarder les intérêts des parties tout en assurant l’efficacité de la sentence arbitrale.
Keywords: Arbitrage; Arbitrage OHADA; Arbitrage commercial international; Arbitragem; Arbitration; Investissements; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'OHADA; Sécurité juridique

Réflexion sur l’arbitrage dans l’espace OHADA - Diallo, Abdou (Université de Perpignan, 2016)
L’arbitrage est la motivation première de la création de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) pour lutter contre l’insécurité juridique et promouvoir son développement. Cet arbitrage s’inspire des règles matérielles de l’arbitrage international qui accorde une importance particulière à la volonté des parties.L’arbitrage dans l’espace OHADA est régi par le Traité, un acte uniforme et le règlement d’arbitrage de la Cour Commune de Justice et d’Arbitrage(C.C.J.A).Le droit de l’arbitrage a certes amélioré le cadre normatif surtout dans les pays qui n’en disposaient pas, mais au bout de plus d’une décennie d’existence, cet arbitrage est confronté à de nombreuses difficultés d’application. Ces difficultés proviennent de ces acteurs (parties, arbitres et juge national).Ainsi, notre réflexion vise à analyser les difficultés d’application à partir du contentieux arbitral et à proposer des mesures susceptibles d’améliorer le droit et la pratique de l’arbitrage.
Keywords: Afrique; Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; CCJA; Common Court of Justice and Arbitration; Cour Commune de Justice et d'Arbitrage; Exéquatur; Ohada; Organisation pour l'harmonisation en Afrique du droit des affaires

The UNCITRAL Model Law on International Commercial Arbitration: Interpretation, General Principles and Arbitrability - Viscasillas, Pilar Perales (Journal of Law, Society and Development, 2016)
This article explores the possible modification of the UNCITRAL Model Law on International Commercial Arbitration (MAL) to include the topic of arbitrability. This is an area in which the domestic legal systems differ, particularly in relation to the arbitrability of intra-corporate disputes. The article also deals with new art 2A, introduced into the Model Law in 2006, which deals with the interpretation and gap-filling system under the Model Law. The interpretation of MAL in accordance with its international character is a very important step towards uniformity and therefore the different tools required for a uniform interpretation are analysed. These include case law and scholarly writings; the meaning and importance of achieving both a uniform and an international interpretation of MAL are also considered. The article also analyses the whole text of MAL in order to arrive at the general principles on which the Model Law is based; when problems have to be solved, these principles should guide issues of interpretation that arise under this law.
Keywords: Arbitrability; Arbitration; General principles; Interpretation; UNCITRAL

Arbitrability and public policy: an African perspective. - Mante, Joseph (Arbitration international, 2016)
Growth in international trade has led to considerable expansion of the scope of matters capable of settlement by arbitration. In spite of sustained scholarly activity on arbitrability, the question of what is arbitrable remains controversial but relevant in many regions of the world, including Africa. Arbitrability has the potential to affect the validity of an arbitration agreement, strip an arbitrator of jurisdiction, or derail enforcement of an award. Given the significance of the concept, it is vital that entities involved in international transactions do not speciously extrapolate knowledge of what pertains in Europe and America across all jurisdictions and regions of the world. This study draws a comparison between arbitrability and its relationship with public policy in Europe and America on one hand, and the trend in Africa in an attempt to critically investigate the extent to which African states are willing to extend the scope of arbitrable subject matters. A number of trends on arbitrability are discernible. Most commercial disputes are arbitrable and this observation generally aligns with practice in Europe and America. Beyond this, there are three significant differences in the areas of scope of subject matter, approaches to arbitrability regulation and the role of public policy.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Policy

Rethinking the Role of Courts and Judges in Supporting Arbitration in Africa - Onyema, Emilia (Rethinking the Role of Courts and Judges in Supporting Arbitration in Africa, 2016)
This second conference in the SOAS Arbitration in Africa Conference series examined how African judges can better support the growth of arbitration. The conference was hosted by the The Lagos Court of Arbitration in their premises in Lagos, Nigeria from 22-24 June 2016. This conference booklet contains some of the papers and slides, and photographs from the conference.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Courts; Judges; Rôle; Support

Towards a suitable domestic arbitration process in Nigeria - Bamgbose, Ademola Jonathan (University of Warwick, 2016)
The Nigerian judicial system is currently in a state of distress. Not only has the judiciary been trailed by allegations of corruption, incompetence and god-fatherism amongst others, the wheels of justice in Nigeria are slowly grinding to a near halt. This is because of the large and growing case list of courts as well as the recurrent industrial strike actions embarked upon by court staff. As a solution to this crisis, stakeholders have put forward a number of suggestions, one of which is the use of alternative dispute resolution methods like domestic arbitration, as a solution to the problems of the judiciary and as a viable alternative to the court system. As we will however come to see in this thesis, Nigeria’s Arbitration and Conciliation Act 1988 (“Arbitration Act”), which is based on the UNCITRAL Model Law 1985, is not only outdated, it is also for many reasons not suitable and relevant to a developing country as Nigeria. For example, the existing Arbitration Act fails to take the legal and social idiosyncrasies of the Nigerian nation into consideration. Furthermore, the Act fails to incorporate the pre-existing and judicially recognized customary arbitration practice into the Act. In addition, the Nigerian Arbitration framework contains a number of anti-arbitration provisions, which have clearly inhibited the growth of domestic arbitration in Nigeria. Moreover, between 1988 and now, a number of beneficial changes have occurred within the sphere of arbitration and from which the Nigerian arbitration framework can draw lessons. All these among others, make the Nigerian Arbitration Act an unsuitable alternative to the court system in Nigeria. This thesis therefore recommends a bespoke domestic arbitration framework, which takes account of the legal and social idiosyncrasies of the Nigerian nation as well as recent but relevant domestic arbitration practices in similar jurisdictions as Nigeria. Among other recommendations, the proposed framework borrows a leaf from the deeply rooted and judicially recognised customary arbitration practice in Nigeria. Furthermore, in a bid to identify and incorporate relevant provisions and practices that have emerged within the sphere of domestic arbitration between 1988 and now, we undertake a comparative analysis of the Ghanaian Alternative Dispute Resolution Act 2010, the UNCITRAL Model Law 2006, the English Arbitration Act 1996 as well as the Uniform Act on Arbitration 1999 of OHADA. It is believed that this modern but tailored framework will encourage the use of domestic arbitration in Nigeria and by extension ameliorate the problems in the judicial system.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (Administrative law); Ghana; Nigeria

L'intervention du juge dans la procédure arbitrale - Najib, Mohamed El Mehdi (Université de Bordeaux, 2016)
L'arbitre est un juge privé, il tranche, il juge, et il détient la balance de la justice, pourtant sesdécisions ne seront exécutoires que si le juge étatique compétent le décide. Ainsi soumise aucontrôle du juge, la sentence arbitrale s'intègre dans l'ordre juridictionnel. Elle doit doncrespecter l'ordre public et, plus généralement, les principes directeurs du procès. Certes, c’estune sentence oeuvre de justice et, au même titre que les décisions des tribunaux étatiques,bénéficie de l'autorité de la chose jugée.Les textes légaux et les règles qui gouvernent la procédure arbitrale ont une très grandeimportance tant pour les parties, que pour les arbitres. Ce sont en effet ces règles, et lapossibilité de les choisir, qui participent à la spécificité de l’arbitrage.La présente thèse identifie et analyse les diverses facettes de l'intervention du juge dans laprocédure d'arbitrage. S'il s'avère d'un précieux appui à l'arbitrage, le juge est aussi chargéd'en vérifier la régularité et d'en assurer l'efficacité.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration proceeding; Judge; Juges; Procédure arbitrale

A mediação incidental como meio de solução dos conflitos trabalhistas individuais: a questão da dispensa de trabalhadores detentores da garantia provisória no emprego - Santos, Ricardo Goretti; Leite, Carlos Henrique Bezerra (Espaço Jurídico Journal of Law, 2016)
Resumo: Este artigo versa sobre a prática da mediação incidental no processo do trabalho e sua potencial contribuição para a efetiva solução de conflitos decorrentes da dispensa de trabalhadores dotados de garantia provisória do emprego. Acusa o uso desordenado da conciliação incidental, indiscriminadamente aplicada na solução de conflitos individuais situados no âmbito de relações trabalhistas, tanto circunstanciais quanto continuadas. Busca responder ao seguinte problema de pesquisa: a prática da mediação judicial incidental na Justiça do Trabalho pode contribuir para a efetiva solução de conflitos decorrentes da dispensa do trabalhador dotado de garantia provisória do emprego? Estabelece as bases do fenômeno da difusão dos métodos alternativos de solução de conflitos, no contexto do movimento universal de acesso à justiça. Desenvolve considerações sobre particularidades da conciliação e da mediação, destacando os aspectos principais de distinção entre elas. Finalmente, avalia a aplicação dos métodos autocompositivos, considerando as particularidades das controvérsias decorrentes da dispensa de trabalhadores dotados de garantia provisória no emprego. Conclui que, por objetivar a exploração aprofundada dos interesses em jogo, o fortalecimento do diálogo e da relação entre as partes, além do empoderamento dos envolvidos, a mediação judicial incidental seria a via mais adequada para a administração de conflitos decorrentes da dispensa de trabalhadores com garantia provisória do emprego. Além isso, evidencia uma proposição legislativa sobre o tema, já submetida à apreciação da Comissão de Juristas responsável pela elaboração do Anteprojeto de Lei de Arbitragem e Mediação, do Senado Federal.
Keywords: Arbitrage (droit du travail); Arbitragem; Arbitration; Conciliation (droit du travail); Conciliação trabalhista; Despedida arbitrária; Garantia no emprego; Labour dispute; Mediation; Mediação trabalhista; Médiation; Resolução alternativa de conflitos

L’arbitrage en droit espagnol des sociétés, à l’aune du droit comparé - Correa Delcasso, Jean-Paul (La Lettre, 2016)
Dans la présente étude, l’auteur expose l’évolution qu’a connue la pratique de l’arbitrage en droit espagnol depuis ses débuts. Il analyse, d’un point de vue pratique, les principales solutions dégagées par la jurisprudence espagnole, en ce qui concerne l’arbitrabilité d’un grand éventail de litiges, question qui s’est traditionnellement posée en droit espagnol. Il compare la situation avec celle d’autres systèmes juridiques européens culturellement proches.

Admission de la question préjudicielle posée par le juge de l’annulation de la sentence - Posocco, Laurent (La Lettre, 2016)
Le juge de l’annulation de la sentence arbitrale internationale a la faculté de demander à la Cour de justice de l’Union européenne (CJUE) de statuer sur une question d’interprétation du Traité sur le fonctionnement de l’Union Européenne (TFUE) en vertu de son art. 267.

Bonne foi de l’avocat dans la mise en œuvre de la clause compromissoire - Posocco, Laurent (La Lettre, 2016)
Ayant fait ressortir que les parties avaient eu la volonté de se soumettre à l’arbitrage, l’exigence de bonne foi pouvait leur être opposée et que les pouvoirs du cabinet d’avocats émirati étant apparents, la croyance de la société d’avocats londonienne mandatée à l’engagement des parties était légitime, la cour d’appel en a exactement déduit que le tribunal arbitral était compétent.

La responsabilité de l’arbitre et son assurance - Raibaut, Jacques (La Lettre, 2016)
La figure de l’arbitre, comme celle du juge, paraît étrangère à la responsabilité tant domine l’image de la fonction recherchée par le justiciable : dénouer le conflit qui les oppose. Au-delà de la déception que peut susciter la décision rendue chacun admet que l’indépendance, l’impartialité et la compétence sont inhérents à cette fonction et justifient que l’arbitre bénéficie d’une immunité juridictionnelle de principe qui le met à l’abri du ressentiment d’une ou des parties.

La responsabilité des centres d'arbitrage - Elatafy, Sherif (Université Jean Moulin Lyon 3, 2016)
Les litigants sollicitent les centres d’arbitrage pour diriger l’arbitrage dans toutes ses phases afin de donner une garantie supplémentaire qui assure la validité de la sentence arbitrale. Compte tenu du rôle important que les centres d’arbitrage jouent pendant l’instance arbitrale, les litigants mécontents de la sentence arbitrale ou du jugement annulant la sentence tentent d’engager la responsabilité du centre d’arbitrage dès lors qu’il a surveillé, dirigé et participé au rendu de la sentence.De plus en plus la responsabilité des centres d’arbitrage est mise en cause devant les juridictions étatiques différentes, les fonctions et les pouvoirs exercés par les centres d’arbitrage ainsi que le régime de responsabilité leur est applicable font l’objet d’une attention critique de la part de la doctrine dans plusieurs systèmes juridiques. On s’interroge sur l’origine des rapports qui lient les centres d’arbitrage aux autres acteurs de l’arbitrage, sur les obligations et les pouvoirs conférés aux centres d’arbitrage, et sur les fonctions exercées par les centres d’arbitrage pour établir enfin un régime de responsabilité homogène et pertinent à l’égard des fonctions exercées par les centres d’arbitrage qui a une vocation à s’appliquer dans la majorité des systèmes juridiques. Parties to arbitration seek arbitral institutions to administrate their arbitration in order to have an extra guarantee that ensures the validity of the arbitral award. Given the role that arbitral institutions play during the arbitral procedure, parties unsatisfied either by the arbitral award or the annulment of the award tend to claim the liability of arbitral institution for the awards it had supervised, administered and participated in.The more the allegations of liability raise against the arbitral institutions before courts, the more the issue of arbitral institutions’ functions, powers and liability becomes controversial in different jurisdictions. Therefore, the present study tends to clarify the origin of the relationship existing between arbitral institutions and other parties involved in the arbitration at issue, the duties and powers assigned to the arbitral institutions and the functions performed by the arbitral intuitions, which helps eventually in establishing a kind of liability that complies with the functions performed by the arbitral institutions and can be applied in many jurisdictions.
Keywords: Acte juridictionnel; Administrative functions; Agreement to administrate an arbitration; Approbation; Arbitrage; Arbitrage commercial international; Arbitrage institutionnel; Arbitragem; Arbitral Awards; Arbitral institutions; Arbitration; Business contract; Centre d'arbitrage; Challenging arbitrator; Civil liability; Clause exclusive de responsabilité; Condition excluding liability; Consensual protection; Contrat de direction d’arbitrage; Contrat d’entreprise; Décision institutionnelle; Examen prima facie; Faute intentionnelle; Faute lourde; Fonctions administratives; Fonctions juridictionnelles; Forum; Gross negligence; Immunity; Immunité; Institutional arbitration; Institutional decision; Judicial conduct; Judicial functions; Prima facie examination; Protection conventionnelle; Responsabilité civile; Récusation d’arbitre; Sentence arbitrale; Willful misconduct

An Introduction and an Evaluation of Arbitration in Ivory Coast - Kalle, Aurélie (Recht in Afrika, 2016)
The paper deals with arbitration law in Ivory Coast and is mainly based on interviews with the most important authorities in this field. After a short introduction into the OHADA legal system the two main arbitration centres of Ivory Coast are presented. First, the paper treats the internationally known OHADA arbitration centre of the Common Court of Justice and Arbitration, hereinafter known as CCJA. It explains the bodies and the organisation of the CCJA, the arbitration procedure in detail, the enforcement of the arbitral award, the interim measures and the legal remedies against decisions of the CCJA. Second, the functioning of the Court of Arbitration of Côte d'Ivoire, hereinafter known as CACI, is explained. It is the second arbitration centre of Ivory Coast and it was created by the Ivorian Chamber of Industry and Commerce and settles mainly disputes between nationals. The analysis treats the same topics as mentioned for the CCJA centre, but is restricted to point out the differences or peculiarities of the CACI procedure, in order to prevent repetitions. Third, the paper analyses the advantages and disadvantages of the two arbitration centres and compares them to the proceedings of the Commercial Court of Abidjan. It avoids the comparison of yet well-known arguments such as confidentiality of arbitration proceedings or the parties' free choice in regard to the place of arbitration and the language, etc. The work rather limits itself to concretely address the problems or the advantages of each dispute solution considering the latest developments in the judicial system. The purpose of the report is to give a practical introduction into the Ivorian arbitration law, in particular to foreign lawyers. It should provide them with solid theoretical knowledge of the different dispute solutions. With the help of concrete comparisons and explanations of the actual situation regarding the civil and commercial judicial system it should enable them to find the most suitable dispute solution for their clients.
Keywords: Arbitrage; Arbitragem; Arbitration; Côte d'Ivoire; Ivory Coast

La sentence arbitrale et le juge étatique : approche comparative des systèmes français et iranien - Danay Elmi, Manijeh (Université Paris 1, 2016)
En France et en Iran, le droit de l’arbitrage est le fruit d’une longue maturation historique. L’arbitrage en Iran plonge ses racines dans l’Antiquité. En raison de la culture du règlement pacifique des différends qui dominait alors, l’arbitrage s’est imposé comme le mode privilégié des règlements des différends. Dans le domaine de l’arbitrage commercial international, l’Iran s’est inspiré de la loi-type de la CNUDCI de 1997. Ce pays a également adhéré en 2001 à la Convention de New York. Le point de convergence entre les deux ordres juridiques français et iranien : ils ont cherché à instaurer des règles plus favorables pour la reconnaissance et l’exécution des sentences arbitrales, chacun ayant adopté une démarche différente. La première partie de cette étude est consacrée à la réception de la sentence arbitrale dans les deux systèmes. Seule la sentence définitive peut faire l’objet du contrôle et de l’exécution. Plus concrètement, la qualification en sentence internationale ou étrangère déterminera les règles applicables à la reconnaissance et l’exécution de celle-ci. La sentence arbitrale identifiée et reconnue est susceptible d'être contrôlée par le juge qui déterminera le sort de la sentence. La deuxième partie de notre analyse décrit ce contrôle qui peut être direct à l’occasion du recours en annulation ou indirect lors de la demande de reconnaissance et d’exécution. Ce mécanisme conduit in fine à protéger les droits de la partie gagnante et à empêcher l’abus, par la partie condamnée, des voies de recours. In France and Iran, the law of arbitration is the result of a long historical development. Arbitration in Iran finds its roots in the Antiquity. Because of a culture favoring the pacific settlement of disputes, which was prevailing at that period, arbitration imposed itself as the privileged mode in resolving disputes. In the field of international commercial arbitration, Iranian legal system has been inspired by the UNCITRAL Model Law in the promulgation of its LICA in 1997. This country has also adhered to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards in 2001. The converging point between the Iranian and French legal systems is the following: they have tried to establish the rules favoring the recognition and enforcement of arbitral awards, any of them adopting a different approach. The First Part of this study is allocated to the reception of the arbitral award in the two legal systems. Solely the final award could be subject to control and enforcement. More concretely, the qualification of the arbitral award as international or foreign award will determine the applicable rules in the matters of recognition and enforcement. The arbitral award, identified and recognized, could possibly be controlled by the judge who will determine its fate. The Second Part of our analysis describes the said control that could be direct, on the occasion of the action for setting aside the award, or indirect, when requesting the recognition and enforcement of the award. This mechanism will lead in fine to protecting the winning party’s rights and avoiding any abuse of the means of recourse by the losing party.
Keywords: Arbitrage; Arbitrage (droit); Arbitrage commercial international; Arbitration; Arbitre; Droit comparé; Droit international; France; International commercial arbitration; Iran; Iranian legal system; Ordre public droit iranien; Reconnaissance et éxécution de sentence; Sentence arbitrale

Contrariétés entre jugements étatiques et sentences arbitrales dans l'espace OHADA - Castellane, Béatrice (Penant : revue trimestrielle de droit africain, 2016)

La cláusula med-arb en la actualidad: mediación y arbitraje vinculados - Cuéllar Tijerina, Ervey Sergio (Universitat Pompeu Fabra, 2016)
La intención de esta investigación, es realizar un breve análisis de las ventajas y desventajas que representa, la inclusión en los contratos comerciales, de una cláusula contractual que prevea la resolución de los posibles conflictos que pudiera suscitarse entre las partes, con la interpretación o el cumplimiento del contrato, a través de un ADR, que vincule en un solo proceso a la mediación y al arbitraje (Cláusula Med-Arb). Lo anterior, se pretende verificar a la luz de las disposiciones emitidas por los principales organismos en el comercio internacional, y su perspectiva de aplicación en el Derecho Español.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Derecho civil; MARD; Mediación; Mediation; Mediação; Médiation

Enforceability of Arbitral Awards Containing Interest: A Comparative Study between Sharia Law and Positive Laws - Althabity, Mohammad M. (University of Stirling, 2016)
The dynamics of our globalised world open the way for international trade and transactions between different countries; this may lead to conflicts in laws where transactions and trade may be subject to different legal systems. One of the biggest issues in international commercial law is disputes over the charging of interest, for example with regard to late payment, interest-based loans, or compensation for damages. Interest disputes are considered to be a complex area of law and even more complex in the international field. At the international level, interest claims may be connected to many areas of commerce and thus governed by various laws, which are different from one country to another; moreover, each country has its own interest rate and such rates are changeable according to the nature of law and economics under some jurisdictions. Furthermore, the concept of interest itself is affected by influences such as religious beliefs and economic, political and cultural trends. Interest can be treated as a substantive or a procedural matter. The settlement of these disputes therefore faces difficulties. Arbitration, as a method for settlement of disputes, is characterised by special features that assist in resolving these issues; but it faces some obstructions, especially in international commercial arbitration. The practices of arbitral tribunals and national courts in this regard are different. The results of different interpretations, approaches, and theories with regard to arbitration, at the pre-arbitration, during arbitration and post-arbitration stages, may also differ widely due to the diversity of financial and legal systems such as Common Law, Civil Law and the Islamic legal system – Sharia Law – across different countries. Each legal system has a different methodology and theories, even within an individual country under one legal system, and a state within a federal system has its own laws, which may have different interpretations in this respect. The New York Convention of 1958 on enforcing foreign arbitral awards was established in favour of arbitral awards and for the purpose of unifying international rules of arbitration. This Convention provides some procedural and substantive rules for the enforcement of foreign arbitral awards, but also provides some grounds for refusal. These rules have been affected by different interpretations under different jurisdictions and legal systems, which lead to different perspectives on the matter of charging interest and settlement by arbitration. The outcome of applying the NYC under these interpretations often has the opposite of its intended effect: the rejection of foreign arbitral awards. Due to such ambiguities, courts occasionally intervene in arbitration in all its stages. The interventions of national courts occur in three stages: enforcement of the arbitration agreement, enforcement of the contract under the applicable law to the agreement, and enforcement of the foreign arbitral award. The confusion between substantive and procedural laws also creates confusion with respect to public policy, non-arbitrability and enforceability. In addition, there may be a lack of clarity on the scope of arbitration with respect to the parties’ agreement, whether or not the parties have agreed to the interest rates and periods and whether or not they have agreed to the authority of the arbitrator. These issues affect the enforceability of an arbitration agreement, the law applicable to the disputed contract, the freedom of parties, the authority of the arbitrators and the enforceability of the awarded interest. The thesis studies how arbitral awards containing interest have been interpreted across the three aforementioned legal systems under the NYC 1958 in Saudi Arabia, Egypt, the UAE, England, France, and the US and the enforceability of such awards.
Keywords: Arbitrage; Arbitral award enforcement; Arbitration; Chari'a law; Sentence arbitrale; Sharia Law

LLCs and the Private Ordering of Dispute Resolution - Molk, Peter; Winship, Verity (The Journal of Corporation Law, 2016)
An emerging question in U.S. business law is how the organizational documents of a business entity set the rules for resolving internal disputes. This practice is routine in commercial contracts, which may specify where or how disputes must be resolved. Recent use of litigation provisions in corporation charters and bylaws have sparked controversy, ultimately leading to legislative action to preserve shareholder suits from contractual waiver. Yet despite accounting for the majority of business organizations and sharing features with corporations, non-corporate business entities and their internal dispute resolution process have been largely ignored. How do these non-corporate entities set ex ante rules for resolving disputes among their constituents? This paper begins to map this uncharted area with an empirical study of the practice of limited liability companies (LLCs). We find widespread use of contract to alter the default dispute resolution practices. This study helps not only to inform the evolving statutory and judicial framework for LLC regulation, but also to predict how corporations may respond in the future to recent judicial and legislative changes.
Keywords: Arbitration; Dispute resolution; Fee shifting; Forum; LLCs; Litigation; Operating agreements

State interference through domestic courts in international commercial arbitration - Badenhorst, Casper Hendrik Jacobus (University of Johannesburg, 2016)
Keywords: Arbitrage; Arbitragem; Arbitration; International and municipal law; International commercial arbitration

Direct actions and arbitration: all at sea - Briggs, Adrian (Lloyd's Maritime and Commercial Law Quarterly, 2016)

L'arbitrage commercial international par rapport à la juridiction étatique en matière de mesures provisoires et conservatoires : étude analytique et comparative - Emara, Fehr Abdelazim (Université Laval, 2016)
Depuis le milieu du XXe siècle, l'arbitrage commercial international a connu un développement phénoménal et acquis une importance significative dans le monde des transactions commerciales internationales. Il est effectivement devenu la juridiction mondiale la plus acceptable, la plus fiable et la plus usuelle pour résoudre les différends relatifs au commerce et aux investissements internationaux. Toutefois, il a rencontré des difficultés en ce qui concerne les mesures provisoires et conservatoires ce qui explique la tendance des parties à éviter d’y avoir recours devant les arbitres, au profit des juridictions étatiques pour obtenir les mesures d’urgence dont ils avaient immédiatement besoin. L’inexistence d’un régime procédural capable de bien régir cette matière était la raison principale qui a réduit l’efficacité de l’arbitrage. Pourtant, ce fait a changé grâce aux modifications majeures qui ont été apportées à la Loi type de la CNUDCI en 2006. Cette loi a établi un régime arbitral spécifique aux mesures provisoires et conservatoires. À un stade ultérieur, les règlements modifiés récemment par les centres d’arbitrage qui agissent sur la scène internationale ont beaucoup développé ce régime en le mettant en pratique. Maintenant, en présence d’un régime arbitral particulier régissant les mesures provisoires et conservatoires, il est opportun d’en évaluer en profondeur l’efficacité par rapport à celle du régime étatique classique régissant la même matière. Voilà l’objectif de cette thèse de doctorat qui présente nombre des propositions doctrinales et normatives dans le but d’améliorer autant que possible ce régime arbitral récent.
Keywords: Acte conservatoire; Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Cours d'État; Droit comparé; Mesures provisoires

La prérogative de l'arbitre de relever un moyen d'office - Gaucher, Natalia (Aix-Marseille Université, 2016)

Arbitration and Justice Denial on Foreign Direct Investment - Hendrawan, Daniel (Indonesian Journal of International Law, 2016)
The economic growth in Indonesia is thrive. The Economic growth can not be separate of the role of investment in Indonesia. The population in Indonesia very much and also the location of the Indonesian state strategic pretty much made Indonesia enjoyed by citizens of Indonesia itself and also foreign nationals who wish to also invest in Indonesia. In Indonesia there is a domestic investment and foreign investment. In this paper will be devoted to foreign investment. Foreign investment that currently exist in Indonesia has a sizeable amount and spread from Sabang to Merauke, and also has sometimes caused the dispute. Dispute occurs either the foreign investment by government or also foreign investment with other parties outside the government well with other foreign investment, and also in the company itself. Foreign investment dispute settlement is not only done through the court owned by the government, but there are also ways of alternative dispute resolution outside the court . One of the alternative dispute resolution outside the court is Arbitration. Arbitration carried out as part of efforts to achieve settlement of the problem in terms of investment activity . Arbitration itself is set in the legislation applicable investment in Indonesia . The parties in capital investment may create a separate section in the agreement governing the settlement of disputes in the case of investments completed by Arbitration. In the event that the parties have arranged to settle the case with Arbitration, then the court is not allowed to try again or to interfere in the decision Arbitration. Arbitration is one of the solutions if justice denial occur in the settlement of foreign direct investment issue.
Keywords: Alternative; Arbitrage; Arbitragem; Arbitration; FDI; Foreign direct investment

Milletlerarası ticari tahkime ilişkin UNCITRAL model kanununda yargılama yetkisi kavramı ve tahkim mahkemesinin yargılama yetkisinin sınırları - Ki̇tapçi, Hakan (Selçuk Üniversitesi, 2016)
Keywords: Arbitration; Authority; International Arbitiation Law; Judgement; Milletlerarası Tahkim Kanunu; Tahkim; UNCITRAL Model Kanunu; UNCITRAL Model Law; Yargılama; Yetki

Developing efficient dispute resolution solutions for international commercial disputes: ways to address concerns associated with the combined use of mediation and arbitration by the same neutral - Nigmatullina, Dilyara (The University of Western Australia, 2016)
Securing fast, inexpensive and enforceable redress is vital for the development of international commerce. In a changing international commercial dispute resolution landscape, the combined use of mediation and arbitration, and particularly a combination where the same neutral acts as a mediator and an arbitrator (same neutral (arb)-med-arb), has emerged as a dispute resolution approach offering these benefits. However, to date there has been little agreement on several aspects of the combined use of processes, which the literature often explains by reference to the practitioner’s legal culture. There is a heated debate in the international dispute resolution community as to whether it is appropriate for the same neutral to conduct both mediation and arbitration. When the same neutral acts as a mediator and an arbitrator, caucuses become a primary concern. This is largely due to the danger that an arbitrator will appear to be, or actually be biased, and the risk that the process may offend the principles of due process.A review of the literature shows that the combined use of mediation and arbitration raises more questions and concerns than it offers answers and solutions. This thesis proposes remedies for this situation. The purpose of this thesis is twofold. First, to investigate ways to address concerns associated with the same neutral (arb)-med-arb, which should allow parties to benefit from time and cost efficiencies of the process and the ability to obtain an internationally enforceable result. Second, to examine whether the perception and use of the same neutral (arb)-med-arb varies depending on the practitioner’s legal culture. The research involved an analysis of legal sources complemented by a two stage empirical study conducted through questionnaire and interview.The thesis identifies three major ways to address concerns associated with the same neutral (arb)-med-arb: 1) the involvement of different neutrals in combinations, 2) procedural modifications of the same neutral (arb)-med-arb, and 3) the implementation of safeguards for using the same neutral (arb)-med-arb. It demonstrates that not all of these ways will achieve the goals of fast, inexpensive and enforceable dispute resolution. The results support the conclusion that the perception and use of the same neutral (arb)-med-arb varies throughout the world depending on the practitioner’s legal culture. This and other factors ultimately affect the choice of ways to address concerns associated with the same neutral (arb)-med-arb. Further to these significant results, the thesis argues that the same neutral (arb)-med-arb is not a ‘one-size-fits-all’ process. Other combinations discussed in the thesis require more attention from practitioners and academics.This thesis makes a substantial and original contribution to the understanding of combinations in international commercial dispute resolution in four ways. First, the empirical study is the first study to investigate specifically the use of combinations in international commercial dispute resolution. Its results shed light on the use of combinations in international commercial dispute resolution, their common triggers, the way in which the processes are combined most frequently, and the most common forms of recording the outcome of combinations. Second, the thesis synthesises existing ways of addressing concerns associated with the same neutral (arb)-med-arb in international commercial dispute resolution and groups them into the three major categories mentioned above. Third, having identified that there is scope for a more widespread use of combinations in international commercial dispute resolution, the thesis provides recommendations on how to enhance the use of combinations. Finally, the thesis highlights several areas where future research is needed.
Keywords: Arbitrage; Arbitragem; Arbitration; Combined processes; Commercial; Dispute resolution (Law); International; Legal culture; MARD; Mediación; Mediation; Mediação; Médiation; Same neutral

Due Process of Law in International Commercial Arbitration with Special Reference to Production of Documents - Zaheeruddin, Mohammed (Journal of Law and Criminal Justice, 2016)
Arbitration provides speedy mode of settlement of disputes between the parties. In the course of arbitration, the arbitration tribunal has an obligation to give a fair opportunity to the parties to present their case. The fair hearing or due process of law in arbitration requires that both parties must be treated equally and given opportunity to be heard, which include a party may request the other party for production of documents, which are relevant to the case. Hence, the international arbitration rules contained the provisions to order a party, on its own or on the request of a party, to produce the documents relevant to the outcome of the case. Unless otherwise agreed by the parties, any denial of this opportunity may be considered as a violation of due process of law, consequently a party may challenge the enforcement of the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Discovery; Due process of law; Production of document; UNCITRAL

دور المحكم في الخصومة التحكيمية - حمودي, سمية (جامعة الوادي university el-oued, 2016)
تناولت هذه الدراسة أهم عنصر من عناصر عملية التحكيم، ألا وهو دور المحكم في خصومة التحكيم، وذلك من خلال معرفة شروط وإجراءات اختاره ومركزه القانوني وسلطاته والتزاماته . و قد بدأت الدراسة بمقدمة تضمنت العناصر الرئيسية للبحث وتناولنا ف الفصل الأول التعريف بالمحكم من خلال بيان معناه وتميزه عن القاضي والخبير والمصالح والوكيل، كذلك بيان الشروط الواجب توافرها في المحكم، كما تم توضيح المركز القانوني للمحكم في خصومة التحكم وكذا بيان طرق تشكيل هيئة التحكيم. كما تناولنا سلطات المحكم، سواء كانت ناشئة عن اتفاق التحكيم، أم المخولة له بموجب القانون، وبيان الالتزامات المرمية على عاتقه أثناء مباشرته لمهمته، وكل ذلك من خلال الفصل الثاني. ومن أهم النتائج التي خلصت إليها الدراسة، هي أن المحكم يتمتع بسلطات واسعة في خصومة التحكيم، إلا أن هذه السلطات الواسعة ليست مطلقة بلا قيود، وإنما يفرض على المحكم عدة التزامات منذ قبوله مهمة التحكيم وحتى صدور الحكم الفاصل في النزاع مرورا بالتزاماته أثناء سير الاجراءات مع مراعاة احترام المبادئ الأساسية للتقاضي. Cette étude portait sur l'élément le plus important du processus d'arbitrage, à savoir le rôle d'arbitre dans l'arbitrage des différends, et grâce à la connaissance des conditions et des procédures choisies statut juridique, pouvoirs et obligations. L'étude a commencé par une introduction comprenait les principaux éléments de la recherche et nous traitée dans le premier arbitre de définition de chapitre à travers les moyens de déclaration et de le distinguer du juge et expert, des intérêts et de l'agent, ainsi que la déclaration des conditions à remplir par l'arbitre, a également clarifier le statut juridique d'un arbitre dans le contrôle des différends, ainsi qu'une description des moyens de la formation du tribunal. Comme nous approchions les autorités de l'arbitre, que ce soit en raison de la convention d'arbitrage, ou qui lui sont conférés en vertu de la loi, et la déclaration des obligations jetées sur lui-même pendant l'exécution de leur mission, et tout au long du deuxième trimestre. Parmi les résultats les plus importants de l'étude, il est que l'arbitre dispose de larges pouvoirs à l'arbitrage des différends, mais ces larges pouvoirs est pas absolue, sans restrictions, mais a imposé à l'arbitre plusieurs engagements depuis accepter la tâche d'arbitrage et jusqu'à la délivrance de l'arbitre décisif dans le conflit par ses obligations au cours de la procédure, avec en tenant compte du respect des principes de base du litige
Keywords: Arbitrage des différends; Arbitration; Arbitre; Obligations de l'arbitre; Pouvoirs de l'arbitre; Statut juridique; Tribunal arbitral; التزامات المحكم; الخصومة التحكيمية; المحكم; المركز القانوني; سلطات و; هيئة التحكيم

Online dispute resolution: The future of justice - Mania, Karolina (International Comparative Jurisprudence, 2015)
The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. The article is an in-depth study of this field, discussing online mediation and electronic arbitration, their uses and their relationships with e-commerce. The strengths and weaknesses of online dispute resolution are identified and used to help formulate de lege ferenda stipulations. The paper is divided into three parts. Part I looks at preliminary aspects of online dispute resolution (ODR), including a definition of the term and an examination of its phases of development, implementation examples and the relationship between ODR and technology. Part II is devoted to examining the two most frequent forms of ODR: online mediation and electronic arbitration. Part III is an analysis of consumer disputes arising from commercial transactions made using electronic communications. As an example of the implementation of ODR, the author emphasises the importance of new European regulations on that and alternative dispute resolution (ADR): Directive 2013/11/EU of the European Parliament and of the Council of 21 May 2013 on alternative dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Directive on consumer ADR), and Regulation (EU) No 524/2013 of the European Parliament and of the Council of 21 May 2013 on online dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Regulation on consumer ODR).
Keywords: ADR; Alternative dispute resolution; Consumer dispute; E-commerce; Electronic arbitration; ODR; Online Dispute Resolution; Online mediation

Les conflits d'intérêts en arbitrage commercial international - Castres Saint Martin, Constance (Université Paris 2, 2015)
Le conflit d'intérêts est un sujet passionnant notamment en raison de son omniprésence dans l'actualité. Approximative, l'expression empruntée au magma lexical des politiciens et juristes anglo-américains s'est récemment diffusée en France dans le monde des affaires et aussitôt reprise par le jargon médiatique pour désigner des éventuelles interférences de l'intérêt privé dans l'exercice de pouvoirs de nature privée ou publique. Il n'existe en l'état actuel du droit positif français aucune réglementation spécifique de ces « conflits d'intérêts », pas plus en droit privé qu'en droit public, alors même qu'on se préoccupe de leur prévention tandis que leur sanction relève de qualifications plus générales. Il convient donc de s'interroger sur la définition et la valeur opératoire de cette notion et le régime juridique qui pourrait lui être réservé, ce que l'on se propose d'entreprendre dans la sphère du droit privé et par préférence dans le champ de l'arbitrage commercial, particulièrement exposé aux appétits hégémoniques des droits anglo-américains. Conflict of Interests is a fascinated subject due to its pervasiveness in the economic life. This approximated expression, borrowed from the politicians and Anglo-American lawyers' jargon, has recently spread into the French business world and was taken up by the media to designate the interferences of private interest in the exercise of powers of private or public nature. In the current state of French Law, there is no specific rule governing conflicts of interests, neither in Private Law, nor in Public Law. Indeed, politicians and scholars paradoxically only focus on their prevention, whereas their sanctions fall within the scope of broader notions. The aim of this research is to lay down the definition, the operative value and the regime of conflict of interests. The scope of this research shall be, within Private Law, Commercial Arbitration Law, which is particularly exposed to the hegemony of Anglo-American laws.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitral abuses; Arbitration; Confiance légitime (droit); Confidence principle; Conflict of interests; Conflit d'intérêts; Conflits d'intérêts; Disclosure; Due process; Dérives arbitrales; Impartiality; Impartialité; Independence; Indépendance; Issue conflict; Justice arbitrale (administration); Principe de confiance; Procès équitable; Révélation; Transparence; Transparency

La médiation en santé : Contribution à une étude des conflits et des différends dans la relation de soins - Gibelin, Anne (Université de Montpellier, 2015)
La médiation peut se définir comme l’action de celui qui est médiateur et qui s’interpose entre deux ou plusieurs personnes pour résoudre un conflit ou un différend. Dans le domaine de la santé et plus particulièrement dans la relation de soins, des conflits et des différends peuvent survenir. La santé touche en effet à l’état des personnes, à leur intimité, à leur intégrité et les relations qui en découlent avec les professionnels de santé sont nécessairement empreintes d’une certaine sensibilité. C’est pourquoi ce secteur est considéré comme pourvoyeur potentiel de tensions. Il est donc intéressant d’étudier la résolution des conflits ou différends inhérents à la relation de soins, par un mode singulier et alternatif de règlement des différends : la médiation. L’étude de la nature juridique de ce processus est indispensable pour le différencier des autres modes alternatifs et exposer clairement ses forces et ses faiblesses. Ceci permettra ensuite de lui appliquer un régime juridique adéquat. En raison des manquements actuels, particulièrement au regard de l’encadrement du statut de médiateur, le constat d’un inévitable remaniement du régime de la médiation devra être effectué. Celui-ci devra impérativement allier souplesse et encadrement du mécanisme dans le but d’une efficacité optimale.
Keywords: Différends; Mediation; Médiation; Relation; Relations médecin-patient; Règlement de conflits; Santé; Soins

International Standards for Commercial Mediators - To, Christopher (University of Stirling, 2015)
This paper talks about the international standards for commercial mediators. It introduces the standards of eight different jurisdictions and afterwards, evaluates whether there should be one accrediting standard for all international commercial mediators. In the introduction chapter, the paper talks about the problems with the current legal system and then explains the growth of mediation in today’s society. By discussing the nature and practice of mediation, whether mediation should be compulsory or voluntary in light of Article 6 of the European Convention on Human Rights, rationale of the various jurisdictions covered, the paper then talks about the attributes that make a good mediator as well as the accreditation and training of mediators. From chapter two to chapter nine, the paper focuses on eight jurisdictions in which mediation is firmly enshrined within one legal culture to those that are just embarking on the concept (namely Australia, New Zealand, Indonesia, Malaysia, India, Hong Kong, California and Canada). Each chapter talks about the developments of commercial mediation, law and institutions as well as training and accreditation of mediators within their respective jurisdictions. In the concluding chapter, it discusses whether there should be one accrediting standard for international commercial mediators by exploring the advantages and disadvantages of having one accrediting standard as well as the author’s analysis and point of view on the subject.
Keywords: Commercial mediator; International standards; Mediation; Mediator; Médiateur

The Role of Arbitration Institutions in the Development of Arbitration in Africa - Onyema, Emilia (Arbitration Institutions in Africa Conference, 2015)
This conference which held at the premises of the African Union Commission, Addis Ababa on 23 July 2015 examined the functions of arbitration institutions in Africa. The conferenced discussions focused on sharing experiences by users and providers for the effective administration of arbitration references in the continent. The conference was organised by Dr Emilia Onyema of the School of Law, SOAS. KEY ARTICLES : - Regional Arbitration Institution for ECOWAS: Lessons from OHADA Common Court of Justice and Arbitration ; - The Role of Arbitration Institutions in the Development of Arbitration in Africa ; - “Africa’s Century” – The rise of International Arbitration in Africa and what it means for users of Arbitral Institutions in Africa ; - Reawakening Arbitral Institutions for Development of Arbitration in Africa ; - Opening Up International Arbitration in Africa ; - Africa as a Viable Space for Arbitration: Role of National Courts and Laws - The Role of Counsel in Promoting African Arbitral Institutions ;
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Conference

Disputes in the Digital era : the evolution of dispute resolution and the model ODR system - Lekkas, Zissis (Université Toulouse 1 Capitole, 2015)
Le sujet de la thèse est la résolution en ligne des litiges (ODR) et l'objectif de la thèse est de proposer un modèle de système ODR basé sur l'expérience du mouvement de résolution des différends. ODR n’est pas un phénomène isolé de ces derniers temps, mais en raison de l'évolution des conflits et la résolution des différends. Initialement, les différends survenus entre les parties à la proximité géographique et pour laquelle les tribunaux traditionnels sont le principal moyen de résolution. Cependant, comme les gens ont commencé à voyager de plus grandes distances et de communiquer de loin, les conflits ont évolué comme ils ont augmenté en nombre, sont devenus frontière plus complexe et de plus en plus transversale. Résolution des différends évolués en règlement des différends parallèle et alternatif (ADR) a été utilisée. Cependant, les conflits ont évolué une fois de plus quand le monde est entré dans l'ère numérique. Non seulement les conflits sont devenus encore plus transfrontalier, mais de nouveaux conflits sont apparus qui proviennent exclusivement dans le cyberespace. Afin de satisfaire aux exigences de l'ère numérique, la résolution des différends fit sortir le concept de l'ODR. ODR est née de la combinaison de l'ADR et de la technologie de l'information et de la communication (TIC) de l'ère numérique. D'autres moyens de règlement des différends ont été transférés dans le monde virtuel et ont donné naissance à la résolution des litiges en ligne. ADR et ODR sont examinés largement, et l'examen comprend leurs concepts, leur origine, les principales formes de négociation, de médiation et d'arbitrage et leurs équivalents en ligne, ainsi que leurs avantages et leurs inconvénients. La thèse illustre l'évolution des conflits et la résolution des différends de l'ère analogique, lorsque la résolution des différends était face à face, à l'ère du numérique, lorsque les différends sont réglés dans le cyberespace. Il démontre que l'ODR est une nécessité de l'ère numérique, mais aussi qu'il a le potentiel pour être un moyen révolutionnaire, efficace et réussi à résoudre les différends; d'une manière qui sera l'avenir de la résolution des différends. Sur la base de l'expérience accumulée par l'examen de l'évolution de la résolution des différends et sur ? Lla base des conclusions tirées, la thèse formule une proposition pour le système ODR. La thèse décrit le système ODR, de son processus en trois étapes et la nécessité de l'arbitrage en ligne, sur le réseau ODR, la régulation du système ODR, l'architecture technologique des fournisseurs ODR, leur financement, ainsi que les mesures nécessaires de la sensibilisation et la confiance afin que ODR remplit son plein potentiel.
Keywords: Arbitrage; Arbitragem; Arbitration; Commerce électronique; Modes électroniques de règlement des litiges; Online Dispute Resolution; Système ODR

A arbitragem em juízo - Valença Filho, Clávio de Melo (Universidade de São Paulo, 2015)
Situado no centro do sistema jurídico transnacional da lex mercatoria, o árbitro é autoridade estrangeira em relação ao juiz nacional do foro. O sistema da lex mercatoria se distingue do nacional pela sensibilidade de suas reações aos ruídos provenientes do sistema da economia, não pelo vinculo a território. O árbitro não tem foro, tem setor; fora dele, a arbitragem se adapta mal. Por impor limites à função jurisdicional do Estado-juiz, a convenção de arbitragem constitui regra de competência internacional do juiz do foro e, de competência internacional indireta do árbitro e dos juízes estrangeiros. Profere sentença inexistente o juiz nacional que atropela as regras de sua jurisdição internacional. Também não ingressam no sistema do foro as decisões proferidas por quem não se adeque às regras de jurisdição internacional indireta do foro. Isso ocorre quando a sentença arbitral ou o julgamento estrangeiro em lide cujo objeto é a própria arbitragem agridem a intensidade que o foro atribui aos efeitos negativos da competência-competência e da convenção de arbitragem. O efeito negativo da competência-competência não decorre da convenção de arbitragem, mas da proteção que o ordenamento outorga à mera aparência. Os efeitos da convenção de arbitragem dizem respeito ao mérito das lides, o negativo e o positivo. Aquele, como o negativo da competência-competência, ostenta natureza de direito público subjetivo. Este, de direito privado subjetivo. Todos constituem direito subjetivo em sentido técnico, na medida em que permitem provocar o Estado-juiz com o fito de apoiar a instauração da instância ou assegurar o afastamento do próprio Estado-juiz. O paralelismo processual tem origens distintas segundo ocorra entre autoridades vinculadas ao mesmo sistema ou a sistemas distintos. Na primeira hipótese, decorre de error in judicando; na segunda, é consequência natural da ausência de harmonia entre os sistemas. Entre árbitro e juiz, não se resolve com remédios concebidos para o conflito de competências, como a litispendência ou o incidente constitucional perante o STJ. Só uma estrutura convencional de acoplamento entre sistemas permitiria a harmonização. Já o efeito negativo da convenção de arbitragem pode ser mitigado em função de risco de denegação de justiça, para devolver ao Estado-juiz a jurisdição de urgência ou a necessária ao julgamento de pretensões do devedor em dificuldades. A abertura da falência não interfere na capacidade do credor ou na natureza de seus bens ou direitos, não suspende a tramitação da arbitragem e não impede a instauração de novas instâncias. É válida a convenção de arbitragem estipulada após a falência e a massa tem o direito de participar da arbitragem, junto com o devedor. The transnational legal system of lex mercatoria is not linked to a given territory. Its differentiation from the civil justice system is based upon its capacity to react to the needs of the economy. The fact that the arbitrator is positioned in the center of the lex mercatoria system makes the arbitrator foreign to the courts and its legal system. By imposing limits upon the jurisdictional State function, the arbitration agreement and its regulation serves as an international jurisdiction rule for the forum court. It also works as an indirect international jurisdiction rule through which the national court inspects the jurisdiction of an arbitrator or a given foreign court. National courts decisions that are rendered in disregard of international jurisdiction rules are non-existent. Foreign decisions that are incompatible with indirect international jurisdiction rules must be set aside by the forum courts. This is the case when arbitral awards and foreign judgments related to arbitration are disrespectful to the forum criterions binding the negative effect of the competence-competence and to the negative effect of the arbitration agreement. The negative effect of competence-competence is not a consequence of the agreement to arbitrate, but of the protection that the legal system gives to its mere appearance. The effects of the arbitration agreement concern the merits of the disputes, the negative and the positive. The former, as well as the negative effect of the competence-competence principle, are in nature of subjective public law. The latter is of the nature of subjective private law. All constitute subjective rights in the technical sense, in the way in which they allow the court system to support the commencement of proceedings or to ensure the removal of the national courts. Procedural parallelism has different origins depending upon whether it occurs among arbitrator and courts belonging to the same legal system of the court deciding the conflict or to a different one. In the first hypothesis, it originates from error in judicando; in the second, it is a natural consequence of the lack of harmony between the systems. Between arbitrator and judge, such lack of harmony cannot be resolved through the remedies created to address jurisdictional conflict, such as lis pendens or the constitutional incident before Brazils STJ. Only by coupling different legal systems through conventional structure would harmonization arise. The negative effect of the arbitration agreement is mitigated by conferring upon courts jurisdiction for the grant of interim and provisional measures based on the risk of denial of justice. By its turn, a bankruptcy filing does not interfere with the creditors capacity nor with the nature of its assets or rights, and it does not suspend the arbitration proceeding or the commencement of new proceedings. The agreement to arbitrate after the initiation of bankruptcy proceedings is valid and the estate-in-bankruptcy may participate in the arbitration along with the debtor.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Arbitre; Argentina; Bankruptcy; Brasil; Civil Procedure; Conflict of jurisdictions; Direito comparado; Estados Unidos; Falência; França; Insolvency; Judge; Lex mercatória; Processo civil; Urgent measures

Economic and Empirical Analysis of Contractual Dispute Resolution - Miller, Samuel Mark (Vanderbilt University, 2015)
This dissertation uses Python-based programming to retrieve and analyze a sample of approximately 400,000 material contracts that companies filed with the Securities and Exchange Commission between 2001 and 2013, focusing on the dispute resolution mechanisms specified therein. The first chapter considers the effectiveness of two state-level efforts to attract dispute resolution business, examining how specialized “business courts” and the Revised Uniform Arbitration Act affected arbitration and choice-of-forum clause use in these material contracts. The second chapter examines whether and how companies and executives “customized” their arbitration clauses in response to Internal Revenue Code Section 409A, which increased both the likelihood and the complexity of potential disputes between these parties. The third chapter considers how companies and executives responded when the Supreme Court overturned the Ninth Circuit’s anomalous refusal to enforce employment-related arbitration clauses. Each chapter finds that contracting parties adjusted their dispute resolution provisions in response to the policy change(s) at issue – suggesting that for the sophisticated parties in my dataset, these provisions receive careful thought and are not mere “boilerplate.”
Keywords: Arbitrage; Arbitragem; Arbitration; Contracts; Dispute resolution; Econometrics

Arguments in favour of reconceptualising the fair and equitable treatment (FET) standard in international investment arbitration : developing countries in context - Islam, Rumana (University of Warwick, 2015)
The Fair and Equitable Treatment (FET) standard is the most important and, because of its flexible nature and its status as a ‘catch-all’ provision, most controversial investment protection standard in international investment treaties. The standard imposes the most far-reaching obligation of any aspect of such treaties. This thesis’ core contention is that the current investment tribunals’ interpretation of the FET standard prioritises the interests of foreign investors and neglects the perspectives of host developing countries. Therefore there is a pressing need to reconceptualise the interpretation of the FET standard. In service to depicting the perspectives of host developing countries, this thesis advances an understanding of classifications such as ‘developing’ and ‘developed’ that reflects the issues and challenges that these countries face in the investment dispute context, such as their lack of resources, administrative capacity, technology, and infrastructure, as much as the economic and social level of development international organisations generally emphasise in their classifications. It addresses socio-political circumstances such as political instability, social unrest, conflict and its aftermath, social and political transition, and economic crises and their impact on host developing countries in the investment dispute context. Through a detailed study of the approaches they have taken to such issues in their interpretation of the breach of FET standard in disputes involving host developing countries, it shows that current investment tribunals have taken inconsistent and inadequate approaches to the issues host developing countries face. It argues that a reconceptualised interpretation of the FET standard which acknowledges the developmental issues and challenges this thesis has identified would accommodate the needs of the host developing countries while continuing to give reasonable protections to foreign investors and therefore serve the needs of the system as a whole.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Developing countries; Dispute resolution (Law); Equity; Foreign investment; Free trade agreemtment; International business enterprises; Investments; Unfair competition

Partes e terceiros na arbitragem - Costa, Guilherme Recena (Universidade de São Paulo, 2015)
A tese discute o problema dos terceiros na arbitragem. Ela distingue os planos substantivo (contratual) e processual (jurisdicional) da arbitragem e, portanto, o status de parte e terceiro com relação, respectivamente, à convenção de arbitragem e ao processo arbitral. Depois de desenvolver as premissas teóricas na Parte 1, a Parte 2 expõe as teorias contratuais e societárias por meio das quais um não-signatário pode ficar vinculado à convenção de arbitragem, com destaque para a extensão a todos os acionistas da companhia da cláusula compromissória estatutária, bem como para a aplicação do princípio da boa-fé objetiva (teoria dos atos próprios, estoppel) para impedir com que determinados signatários burlem a convenção de arbitragem ao incluir terceiros no polo passivo da demanda ou, ainda, para impor a arbitragem a não-signatários que derivaram um benefício do contrato inter alios. Na Parte III, a atenção volta-se para o processo e a sentença arbitral. Expõe-se uma teoria dos efeitos da sentença, buscando-se explicar a sua potencial eficácia ultra partes com base: a) na necessidade de realizar o direito da contraparte à tutela jurisdicional (adquirente do direito litigioso, sucessores post rem judicatam); e b) na identificação de nexos de prejudicialidade-dependência permanente entre as relações jurídicas no plano do direito material (terceiro titular de situação dependente). Refutam-se, em passo seguinte, teorias que preconizam o valor absoluto da sentença. Oferece-se, como núcleo da tese, uma reconstrução dogmática das modalidades de intervenção de terceiro, buscando adaptá-las à arbitragem para alcançar, em cada situação, um justo equilíbrio entre as expectativas contratuais das partes originárias e a natureza privada da arbitragem, de um lado, e os efeitos da sentença perante terceiros, de outro. Conclui-se que, em alguns casos, legitima-se o terceiro a intervir voluntariamente, mesmo contra ou independentemente da vontade das partes, se ele estiver sujeito aos efeitos da sentença. Em hipótese excepcionalíssimas, ademais, a parte pode sujeitar um terceiro aos efeitos de intervenção, provocando a sua assistência no processo arbitral. The thesis addresses the problems of third parties in arbitration. It distinguishes the substantive (contractual) and procedural dimensions of arbitration and, hence, the status of parties and third parties in connection with, respectively, the arbitration agreement and the arbitral proceedings. After spelling out theoretical premises in Part 1, Part 2 covers the contractual and corporate theories by which a non-signatory may be bound by the arbitration agreement, highlighting the extension to all shareholders of the agreement in the corporate bylaws, as well as the application of the equitable doctrine of estoppel to bar certain signatories from avoiding the arbitration agreement by including third parties as defendants or even to impose arbitration onto non-signatories who derived a benefit from the contract inter alios. In Part III, my attention turns to the proceedings and the arbitral award. I set out a doctrine of the effects of judgments, seeking to explain their potential effects on third parties based: a) on the prevailing need to preserve the counterpartys right to a binding declaration on its asserted claims (acquirers, successors post rem judicatam); b) the identification of substantive ties between legal relationships that make the third parties rights permanently dependent on the situation between the parties. I then refute theories ascribing absolute value to the award vis-à-vis third parties. As the core of the thesis, I offer a doctrinal reconstruction of third party interventions, seeking to adapt them to arbitration in order to achieve, in each situation, a fair balance between the contractual expectations of the original parties and the private nature of arbitration, in one hand, and the effects of the award on third parties, on the other. I conclude that a third party should be allowed to intervene, albeit against the will of the parties, if it is subject to the concrete effects of the arbitral award. In exceptional situations, moreover, a party may vouch in a third party, who will then be bound by the determinations of factual and legal issues made in the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Coisa julgada; Direito processual civil; Effects of arbitral awards; Non-signatories; Third parties; Third party intervention; Tierces parties

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

Milletlerarası ticari tahkimde hakemlerin bağımsızlığı ve tarafsızlığı - Kayali, Di̇dem (Ankara Üniversitesi, 2015)
Milletlerarası ticarî sözleşmelerden kaynaklanan uyuşmazlıklar söz konusu olduğunda akla ilk gelen çözüm yöntemi tahkimdir. Zira milletlerarası ticarî tahkimin devlet yargılamasına göre önemli avantajları bulunmakta, hakemlerin bağımsızlığı ve tarafsızlığı ise bu avantajların en önemlilerinden biri olarak karşımıza çıkmaktadır. Bu çerçevede, tahkim süreci başlarken hakemlerin bağımsız ve tarafsız olmaları ile süreç tamamlanana kadar bu şekilde kalmaları gerektiği hususu milletlerarası ticarî tahkimin en temel ilkesi olarak genel kabul görmüş; millî kanunlarda, milletlerarası metinlerde ve milletlerarası tahkim kurumlarının düzenlemelerinde doğrudan ya da dolaylı bir şekilde yerini almıştır. Bu çalışmada da bağımsızlık ve tarafsızlık kavramlarından ne anlaşılması gerektiği, bu kavramların uygulamada nasıl yorumlandığı, tahkim yargılamasındaki önemi ve nasıl korunduğu, yukarıda bahsedilen düzenlemeler ile millî mahkemeler ve milletlerarası tahkim kurumlarının kararları ışığında incelenmiştir. When disputes emerging from international commercial contracts are in question, arbitration is the first resolution method that comes to mind. This is because international commercial arbitration has significant advantages compared to the state jurisdiction where impartiality and independence of arbitrators is considered to be one of the most important ones of those advantages. In this framework, the necessity that arbitrators ought to be impartial and independent from the very start till the end of the arbitration process has gained general acceptance as the basic principle of international commercial arbitration and directly or indirectly has taken its place in national laws, international texts and regulations of international arbitration institutions. In this study, the meaning of independence and impartiality, how they are interpreted in practice, the importance of these concepts in international commercial arbitration and how they are protected are examined in the framework of above mentioned regulations and decisions of national courts and international arbitration institutions.
Keywords: Arbitrage; Arbitration; Arbitrators; Arbitre; Bağımsızlık; Hakemler; Impartiality; Impartialité; Independence; International Arbitiation Law; International Trade; International disputes; Milletlerarası Tahkim Kanunu; Tahkim; Tarafsızlık; Uluslararası ticaret; Uluslararası uyuşmazlıklar

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Convention on the Recognition and Enforcement of Foreign Arbitral Awards (New York, 1958) - UNCITRAL (United Nations, 2015)

L'Acte Uniforme OHADA relatif à l'Arbitrage (AUA) à l'épreuve des standards transnationaux de la justice arbitrale : approche comparée de droit international privé - Sossou, Cassius Jean (Université de Genève, 2014)
Après plus de deux décennies d'expérimentation, le moment est venu pour l'Organisation pour l'Harmonisation en Afrique du droit des Affaires ou OHADA de marquer une pause et de récapituler l'application de ses valeurs normatives aux différents domaines relevant du champ matériel d'application du Traité ayant fondé l'organisation. L'intérêt et l'utilité d'un tel bilan passent, entre autres, par la relecture de sa norme juridique sur l'arbitrage ad hoc qu'est l'Acte Uniforme OHADA relatif à l'Arbitrage (AUA). Ce bilan doit pouvoir se faire non pas au regard de ce qui a été dit et analysé. Il s'impose plutôt d'examiner la perspective de ce qui lui reste d'exceptionnel et d'inédit. Sur ces aspects inédits, il manque une analyse comparée au plan du droit international, maillon manquant des différentes approches abordées. C'est à cet exercice intellectuel que s'est livrée notre étude, procédant à la relecture à l'aune des standards transnationaux de la justice arbitrale par le prisme d'autres normes sur l'arbitrage international, qu'elles soient d'origine étatique ou conventionnelle, de la pratique internationale et dans une certaine mesure de la jurisprudence.
Keywords: Arbitrage; Arbitrage (droit international privé); Arbitrage international; Arbitragem; Arbitration; Convention d'arbitrage; Droit international privé; International; Juridiction arbitrale; Justice arbitrale; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; Procédure arbitrale; Schiedsentscheid; Schiedsgericht; Schiedsgerichtsbarkeit; Schiedsrichterliches Verfahren; Schiedsvereinbarung; Sentence arbitrale; Standards transnationaux; Tribunal arbitral

Les procédures de règlement de la double imposition résultant de la correction des prix de transfert entre entreprises associées - Hublot, Marie-Laure (Université Paris 2, 2014)
Avec l’accroissement des échanges transfrontaliers entre entreprises associées et des moyens de contrôles des transactions internationales par les administrations fiscales, les risques de différends en matière de prix de transfert augmentent nécessairement. Si ces conflits ne sont pas résolus, ils peuvent entraîner des doubles impositions, principalement économiques, et constituer des obstacles pour la libre circulation des biens et des services dans une économie globalisée. Les contribuables et les Etats ont donc besoin de procédures efficaces pour résoudre ces situations, unanimement dénoncées par les organisations internationales et les contribuables. Or les procédures actuelles ne sont pas totalement satisfaisantes. La Commission européenne, puis l’O.C.D.E ont récemment mené des travaux d’envergure visant à en améliorer les mécanismes. Le règlement de la double imposition en matière de prix de transfert est incontestablement un sujet d’actualité. Ces travaux invitent à une analyse critique de l’ensemble des mécanismes internationaux de règlement de la double imposition résultant de la correction des prix de transfert. Ces procédures sont étudiées, les causes de dysfonctionnement recherchées et des mesures d’amélioration sont proposées, notamment à la lumière des récents travaux des organisations internationales. La première partie est consacrée à la procédure amiable dans le cadre des conventions fiscales bilatérales. L’analyse menée suit une approche chronologique des étapes de la procédure, depuis son ouverture jusqu’à la mise en oeuvre de l’accord amiable. La seconde partie traite des voies nouvelles de règlement des doubles impositions que constituent la médiation, la conciliation et l’arbitrage en matière fiscale. Une large place est consacrée à l’arbitrage qui est analysé tant sur le plan conventionnel, puisqu’il a été récemment intégré dans les conventions modèles O.C.D.E. et O.N.U., que dans le cadre de la convention européenne d’arbitrage. Cette étude fait largement référence à l’approche de l’O.C.D.E. et des principaux Etats partenaires de la France. Néanmoins, il ne s’agit pas là d’un exercice de droit comparé mais seulement d’une mise en exergue d’autres pratiques pour servir le propos. With increasing cross-border trade between associated enterprises and means of control of international transactions by the tax authorities, the risk of disputes over transfer pricing necessarily increase. If these conflicts are not resolved, they can lead to double taxation, mainly of economic nature, and constitute obstacles to the free movement of goods and services in a globalised economy. Taxpayers and States therefore need effective procedures to resolve these situations, unanimously denounced by international organizations and taxpayers. However, current procedures are not entirely satisfactory. The European Commission and the O.E.C.D. have recently completed extensive work to improve the mechanisms. Dispute resolution in transfer pricing is certainly a hot topic. A critical analysis of all international settlement mechanisms of double taxation arising from transfer pricing adjustments is conducted. These procedures are examined, the causes of dysfunction sought and improvement measures are proposed, particularly in light of recent work of international organizations. The first part is devoted to the mutual agreement procedure under bilateral double tax treaties. The analysis is carried out following a chronological approach of the stages of the procedure, from its opening till the implementation of the mutual agreement. The second part deals with the new ways of resolving transfer pricing double taxation that are mediation, conciliation and arbitration in tax matters. Emphasis is on arbitration that is analysed both in conventional terms, as it has recently been integrated into the O.E.C.D. and U.N. model conventions, and as part of the European arbitration convention. This work makes extensive reference to the O.E.C.D and France key partners’ approaches. Nevertheless, it is not a work of comparative law but only examples to illustrate other practices
Keywords: Ajustement corrélatif; Arbitrage; Arbitrage commercial international; Arbitration; Conciliation; Double imposition; Droit international privé; Entreprises associées; Entreprises communes; Impôt; MARD; Mediación; Mediation; Mediação; Médiation; OCDE; Prix de cession interne; Prix de transfert; Procédure amiable; Procédure d'arbitrage

Alle origini della mediazione - Donati, Viola (Università di Pisa, 2014)
L’esigenza di alleggerire il carico dei tribunali mediante forme di soluzione diverse e alternative al processo giurisdizionale trae le sue origini da esperienze culturali remote: l’arte della composizione del conflitto rappresenta un'attività di cui l’uomo si è fin da subito dovuto occupare, per lo meno dal momento in cui ha cominciato a vivere all’interno di una comunità, proprio perché si tratta di un’attività che sfiora tutti gli aspetti della vita sociale. La mediazione ha origini antichissime, infatti la necessità di sviluppare nei secoli procedure alle quali ricorrere per garantire un'ordinata convivenza e armonia sociale risale già all'antica Roma del V secolo A.C.: la prima delle XII Tavole (il più antico diritto scritto dell’antichità romana), richiama il tentativo di compromesso da esperirsi davanti al pretore con cui le parti in lite trovano un accordo sull’oggetto del contendere, nel qual caso il giudice è tenuto a consacrarlo con l’emanazione della sentenza mentre in caso di mancato raggiungimento di un accordo allora si sarebbero adite le vie giudiziali instaurando il processo. Le origini della mediazione trovano fondamento in tempi antichi anche in Paesi dell’estremo oriente ed in particolare in Cina dove la mediazione fu lo strumento principale nella risoluzione delle dispute: Confucio sosteneva che il modo migliore per dirimere una disputa fosse la persuasione morale e il raggiungimento di un accordo, piuttosto che la coercizione del Sovrano. L’idea stessa di “compromesso” è profondamente radicata nella cultura cinese, infatti non tener in alcun conto gli interessi dell’altra parte è considerato particolarmente deplorevole sul piano etico-giuridico ed il pensiero confuciano è promotore della mediazione, tanto che l’istituto continua tuttora ad essere praticato nella Repubblica Popolare Cinese. In tempi più recenti, dopo l’unificazione del Regno d’Italia e la conseguente stesura del codice di procedura civile del 1865, il legislatore ha dedicato ampio spazio alla composizione bonaria delle controversie, disciplinando la conciliazione nel titolo preliminare all'art.1, dando vita così alla figura professionale del giudice conciliatore: caratteristiche essenziali del procedimento consistevano nella compresenza della funzione conciliativa con quella giurisdizionale nel giudice conciliatore, la municipalità del giudice stesso e infine la completa assenza di formalità (il rito si svolgeva verbalmente) per consentire a tutti un facile accesso alla procedura. Se invece apriamo il Codice di procedura vigente, per trovare un accenno alla conciliazione bisogna aspettare l'art. 320, e questa sfiducia a cui è andata in contro la figura del giudice conciliatore è arrivata fino ai nostri giorni. Negli USA la mediazione fu introdotta come sistema volontario (nelle controversie sindacali tra le compagnie ferroviarie e i loro dipendenti) nel 1887, con la legge sul commercio tra gli Stati (Intestate Commerce Act), e a partire dalla fine degli anni ’60 trovò un applicazione sempre maggiore. Ma la svolta fondamentale si ebbe nel 1998, in occasione della modifica del Titolo 28° della Carta dei Diritti e nell'Alternative Dispute Resolution Act, che consacrarono il successo della cultura alternativa della gestione del conflitto nella società americana. Oggi il ricorso agli A.D.R. ha portato ad una riduzione del contenzioso giudiziario di quasi il 90%. Visto l’esito positivo avutosi oltreoceano, nell’aprile del 2002 la Commissione Europea ha presentato un Libro Verde relativo ai modi alternativi di risoluzione delle controversie in materia civile e commerciale per promuovere l’utilizzo della mediazione, ed in seguito alla Direttiva n. 2008/52/CE il governo italiano ha emanato il D.lgs. 28/2010 al fine di coordinare le disposizioni vigenti in materia di mediazione e conciliazione in ambito civile e commerciale, solo che appena due anni dopo, il 6 dicembre 2012, la Corte costituzionale ha dichiarato l'illegittimità del decreto per eccesso di delega legislativa, così che il governo Letta ha cercato di disciplinare nuovamente l'istituto con la Legge n.98/2013, sebbene stavolta la mediazione sia stata prevista come temporanea perché contemplata come obbligatoria per i soli quattro anni successivi alla sua entrata in vigore, a metà dei quali il ministero di giustizia avvierà un monitoraggio per valutare se la sperimentazione della procedura di mediazione ha funzionato. Speriamo che intanto la “cultura della mediazione” cominci a diffondersi anche in Italia.
Keywords: ADR; Conciliation; Conciliazione; MARC; MARD; Mediación; Mediation; Mediazione; Mediação; Médiation

Arbitration in administrative contracts : comparative law perspective - Lin, Ching-Lang (Institut d'études politiques, 2014)
Il a été longuement discuté de savoir si le système d'arbitrage est applicable pour régler les litiges administratifs qui concernent certains contrats administratifs ou d’autres sans rapport avec le contrat administratif. Dans cette thèse, les trois questions spécifiques sont analysées tour à tour : (1) Est-il possible pour un arbitre ou un tribunal arbitral de trancher des questions relevant du droit administratif? (2) Y a-t-il, ou devrait-il y avoir, des limitations à l'autorité des arbitres et des tribunaux arbitraux? (3) Enfin, après la délivrance d'une sentence arbitrale, quel rôle devrait jouer l'État dans la phase de contrôle judiciaire? La première question concerne l'arbitrabilité et a été discutée dans la première partie (FIRST PART: ARBITRABILITY). La deuxième question a été discutée dans la deuxième partie (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Enfin, sur la dernière question a fait l’objet d’une troisième partie (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). Dans cette thèse, nous avons comparé les systèmes de quatre pays (Canada, Chine, France, Taïwan). En conclusion, nous pouvons donc conclure que l’évolution de la conception du contrat administratif implique de nombreux aspects, y compris les aspects juridiques, économiques, politiques et même culturels. Le développement de la fonction de contentieux administratif, comme ‘’subjectivement orienté" ou "objectivement orienté" aura une incidence sur l'acceptation de l'arbitrage en matière administrative. Dans l'ensemble, l'arbitrage sera plus acceptable dans les systèmes dont la fonction est plus ‘’subjectivement orientée" que dans ceux dont la fonction est "objectivement orientée". While arbitration has traditionally been considered as a means to resolve private disputes, its role in disputes involving administrative contracts is a crucial question in administrative law. In brief, the three specific questions are (1) Can arbitrators or arbitral tribunals decide issues involving administrative law? and (2) Is there, or should there be, any limitation on the authority of arbitrators or arbitral tribunals? (3) Moreover, after the issue of an arbitration award, what role should the State play in the judicial review phase? The first question, the issue of arbitrability, is discussed in part 1 (FIRST PART: ARBITRABILITY). The second question will be discussed in part 2 (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Finally, on the question of what happens after the arbitration award, we will discuss judicial review in part 3 (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). We compare legal systems between the four countries: in France, in Canada, in China and in Taiwan. We believe that an administrative contract, at least in its function and conception, is gradually becoming different from a private contract. Innovation with respect to administrative contracts will also reflect the concentration and function of the administrative litigation systems in each country. In addition, the “objective” or “subjective” function of administrative litigation will also affect the degree of arbitrability, as well as arbitration procedures. Taken together, arbitration will be more acceptable in systems whose function is more “subjectively oriented” than in those whose function is “objectively oriented". Finally, “the arbitration of administrative matters” traditionally has been an important question in administrative and arbitration law. In the future, we will continue to see it shine in the doctrine and jurisprudence of both the administrative and arbitration law fields.
Keywords: Administrative litigation system; Arbitrability; Arbitrabilité; Arbitrage; Arbitragem; Arbitration; Arbitration award; Contentieux administratif; Contrats administratifs (exécution); Judicial review; Litige; Légalité objective; Objective and subjective function; Prerogative of administrations in contracts; Sentence arbitrale (contestation); Études comparatives

Imparcialidade dos árbitros - Elias, Carlos Eduardo Stefen (Universidade de São Paulo, 2014)
O presente estudo tem como objetivo superar as diversas noções genéricas a respeito da imparcialidade do árbitro e assim atribuir-lhe um conceito próprio, estabelecido a partir do reconhecimento da vital importância do exercício da influência das partes na relação jurídica processual. O estudo parte da premissa de que todas as experiências pretéritas do árbitro (como as de qualquer indivíduo) constituem condição necessária para que este forme pré-conceitos e assim conheça e decida um conflito e que, por isso, tais experiências e conceitos pretéritos sempre existem e sempre influenciam o julgador. Também é premissa de análise o ambiente institucional em que a arbitragem se desenvolve e no qual os profissionais buscam auferir capital simbólico que lhes possibilite êxito nas nomeações para a função de árbitro. Essas premissas impedem que se aprove a noção genérica da imparcialidade como equidistância, ausência de interesse próprio na solução do litígio ou ausência de outras influências no convencimento do árbitro além dos argumentos lançados pelas partes no litígio, e impõem o reconhecimento de um conteúdo apoiado na inexistência de barreira à influência que os argumentos das partes exercerão na decisão do árbitro (a despeito, portanto, de quaisquer outras influências às quais o julgador como todo indivíduo está sujeito). A identificação de um conteúdo para a imparcialidade é, todavia, insuficiente para a solução de problemas práticos, razão pela qual o presente estudo sugere sua operacionalização por norma concreta extraída de regras vinculantes que imponham um comportamento (art. 14, caput, da Lei de Arbitragem brasileira) ou um estado de coisas (art. 13, § 6º da Lei de Arbitragem brasileira) que atenda a certas premissas de estrutura e de conteúdo. As premissas de estrutura têm como finalidade garantir a coerência e coesão sistemáticas da norma concreta, ao passo que as premissas de conteúdo (extraídas de casos reais) buscam a coerência interna da norma, ou seja, a coerência entre o juízo hipotético-normativo e o juízo sobre o evento fático subjacente. Essas premissas são examinadas à luz do ambiente institucional no qual a arbitragem se desenvolve, caracterizado principalmente pela interdependência e contínuo contato entre profissionais, a constante troca de papéis a que tais profissionais se sujeitam (ora como árbitros, ora como advogados) e a assimetria de informação. Propostos um conteúdo e um método de operacionalizá-lo para a solução de casos concretos, o presente estudo procura desatrelar a imparcialidade e seus efeitos da noção geral de independência do árbitro, sem apelar para a imprecisa dicotomia subjetividade-objetividade. Reconhece, ainda, que do árbitro são demandadas posturas diferentes daquelas preconizadas aos juízes, razão pela qual a aplicação de regras equiparativas (tal como o art. 14, caput, da Lei de Arbitragem brasileira), além de não esgotar todas as hipóteses de ataque à imparcialidade, deve ser precedida de diversas adaptações. Reconhece, também, o sentido e o alcance do binômio ciência-aceitação na prática arbitral. Por fim, o estudo trata da diversa natureza entre o dever de revelação e a imparcialidade impostos ao árbitro, de cujas violações derivam consequências também distintas. The present study aims to overcome several general notions concerning the impartiality of the arbitrator and thus gives it a proper concept, drawn from the recognition of the vital importance of parties to exercise influence on the procedural legal relationship. The study assumes that all past experiences of the adjudicator (as any individual) constitute a necessary condition for him to create pre-conceptions and so understand and decide a conflict - and that therefore these experiences and past concepts always influence the adjudicator. The institutional environment in which the arbitration is developed and in which practitioners seek to derive symbolic capital that enables them to succeed in the nominations for the role of arbitrator is also a premise of analysis. This premise prevents from approving the generic notion of impartiality as "equidistance", "the absence of self-interest in the outcome of the case" or "the absence of other influences in the convincing process of the adjudicator beyond the arguments submitted by the parties in dispute", and requires the recognition of content based on the "absence of barriers to the influence that the arguments of the parties shall exercise on the arbitrator's decision" (regardless of any other influences to which the judge as any individual is exposed). Identifying content for impartiality is, however, insufficient for the solution of actual problems, and due to that, the study suggests its operation by a norm extracted from binding rules imposing conduct (art. 14, caput of Brazilian Arbitration Law) or a state of affairs (art. 13, § 6 of the Brazilian Arbitration Law) that meets certain premise of structure and content. The premise of structure is designed to provide systematic consistency and cohesion of the norm, and the premise of content (drawn from actual cases) seeks internal consistency of the standard, i.e., the consistency between the description of the event anticipated in the norm and the description of the underlying factual event. This premise is examined in the light of the institutional environment in which the arbitration is developed, mainly characterized by interdependence and continuous contact between professionals, the constant exchange of roles among such professionals (either as arbitrators or as lawyers) and information asymmetry. Proposed both a content and a method to operationalize it for the solution of actual cases, this study seeks to release fairness and its effects from the general notion of independence of the arbitrator, without resorting to imprecise objectivity-subjectivity dichotomy. It also recognizes that the institutional environment requires postures from the arbitrators that differ substantially from those required from judges; due to this reason, the application of rules that apparently prescribe the same standards or behaviors for both (such as art. 14, caput, the Brazilian Arbitration Law) does not fill all the hypothesis capable of menacing the impartiality and must be preceded by various adaptations. It also recognizes the meaning and scope of the binomial information-acceptance in arbitral practice. Finally, the study addresses the diverse nature of the duty of disclosure and impartiality imposed on the arbitrator, whose respective violations also imply different consequences.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Arbitre; Civil Procedure; Due process; Impartiality; Impartialité

L’internationalisation du droit public des affaires face à l'arbitrage international : approche comparée en droit franco-maghrébin - Baisset, Didier (Annales de l’Université d’Alger, 2014)
Indiscutablement la sphère du droit public des affaires se déploie aujourd'hui dans un espace mondialisé, où les rapports entre les opérateurs se nouent en des termes qui différent radicalement de ceux qui posèrent les premiers linéaments de la matière au début du XXe siècle. Cela est en réalité lié aux tendances de fond qui touchent le monde contemporain. C'est donc dans un contexte profondément modifié par la globalisation, que les relations d'échanges internationaux et les litiges auxquels elles peuvent donner lieu s'envisagent désormais. On assiste ainsi, depuis déjà plusieurs décennies, à l’émergence d’un véritable droit public international des affaires. A cet endroit, le cas des marchés publics et des partenariats public-privé internationaux est particulièrement révélateur des mutations profondes qui taraudent la matière au niveau international. En effet, l'internationalisation des échanges économiques s'inscrit dans une réalité qui modifie en profondeur l'organisation des acteurs économiques et opère une vaste mutation des modalités d'intervention de la puissance publique; elle se fait maintenant dans un champ économique à l'échelle supra-nationale.

La participation à l'arbitrage des personnes morales de droit public : L’exemple de l’OHADA - Fénéon, Alain (Annales de l’Université d’Alger, 2014)
Dans beaucoup de législations nationales sur l’arbitrage, le principe de la non-arbitrabilité des litiges impliquant les personnes morales de droit public, en particulier l’Etat et les collectivités territoriales, est clairement posé, et ce depuis longtemps. Cette position s’explique aisément dans le système juridique français comme dans ceux qui s’en inspirent. La distinction entre la justice des particuliers et celle de l’administration, c’est à-dire de l’Etat, y est fermement établie.

Arbitrage en droit, arbitrage en équité : perspectives historiques - Juhel, Christophe (Annales de l’Université d’Alger, 2014)
L’expression « modes alternatifs de règlement des conflits » en vogue depuis quelques années et reprise dans l’intitulé de ce colloque est trompeuse. Elle procède d’une vision ethno-centrée moderne et plus spécifiquement occidentale et continentale du règlement des conflits. En effet, le qualificatif « alternatif » est employé par référence au mode de règlement des conflits actuellement privilégié par les sociétés modernes, notamment de la famille romano-germanique: la justice étatique. Or, historiquement, les sociétés traditionnelles les plus anciennes ne connaissaient pas de justice publique mais seulement des modes traditionnels et privés de résolution des litiges pacifiques comme la médiation, la conciliation et l’arbitrage, c’est-à-dire ceux que nous désignons « modes alternatifs de règlement des conflits », ou non pacifiques comme la vengeance privée.

Assessment Report of Arbitration Centres in Côte D’ivoire, Egypt and Mauritius - ORPF (African Development Bank, 2014)

Étude des règles d'indemnisation du préjudice dans l'arbitrage international : vers une indemnisation adéquate du préjudice - Mohamed Gamaleldin, Hossam (Université Paris 1, 2014)
Le recours à l'arbitrage par les opérateurs du commerce international a une finalité très importante, qui est celle de l'indemnisation appropriée et efficiente du préjudice. En vue d'évaluer celle-ci, notre étude adopte une recherche juridique détaillée en matière de réparation pour aboutir à un résultat satisfaisant concernant le principe le plus adapté en tant que cadre commun de l'opération d'évaluation de l'indemnisation du préjudice par les arbitres internationaux, en mettant notamment la lumière sur l'arbitrage CIRDI et CCI. À cette fin, il était nécessaire de suivre une analyse juridique tant sur les règles fondamentales que contingentes de l'indemnisation dans le souci d'avoir une perspective entière du processus de l'évaluation du quantum du préjudice. Un passage transversal était ainsi inéluctable sur les règles juridiques relatives à la réparation en droit privé français ainsi qu'en système juridique de Common Law. Au demeurant, un examen sur la codification de ces règles a été suivi dans le cadre des instruments internationaux de droit uniforme. Toutes ces réglementations ont inspiré le droit de l'arbitrage et ont servi comme des sources de celui-ci en matière de la réparation. Ces développements nous ont conduits à percevoir que l'indemnisation doit être adéquate en prenant en compte non seulement les préjudices subis, conformément au principe général de l'indemnisation intégrale, mais aussi tous les intérêts lésés. Sachant que certains préjudices ne sont pas mathématiquement évaluables, une indemnisation arbitraire s'impose dans ce cas. Un nouveau concept d' « indemnisation adéquate» du préjudice pourrait alors dans l'avenir s'imposer dans le droit de l'arbitrage international.
Keywords: Adequate compensation; Arbitrage international; Damages suffered; Dommages-intérêts; Full compensation; Indemnisation adéquate; Indemnisation intégrale; International arbitration; Intérêts lésés; Mercatoria; Prejudices; Process of the evaluation; Processus d'évaluation; Préjudices; Règles d'indemnisation; Réparation (droit international)

L’arbitrage, une justice citoyenne, émancipée et pragmatique - Raibaut, Jacques (Académie de Législation, 2014)
Keywords: ARBITRAGE; Arbitration

Alternative Dispute Resolution (ADR): An Overview of Some Common Mechanisms, and their Strengths and Weaknesses in Context - Perrin, Harry (The Plymouth Law & Criminal Justice Review, 2014)
Alternative Dispute Resolution, or ’ADR’, offers parties in dispute an alternative to traditional court-based litigation, which is often seen as slow, costly and ineffective. ADR frequently involves a neutral third party who will settle or facilitate resolution of the dispute. This paper examines three common ADR mechanisms, adjudication, arbitration and mediation, and explores their relative advantages and disadvantages in different contexts.
Keywords: ADR; Adjudication; Alternative dispute resolution; Arbitration; Construction adjudication; Mediation; Negotiation

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

Dispute resolution in transnational securities transactions - Andreotti E Silva, Tiago (European University Institute, 2014)
This PhD thesis explores how the legal infrastructure for dispute resolution in transnational securities transactions can be improved, considering the regulatory and legal limits of the financial sector in each jurisdiction under study (US, Europe and Brazil). The two main objectives of the work are to a) identify the problems that currently exist for a dispute resolution mechanism in the securities area that can be used transnationally and b) propose solutions that can create a safe legal environment that can be used by the investor in case regulatory rules or the terms of the transaction are breached. The work is justified by the fact that financial markets are legal constructions, making legal certainty and the mechanisms available to enforce the terms of a transaction and apply regulatory rules, especially to the investor that is part of the transaction, essential for the own existence of financial markets. Therefore, the existence of transnational financial markets also depends on the existence of a transnational legal infrastructure, at least broad enough to protect the interest of investors. The argument developed through the work is that the creation of a transnational legal infrastructure depends on the type of dispute that is considered, since not only each type of dispute has its own peculiarities, but the national dispute resolution systems are also built based on the type of dispute that will be submitted to it. To create transnational dispute resolution systems for securities transactions, I propose the use of collective mechanisms of dispute resolution based on the initiative of private parties, the use of arbitration and the establishment of cooperation networks among national alternative dispute resolution mechanisms used to solve financial disputes.
Keywords: Dispute resolution (Law); Financial market; International finance; Security (Law)

L’arbitrage OHADA - Kenfack Douajni, Gaston (Droit OHADA et droits communautaires africains, 2014)
L’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a été créée par le Traité de Port-Louis (Ile Maurice) le 17 octobre 1993, modifié à Québec (Canada) le 17 Octobre 2008. L’OHADA a pour but de promouvoir les investissements dans ses 17 États parties à travers la sécurisation juridique et judiciaire de l’environnement des affaires, par la production de normes juridiques, simples, adaptées et modernes en droit des affaires, au nombre desquelles les instruments relatifs à l’arbitrage. Premier ouvrage de la collection droits OHADA et droits communautaires africains, l’Arbitrage OHADA procède à une présentation synthétique et à une analyse exhaustive des instruments OHADA relatifs à l’arbitrage, que sont l’Acte uniforme relatif au droit de l’arbitrage et le Règlement d’arbitrage de la Cour commune de justice et d’arbitrage de l’OHADA (Règlement CCJA). Outre les textes normatifs posant les bases de l’arbitrage OHADA, cet ouvrage met aussi à la disposition du lecteur la jurisprudence de la CCJA et commente les premières applications pratiques de l’arbitrage OHADA. Il est en cela indispensable à tous les praticiens de l’arbitrage OHADA. Mais au-delà, par la réflexion qu’il développe sur les difficultés rencontrées et les espérances suscitées par la mise en œuvre de l’arbitrage OHADA et – en définitive – sur l’apport de l’arbitrage dans le développement du droit OHADA et l’amélioration du climat des affaires en Afrique, cet ouvrage intéresse un public bien plus vaste (Universitaires, Barreau, Magistrature, Opérateurs économiques) et est appelé à constituer la référence en matière d’arbitrage pour l’ensemble des usagers du droit OHADA.
Keywords: Arbitrage; Arbitragem; Arbitration

L'arbitrage maritime : une étude comparative entre Londres et Paris - Khaldi, Jihane (Aix-Marseille Université, 2014)
Keywords: Arbitrage; Arbitration

Les modes alternatifs de règlement des conflits : à la recherche d'une clé d'accès à la justice administrative congolaise - Nyaluma Mulagano, Arnold (Université Catholique de Louvain, 2014)
L'accès au juge de l'administration est un droit consacré par les textes nationaux et internationaux au profit de tout administré congolais. L'effectivité de ce droit reste néanmoins aléatoire. A chaque étape de la procédure, le justiciable rencontre des difficultés énormes, parfois infranchissables. Les MARC comportent-ils une réponse à cette crise ? L'assertion de départ était tentante : l'Afrique étant reconnue comme une terre du règlement négocié, l'on a pris comme hypothèse de travail que le vent planétaire favorable aux MARC pourrait trouver, en droit administratif congolais, un terrain de prédilection. Le contrôle juridictionnel de l'administration congolaise est effectué par les juridictions de l'ordre administratif et les juridictions de l'ordre judiciaire, civiles et militaires. La Constitution du 18 février 2006 a instauré un ordre autonome de juridictions administratives. En attendant leur installation effective, le contentieux administratif relève, à titre transitoire, de sections incorporées au sein des juridictions de l'ordre judiciaire. Le texte actuellement en vigueur n'organise que la procédure devant la section administrative de la Cour suprême de justice. Le juge administratif intervient, à titre principal, dans le contentieux de légalité et, à titre subsidiaire, dans le contentieux d'indemnités. Il est également doté du pouvoir de contrôler l'acquisition et l'exercice des mandats publics. Les juridictions judiciaires se répartissent entre les juridictions de droit commun et les juridictions militaires. Les juridictions civiles interviennent principalement dans la mise en jeu de la responsabilité de l'administration et exceptionnellement dans le contrôle de la légalité des actes des autorités administratives. Le juge militaire connaît de la responsabilité de l'administration à l'occasion de la répression des infractions commises par les militaires et les policiers. Les constats réalisés dans la présente étude permettent d'affirmer que le contrôle juridictionnel de l'administration congolaise constitue une justice marginale, éloignée du citoyen et rejetée par lui. La défaillance des acteurs judiciaires, les carences institutionnelles et les inadéquations normatives éloignent la justice administrative congolaise des missions élémentaires de service public qu’elle devrait pourtant assumer. Les décisions de justice souffrent d'une faible qualité et d'une inexécution chronique. Tout ceci disqualifie le recours juridictionnel et dévalorise la notion de légalité. La médiation institutionnelle, la médiation processuelle, la conciliation et l'arbitrage constituent-ils une réponse à ces difficultés ? Alors que l'Afrique est réputée terre de MARC, c'est plutôt en Belgique qu'ils se développent. La médiation institutionnelle y joue un rôle régulateur incontestable. Par contre, le régime de la médiation processuelle reste peu incitatif. L'habilitation légale imposée au sujet des personnes morales de droit public ne permet pas l'éclosion de ce MARC en droit administratif belge. L'habilitation légale est également requise pour la participation de l'administration à la conciliation. Cette habilitation est intervenue à maintes reprises. Les cas étudiés démontrent une faible contribution de la conciliation aux litiges ponctuels. Elle semble mieux convenir aux litiges des masses dont les faits sont incontestés. En droit public belge, l'arbitrage est limité aux litiges contractuels. L'arbitrabilité des litiges extra-contractuels est soumise à une habilitation légale. La modification intervenue pour étendre le régime d'arbitrage à l'ensemble du litige contractuel et non plus seulement aux différends relatifs à l'élaboration ou à l'exécution ne suffit pas à lui assurer une grande efficacité. En règle générale, l'hésitation du législateur belge s'explique par le succès du juge de l'administration. La R.D.C. figure parmi les rares pays africains qui ignorent l'institution d'Ombudsman. La médiation traditionnelle à travers la palabre africaine a été évincée par l'administration coloniale et post-coloniale. Par contre, la conciliation se développe en droit administratif depuis les années 2000. Chaque nouveau texte réserve un espace à la conciliation. Longtemps cantonné au droit privé et aux litiges internationaux, l'arbitrage apparaît progressivement dans certains secteurs du droit administratif congolais à partir des années 2000. L'adhésion de la R.D.C. à l'OHADA consolide l'arbitrabilité des litiges impliquant l'administration. L'environnement socio-juridique congolais semble ainsi ouvert aux MARC. Il s'observe, en outre, une convergence favorable de la jurisprudence, de la doctrine et des acteurs politiques. Leur efficacité devant les difficultés d'accès à la justice administrative congolaise reste néanmoins sujette à caution. En l'absence d'une volonté de transparence administrative, il est à craindre que la tendance favorable au règlement négocié ne conduise à l'instauration de MARC en trompe l'œil, sans impact réel sur les difficultés d'accès à la justice administrative congolaise. Au terme de cette étude, il apparaît que la perspective d'un meilleur accès à la justice administrative passe plutôt par une alternative citoyenne. Celle-ci semble distiller des vertus susceptibles de favoriser l'implémentation des MARC et la rationalisation du contrôle juridictionnel de l'administration congolaise. La justice citoyenne préconisée dans cette thèse désigne la faculté pour l'administré et l'agent public de régler directement leur conflit sans s'en référer à l'appareil judiciaire. Elle repose sur deux piliers : la défiance et le dialogue. La justice citoyenne alimente la responsabilité et l'émancipation des citoyens. Les réponses inventées par les citoyens et les agents publics révèlent une véritable résilience qui augure une perspective intéressante pour l'accès à la justice administrative congolaise. Apprivoiser et intégrer cette justice pragmatique dans le giron de la justice étatique devrait ouvrir des horizons nouveaux pour les justiciables congolais. L'interaction entre ces MARC et le contrôle juridictionnel devrait faire bouger les lignes et générer ainsi une certaine amélioration de la justice administrative. En examinant la question au départ d'initiatives citoyennes, la thèse réinterroge le paradigme dominant dans la réforme de la justice en RDC et dans les Etats qui partagent le même contexte.
Keywords: Accès à la justice; Administration; Arbitrage; Arbitragem; Arbitration; Congo (République démocratique); Décision; Justice administrative; MARD; Mediación; Mediation; Mediação; Modes alternatifs; Médiation; Palabre africaine; RDC

Les contours de l’arbitrage - Posocco, Laurent (La Lettre, 2014)
Les frais d’arbitrage peuvent compromettre l’accès au juge. L’exclusion de l’arbitrage comme méthode de recours à l’encontre d’une ordonnance du juge commissaire. Il ne revient pas aux parties d’apprécier la nature interne ou internationale de l’arbitrage.
Keywords: ARBITRAGE; Arbitration

L'arbitre et le droit - Prujiner, Alain (Revue de règlement des différends de McGill, 2014)
L’auteur se penche sur la relation qui existe entre l’arbitre et le droit, en focalisant sur les questions de procédure et de droit applicable au fond du litige en arbitrage international. L’auteur montre que les arbitres ne se réfèrent plus automatiquement au droit international privé de l’Etat du siège afin de déterminer le droit applicable à la procédure ou au fond du litige, ni même au droit international privé d’un Etat en particulier. Au contraire, l’auteur avance que la tendance est à l’internationalisation des règles de droit international privé : l’arbitre puise directement les règles de rattachement d’un ordre juridique transnational autonome, qui dispose de ses propres règles de droit international privé, tant pour le fond du litige que pour la procédure arbitrale. The author addresses the relationship between the arbitrator and the law, with an emphasis on the law and procedure that is applicable to international arbitration. It is demonstrated that arbitrators no longer automatically refer to the private international law of the state that is the seat of arbitration to determine the applicable law, nor to private international law rules of a particular country. On the contrary, there is a trend towards internationalizing the rules of private international law: the arbitrator obtains the governing law directly from an autonomous transnational legal system that has its own substantive and procedural rules in private international law.

Mediación mercantil. Mediación mercantil empresarial - Rojas Roldán, María de la Encarnación (Universidad Internacional de Andalucía, 2014)
Trabajo de Curso de Experto Universitario en Mediación Civil, Familiar, Mercantil y Organizaciones Complejas (2013). Tutora: María Sonia González Ortega. El objetivo del presente trabajo es abordar la Mediación en el seno de las organizaciones, teniendo en cuenta que estas constituyen sistemas de interrelación entre personas, donde confluyen numerosos intereses. Se trata por tanto, de abordar la resolución de los problemas no solo existentes sino de los emergentes, aportando herramientas eficaces en el desarrollo de la actividad empresarial, que permitan gestionar y modular los conflictos, de forma que los mismos, se transformen en oportunidades de mejora y de crecimiento empresarial.
Keywords: Mediación; Mediation; Médiation

Le consentement dans l'arbitrage des litiges sportifs - Yamdjie, Elie (Université de Nice Sophia-Antipolis, 2013)
Le consentement dans l’arbitrage des litiges sportifs témoigne des mutations profondes que subissent les piliers du droit dans le domaine économique. L’unilatéralisme visible des puissances sportives supplante nettement le bilatéralisme où, en principe, la fusion paisible des volontés donne naissance aux conventions. Mus par la recherche de l’efficience, les pouvoirs privés sportifs s’emparent du consentement, le mettent résolument à leur service au point que leur arbitrage se rapproche plutôt du sens qu’y donnent les économistes. La convention issue de ce consentement rime plutôt avec les contrats économiques. L’automaticité des effets liés à ce consentement nie à l’arbitrage ainsi institué le minimum de légitimité dont il a besoin. Le juge du for en a enfin pris conscience et c’est heureux ! Mais c’est sur les arbitres du TAS que repose le plus grand travail nécessaire à sa légitimation.
Keywords: ABUS; Acceptation; Arbitrage; Arbitragem; Arbitraje; Arbitration; Litiges; Règlement de conflits; Sports; Tribunal arbitral du sport

Arbitrating and Mediating Disputes: Benchmarking Arbitration and Mediation Regimes for Commercial Disputes Related to Foreign Direct Investment - Pouget, Sophie (World Bank, 2013)
An effective commercial arbitration regime matters for foreign investors. It gives parties the autonomy to create a dispute resolution system tailored to increasingly complex disputes. Foreign investors view arbitration as a way to mitigate risks by providing legal certainty on enforcement rights, due process, and access to justice. The Arbitrating and Mediating Disputes indicators assess the legal and institutional framework for commercial arbitration, mediation, and conciliation regimes in 100 economies. All surveyed economies recognize arbitration as a tool for resolving commercial disputes and only nine economies have not acceded to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards. In the Arbitrating and Mediating Disputes indicators, High Income OECD and Eastern Europe and Central Asia are the regions that reformed their laws on alternative dispute resolution the most between 2011 and 2012. The data also show that, globally, arbitration proceedings take 326 days on average, while recognition and enforcement proceedings of foreign arbitral awards take 557 days on average. The Arbitration and Mediating Disputes indicators are significantly correlated with perception data on the importance of alternative dispute resolution, as well as other measures such as total foreign direct investment inflows and inflows per capita, the Doing Business 2013 Enforcing Contracts data, the World Bank Group's Governance Indicators, the World Economic Forum's Global Competitiveness Indicators, and the Multilateral Investment Guarantee Agency's World Investment and Political Risk data. The paper concludes by identifying several opportunities for improvement, such as greater flexibility for domestic arbitration regimes, faster arbitration proceedings, and better domestic court capabilities.

Arbitrage commercial international et développement : étude du cas des États de l’OHADA et du Mercosur - Yougoné, Franck Nicéphore (Université Bordeaux 4, 2013)
L’OHADA et le Mercosur sont deux organisations régionales qui ont été créées afin d’accentuer l’intégration et de favoriser la sécurité judiciaire et juridique pour les opérateurs du commerce international. En d’autres mots, leur objectif est d’aider au développement économique des pays membres. Dès le fonctionnement de ces deux organisations, le recours à l’arbitrage a été privilégié comme mode de règlement des différends liés au commerce international. Partant de là, il nous est apparu envisageable d’établir un lien entre la notion de développement et celle arbitrage commercial international. Presque vingt ans après la création de l’OHADA et du Mercosur, cette étude se propose d’évaluer les liens entre l’arbitrage et le développement. Cette évaluation se base sur l’observation de l’influence de l’arbitrage sur le processus d’intégration et sur l’apport de cette technique aux efforts d’amélioration de la sécurité judiciaire et juridique dans le milieu du comme international.
Keywords: Alignment; Arbitrage; Arbitrage commercial international; Certainty; Commerce international; Damage; Development; Dommage; Développement; Harmonisation; Integration; International commercial arbitration; Intégration; Investissements; Investments; Judicial security; Mercado común del Sur; Organisation pour l'harmonisation en Afrique du droit des affaires; Repair; Réparation; Sécurité judiciaire; Sécurité juridique; Uniform; Uniformisation

Les Preuves dans l'arbitrage international - Richani, Joseph (Université de Cergy Pontoise, 2013)
L'arbitrage est un mode de résolution des litiges par l'intermédiaire d'un tribunal arbitral composé d'un ou plusieurs arbitres. Il permet, comme devant les tribunaux étatiques, de régler un litige en vertu d'une sentence rendue à l'issue d'une procédure arbitrale dans laquelle chacune des parties doit prouver ce qu'elle allègue afin d'établir la conviction des arbitres. C'est par le recours aux divers modes de preuve inspirés des différents systèmes juridiques notamment du système de Common Law et du système de droit civil que les plaideurs pourront atteindre cette finalité.En revanche, parce que l'arbitrage international ne possède ni for ni législation spéciaux, l'administration des preuves dans une instance arbitrale internationale revêt un caractère sui generis de fait que l'arbitrage international a reconnu un système de preuve qui a utilisé les avantages des divers systèmes juridiques. Ainsi, on retrouve que la preuve écrite, qu'elle soit sur support papier ou sur support électronique, est administrée selon le model civiliste qui donne la primauté à une preuve préconstituée à l'avance. Mais, en ce qui concerne la preuve par témoin, l'influence des droits de Common Law paraît claire surtout que dans la plupart des cas, le pouvoir de nommer et d'interroger les témoins revient aux plaideurs qui utilisent la méthode d'Examination lors de l'interrogation des témoins. C'est aussi le cas de l'expertise qui est souvent considérée comme une preuve orale dans laquelle il revient aux parties le pouvoir de désigner les experts et de les interroger suivant l'interrogatoire direct et le contre interrogatoire tout comme des témoins. Ainsi, les preuves dans l'arbitrage international peuvent être reparties en preuves écrites et preuves orales dont les premières sont constituées de l'écrit sur support papier ou sur support électronique et les secondes sont formées par la preuve par témoin et la preuve par expertise. The arbitration is a method of resolving disputes through an arbitration tribunal composed of one or several arbitrators. He allows resolving a dispute under a sentence delivered after an arbitration procedure in which all parties have to prove what they adduce to convince the tribunal. It is by using various modes of proof inspired specially from the system of Common Law and the system of Civil Law that parties can achieve this purpose.On the other hand, because the international arbitration has neither a territory nor legislation, it was created a system which combines between best practices of Common Law and Civil Law. So, the written evidence is produced according to the practice of Civil Law which gives primacy to a proof written in advance. But for the oral testimony, it is the common Law which dominates the administration of this proof by giving parties the right to nominate and interrogate witnesses. This is also what happens when arbitrators decide to use an expertise in which the parties have the power to nominate experts and interrogate them as witnesses. So, the evidence in international arbitration can be divided into written evidence made up by the writing on paper medium and electronic medium and oral evidence formed by proof by witness and proof by expertise.
Keywords: Act; Acte; Arbitrage; Arbitrage international; Arbitragem; Arbitration; Evidence; Expert; International Arbitration; Preuve; Temoin; Witness

The Enforcement of Arbitral Awards in Cameroon - Tumnde, Taylor (Social Science Research Network, 2013)
The increase in international trade creates a growing number of disputes between parties from different countries. Arbitration has become the most preferred mechanism to solve disputes in international trade. If a party does not voluntarily comply with an award, the successful party must apply for recognition and enforcement of the award in order to obtain the remedies. Cameroon is one of the major business markets in West and Central Africa, several companies committed to arbitral procedures are likely to have assets in Cameroon. This means that if a party fails to honour an award, an enforcement procedure may begin within a Cameroonian court. The enforcement procedures in Cameroon are sufficient and do comply with international standards. The most used and important instruments for recognition and enforcement are the United Nations Convention on the Recognition and Enforcement of Foreign Arbitral Awards of 1958 and the Uniform Act on Arbitration 1999 in the OHADA territory, to which Cameroon is a signatory State. According to this Convention and the Uniform Act, an arbitral award may be refused enforcement under certain grounds laid down in them. There are various types of arbitral awards contemplated by the Cameroonoan legislature and will be herein examined to see how they can be enforced in Cameroon. An analysis of the legal situation in Cameroon confirms that there are problems associated with the enforcement of arbitral awards. These problems are not, however, connected with the concept of arbitral awards, but rather with the entire judicial system in Cameroon. Even though an enforcing party can do little to overcome these problems, certain measures can be taken in order to ease the enforcement procedure
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Cameroon; Enforcement; OHADA

A comparative study of law and practice of arbitration in Kenya, Nigeria and Zimbabwe, with particular reference to current problems in Kenya - Torgbor, Edward Nii Adja (Stellenbosch University, 2013)
Arbitration as a mode of dispute settlement has been growing steadily all over the world. The momentum for commercial arbitration in particular was provided by the 1985 UNCITRAL Model Law on International Commercial Arbitration (“the Model Law”). Legislation based on the Model Law has been enacted in many countries. The arbitration laws of three of these countries, Kenya, Nigeria and Zimbabwe, are selected for consideration in this dissertation because of their common origins, similar statutes, similar problems, shared experiences, and their regional distribution. As the writer’s arbitration practice is based in Kenya, that jurisdiction is the primary, albeit not the only, source and foundation for this work, the focal point of reference and the citations from the law and practice incorporated in this research. The work consists of three chapters. Chapter one is a brief introduction and an overview of arbitration. This is followed by the statement of the research question, the justification for the research, methodology and the structure and content of the dissertation. Chapter two describes the legal and contextual framework for the investigation of the research questions in the selected jurisdictions of Kenya, Nigeria and Zimbabwe. Customary Law arbitration is included as a significant feature of African arbitration law. The UNCITRAL Model Law, the Arbitration Act, 1995 (Kenya), the Arbitration and Conciliation Act, 1988 (Nigeria), the Arbitration Act, 1996 (Zimbabwe), the Arbitration Act, 1996 (England), and the South African Draft Arbitration Bill are all used as legislative or statutory points of reference in the discussion of the research questions. Chapter 3 contains the main focus of the dissertation in which six recurrent arbitration problems in Kenya are discussed in the context of domestic arbitration. The research investigates (i) the illusiveness of consent as the basis for consensual arbitration (ii) jurisdictional challenges (iii) the procedural powers of the arbitral tribunal (iv) the disruptive effect of adjournments and postponements on the arbitral process (v) constraints on the granting of interim relief and (vi) the enforcement of the arbitral award. Original, creative and innovative proposals in response to these problems include: the express legislative recognition of the manifestation of consent in both the verbal and written forms of the arbitration agreement, the use of the constructive dispute resolution technique, statutory recognition of customary law arbitration, the use of an expedited arbitration procedure, the award of exemplary and punitive damages in arbitration, a code of sanctions to facilitate the arbitration process, and a simplified method of enforcement and execution of the arbitral award. The dissertation concludes with reflections on the future of arbitration in Africa, and the need for modernization and harmonization of arbitration laws for peaceful resolution of disputes and serious conflicts across Africa. The aim of this study is best illustrated by a short story: In the early nineties there was a man, untrained in any known discipline, who strutted court corridors, trade centres and market places, carrying a placard advertising himself to lawyers, traders and marketers as “An Arbitrator and Private Judge”. He attracted business, charged a handsome percentage fee on the value of the claim, was duly paid, until officialdom caught up with him and put paid to his burgeoning career as “Arbitrator-Judge”. But the reckless enthusiasm spawned by his wit and imagination, and the idiosyncratic practices in dispute resolution persisted and are manifest in Kenyan arbitration culture today. The need to remove bad practices, avoidable impediments, and inefficiency in the arbitration culture of Kenya in order to make its procedures and processes more efficacious, is the heart of this study.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Comparative law; Dispute resolution; Kenya; Nigeria; Zimbabwe

L'exécution des sentences arbitrales étrangères selon la Convention de New York de 1958 - Al Mana, Ahmad (Université Paris 1, 2013)
L'arbitrage est devenu le mécanisme de règlement des différends dans les contrats internationaux. L'arbitrage international offre aux parties non seulement la possibilité d’éviter les juridictions étatiques, mais facilite également l'exécution internationale des sentences arbitrales. Dans ce cadre, la Convention de New York de 1958 sur la reconnaissance et l’exécution des sentences arbitrales étrangères constitue sans aucun doute le traité le plus important dans le domaine de l'arbitrage international, et a connu un succès remarquable au cours de sa ratification par 147 États. Cette étude apporte une analyse approfondie sur la mise en application et l’interprétation par les différentes juridictions des dispositions prévues par cette Convention, surtout en matière de reconnaissance et d’exécution des sentences arbitrales étrangères. Arbitration has become the dispute resolution mechanism in international contracts. International arbitration does not only offer to the parties the possibility of avoiding the States jurisdictions, it also facilitates the international enforceability of arbitral awards. In this respect, the New York Convention of 1958 on the Recognition and Enforcement of Foreign Arbitral Awards constitutes without a doubt the single most important treaty in the field of international arbitration, and has enjoyed remarkable success through its ratification by 147 States. This study presents a thorough analysis of the application and interpretation of the provisions, provided by the Convention, by different jurisdictions especially in the area of the recognition and enforcement of foreign arbitral awards.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Contrats internationaux; Convention de New York; Convention de New York de 1958; Exécution (droit); L'atteinte à l'ordre public; L'exécution; L'immunité des États; L'inarbitrabilité; La reconnaissance; New York Convention of 1958; Recognition; Sentences arbitrales

Common Court of Justice and Arbitration: A Supranational Institution for the Administration of Commercial Disputes in Africa - Ogwezzy, Michael C. (Nordic Journal of Commercial Law, 2013)
Due to the expansion of business transaction across the globe, the private sector demands an adequate legal framework that is sufficiently clear, modern, predictable and transparent to permit investment with a sense of security. The Organisation for the Harmonisation of Business Law in Africa (Organisation pour l’harmonisation en Afrique du Droit des Affaires) is generally known by its French acronym OHADA. As long-standing idea, the foundation of the OHADA Treaty was first laid during a meeting of finance ministers of the members of the franc CFA1 area held in Ouagadougou, Burkina Faso, in April 1991. A group of experts, led by Senegalese Justice Keba Mbaye, was appointed to conduct a feasibility study on a form of legal collaboration designed to promote economic integration and attract investments.2 Identifying low investment as a major obstacle to economic growth, Keba Mbaye presented his report to the French-speaking African summit in Libreville, Gabon, in October 1992, recommending the creation of a supranational organization comprising the entire franc area. The recommendation was adopted and a steering committee of three experts were appointed and tasked with drafting an international instrument as well as identifying the areas of law to be harmonized. The OHADA was established through the treaty of Port Louis in Mauritius on 17th October, 19933 The treaty is open to any Member State of the Organization of African Unity (AU) as well as any other non-member of the AU invited to join with the common agreement of all the Member States.4 The OHADA has progressively become the common business law in anglophone and francophone African countries, taking the best from the civil law and the common law systems.5 The OHADA provides its Member States with 1) a single, modern, flexible and reliable business law adapted to each country’s economy; 2) arbitration as an appropriate and trustworthy way to settle disputes; and 3) an opportunity for training judges and judicial staff and ensuring their specialisation. In May 2003, the uniform OHADA business law came into force in the sub-Saharan African States of Benin, Burkina Faso, Cameroon, Central African Republic, Comoros, Congo, Ivory Coast, Gabon, Guinea, Guinea Bissau, Equatorial Guinea, Mali, Niger, Senegal, Chad, Togo and later the Democratic Republic of the Congo. The OHADA Treaty secures a legal framework for the conduct of business in Africa.6 Pursuant to Article 53 of the OHADA Treaty, any member State of the African Union may become a member, if it wishes to do so.7 Many countries are currently giving active consideration to joining the OHADA common system of business law.8 Most of the countries have a French colonial heritage, with the exception of the Democratic Republic of the Congo (former Belgian colony), Guinea-Bissau (former Portuguese colony), Equatorial Guinea (former Spanish colony), and Togo and Cameroon (formerly under partly British and partly French colonial rule). French is also an official language in most of the countries and many OHADA sources are only available in French. 9 It is interesting to know that the Council of Ministers of the OHADA organisation which is the legislative organ of the organisation have adopted the following uniform business law: the general commercial laws, corporate laws and rules concerning different types of joint ventures, laws concerning secured transactions, debt recovery and enforcement laws, bankruptcy laws, arbitration law, accountability law, and law regulating contract for the carriage of goods by roads.10 The OHADA treaty established the Common Court of Justice and Arbitration (CCJA) which is a supranational11 judicial institution based in Abidjan, Ivory Coast.12 2.

Les contrats de joint ventures sino-étrangères devant l'arbitre international - Willems, Jane (Université Angers, 2013)
Cette thèse a pour objet de déterminer à quelles conditions l’arbitre international, saisi d’un litige relatif à un contrat de joint venture sino-étrangère, est susceptible d’apporter une solution aux cocontractants et une contribution à la construction du droit de l’arbitrage des investissements étrangers en Chine. L’examen des conditions d’accès à l’arbitrage et de la détermination et de la mise en oeuvre, par l’arbitre international, des règles de droit permettra de cerner les limites du caractère véritablement international de l’arbitrage auquel est soumis le contrat de joint venture sino-étrangère. La limitation de l’autonomie des parties en droit chinois de l’arbitrage et en droit international privé chinois impose des contraintes à l’arbitre international, siégeant en Chine ou à l’étranger tant pour apprécier la validité de la clause compromissoire et l’existence et l’étendue ratione personae et ratione materiae du consentement à l’arbitrage, que pour déterminer et appliquer les règles de droit auxquelles est soumis le litige. L’examen des solutions apportées par l’arbitre international permettra d’apprécier son apport substantiel à la clarification des conditions de formation du contrat de joint venture sino-étrangère, qu’il s’agisse des conditions de fond, tirées de la qualification des parties et de l’existence et de la sincérité de leur consentement au contrat de joint venture, que des conditions de forme, tirées de l’approbation des contrats d’investissement. Cet apport est confirmé en matière d’obligations des parties, par la reconnaissance et la diversification des obligations pécuniaires, de participation et de coopération auxquelles sont tenus les associés de l’entreprise commune
Keywords: Arbitrage; Arbitration; Chine; Clause compromissoire; Conventions d'arbitrage international; Droit commercial (droit international); Entreprises communes; Investissements étrangers; Joint-stock company; Joint-venture

Applicable law in investor-state arbitration: the interplay between national and international law - Elisabeth Kjos, Hege (Oxford Monographs In International Law, 2013)
This book examines the law, national and/or international, that arbitral tribunals apply on the merits to settle disputes between foreign investors and host states. In light of the freedom that the disputing parties and the arbitrators have when designating the applicable law, and because of the hybrid nature of legal relationship between investors and states, there is significant interplay between the national and the international legal order in investor-state arbitration. The book contains a comprehensive analysis of the relevant jurisprudence, legal instruments, and scholarship surrounding arbitral practice with respect to the application of national law and international law. It investigates the awards in which tribunals referred to consistency between the legal orders, and suggests alternatives to the traditional doctrines of monism and dualism to explain the relationship between the national and the international legal order. The book also addresses the territorialized or internationalized nature of the tribunals; relevant choice-of-law rules and methodologies; and the scope of the arbitration agreement, including the possibility of host states presenting counterclaims in investment treaty arbitration. Ultimately, it argues that in investor–state arbitration, national and international law do not only coexist but may be applied simultaneously; they are also interdependent, each complementing and informing the other both indirectly and directly for a larger common good: enforcement of rights and obligations regardless of their national or international origin.
Keywords: Arbitral tribunals; Choice-of-law rules; Foreign investors; Host states; International law; Investor-state arbitration; National law; OAPEN

Written Arbitration Agreements: What Written Arbitration Agreements? - Yu, Hong-Lin (Civil Justice Quarterly, 2013)
First paragraph: This article considers the issue of an oral arbitration agreement in relation to the New York Convention. As Townsend once said "[a]rbitration offers a means to an end, and the end is to the resolution of disputes." This end would be extremely difficult to achieve without the approval of national courts. Fortunately, with 146 signatory countries signed on the New York Convention on the Recognition and Enforcement of Arbitral Awards 1958 (The New York Convention), the success of this Convention has attracted businessmen into using arbitration to resolve their disputes. Nevertheless, a voluntary arbitration cannot be commenced without a valid arbitration agreement. Setting out to achieve harmonisation in the enforcement of arbitration agreements, art.II of the New York Convention provides the written requirements to be followed by all 146 signatory countries. Accordingly, written requirements for arbitration are imposed upon all signatory countries and they are obliged under the convention to recognise all arbitration agreements which are made in writing.
Keywords: Arbitration agreements; Comparative law; Convention d'arbitrage; France; New York Convention awards; New Zealand; Oral contracts; Scotland

I sistemi di risoluzione stragiudiziale delle controversie in materia bancaria e finanziaria - Cannavo, Mauro (Università di Pisa, 2012)
Il presente elaborato mira ad analizzare le forme di tutela accordate in sede europea al “consumatore” si servizi finanziari, al fine di verificarne, da un lato, l’adeguatezza rispetto all’evoluzione normativa che ha interessato tale segmento del mercato (Capitolo I) e, dall’altro lato, le modalità e le tecniche di diffusione nell’ordinamento italiano (Capitolo II) e in quelli dei principali Paesi Europei (Capitolo III). L’indagine muove dal processo di integrazione comunitaria avviato nel 1999 con l’elaborazione del “Financial Service Action Plan”, mettendo in luce come tale azione stia progressivamente contribuendo, attraverso la predisposizione di nuove regole e principi, alla creazione di un “diritto privato europeo”. In tale contesto, infatti, lo spazio rappresentato dal mercato dei servizi finanziari è significativo e di eccezionale rilevanza. Si è osservato, infatti, come l’integrazione dei mercati finanziari – avviata dalle Istituzioni europee, tra l’altro, attraverso l’aggiornamento della normativa comunitaria sui servizi di investimento (direttiva MiFID) – abbia avviato, e progressivamente sostenga, la massima armonizzazione delle regole economiche e giuridiche applicabili alle relazioni con i clienti, anche attraverso l’introduzione di nuovi meccanismi di tutela dei consumatori, volti a preservare la parte “debole” del rapporto contrattuale dai fisiologici rischi connessi alla prestazione dei servizi finanziari. In tale contesto, si è evidenziato come l’omogeneizzazione delle regole dei mercati finanziari abbia comportato, da un lato, l’aumento del flusso di risparmio destinato agli investimenti cross-border, nonché il progressivo coinvolgimento dei consumatori nelle transazioni finanziarie ma, dall’altro lato, abbia contribuito ad esporre maggiormente gli stessi ai rischi connessi agli eventi di crisi che hanno interessato le economie a capitalismo avanzato (ad esempio, il default della banca d’affari Lehman Brother’s). L’esposizione della clientela a situazioni di instabilità, peraltro, è fortemente avvertita anche sul versante dei servizi bancari tradizionali, non soltanto in ragione della diffusione del modello di banca universale e multicanale, ma che per effetto dell’attesa internazionalizzazione dei player del mercato, conseguente al livellamento del relativo “campo da gioco”. Si è perciò sottolineato come la proliferazione delle controversie intermediario-cliente nei diversi segmenti del comparto bancario-finanziario abbia mostrato come il nuovo sistema di tutele introdotto dal legislatore comunitario non sia stato in grado, da solo, di garantire la massima protezione dei consumatori dai rischi connessi alla fruizione dei servizi finanziari. A tale proposito, ci si è interrogati – anche alla luce della copiosa letteratura nazionale ed europea in materia – riguardo ai rimedi esperibili per superare le criticità legate alle procedure giudiziali di risoluzione delle controversie transfrontaliere (i.e. la durata dei tempi processuali, ovvero il costo per accedere alla giustizia), giungendo ad individuare nei sistemi alternativi di risoluzione delle controversie (c.d. ADR) una valida alternativa rispetto alla tutela giudiziale ordinaria. Ancora nel corso del Capitolo I, si è dato conto di come tali meccanismi di mediazione e conciliazione – caldeggiati e, in parte, disciplinati dalle istituzioni comunitarie – potranno, da un lato, comportare la semplificazione e la deburocratizzazione degli apparati giudiziari e, dall’altro, offrire un ulteriore presidio di tutela per i cittadini europei, particolarmente esposti ai rischi connessi ad attività complesse come la prestazione dei servizi di investimento. Come evidenziato nel corso del Capitolo II, non sorprende che in un settore fisiologicamente esposto al rischio di contenzioso come il comparto dei servizi finanziari, le Istituzioni comunitarie abbiano introdotto e progressivamente sospinto la diffusione in Europa dei modelli di ADR, appunto come strumenti di risoluzione delle controversie alternativi agli ordinari rimedi di natura giudiziaria. E sulla spinta comunitaria, anche il legislatore italiano sta progressivamente introducendo nel nostro ordinamento nuove modalità e nuovi sistemi per la risoluzione stragiudiziale delle controversie insorte in sede di prestazione dei servizi finanziari: tra le prime, la disciplina della mediazione finalizzata alla conciliazione delle controversie in materia civile e commerciale (di cui al d.lgs. 4 marzo 2010, n. 28); tra i secondi, i due nuovi organismi di derivazione pubblica, rappresentati dall’Arbitro Bancario Finanziario attivo presso la Banca d’Italia e la Camera di Conciliazione e Arbitrato, costituita presso la Consob. Si è visto, quindi, che le esigenze di tutela della clientela hanno condotto negli ultimi anni all’emanazione di regole e principi, come la disciplina della trasparenza del 2003 (successivamente novellata nel 2009 e, da ultimo, nel 2011 per recepire le nuove regole in materia di contratti di credito ai consumatori) e le regole di funzionamento dei sistemi di risoluzione stragiudiziale delle controversie, che operano proprio a completamento del quadro delle iniziative di tutela della clientela bancaria e finanziaria, come strumenti di redress rapidi, economici ed efficaci. Sempre nel corso del Capitolo II, quindi, si analizzano le caratteristiche principali dell’organismo nazionale deputato alla risoluzione stragiudiziale delle controversie bancarie, costituito dall’Arbitro Bancario Finanziario, al fine di rappresentare la natura giuridica di tale meccanismo, il relativo ambito di applicazione territoriale ed oggettivo, nonché individuando i rimedi esperibili dagli intermediari avverso le decisioni pronunciate dall’ABF. L’indagine prosegue attraverso l’indicazione degli elementi essenziali della Camera di Conciliazione e Arbitrato, istituita presso la Consob al fine di redimere le controversie insorte in sede di prestazione dei servizi di investimento, anche attraverso un approfondito confronto con la natura giuridica e l’ambito di applicazione dell’ABF. Infine, nel Capitolo III dell’elaborato – dopo aver esaminato le principali ragioni poste alla base della diffusione degli strumenti ADR in Europa, le principali iniziative legislative (direttiva mediation) e di autoregolamentazione (reti EEJ-NET e FIN-NET) in materia – si offre un’analisi dei principali sistemi ADR attivi in Europa, attraverso una dettagliata indagine comparatistica che ha interessato gli ordinamenti francese, spagnolo, tedesco e inglese. La menzionata indagine, in particolare, ha messo in luce le principali differenze e le numerose analogie presenti tra i sistemi ADR attivi nell’Unione europea, principalmente con riguardo alla natura giuridica dei rispettivi organismi, alle funzioni svolte, alle condizioni di accesso ai sistemi, nonché alle caratteristiche delle relative decisioni.
Keywords: ABF; ADR; Arbitrage; Arbitragem; Arbitration; Arbitrato; Arbitro; Banca; Cliente; Collegio; Conciliazione; Consob; Controversie; Finanziario; Intermediari; Intermediazione; MARD; Mediación; Mediation; Mediazione; Mediação; Médiation; Reclamo; Ricorso; Stragiudiziale

L'émergence du droit international des investissements : contribution des traités bilatéraux d’investissement et de la jurisprudence du CIRDI - Danic, Olivia (Université Paris 10, 2012)
La relation dialectique qui unit les traités bilatéraux d’investissement et la jurisprudence du Centre International de Règlement des Différends relatifs aux Investissements (CIRDI) a fait émerger un droit international des investissements. La rencontre de ces deux dynamiques a permis de dépasser leur caractère a priori isolé et fragmenté, pour aboutir à un véritable système juridique international, doté d’une structure, d’une logique et de principes propres. En effet, rien ne pouvait laisser envisager une telle évolution, le régime de l’investissement international se fondant sur une multitude de traités bilatéraux et sur une instance arbitrale ne faisant qu’héberger des tribunaux éphémères. Les mouvements de va-et-vient qui unissaient ces deux phénomènes ont permis de lui donner des normes quasi-universelles, mais aussi un véritable juge à la compétence extensive et surtout de lui insuffler l’unité, l’efficacité, la cohérence et la complétude, faisant de plus en plus ressembler le droit international des investissements à un véritable ordre juridique qui, même s’il relève du droit international, lui permet également d’évoluer. The relashionship between bilateral investment treaties and the case-law of the International Centre for Settlement of Investment Disputes (ICSID) has led to the emergence of international investment law. It seems surprising, at first, that these two distinct phenomena, being isolated and fragmented, would reach a certain degree of unity so that a real international legal order could appear, with its own structure, reasoning and principles. No one could foresee such an evolution, the regime of international investment being founded on a large number of bilateral treaties and on an international institution which only provides facilities for arbitration of international investment disputes. The unity of the system has been discovered through the back and forth movements between treaties and arbitration which gave rise to international investment law. This system has now almost universal norms, an international judge and satisfies the criteria of unity, efficiency, consistency and completeness, producing a real legal order functioning in accordance with its own logic. There is no doubt that this evolution will influence the course of international law.
Keywords: Arbitrage; Arbitrage (droit); Arbitration; Bilateral Investment Treaties (BITs); CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Droit international; ICSID; International law; Investissements; Investissements étrangers (droit international); Investment; Investments; Jurisprudence; Legal order; Ordre juridique; Traité bilatéral d’investissement

La responsabilité sociétale des entreprises et la médiation - Mattei, Laetitia (Université Paris 9, 2012)
Les crises actuelles, sous leurs multiples aspects, mettent en lumière la responsabilité des entreprises dans notre société, bousculant ainsi l'un des dogmes néolibéraux résumé par la célèbre formule de Milton Friedman (1970) : « La responsabilité sociétale de l’entreprise est d’accroître ses profits». C’est en réaction à ces crises et grâce au rôle actif de la société civile qui condamne désormais certaines pratiques, que le concept de responsabilité sociétale des entreprises (ci-après RSE) a émergé. L’enjeu est donc, aujourd’hui, de mettre en place un marché responsable entre l’entreprise et ses parties prenantes. Le législateur, par la loi Grenelle I, dispose que la médiation sera un des outils de mise en oeuvre de la RSE. Il en appelle donc au développement du droit processuel qu’est la médiation pour mettre en oeuvre ce droit substantiel qu’est la RSE. La médiation, à la fois préventive et curative, est donc un outil de mise en oeuvre de la RSE. Le couple RSE et médiation permet ainsi de combiner efficacité économique, respect social,sociétal et environnemental
Keywords: Company; Entreprise; Grenelle Environnement 2007; Législation; MARD; Mediación; Mediation; Mediação; Médiation; Paris; Parties prenantes; Parties prenantes (gestion d'entreprise) -- France; Procédure (droit); Responsabilité; Responsabilité sociétale; Responsibility; Sociétal; Stakeholders

The Influence of ICC Arbitral Decisions on Canadian Law: Comparative Study between Civil Law and Common Law Jurisdictions - Hedaraly, Saleha (Université de Montréal, 2012)
L’objectif de cette recherche est de démontrer que les décisions arbitrales de la Chambre de commerce internationale peuvent être considérées comme une source potentielle de droit au Canada. Il existe actuellement une incertitude quant au droit matériel utilisé en arbitrage international pour résoudre les différends commerciaux. Bien que l’utilisation de la lex mercatoria pour résoudre un litige soit une option, elle se heurte à de nombreuses incertitudes terminologiques et conceptuelles. L’utilisation d’une approche méthodologique de la lex mercatoria permettrait une classification de ses sources en deux branches: (1) le droit statutaire international et (2) le stare decisis des tribunaux d’arbitrage commercial international. Une telle approche méthodologique conférerait plus de certitude quant à l’application d’un droit uniforme. De plus, elle faciliterait l’étude de l’interlégalité entre les règles de la lex mercatoria et le droit matériel interne. Plus particulièrement, elle permet de comparer les similitudes et les différences des règles du droit matériel entre les décisions arbitrales internationales, le droit statutaire international et les juridictions canadiennes de common law et de droit civil. Cette comparaison rend possible une évaluation de l’influence potentielle des décisions arbitrales de la Chambre de commerce internationale sur le droit matériel canadien et si cette influence est plus importante en droit civil ou en common law. This paper’s objective is to demonstrate that the International Chamber of Commerce’s arbitral awards may be considered as a potential source of law in Canada. There currently exists an uncertainty as to the substantive law used in international commercial arbitration. While the use of lex mercatoria to solve commercial disputes is often referred to, several terminological and conceptual uncertainties undermine its credibility. The use of a methodological approach to lex mercatoria allows for a twofold classification of its sources through: (1) international legislation and (2) stare decisis from international arbitral tribunals. This methodological approach provides a greater certainty for the application of a uniform law which, in turn, allows for the study of interlegality between rules of lex mercatoria and substantive domestic law. Furthermore, this methodological approach facilitates the demonstration of the similarities and differences between international arbitral decisions, international legislation as well as Canadian common law and civil law jurisdictions. This comparative analysis will allow the study of the potential influence of the arbitral decisions of the International Chamber of Commerce on substantive Canadian law and whether this influence is more important in civil law or common law.
Keywords: Approche méthodologique; Arbitrage; Arbitragem; Arbitral decisions; Arbitration; CCI; Civil law; Common law; Droit civil; Droit commercial transnational; Décisions arbitrales; ICC; Interlegality; Interlégalité; Lex mercatoria; Methodological approach; Sentences arbitrales; Transnational commercial law

The legal and institutional framework for the enforcement of online consumer arbitration awards: evidence from Australia and Sri Lanka - Kananke, Chinthaka Liyanage (La Trobe University, 2012)
Keywords: Australia; Commercial law; Conflict of laws; Consumer protection; Dispute resolution; Electronic commerce; Sri Lanka

A proposal to guide future draft article provisions for a model harmonised international commercial arbitration law code (HICALC) in the Middle East and North Africa or a uniform Arab arbitration law - Ayad, Mary Boulos (Macquarie University, 2012)
MENA law codes are a well-crafted blend of civil and Islamic law in which civil law principles do not contravene with Islamic provisions. They were originally based on Sanhuri’s codes to varying degrees. Yet, common law principles derived either from English common law or Islamic customary usages are unidentified and thus ignored. Here, this lacuna is rectified through a comparative analysis of the primary data (eg, cases, statutes and arbitral award decisions), adding common law and uncodified Islamic custom to MENA law codes. The purpose of this comparative analysis is to allow common legal principles found at civil, common and Islamic law to be distilled in the service of creating a new harmonised international commercial arbitration law code (HICALC) or uniform Arab arbitration law (UAAL) for adoption in the MENA.1 These principles already form part or all of the legal systems in the MENA. They can be readily assimilated into a harmonised or uniform code. Would this new harmonised code lead to higher arbitral award enforcement in the MENA? According to the evidence the answer is yes. The author understands that at the present time the HICALC articles are ambitious and as such they are a beginning point and can initially be taken as a harmonised international commercial arbitration common rule (HICACR). A brief overview of the history of harmonisation is given. An assessment of the status of the laws and traditions of the MENA was carried out. A comparative analysis of the relevant differences and similarities of the case study countries (Egypt and the United Arab Emirates) was carried out to show the gaps in the laws and areas requiring reform. An analysis of enforcement of arbitral awards was carried out. The unique problems that ICA and IIA encounter in the MENA as derived from an analysis of cases and the laws therein are expounded in consideration of matters pertaining to enforcement. A comparative analysis of universal principles which must be included in a new code, including custom, was carried out. An analysis of the unique features and unique needs of the MENA was carried out in order to inform the Draft Article Provisions. An analysis of important international legal instruments dealing specifically with international arbitration and the gaps therein is given. The draft articles for a HICALC or uniform Arab arbitration law were derived as a result of these multiple layers of analysis. The matters of compétence de la compétence, expropriation, interest, public policy and sovereign immunity are highlighted as the most important areas requiring urgent reform. The results of this research are suggested Draft Article Provisions for a model Harmonised International Commercial Arbitration Law Code (HICALC) or a uniform Arab arbitration law. Future drafters may refer to and revise these articles for implementation. The synthesis of theory and practice addresses doctrinal matters that arise in international investment arbitrations and international commercial arbitration, with a focus on investor–State arbitrations. This synthesis provides a new theoretical conception of the jurisprudence of international arbitration, particularly in regard to the matters of res iudicata, precedent and expansion of arbitral tribunal powers and jurisdiction.
Keywords: Arab countries; Arbitrage; Arbitragem; Arbitration; Arbitration Law; Arbitration and award; Commercial law; Commercial law (Islamic law); Common rule; Dispute resolution; HICACR; HICALC; Harmonised International Commercial Arbitration; International commercial arbitration; MENA law codes; Middle East; North Africa; UAAL; Uniform Arab arbitration law

L'Influence de l'accueil de la sentence arbitrale par le juge algérien sur l'efficacité de l'arbitrage commercial international - Hocine, Farida (Université Mouloud Mammeri, 2012)
Keywords: Algérie; Arbitrage commercial; Arbitrage international; Arbitragem; Arbitraje; Arbitration; Efficacité de l'arbitrage; Juge algérien; Sentence arbitrale

From Port Louis to Panama and Washington DC: Two Regional Approaches to International Commercial Arbitration - Bashi Rudahindwa, Jonathan (European Journal of Law Reform, 2012)
In recent decades, regional efforts have been made to reform and harmonize the rules governing international arbitration. These efforts have resulted in the adoption of regional instruments governing commercial arbitration in specific areas. This paper analyzes the arbitration regimes created at a regional level in Africa and America, and particularly focuses on arbitral institutions that were created within the Organization for Harmonization of Business Law in Africa (OHADA) and within the Organization of American States (OAS). The objective of the paper is to identify any advantages provided by either regime, which can help improve regional and international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Efetividade das estipulações voltadas à instituição dos meios multiportas de solução de litígios - Guerrero, Luis Fernando (Universidade de São Paulo, 2012)
Este estudo examina as estipulações voltadas à instituição de meios multiportas de solução de controvérsias, mecanismo responsável por materializar a vontade da partes em solucionar os seus conflitos via métodos alternativos ou adequados de solução de controvérsias, tendo relevante papel na materialização do escopo social do processo. Há uma clara dicotomia entre os denominados métodos de solução de controvérsias consensuais, nos quais a própria participação das partes levará à solução e à conformação do litígio e, de outro lado, os métodos adjudicatórios de solução de controvérsias, no qual haverá um terceiro imparcial escolhido pelas partes ou de acordo com mecanismos por elas estabelecido e que será responsável pela solução da controvérsia. Existem ainda métodos combinados ou mistos, em que são aglutinados elementos dos métodos denominados primários, quais sejam negociação, conciliação, mediação e arbitragem. Clara a diferença entre essas categorias de métodos de solução de controvérsias, deve-se analisar, ainda, se há alguma diferença no tocante à vinculação das partes a cada uma das mencionadas categorias de solução de controvérsias e, com grande importância, de que modo métodos consensuais podem interferir no surgimento e desenvolvimento de métodos adjudicatórios. Em relação à vinculação dos métodos de solução de controvérsias adjudicatórios, a grande referência no direito brasileiro é a arbitragem, que conta com legislação própria e deve muito de seu sucesso no atual estado dos métodos de solução de controvérsias no direito brasileiro a alterações relativas à sua vinculação e efetivação. Nitidamente, há uma inserção das cláusulas de solução de controvérsias, seja qual for o método utilizado no âmbito da ciência processual. A base de tais cláusulas é de direito privado, fundamentando-se em institutos bastante conhecidos: transação e compromisso que ganharam a categorização jurídica de contrato após o Código Civil de 2002. Do ponto de vista da adoção desses instrumentos jurídicos como veículos da utilização dos métodos de solução de controvérsias, são previstas técnicas diversas de uso. A primeira é extrajudicial, baseada na planificação de solução de conflitos, que pode ser feita pelas partes e seus advogados, e uma segunda, que é extrajudicial baseada no caseflow e no case management, nos quais o Judiciário assume o papel de coordenador e aplicador de tais métodos. A relação entre os métodos de solução de controvérsias ganha caráter dinâmico na medida em que determinados sistemas de solução de controvérsias são combinados para uma dada questão. Trata-se das chamadas cláusulas escalonadas que têm por escopo acompanhar a escalada de litigiosidade que possa surgir em determinada discussão jurídica, combinando métodos consensuais e adjudicatórios de solução de litígios. Em qualquer situação, de acordo com os termos dos arts. 158 e 466-B do Código de Processo Civil que podem analogamente ser comparados com os arts. 4.º e 7.º da Lei de Arbitragem, há a total vinculação das partes ao método de solução de controvérsias escolhido. Questão bastante tormentosa é a inserção e a inter-relação dos métodos de solução de controvérsias, especialmente com o processo civil e os efeitos que daí podem decorrer. Nesse aspecto, sendo um método consensual, as partes que a ele aderiram terá que realizá-lo antes da busca de um método adjudicatório de adesão voluntária, como é a arbitragem, ou um método adjudicatório inevitável, como é o Judiciário. Trata-se do efeito negativo das cláusulas ADR. Contudo, há que verificar que efeitos seriam gerados aos métodos adjudicatórios pela não realização de um método consensual precedente. Os métodos de solução de controvérsias poderiam ser encarados como pressupostos processuais, condições da ação ou questões prévias, promovendo diferentes resultados em um processo judicial ou arbitral. Há que se buscar a solução que melhor se adequar a um contexto de solução de controvérsias. Desta feita, os MASCs devem ser colocados como hipóteses suspensão dos processos arbitral ou judicial, suspensão essa que deve durar até a realização do referido método acordado anteriormente, garantindo-se a sua eficácia. No tocante a este ponto, o Estado tem um relevante papel político e legislativo de modo a incentivar a utilização de tais métodos e garantir-lhes a eficácia. Além disso, a parte que se furtar está sujeita a consequências contratuais que podem ser previstas, tais como a imposição de multas e cláusulas penais. Vislumbram-se também hipóteses de perda de uma chance, com o agravamento do litígio e prejuízos que podem advir do tolhimento da chance de um método de solução de controvérsias produzir um resultado. De qualquer modo, aquele que pretendia utilizar o método, para se valer dessas possíveis indenizações, tem o dever de mitigar o próprio dano como resultado da mesma cláusula geral de boa-fé que, ao reverso, obrigou o ex-adverso a utilizar o método e foi violada. Pode-se pensar nesse contexto, ainda, a possibilidade de métodos alternativos de solução de controvérsias serem estabelecidos por meio de cláusulas que prevejam a venda de excussão entre as partes ou mesmo medidas corporativas, tais como ocorrem na BM&F Bovespa, apenas de acordo com a manifestação de vontade das partes de adesão ao referido sistema, sendo uma prova da força e extensão do vínculo surgido de uma estipulação de solução de controvérsias, ainda que consensual. Há, de qualquer modo, uma execução por transformação em que a manifestação de vontade apresentada pelas partes pode ser efetivada pelo magistrado permitindo a utilização dos métodos de solução de controvérsias a partir do momento em que ocorreu a adesão das partes. Por fim, a confidencialidade que pode ser aplicada aos métodos de solução de controvérsias tem natureza contratual, não interferindo na eficácia das cláusulas ADR. This study examines the stipulations aimed to establishing alternative settled mechanism responsible for materializing the will of the parties to resolve their disputes through alternative or appropriate dispute settlement with a relevant role in the materialization of the social scope of the process. There is a clear dichotomy between the called consensual methods of dispute resolution in which the participation of the parties will lead to the solution and the conformation of the dispute and, on the other hand, the called adjudicatory methods in which an impartial third party will be chosen by parties or in accordance with mechanisms established by them and will be responsible for resolving the dispute. There are also mixed or combined methods, which contains elements of the primary methods, namely, negotiation, conciliation, mediation and arbitration. Differences between these categories of methods of dispute settlement shall be analyzed, even if there is any difference with respect the binding feature of those methods and, with great importance, so that consensual methods can interfere in the emergence and development of adjudicatory methods. In relation to binding adjudicatory methods of dispute settlement, the most important reference in Brazil is Arbitration. Its Law is responsible for it succed as a method of dispute resolution in the Brazil, specially for ten. changes to their binding feature and enforcement of its result, now recognized as a sentence. The legal basis of such clauses is private law and are based on well-known institutions: transaction and commitment that are a contractual legal categorie after the Civil Code. From the standpoint of using, these legal instruments are vehicles and are expected to use different techniques. The first rendition is based on planning for conflict resolution that can be made by the parties and their lawyers and a second which is based on caseflow and case management, in which the judiciary takes over the role to coordinate and implement these methods. The relationship between the methods of dispute settlement became dynamic when individual methods of dispute settlement are combined to a given question. These are the called staggered terms which seeks to track the escalation of litigation that may arise in a particular legal issue, combining both consensual and adjudicatory dispute resolution methods. In any event, in accordance with the terms of the arts. 158 and 466-B of the Civil Procedure Code that can similarly be compared with the arts. 4o and 7o of the Arbitration Act, there is the share of binding feature of the method of dispute resolution chosen. Question very stormy is the interrelationship of the insertion of dispute resolution methods, especially consensual and adjudicatory methodse. In this aspect, a method is agreed, the parties have to do it before the search for an adjudicatory method. This is the negative effect of ADR clauses. However, there it is found that the effects would be generated by methods Adjudicative not performing a method consesual precedent. The methods of dispute settlement may be seen as procedural requisites, conditions of action or issues prior action by promoting different results in a lawsuit or arbitration. We must seek the solution that best fits the context of a multi door dispute settlement. The conclusion is that the ADR methods should be placed as hypotheses of suspension for arbitration or judicial processes. That suspension should last until the completion of this method previously agreed, assuring its effectiveness. Concerning this point, the State has an important political and legislative role in order to encourage the use of such methods and guarantee their effectiveness. In addition, the part that is subject to evade contractual consequences that can be provided such as the imposition of fines and penalty clauses. In case of ADR clauses breach the lost of a chance theory shall applyo, with increased litigation and damages that may arise from the chance of stunting a method of dispute resolution to produce a result. Anyway, who intended to use the breach of the other party to take advantage of possible damages, has the duty to mitigate the loss itself as a result of the same general clause on good faith that, in reverse, enforces the former adverse to using the method and was violated. One might think in this context also the possibility of alternative methods of dispute settlement be established by means of clauses providing for the sale of excussion between the parties or even intracorporis issues such as occur in the BM&F Bovespa, only in accordance with the manifestation the will of the parties to accede to such a system, a testament to the strength and extent of the relationship arising from a stipulation of settlement of disputes, even if consensual. The intetion to use an alternative dispute resolution shall be given by the partíreis but in case of breach of this obligation the interested party can obtain an mandatory decision by the Judge indicating that the other party must attend the dispute resolution method. Finally, the confidentiality that can be applied to methods of dispute settlement is contractual in nature, not interfering with the enforcement of ADR clauses.
Keywords: ADR; Civil Procedure; Conciliação (processo civil); Direito processual civil; Dispute Resolution; Enforceability; Multidoor; Solução de conflito; Transação; Tutela jurisdicional

Arbitrability in the context of Ghana's new arbitration law. - Mante, Joseph; Ndekugri, Issaka (International arbitration law review, 2012)
Examines the approach of Ghana's Alternative Dispute Resolution Act 2010 to the question of arbitrability. Reflects on the concept of arbitrability under international law, the relevant trends emerging from case law, and the approach adopted by the Ghanaian High Court in Attorney General v Balkan Energy LLC. Reviews the Act's arbitrability exemptions, their implications for international arbitration in Ghana, the potential jurisdictional challenges under the legislation and how its provisions could be amended to increase its conformity with international trends on arbitrability.
Keywords: Arbitrability; Arbitrage; Arbitragem; Arbitration; Comparative law; Ghana; International commercial arbitration; Jurisdiction

Reflections on finality in arbitration - Roodt, Christa (De Jure, 2012)
Ondersoek na die Finaliteit van 'n Arbitrasiebevel Hierdie artikel oorweeg die Telcordia- en Lufuno-sake vanuit die oogpunt van die finaliteit van 'n arbitrasiebevel. Die vraag wat te berde kom, is wanneer 'n arbitrasiebevel finaliteit bereik waar 'n saak voor meer as een forum (arbitrasie en staatlike howe), in meer as een jurisdiksie gevoer word. Die prosedurele meganismes wat Amerikaanse en Suid-Afrikaanse howe tydens die Telcordia-dispuut toegepas het asook hul onderskeie benaderings tot res iudicata, het 'n groot mate van ooreenstemming getoon. Dit is te verstane dat die afhandeling van 'n internasionale proses vertraag kan word deur bepaalde grondwetlike regte wat die spoed van die afhandeling van 'n saak kan beÃ¯nvloed. Nietemin, indien die reg op 'n billike verhoor op enige stadium in die verrigtinge gepleit mag word, word 'n geleentheid geskep vir die dispuut om vryelik te eskaleer gedurende die verhoor. Dit kan die hofproses oopstel vir misbruik en die afhandeling van die geskil vertraag. Die minderheidsbeslissing in Lufuno skenk 'n mate van oorweging aan die potensiële negatiewe implikasies hiervan. Die finaliteit van die geskilbeslegtingsproses kan na behore bestuur word aan die hand van 'n wyer interpretasie van res iudicata in internasionale dispute en 'n meer geredelike ondersoek hierna, op die hof se inisiatief. Die moontlikheid dat die Telcordia-dispuut verder bespoedig sou kon word, word ondersoek met verwysing na die New York Konvensie op die Erkenning en Afdwing van Arbitrasiebevele van 1958, en aan die hand van aanbevelings wat deur ander gerekende internasionale liggame uitgereik is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Lex mercatoria in international arbitration theory and practice. Vol 1 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Lex mercatoria in international arbitration theory and practice. Vol 2 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Arbitrage transnational et droit international général (2012) - Jacob, Patrick; Latty, Franck (Annuaire Français de Droit International, 2012)

La priorité chronologique reconnue à l'arbitre en droit maritime français, particularisme ou universalisme ? Le principe dit de compétence-compétence - Yildiz, Irfan (Aix-Marseille Université, 2012)
L’abandon progressif du contrôle de l’opposabilité de la clause d’arbitrage au destinataire par la juridiction étatique au profit de l’arbitre sur le fondement de l’aspect négatif du principe de compétence-compétence a donné lieu à de nombreux critiques. Certains auteurs l’ont approuvé, valorisant une application rigide de l’effet négatif du principe, tandis que d’autres l’ont critiqué solidement. Ainsi, il est légitimement permis de s’interroger sur les excès de l’effet négatif du principe de compétence-compétence et le bien-fondé de l’abandon du contrôle de l’opposabilité à l’arbitre par les juges étatiques. Pour ce faire, nous allons, dans un premier temps, examiner le droit accordé à l’arbitre d’être juge de sa propre compétence de manière prioritaire, plus précisément le principe de compétence-compétence (Chapitre I). Ensuite, nous allons nous interroger sur l’extension de la clause d’arbitrage au destinataire au regard du principe de compétence-compétence, qui est considéré de remettre en cause ce principe (Chapitre II).
Keywords: Arbitre droit maritime; Compétence-compétence; Transport maritime

Duty of Confidentiality: Myth or Reality? - Yu, Hong-Lin (Civil Justice Quarterly, 2012)
Explores the extent to which there is a duty of confidentiality in relation to the information used in arbitration proceedings. Considers how the duty is regulated by arbitration rules in different countries and whether there is a sufficient consensus to develop an internationally accepted principle of duty of confidentiality. Discusses which jurisdictions have an implied duty of confidentiality in the parties' arbitration agreement. Looks at how confidential information is defined in different jurisdictions, who is bound by the duty of confidentiality and the exceptions to the duty.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Confidential information; Confidentiality; Confidentialité; Information confidentielle

L'arbitrage CCJA - Wambo, Jérémie (Revue de l'ERSUMA, 2011)
L’arbitrage est désormais une institution traditionnelle de la vie des affaires sur le plan national, mais aussi et surtout sur le plan international. C’est un « mode alternatif de règlement des litiges qui consiste à faire trancher un différend par de simples particuliers », qui peuvent être des « personnes choisies par les parties »115. On distingue généralement deux types d’arbitrage, l’arbitrage Ad Hoc, qui demeure le plus fréquent, et l’arbitrage Institutionnel. Mais notre discussion va beaucoup plus porter sur le deuxième type d’arbitrage à travers le Centre d’arbitrage de la Cour Commune de Justice et d’Arbitrage de l’OHADA. Les signataires du Traité de Port Louis (Traité OHADA) du 17 Octobre 1993 avaient, dès le préambule, exprimé leur désir de « promouvoir l’arbitrage comme instrument de règlement des différends contractuels ». C’est pourquoi l’article 1er dudit Traité qui définit ses objectifs précise qu’il est question entre autres d’encourager le « recours à l’arbitrage pour le règlement des différends contractuels ». Les articles 21 à 25 posent les bases de cet arbitrage. La concrétisation de ces intentions s’est manifestée par l’adoption à Ouagadougou par le Conseil des Ministres de l’OHADA le 11 Mars 1999, de l’Acte Uniforme relatif au Droit de l’Arbitrage, et du Règlement d’Arbitrage de la CCJA qui fixe les règles applicables à l’arbitrage CCJA. Plusieurs textes ont été pris par la suite qui ont permis d’organiser l’arbitrage CCJA (I) afin de rendre lisible le professionnel le déroulement de procédure arbitrale.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Procédure arbitrale; Règlement d'arbitrage

Culture of international arbitration and the evolution of contract law - Karton, Joshua David Heller (University of Cambridge, 2011)
Keywords: Arbitrage; Arbitragem; Arbitration; Contract law; International Arbitration

Mediação e judiciário: condições necessárias para a institucionalização dos meios autocompositivos de solução de conflitos - Gabbay, Daniela Monteiro (Universidade de São Paulo, 2011)
A questão central deste trabalho refere-se à institucionalização da mediação no âmbito do Judiciário e às condições necessárias para uma boa relação entre a mediação e o processo judicial. Esta questão foi analisada sob as perspectivas processual e institucional. A primeira recai sobre as bases do processo de mediação, em especial o devido processo legal mínimo, e a sua interação com o processo judicial, diferenciando a justiça do processo e a justiça do resultado. A segunda recai sobre o desenho dos programas de mediação que funcionam junto ao Judiciário e os papéis assumidos pelos diferentes atores que participam destes programas: juízes, mediadores, partes, advogados e funcionários dos Tribunais. Sob esta última perspectiva, foi realizada pesquisa empírica e comparada em programas de mediação que funcionam junto ao Judiciário no Brasil e nos EUA. The main issue of this work is the institutionalization of mediation within the Courthouse and the pre-conditions for having a good relationship between mediation and the Judiciary. This issue is analyzed from both procedural and institutional points of view. The procedural perspective falls on the mediation due process (minimal but meaningful due process standards) and on the differences between the procedural and substantial justices. The institutional perspective falls on the design of the Court-Connected Mediation Programs and on the roles of the players who participated in these programs: judges, mediators, plaintiff and defendant, attorneys, and Court workers. An empirical research was also done about the Court-Connected Mediation Programs in Brazil and in the United States.
Keywords: Arbitrage; Arbitragem; Arbitration; Court-connected mediation programs design; Empirical research; Institutionalization of mediation; Juizo arbitral; MARD; Mediación; Mediation; Mediação; Mediação e conciliação; Minimal due process; Médiation; Solução de conflito

Effectiveness and Remedies of the Arbitral Awards in OHADA’s System and in People’s Republic of China. - Samassekou, Mamoudou; Lianbin, Song (Journal of Politics and Law, 2011)
Today the arbitral justice has experienced an exceptional development. It is a universal phenomenon which requires the involvement of all economic and legal players of developed and developing countries.OHADA is a common business law and wish to secure legal security for regional and foreign economic agents by offering a vast economic space. The People’s Republic of China (PRC) is an emerging country which increases its economic outlets in a context of globalization. This natural interdependence will increase the scope of economic exchanges, which may generate some disputes in businesses. This article aims to compare two legal systems in the international commercial arbitration field: the legal system of OHADA and the PRC’s legal system; especially in the effectiveness and the remedies of the arbitrators’ decisions.

Le principe de compétence-compétence en droit de l'arbitrage - Boucaron-Nardetto, Magali (Université Nice Sophia Antipolis, 2011)
Dans son sens originaire, le principe compétence-compétence permet au tribunal arbitral, comme à tout juge, de statuer sur sa compétence. En droit français, il s’est transformé en règle de conflit entre justice publique et justice privée doublement originale : d’une part, il repose sur l’exercice coordonné du pouvoir de juger de la compétence ; d’autre part, il est pluraliste. Enclenché par l’apparence vraisemblable d’une convention d’arbitrage, le principe compétence-compétence consiste en un mécanisme composite se déployant dans le temps du procès arbitral et dans l’espace des deux ordres juridiques considérés. Ainsi, trois règles distinctes permettent à chacune des justices – justice française et justice arbitrale – de connaître de sa propre compétence de manière coordonnée. Tout d’abord, en amont et en parallèle de l’instance arbitrale, l’effet négatif de la compétence-compétence paralyse le pouvoir des juridictions étatiques de statuer sur leur compétence. Ensuite, le temps du procès arbitral, l’effet positif de la compétence-compétence des tribunaux arbitraux reconnaît à ces derniers le pouvoir de juger de leur compétence. Enfin, au stade post-arbitral, l’effet positif de la compétence-compétence des juridictions publiques permet à ces dernières de retrouver le pouvoir de statuer sur leur compétence lors des recours ouverts contre la sentence. Chacune des règles examinées connait limites ou écueils. Parfois, l’équilibre est rompu soit au profit des juridictions d’Etat, soit au profit des juridictions arbitrales. Force est de constater que le caractère pluraliste du principe compétence-compétence est tantôt réalité, tantôt mirage. In its original sense, the principle of competence-competence empowers the arbitral tribunal, as well as any judge, to decide on its own jurisdiction. Under French law, it has been transformed into a rule on conflict of jurisdiction between state court and arbitration tribunal doubly innovative. On one hand, it rests on the coordinated exercise of the power to rule on its jurisdiction; on the other hand, it is pluralist. Activated by the appearance of an arbitration agreement, the principle of competence-competence consists of a heterogeneous mechanism, using the time of arbitration proceedings and space of both legal orders. Thereby, three distinct rules allow each justice - French courts and arbitration - to rule on its own jurisdiction coordinately. First, during or prior the arbitration proceedings, the negative effect of the competence-competence paralyses the power of the state court to rule on its own jurisdiction. Secondly, during the arbitration proceedings, the positive effect of the competence-competence of the tribunal arbitral recognizes that arbitrators decide upon their own jurisdiction. Finally, at the post-arbitral stage, the positive effect of the competence-competence of state courts permits them to recover the power to rule on their own jurisdiction at the setting aside or enforcement stage of the arbitration. Each analyzed rule has its own limits. Sometimes, the balance is disrupted either in favour of state courts, or in favour of the arbitral tribunal. To conclude, it is clear that the pluralist character of the principle of competence-competence is in some cases a reality, in others a mirage.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Pluralisme juridique; Règlement de conflits

Dispute Resolution in International Electricity Trade - Han, Baoqing (Energy Procedia, 2011)
International electricity trade disputes can arise at three key levels: state to state; investor to state; private party to private party. Parties may be more open to submission of their disputes to international arbitration. However, they should make proper arbitration options according to the types of disputes. At the same time, considering the risks facing dispute resolution, it is imperative to specifically design effective tools to mitigate these risks.
Keywords: Dispute resolution; Disputes; International Arbitration; International electricity trade; Risk mitigation

L'annulation de la sentence arbitrale au Québec et dans l'espace OHADA : une approche comparée. - Kouassi, Fabrice Constant (Université de Sherbrooke, 2011)
Le processus de règlement des litiges par la voie de l’arbitrage a nourri des ambitions économiques énormes dans les sphères juridiques où ce mécanisme a été instauré. L’efficacité de ce processus qui signifie entre autre un processus ayant abouti à une application, voire une exécution effective des protagonistes est un gage de la réalisation de ces ambitions. Or, ce processus peut être compromis du fait de l’annulation de la sentence arbitrale par un juge dont l’intervention dans le processus peut soit le renforcer, soit l’annihiler fondamentalement. Cette situation explique dans une large mesure les raisons pour lesquelles la doctrine juridique se place en faveur d’une collaboration solide entre la justice publique et la justice privée de l’arbitrage. Comment cette question de l’annulation de la sentence arbitrale est abordée dans les sphères juridiques du Québec et de l’Ohada? Quels sont les effets juridiques issus de la comparaison de cette situation dans chacune de ces sphères? Telle se présente la substance de cette recherche dont la méthode comparative est alimentée par le paradigme de l’herméneutique juridique et son corollaire le pluralisme juridique. Les résultats issus du dialogue comparatif devraient participer à une amélioration des situations problématiques décelées dans les sphères concernées. The rule process of lawsuits based on arbitration has filled out huge economic ambitions related to judicial spheres where this mechanism has been established. The efficiency of this process, which among others, has led to an application, indeed a real execution of the protagonists, is somewhat a guarantee to the fulfilment of these ambitions. However, this process can be compromised because of the cancellation of the arbitral sentence by a judge whose intervention in the process can either reinforce it or destroy it. This situation mainly explains the reasons why the juridical doctrine is in favour of a solid collaboration. How do the juridical sphere of Quebec and Ohada tackle this issue of the cancellation of the arbitral sentence? What are the juridical effects stemmed from the comparism of this situation in both spheres? The way the substance of this research appears and whose comparative method is fed by the paradigm of the juridical hermeneutics and its juridical pluralism corollary. The results stemmed from the comparative dialog should participate in improving problematic situations detected in the applied spheres.
Keywords: Annulation; Arbitrage; Arbitragem; Arbitration; Litiges; Sentence arbitrale

Arbitration: One Size Does Not Fit All: Necessity of Developing Institutional Arbitration in Developing Countries - Namrata Shah, Niyati Gandhi (Journal of International Commercial Law and Technology, 2011)
Litigation in developing countries has many defects which has prompted a need for the development of alternative dispute resolution mechanisms. Arbitration, being one such substitutive mechanism as a type of private litigation is the most suitable for the same. This paper deals with the need to develop institutional arbitration to co-exist with ad hoc arbitration and scale it down to be available for dispute resolution in developing countries using an illustration of India. Certain recommendations to make institutional arbitration, which is considered to be appropriate for International commercial dispute resolution, suitable for domestic disputes in developing countries have been highlighted.
Keywords: Arbitrage; Arbitragem; Arbitration; Developing countries; Institutional arbitration

Les MARC en OHADA (Journal africain du droit des affaires, 2011)
GENERALITES SUR LES MARC La justice arbitrale La médiation commerciale : une alternative au système judiciaire L’utilité de l’expertise Interactions entre médiation et arbitrage LES MARC EN OHADA Approche culturelle des MARC en OHADA Regards franco-africains sur les étapes de la médiation commerciale La gestion d’une procédure d’arbitrage : vue d’un opérateur économique de l’espace OHADA Analyse comparée du droit de l’arbitrage OHADA et du droit international L’arbitrage de la Cour Commune de Justice et d’Arbitrage (CCJA) de l’OHADA Nouveau Règlement de médiation de la Cour d’Arbitrage de Côte d’Ivoire (CACI)
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Mediation; Médiation

L'arbitre international : étude de droit comparé - Partida, Sebastián (Université Paris 2, 2011)

A comparative study: Arbitration agreement in OHADA and People's Republic of China arbitration laws - Samassekou, Mamoudou; Song, Lianbin (Journal of Politics and Law, 2011)
This article aims to compare the arbitration agreement of the OHADA legal system to that of the People's Republic of China. In the Chinese legal system the parties to a contract are required to have an arbitration agreement written before the occurrence of any incident in the execution of their contract. The parties must specify in advance, in the said agreement, the chosen arbitration institution for potential disputes. In the OHADA legal system, the parties are free to decide before or during execution of the contract of an arbitration agreement. They may also decide whether in case of a dispute, they would want to refer to an institutional arbitration or an ad hoc arbitration. According to the chosen legal system the consequences are different.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; China-OHADA

Contratación y arbitraje internacionales - Méndez Silva, Ricardo (Doctrina Jurídica, 2010)
https://archivos.juridicas.unam.mx/www/bjv/libros/6/2776/1.pdf
Keywords: Arbitrage international; Arbitragem; Arbitraje; Arbitraje Comercial International; Arbitration; International commercial arbitration

Uluslararası Ticari Tahkim ve geçici hukuki koruma tedbirleri - Balkar, Süheyla (Galatasaray Üniversitesi, 2010)
Yargılama sürecinin yaratabileceği olumsuzluklardan hak arayan kişileri korumaya ve onlara hukuki güven ortamı sağlamaya yarayan geçici hukuki koruma tedbirleri tüm hukuk sistemleri açısından yargılamanın etkinliğinin teminatıdır. Devlet yargısında olduğu gibi, özellikle ticari uyuşmazlıklar açısından büyük önem taşıyan tahkim yargılamasında da bu tür tedbirlerin varlığına ihtiyaç gün geçtikçe artmaktadır. Çalışmamızda, uluslararası ticari tahkime konu olan uyuşmazlıklarda geçici koruma tedbirlerine hükmedebilme yetkisi, bu yetkinin sınırları ve bu tür tedbir kararlarının icrası meseleleri gerek mahkemeler gerekse hakemler açısından incelenmiştir. Interim relief or provisional measures may be as important as an award on the merits of any arbitration case. If the subject matter of the arbitration is not preserved, a long and costly arbitration procedure may just end up in learning at the time of execution of the award, that there is no substance right to enforce anymore. Consequently, the topic of provisional measures, in the understanding that they maintain the status quo of the arbitration, becomes of great relevance to all who may be involved in the arbitration world. Nonetheless, the topic of provisional measures, the powers to enforce them and even, the degree of court cooperation/intervention in such matters, varies from one country to another. Unfortunately, provisional measures in arbitration face several problems related to the lack of actual enforceability of the arbitrators? resolutions as well as to the good will of the parties to arbitrate and to grant the other parties enough securities that the subject matter of the arbitration will be executable.
Keywords: Arbitration; Geçici hukuki korumalar; Hukuksal korunma; Incompatibility; Koruma tedbirleri; Legal protection; Protection measures; Tahkim; Temporary legal protection; Uyuşmazlık

Différends entre investisseurs et État : Prévention et modes de règlement autres que l’arbitrage - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Publications des Nations Unies, 2010)
Keywords: Différends; Etat; Investisseurs; Modes de règlement; Prevention

Chapitre II. Le consentement à l’arbitrage, manifestation d’une volonté contenue - Diallo, Ousmane (Le consentement des parties à l'arbitrage international, 2010)

Le consentement des parties à l’arbitrage international - Diallo, Ousmane (International, 2010)
Mode juridictionnel privé de règlement des litiges, l’arbitrage offre une alternative à la saisine du juge. Qu’il soit interne ou international, l’arbitrage repose généralement sur le consentement des parties. C’est donc à juste titre que celui-ci a été qualifié de pierre angulaire de l’arbitrage. Effectivement, c’est sur ce consentement que la justice privée s’est longtemps appuyée pour justifier sa légitimité, revendiquer son autonomie et conquérir un nouvel espace de liberté. Solidement porté par le consentement qui lui sert de fondement, l’arbitrage n’a cessé de se développer au point d’apparaître de nos jours comme le mode normal de règlement des litiges du commerce international. On le dit particulièrement adapté au règlement de telle ou telle catégorie de litiges, manière d’affirmer sa vocation à étendre son emprise. Parvenu à l’âge adulte, c’est donc tout naturellement que l’arbitrage cherche à s’affranchir du caractère exceptionnel que lui imprime sa subordination au consentement, lequel apparaît de plus en plus comme un îlot de résistance à son expansion, sinon à son efficacité. Première étude d’ensemble sur la question, le présent ouvrage a le grand mérite d’exploiter au mieux la richesse qu’offre une approche comparative, non seulement pour retracer le rôle important joué par le consentement dans l’évolution de l’arbitrage, mais aussi, et surtout, pour mettre à nu les multiples tentatives en vue de son émancipation de la tutelle des parties. Il en résulte une éclipse momentanée du consentement, qui ravive les contestations de la compétence arbitrale et dévoile à nouveau sa subordination au consentement, facteur de légitimation par excellence de l’arbitrage. C’est dire que le consentement ne fait pas que survivre à ces assauts, il réussit même à prospérer. Autant de questions aussi brûlantes qu’actuelles, sur lesquelles cet ouvrage offre une analyse détaillée et des solutions originales.
Keywords: Arbitrage international; Arbitration; Droit privé; International arbitration; Litige; Règlement des différends

L’ordre juridique arbitral : réalité, utilité et spécificité - Gaillard, Emmanuel (McGill Law Journal, 2010)
L’ordre juridique arbitral existe-t-il ? S’il est perçu par les arbitres, souvent de manière intuitive mais très réelle, c’est qu’il existe. L’ordre juridique arbitral ne doit pas cependant être exclusivement conçu comme une représentation mentale du rôle des arbitres et de la source de leur pouvoir de juger. Il existe en tant que système de droit.

Enforcement of Arbitral Awards in Sub-Sahara Africa - Onyema, Emilia (Arbitration International, 2010)
As the world celebrated the fiftieth anniversary of the New York Convention in 2008 it became necessary to examine the enforcement regimes for arbitration awards in Sub-Sahara Africa. This article examines the provisions for the recognition and enforcement, and requirements for the setting aside of both domestic and international arbitral awards under the arbitration laws of OHADA member states, Nigeria and Sudan, as representative of the legal regimes in Sub-Sahara African countries. The New York Convention applies to Convention awards in half of the countries of Sub-Sahara Africa. It is therefore relevant to examine the requirements for the enforcement of non-Convention awards in those states that are members of the New York Convention, and also in those states that are not members of the New York Convention. Different arbitration laws and regimes apply in the three representative jurisdictions chosen for this comparative analysis and these are also representative of the legal regimes in those countries with arbitration laws in the region. Though a generally supportive tendency towards the enforcement of arbitral awards can be gleaned from the examination of some arbitration-related judgments, this article again highlights the importance for the remaining countries in the region yet to sign up to and implement the New York Convention to consider adopting it, and for more arbitration hearings to be held within the region.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Enforcement of Arbitral Awards; Sub-Sahara

Chapter 42, Dissenting Opinions by Party-Appointed Arbitrators in Investment Arbitration - van den Berg, Albert Jan (Looking to the future: essays in international law in honor of W. Michael Reisman, 2010)
Dissenting opinions appear to have become an accepted practice in international arbitration. Th e current debate concentrates on their procedure, form, and content. Alan Redfern noted that “[a]t present, a generally relaxed attitude towards dissenting opinions seems to be taken not only by the arbitral institutions, but also by the arbitrators themselves … .” In this contribution, I would like to explore the cautionary note with which Redfern concluded his seminal article, namely, that the “[t]ime has perhaps come to inquire whether the present leniency towards dissenting opinions … has gone too far.” I propose to do so with respect to investment arbitrations because ade available publicly, particularly party-appointed arbitrators’ dissenting opinions.
Keywords: Arbitrage; Arbitration; Arbitrator; Dissenting opinion; Investment arbitration; Opinion dissidente

L'interprétation arbitrale du contrat de commerce international - Arfaoui, Besma (Université de Limoges, 2008)
En interprétant le contrat, l'arbitre du commerce international a forgé un certain nombre de principes généraux qui consolident l'édification d'un corps de normes spécifiques au besoin de la communauté internationale des commerçants. Les principes généraux de la lex mercatoria font de l'arbitre une source de droit objectif. A ce premier volet sur lequel débouche l'approche interprétative de l'arbitre s'ajoute le second aspect de l'apport de l'interprétation du contrat. Ce second aspect met en exergue le rôle de l'arbitre en tant que source de droits subjectifs attachée à la détermination des prérogatives et des obligations respectives des parties. A travers cette détermination s'ouvre le débat relatif à l'étendue du pouvoir de l'arbitre à l'égard du contrat. La dimension créative de l'arbitre s'accentue à travers un contrôle restreint des juridictions étatiques. Ce contrôle fait de la sanction de la dénaturation commise par l'arbitre et de la révision au fond de la sentence des interdits à ne pas franchir. Interpreting the contract, the arbitrator of international commerce built up a number of general principles that consolidate the building of standards specific to the needs of the traders' international community. The general principles of Lex Mercatorea make of the arbitrator an objective law source. In addition to this constituent resulted by the interpretative approach of the arbitrator, there is the second aspect which the arbitration interpretation of the international commerce contract comes out with. This aspect highlights the role of arbitrator as a source of subjective laws, a role related to the determination of prerogatives and obligations respective to the parties. This determination leads to a debate relative to the range of powers of the arbitrator with regard to the contract. The creative dimension related to the interpretative approach of the arbitrator becomes more pronounced with the restricted control of state jurisdictions. This control controls the distortion committed by the arbitrator and the revision in the sentence of the proscription not to get over.
Keywords: Arbitrage; Arbitrage (droit international privé); Arbitragem; Arbitration; Commerce international; Commercial Law; Droit commercial; Droit international; International Trade; International law; Lex mercatoria

L'arbitrage et les tiers - Boularbah, Hakim; Caprasse, Olivier; Cox, Kristof; Dal, Marc; De Meulemeester, Dirk; Keutgen, Guy; Verbist, Herman; Wautelet, Patrick (Actes du colloque du CEPANI 40 du 28 novembre 2008, 2008)

L'expérience internationale de la Cour commune de justice et d'arbitrage de l'OHADA - Kenfack Douajni, Gaston (2è Congrès de l'Association des Hautes juridictions de cassation ayant en partage l'usage du Français (AHJUCAF), 2007)
Issu des actes du deuxième congrès de l'Association des Hautes juridictions de cassation ayant en partage l'usage du Français (AHJUCAF), Monsieur Gaston Kenfack-Douajni expose le bilan des activités de la Cour commune de justice et d'arbitrage de l'Ohada, ainsi que les actions susceptibles de renforcer son efficacité.
Keywords: Indépendance; Justice; Magistrature; OHADA

La clause de médiation - Huchet, Guillaume (Université Jean Moulin Lyon 3, 2007)
La clause de médiation est une stipulation qui a pour objet le règlement amiable des conflits apparaissant au cours de la vie d'un contrat. En ce sens, les parties contractantes s'obligent lors de la survenance d'un différend à mettre en oeuvre préalablement à toute action en justice, un processus de médiation, afin de trouver sous l'égide d'un médiateur une solution amiable. La clause de médiation est une stipulation originale, car elle a un objet duel à la fois contractuel et processuel. Elle comporte en effet un engagement de ne pas agir en justice et une obligation de négocier. Pour permettre une négociation utile, la clause de médiation suspend le droit d'action de chacune des parties. Toute action en justice exercée au mépris de cet engagement entraîne le prononcé d'une fin de non-recevoir ; l'action est dite prématurée. L'obligation de négocier peut se définir comme l'obligation par laquelle les parties s'engagent dans un premier temps à mettre en place le processus de médiation par la désignation d'un médiateur puis à conclure un protocole de mission. Elles devront ensuite s'efforcer de négocier, dans un esprit de bonne foi et de loyauté, une éventuelle solution amiable. Le processus de médiation prendra alors fin soit par la conclusion d'un accord de conciliation, généralement une transaction, soit par le constat d'un échec permettant alors aux parties de retrouver leur liberté d'agir en justice.
Keywords: Contrats; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; Procédure (droit); Règlement de conflits

La responsabilité de l'arbitre - Sorrente, Jean-Yves (Université Jean Moulin Lyon 3, 2007)
L'arbitrage est une institution de nature contractuelle. II est donc de coutume d'aborder les questions de responsabilité liées à cette activité sous l'angle exclusivement contractuel. Néanmoins, l'arbitre remplit une fonction juridictionnelle qui doit être préservée de toute interférence extérieure. De fait, la responsabilité de l'arbitre relève aussi bien du domaine disciplinaire, pénale, contractuel que délictuel. Aussi, l'étude de sa responsabilité doit-elle aborder ces différents aspects, tout en tenant compte de la nécessaire immunité dont doit bénéficier l'arbitre pour accomplir sa mission, sans pour autant jouir d'une totale impunité. Arbitration is a contractual institution. It is usual to approach questions of the arbitrator's responsibility only under the contractual aspect. Nevertheless, the arbitrator fills a jurisdictional function that must be preserved of exterior interference. The responsibility of the arbitrator concern just as well many domains: disciplinary aspect, criminal and civil liability. Also, the study of his responsibility must she approach these different aspects, all while taking account of the necessary immunity of which must profit the arbitrator to accomplish his mission, without for as much to enjoy a total impunity.
Keywords: Arbitrage; Arbitrage (droit); Arbitragem; Arbitration; Arbitres; Arbitres (droit); Immunité pénale; Responsabilité contractuelle; Responsabilité délictuelle

Waiver of a Right to Arbitrate by Resort to Litigation, in the Context of International Commercial Arbitration - Gillies, Peter; Dahdal, Andrew (Journal of International Commercial Law and Technology, 2007)
This paper examines the circumstances in which a party to an arbitration agreement may be deemed tohave waived its right to arbitrate a dispute comprehended by the agreement, by involvement in litigation concerning this dispute. The focus is on the law in common law jurisdictions, particularly Australia and theUnited States of America. United Kingdom law will also be briefly surveyed. The paper focuses on the 2006 decision of the Australian Federal Court in Comandate Marine Corp v Pan Australia Shipping Pty Ltd, whichafforded the topic significant treatment. The theoretical bases for sustaining waiver claims are analysed, includingwaiver as a discrete doctrine, abandonment, estoppel, election, repudiation of contract and variation of contract.The policies that underlie and inform the development of principles for testing waiver submissions are noted.

'Legal Traditions' and International Commercial Arbitration - Trakman, Leon (University of New South Wales, 2007)
Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration, the International Bar Association and the International Chamber of Commerce have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. More recent concerns have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it. Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration (ICA), the International Bar Association (IBA) and the International Chamber of Commerce (ICC) have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. From the doctrine of freedom of contract to specific rules of evidence and procedures that govern arbitral hearings, the international arbitration community has sought to maintain the respected legal traditions that lawyer-arbitrators and counsel find familiar and comfortable. More recent concerns, partly expressed by William K. Slate II, President of the American Arbitration Association, have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Are they sufficiently uniform in nature and operation to justify their dominant status in formulating codes, laws and rules governing international commercial arbitration? And has international commercial arbitration become unduly reliant upon both the Common and Civil Law traditions at the expense of other legal traditions that operate against the background of different and changing legal cultures? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it.

Arbitrage et procès équitable dans la zone sud-ouest de l’Océan indien - Zattara-Gros, Anne-Françoise (Revue internationale de droit comparé, 2007)
L’étude des rapports qu’entretiennent l’arbitrage et le procès équitable dans les différents droits des îles de la zone sud-ouest de l’Océan indien prend toute sa dimension dès l’instant où la zone offre un patchwork de systèmes juridiques différents. La question est alors de savoir si dans les droits des îles des Grandes Mascareignes, l’arbitrage revêt le costume juridique français, sachant que le Nouveau Code de Procédure civile (NCPC) édicté en France le 5 décembre 1975 a été, suite à l’accession à l’indépendance de ces différentes pays, transplanté à Madagascar, aux Comores et à Maurice. La logique conduirait à répondre par l’affirmative. Mais la diversité du contexte, constitué soit de transposition du droit français de l’arbitrage, qui intègre le modèle de procès équitable notamment défini par l’article 6 de la Convention européenne des droits de l’homme, soit d’érection d’un droit interne de l’arbitrage composé partiellement de dispositions juridiques françaises, offre des situations inédites. Si à l’instar des grandes tendances, l’étude croisée des dispositions relatives à l’arbitrage et celles du procès équitable dans l’Océan Indien révèle une perméabilisation croissante de ce deux dernières sphères, et de là un risque de processualisation de l’arbitrage, l’institutionnalisation de l’arbitrage permet également aux parties, de trouver des garanties, ce qui est pleinement satisfaisant dans des pays où l’État de droit est défaillant et la justice étatique mise à mal de façon à assurer la sécurisation juridique des investissements et des échanges commerciaux. The study of reports stating that arbitration and fair judgment exist in the different laws of the islands in the south western zone of the Indian Ocean takes on a whole new dimension if the zone provides a patchwork of different legal systems. The question is whether or not arbitration is the same as in the French legal system. One must consider that the New Civil Procedure Code (NCPC) which was decreed in France on 5th December 1975, was transplanted to Madagascar, the Comoros Islands and Mauritius. Logic would thus lead one to believe the affirmative. However the diversity of the context, which is constituted either by transposing French arbitration law that integrates the decreed trial model as defined by article 6 of the European Convention of Human Rights, or the erection of internal arbitration law composed partially of French legal dispositions, provides some new situations. If, in accordance with the trends, the cross study of dispositions relative to arbitration and those of the fair trial in the Indian Ocean reveal that these two spheres are growing, and that a result of this there is a risk of procedure arbitration, the institutionalization of arbitration also allows for the concerned parties to find guarantees, which is very satisfying for countries whose state law is weak and where state justice has difficulty in ensuring legal security for investments and commercial exchange.

La problématique du consentement à l'arbitrage multipartite au sein des groupements de sociétés - Manirabona, Amissi Melchiade (Université de Montréal, 2006)
L'arbitrage étant une institution basée sur la volonté des parties, le consentement à la procédure arbitrale multipartite soulève de nombreuses questions relativement à la manière dont les parties expriment leur intention de faire partie d'une instance unique. Cette étude vise à déterminer les conditions dans lesquelles l'arbitre peut arriver à unifier la résolution des litiges qui impliquent les groupements de sociétés. Le plus naturel des moyens pour aboutir à une procédure multipartite est de prévoir cette possibilité à travers la convention d'arbitrage. Cela peut notamment provenir de la signature d'une convention d'arbitrage unique par toutes les parties concernées. Dans certains cas précis, l'arbitrage multipartite peut également résulter de plusieurs conventions d'arbitrage spécialement lorsque les parties participent à la réalisation d'un même ouvrage. Cependant, il arrive souvent qu'une partie qui n'a pas signé la convention d'arbitrage soit obligée à participer à l'instance. Même sans y être obligée, une partie non-signataire de la convention d'arbitrage peut aussi demander de participer à l'arbitrage pour défendre ses intérêts. Pour pouvoir admettre la participation à la procédure d'un tiers non-signataire de la convention d'arbitrage, les arbitres ont recours à plusieurs notions prévues par les droits internes. C'est ainsi que la levée du voile corporatif, la théorie de la réalité économique et le principe de l'estoppel constituent les meilleurs outils pour les arbitres d'amener à la procédure, par force ou sur demande, un non-signataire de la convention d'arbitrage. Enfin, les mécanismes du Code civil servent efficacement à neutraliser les effets du principe de relativité de la convention d'arbitrage. Il s'agit notamment de la bonne foi, du mandat, de la stipulation pour autrui et de la cession. Arbitration as an institution based on the intention of the parties, the consent on the multi-party arbitration procedure raises many problems relating to the way in which the parties express their intention to participate in a unique arbitration forum. This study aims to determinate the manner in which the arbitrator can join disputes resolution involving the groups of companies. The normal way to get a multi-party procedure is to provide it in an arbitration clause. This can be by signing a single arbitration agreement by all the parties involved. In certain cases, the multi-party arbitration can also be possible with several arbitration agreements especially when the parties took part in carrying out ofthe same economic operation. However, in other situations, the multi-party arbitration procedure is unrelated to consent. A non-signatory party can nevertheless be bound by an arbitration agreement signed by an other party. To allow the participation in the arbitration procedure of a third party non-signatory of the arbitration agreement, the arbitrators use several concepts provided chiefly by the national laws. 80, the lifting of the corporate veil, the doctrine of economic reality and estoppel, are the best tools for the arbitrators to bring to the arbitration procedure, by force or on request, a non-signatory of the arbitration agreement. Lastly, the mechanisms of the Civil code are used with efficiency by arbitrators to neutralize the effects of the relativity principle of the arbitration agreement. Those mechanisms are in particular the good faith, mandate, stipulation for another and assignment.
Keywords: Arbitrage; Arbitragem; Arbitration; Convention d'arbitrage; Effets (extension); Extension of the arbitration clause; Groupes de sociétés; Groups of Companies; Third Party non-signatory; Tierces parties non-signataires

The Role of International Arbitrators - Franck, Susan D. (ILSA Journal of International & Comparative Law, 2006)

The Contractarian Model of Arbitration and Its Implications for Judicial Review of Arbitral Awards - Kirgis, Paul F. (Oregon Law Review, 2006)

Harmonizing Business Laws in Africa: Ohada Calls the Tune - Dickerson, Claire Moore (Columbia Journal of Transnational Law, 2005)
OHADA (in English, Organization for Harmonization in Africa of Business Laws) is a system of business laws and implementing institutions. Sixteen West African nations adopted this regime in order to increase their attractiveness to foreign investment. Because most of the member states are former French colonies, the OHADA laws are based on the French legal system. Despite certain economists’ recent, well-publicized assertions that any French-based legal system is incompatible with development, other studies challenge those claims and in doing so outline characteristics that a pro-development system of business laws should possess. This Article reviews selected provisions from OHADA’s corporate law and of OHADA’s institutions, revealing that they correspond to those pro-development characteristics. Interviews conducted with legal professionals in Senegal, Côte d’Ivoire, and Cameroon highlight the local perception that the OHADA regime, while still
Keywords: Africa; Claire Moore Dickerson; Harmonizing Business Laws; OHADA; SSRN

L'arbitrage et la distribution commerciale - Jardin, Laurent du; Erauw, Johan; Hollander, Pascal; Keutgen, Guy; Matra, Didier; Van Houtte, Hans (Actes du colloque du CEPANI du 17 novembre 2005, 2005)

O processo de composição do Tribunal arbitral internacional e o seu funcionamento - Vescovi, Luiz Fernando (Espaço Jurídico Journal of Law, 2005)
O presente trabalho vem a delinear, sob forma objetiva, o efetivo escopo de um Tribunal Arbitral, ponderando as suas características e o comprometimento com as partes que a elegem. Apresenta o procedimento e o processo de como se constitui um tribunal dessa espécie, assim como as vantagens existentes quando da sua utilização. Enfatiza, de plano, a escolha dos apreciadores do juízo arbitral, assim como a análise circunstancial sobre a incidência da Lei de Arbitragem brasileira à luz do Direito supranacional. Enaltece a viabilidade jurídica (segurança e validade) que o instituto arbitral expressa, concernente às disposições principiológicas que dele decorrem. Ainda, descreve, de maneira esmiuçada, a forma de como o Tribunal Arbitral se compõe, sua competência, prerrogativas, e finalidades, bem como do funcionamento efetivo, no plano do Direito Internacional Privado.
Keywords: Composição; Direito Internacional Privado; Tribunal Arbitral

L'intervention du juge canadien avant et durant un arbitrage commercial international - Bachand, Frédéric (Université de Montréal ; Université Paris 2, 2004)
Cette thèse précise les conditions dans lesquelles les tribunaux judiciaires canadiens peuvent intervenir avant ou durant un arbitrage commercial international, soit afin d'y prêter assistance, soit afin d'en contrôler la légalité. Elle soumet également ces conditions à l'analyse critique, dans le but d'esquisser une théorie générale de l'intervention avant et durant un arbitrage commercial international des juges oeuvrant dans les États qui ont choisi d'accorder leur concours à la justice arbitrale internationale. Principalement, cette théorie repose sur l'idée selon laquelle l'intervention judiciaire survenant avant le prononcé de la sentence ne doit - à quelques exceptions près - servir que les intérêts des opérateurs du commerce international, les intérêts publics prépondérants ne devant être pris en compte que dans l'élaboration des conditions de l'intervention judiciaire survenant après le prononcé de la sentence. De cette idée directrice découlent deux conséquences majeures. D'abord, les ordres juridiques des États qui accordent leur concours à la justice arbitrale internationale doivent être perméables à des faits normatifs transnationaux qui s'intéressent à l'intervention judiciaire avant et durant un arbitrage commercial international, car l'adoption d'une loi ayant vocation à régir spécialement l'arbitrage commercial international ne peut jamais - à elle seule - assurer que les tribunaux judiciaires agiront de manière pleinement satisfaisante. Ensuite, les conditions de cette intervention doivent surtout avoir pour objectif d'accroître l'efficacité - envisagée du point de vue des opérateurs du commerce international - de ce système de justice internationale. This thesis sets out the conditions under which Canadian courts can intervene prior to and during an international commercial arbitration, either to assist the arbitral process or to control its legality. These conditions are also analyzed in a critical manner, with a view to elaborating a general theory of judicial intervention prior to and during an international commercial arbitration in States that have chosen to support international arbitral justice. This theory essentially rests on the idea that judicial intervention occurring before the rendering of the award must almost entirely be geared towards satisfying the interests of international business operators, as superior public interests need only be reflected in the conditions under which courts may intervene after an award has been rendered. Two major consequences flow from this idea. Firstly, the legal orders of States that have chosen to support international arbitral justice must be permeable to transnational normative facts which relate to judicial intervention prior to and during an international commercial arbitration, as the adoption of legislation dealing specifically with international commercial arbitration can never - in itself - ensure that courts will act in a fully satisfactory manner. Secondly, the conditions of such intervention must essentially be aimed at increasing the efficiency - assessed from the point of view of international business operators - of this system of international justice.
Keywords: Arbitrage commercial international; Arbitration; Canadian law; Civil procedure; Comparative law; Droit canadien; Droit comparé; Droit international privé; Droit judiciaire privé; International commercial arbitration; Intervention judiciaire; Judicial intervention; Loi type de la CNUDCI; Private international law; UNCITRAL Model Law

Qui contrôle l’arbitrage ? : autonomie des parties, pouvoirs des arbitres et principe d’efficacité - Kaufmann-Kohler, Gabrielle (Liber amicorum Claude Reymond : autour de l'arbitrage, 2004)

Conciliation et médiation judiciaires - Joly-Hurard, Julie (Droit privé, 2003)
Keywords: Concilition judiciaire; Médiation judiciaire; Pourparlers judiciaires

Les recours dilatoires contre les sentences arbitrales devant la Cour d'Appel de Paris (Analyse des décisions rendues entre janvier 1996 et décembre 2000) - Mantilla Espinosa, Fabricio (Estudios Socio-Jurídicos, 2003)
Este artículo está basado en el ensayo realizado en mayo de 2001, bajo la dirección de los doctores Jean de Hauteclocque y Christian Larroumet del departamento Contentieux et Arbitrage de la firma de abogados Lovells en París.

Essays on Bargaining with Outside Options - Adamuz Peña, Mercedes (Universitat Autònoma de Barcelona, 2002)
Los modelos de negociación con opciones exteriores normalmente suponen que los pagos de estas opciones son independientes de las acciones que los negociadores toman durante el proceso negociador. Sin embargo, en muchos contextos, la opción exterior depende de lo que las partes hagan durante la fase negociadora. Uno de estos contextos es el de aquellas negociaciones que se llevan a cabo en presencia de un árbitro. Esta tesis realiza algunas contribuciones a la teoría de la negociación con opciones exteriores, enfatizando aquellas situaciones donde las opciones exteriores aparecen por la intervención de árbitros. En el capítulo 2 analizo los efectos del arbitraje en las negociaciones cuando su uso es voluntario. Considero un modelo de negociación por concesiones donde las partes tienen la posibilidad de llamar a un árbitro con el consentimiento del oponente. Demuestro que la introducción del arbitraje distorsiona el resultado de la negociación. Esta distorsión depende de los costes relativos de implementar una partición mediante un proceso negociador versus un proceso arbitral. Si los costes del arbitraje son pequeños en relación a los costes de la negociación, entonces la partición negociada se aproxima a la propuesta por el árbitro, y en casos extremos el arbitraje es utilizado en equilibrio. Sin embargo, los jugadores no eligen siempre el método más eficiente de resolver su disputa: a veces negocian cuando es más eficiente acudir al arbitraje. En el capítulo 3 estudio los efectos de diferentes procedimientos arbitrales en el resultado de una negociación, en un modelo donde los jugadores realizan demandas no crecientes y el árbitro es llamado solo cuando las negociaciones se declaran rotas. Dos procedimientos arbitrales son analizados: el arbitraje convencional, donde el árbitro es libre de elegir su acuerdo y el arbitraje de oferta final, donde el árbitro está obligado a elegir una de las últimas ofertas de los jugadores. Demuestro que si los jugadores son suficientemente pacientes y el árbitro sigue un procedimiento de oferta final, en equilibrio, los jugadores negocian una partición pero toma algún tiempo llegar a ella. Sin embargo, si el árbitro sigue un procedimiento convencional, en equilibrio los jugadores utilizarán esta institución para resolver su disputa. Finalmente, en el capítulo 4 discuto el papel que juegan las opciones exteriores inciertas en las negociaciones cuando existe información incompleta acerca de su existencia. Examino una guerra de desgaste donde los jugadores disfrutan de información privada acerca de sus posibilidades de dejar la mesa de negociación para tomar una opción exterior. Hay dos tipos de jugadores: los tipos débiles, que no tienen opciones exteriores y prefieren conceder que salirse del juego, y los tipos fuertes que tienen opciones exteriores tales que prefieren salirse que conceder. El principal mensaje que surge del análisis de este juego es que la incertidumbre acerca de la posibilidad de que el oponente se vaya, mejora la eficiencia porque incrementa la probabilidad de concesión. Más precisamente, si la probabilidad de que el oponente sea fuerte es relativamente alta, la negociación acaba con una concesión segura. En el otro extremo, si la probabilidad de que el oponente sea débil es alta, los tipos fuertes dejarán en algún momento el juego con probabilidad igual a 1, dejando a los débiles jugando, desde ese momente en adelante el ineficiente equilibrio de la guerra de desgaste clásica. Incluso en este caso, la probabilidad de concesión a lo largo de la fase de incertidumbre del juego se incrementa.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Ciències Socials; Conventional arbitration; Final-offer arbitration; Negociación; Opciones exteriores

L’arbitrage international en Afrique : quelques observations sur l’OHADA - Boivin, Richard; Pic, Pierre (Revue générale de droit, 2002)
Avec le Traité relatif à l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) de 1993, l’Acte uniforme relatif au droit de l’arbitrage et le Règlement d’arbitrage de la Cour commune de justice et d’arbitrage (CCJA) de 1999, l’arbitrage international a fait une entrée remarquée en Afrique francophone. Dans cet article, les auteurs esquissent une vue d’ensemble du fonctionnement et des mécanismes de l’arbitrage OHADA.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitration; International Arbitration; OHADA

Les sociétés et l'arbitrage - Caprasse, Olivier (Bruylant, 2002)

Les modes alternatifs de règlement des conflits - Rivier, Marie-Claire; Ancel, Pascal; Blanc, Gérard; Cottin, Marianne; Gout, Olivier; Haubry, Xavier; Lawson-Body, Latékoué; Pourret, Jean-Louis; Sayn, Isabelle (Mission de recherche droit et justice, 2001)
La recherche effectuée a conduit à examiner comment les modes alternatifs de règlement des conflits (MARC), a priori nouveaux dans le droit français, ont été intégrés dans le discours des juristes, tel que tenu dans un ensemble de publications sélectionnées. Le dépouillement a permis l'établissement de 88 fiches concernant les ouvrages, et de 336 fiches s'agissant des revues. L'étude de cette masse documentaire, représentative du réseau de publications par lesquelles les juristes présentent, analysent le droit et contribuent à le faire, a montré comment la formule de "modes alternatifs" est entrée dans le discours doctrinal, mais aussi l'hétérogénéité des termes et des sens que recouvre cette formule. Quant au contenu du discours, on constate des constantes (un discours "de mode" et un discours "de crise") et des variantes dans l'appréciation portée sur cet objet. Loin de voir dans le développement des modes alternatifs de règlement des conflits une raison de remettre en cause leur activité et leur rôle, les juristes français ont intégré cet objet, recouvrant pour l'essentiel des mécanismes juridiques classiques, dans leurs analyses, et pour chacun des secteurs du droit concerné, l'ont situé dans un débat préexistant. La recherche de définitions, la (re)construction de catégories juridiques, l'élaboration d'un régime, sont autant de questions aujourd'hui considérées comme part intégrante de toute présentation de la justice ou des appareils judiciaires. Le discours tenu par les juristes tend aujourd'hui à privilégier l'examen technique de questions, situées dans le contexte d'une évolution caractérisée par la contractualisation, la procéduralisation du droit. Cette évolution, et non révolution, est désormais, dans la majorité des cas, présentée comme un phénomène irréversible.

Procedural detachment in international commercial arbitration : the law applicable to arbitral procedure - Petrochilos, Georgios (University of Oxford, 2000)
This thesis seeks to ascertain the rules of private international law determining the procedural law of international commercial arbitral proceedings. In an Introduction, the author outlines the fundamental notions, introduces the topic and the major doctrines and issues, and sets out his methodology and structure of the work. The thesis examine first, as a preliminary issue, the considerations influencing the assumption of jurisdiction over arbitral proceedings. Chapter 1 discusses the various theories on the lex arbitri (the law supplying the general legal framework of an arbitration) as relevant to the procedural law, and concludes that they are deductive and therefore unable to satisfactorily to determine the applicable procedural law. Chapter 2 analyses major national laws as case-studies of the technique and scope of application of international arbitration law, and suggests a model of legislative and court jurisdiction based on the legal concept of 'seat of the arbitration' and on considerations based on the most appropriate court to control an arbitration. Chapter 3 discusses the obligations of the state of the seat under the European Convention on Human Rights and confirms the findings in Chapter 2. In a second part, the thesis elaborates on the title and extent of permissible municipal law interference. Chapter 4 tests the validity of the propositions derived from Chapters 2 and 3 against arbitral practice and concludes that seldom will arbitrators derogate from the law of the seat. Chapter 5 examines the particular case of arbitrations with states and similar entities. The third part discusses the relevance of compliance with the law of the seat at the stage of enforcement of an award. Chapter 6 deals with the technical issue of whether annulment at the place of making precludes enforcement in other fora. That chapter gives the opportunity to discuss models of separation of international jurisdiction and co-operation between different jurisdictions from a practical perspective. It thus serves as a convenient introduction to Chapter 7, which discusses the more abstract question of the nexus required between an arbitral award and the municipal law of the state of rendition in order for the award to enter, in limine, the scope of application of the international instruments in the field. The thesis ends with Conclusions in the form of model provisions for municipal law and arbitration rules.
Keywords: Arbitrage; Arbitragem; Arbitration; International commercial arbitration; Procédure arbitrale

L'exécution des sentences arbitrales en vertu de la Convention de New York : expériences et perspectives - Mazilu, Dumitru; Houzhi, Tang; Kaplan, Neil; Delvolvé, Jean-Louis; Lebedev, Sergeï N.; Paulsson, Jan (Nations Unies, 1999)

La portée internationale de l'annulation de la sentence arbitrale dans son pays d'origine - Fouchard, Philippe (Revue de l'arbitrage, 1997)
Keywords: Annulation; Sentence arbitrale

Improving the administration of justice through the implementation of third party alternative dispute resolution processes: An analysis of process productivity and disputant strategic behavior - Stanford, John D. (Ohio State University, 1996)
The institutionalization of alternative dispute resolution (ADR) processes is the most recent development in the policy effort to reform the American civil justice system. However, the research is inconclusive and contradictory on the performance of ADR processes in institutionalized settings. This study introduces a production m odel of third party dispute resolution processes to compare the performance of court annexed arbitration, judicial settlem ent conference, and trial processes. To explain the processes’ performance, a strategic behavior model of third party dispute resolution processes identifies four strategic behaviors which influences process perform ance: integrative, distributive, opportunistic, and distributive. Through conceptualization of the m odels, several hypotheses are developed. This study introduces a production m odel of third party dispute resolution processes to compare the performance of court annexed arbitration, judicial settlem ent conference, and trial processes. To explain the processes’ performance, a strategic behavior model of third party dispute resolution processes identifies four strategic behaviors which influences process perform ance: integrative, distributive, opportunistic, and distributive. Through conceptualization of the m odels, several hypotheses are developed. This study concludes that the court annexed arbitration is the best performing process. Of the various dispute, disputant, and process characteristics identified to explain process perform ance, only the disputant’s perception of process equity during the process is significant and positive. The policy inference is that policy makers can reduce disputant costs while improving delay, process equity, and satisfaction through court-annexed arbitration.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitraje; Arbitration; Mediation; Third party

Le règlement des différends dans le nouveau droit de la mer - Djibril, Ly (Université de Droit d'économie et de gestion de Tunis, 1992)
L'introduction d'un système.' de règlement des différends, faisantpartie intégrante de la Convention et dont il est l'un des pivôts constituevraisemblablement l'un des apports les plus significatifs des travaux de laIIIe conférence des Nations-Unies sur le droit de la mer. Pour cette raisonsans doute, ce sujet a fait l'objet de nombreuses recherches.Ce présent travail constitue le maillon d'une chaîne dont la finalitéest d'essayer de comprendre les raisons qui expliquent la mise en placepar la IIIe convention des Nations-Unies sur le droit de la mer d'un cadrede règlement des différends spécifique. Y'avait-il des raisons sérieusesexpliquant un tel choix? Existait-il des motivations légitimes pouremboiter le pas à d'autres conventions ayant mis sur le place desmécanismes de règlement des différends spécifiques? -~Telles sont les questions auxquelles cette présente thèse tente d'apporterdes éléments de réponse.L'examen de la question du règlement des différends _est _avant touttributaire de l'analyse des dispositions conventionnelles relatives à cesujet. Il fait nécessairement appel à la méthode juridique. Mais, cettedémarche à elle seule parait incapable d'aller au delà des dispositionstechniques. Aussi. chercherons nous à pousser plus loin -l'étude en faisantappei à un raisonnement inductif, permettant de s'in~erroger sur lesraisons et les motivations expliquant les orientations.L'effort de systématisation perniet de dégager un certain nombrede résultats.On relève d'abord que le règlement des différends dans le droit dela mer concrétise fortement la volonté des Etats de faire progresser lapaix par le droit.Ensuite, l'observateur peut également percevoir que le système mis enplace introduit une dose de dirigisme raisonné. Car le droit de la mer nese veut plus régenté par un ordre oligarchique comme cela a été le casauparavant. Aussi, le système introduit un choix d'organes de règlementdes différends presque à la carte pour solutionner les différends les plusinhabituels.Enfin, en introduisant une variété de mécanismes de règlement, lesystème risque aussi d'ouvrir la voie à des craintes justifiées de la part desEtats qui en sont encore les principaux justiciables.
Keywords: Arbitrage; Arbitragem; Arbitration; Conventions; Droit de la mer; Droit maritime; Droit public; Règlement des différends

L’arbitrage en réassurance : la fin d’une idylle ? - Havens III, Charles W (Assurances, 1992)
In order to avoid resorting to the courts when faced with litigation, insurers and reinsurers have favored arbitration services. Today, arbitration and reinsurance no longer live in harmony. Charles W. Havens III, Partner of LeBoeuf, Lamb, Leiby & MacRae, an American law firm, explains why with numerous examples.

Le controle de la régularité internationale des jugements et sentences arbitrales en droit camerounais - Tchakoua, Jean Marie (Université de Yaoundé, 1991)
Keywords: Contrôle de régularité; Droit camerounais; Jugement; Sentence arbitrale

Internationales Schiedsverfahrensrecht: Doppelexequatur - Anderegg, Kirsten (Rabels Zeitschrift für ausländisches und internationales Privatrecht, 1989)

La cour d'arbitrage : actualités et perspectives - Andersen, Robert; Delpérée, Francis; Jadot, Benoît; Lejeune, Yves; Rasson-Roland, Anne; Rigaux, Marie-Françoise; Simonart, Henri; Tulkens, François; Van Compernolle, Jacques (Centre d'Etudes constitutionnelles et administratives, 1988)

Les qualités essentielles de l’arbitre en droit OHADA - Agbénoto, Koffi Mawunyo

La Cour Commune de Justice et d'Arbitrage de l'OHADA - Sane, Aïssatou (Université Cheikh Anta Diop)